Biogeochemical markers in juvenile Leach's storm-petrels (Hydrobates leucorhous) stranded offshore are distinct from inshore stranded juveniles and nestlings - Anne N.M.A. Ausems; Sophie Roy; Alexander L. Bond; Laura Crick; Joshua T. Cunningham; April Hedd; Laura A. McFarlane Tranquilla; Jennifer C. Rock; Robert A. Ronconi; Katharine R. Studholme; Christopher R.E. Ward; Sabina I. Wilhelm; et al. (Marine Pollution Bulletin, 2026)

From bycatch to litter: a systematic map of the ecological impacts of fishing in European seas - Esther D. Beukhof; Sven Sebastian Uhlmann; Karin J. van der Reijden; Aikaterini Anastasopoulou; Miren Altuna-Etxabe; Amaia Astarloa; Oihane C. Basurko; Logan Binch; Joanna K. Bluemel; Pierluigi Carbonara; Grete E. Dinesen; Ole R. Eigaard; et al. (Reviews in Fish Biology and Fisheries, 2026)

Resource limitation in intensively managed agricultural ecosystems compromises reproductive success and increases wing asymmetry in bumble bees - Bilyana S. Wild; Belén Gallardo; Christopher Wild; Patrycja Pluta; Mark Frenzel; Oliver Schweiger; Robert J. Paxton; Antonella Soro; Panagiotis Theodorou (Agriculture, Ecosystems & Environment, 2026)

Effects of temperature and Nocardia crassostreae on the immune response of the Pacific oyster, Magallana gigas - George Mason; Christopher Dwane; Luke A. Holmes; Robert P. Ellis; Lucy M. Turner; Manuela Truebano (Fish & Shellfish Immunology, 2026)

Towards a Refined Definition of “tidal Influence” for the Coastal Wetland Sciences - Ken W. Krauss; Laura S. Brophy; Judith Z. Drexler; Jeffrey A. Kelleway; Janine B. Adams; Havalend E. Steinmuller; Gregory B. Noe; Michael J. Osland; Jamie A. Duberstein; Kurt P. Kowalski; Amanda L. McCutcheon; Kaileʻa M. Annandale; et al. (Wetlands, 2026)

Biodiversity, food webs and an ecologically safe space for fisheries - Christopher P. Lynam; Robert B. Thorpe; Murray S.A. Thompson (Fisheries Research, 2026)

Behavioural Diversity of Fishes: Concepts, Drivers and Its Role in Conservation and Management - Marie Prchalová; Robert Arlinghaus; Samuel Westrelin; Ivan Jarić; Michael G. Bertram; Josep Alós; Henrik Baktoft; Jack A. Brand; Tomas Brodin; Adolfo Cordero‐Rivera; Carlina Feldmann; Ryo Futamura; et al. (Fish and Fisheries, 2026)
Human activity has altered nearly all ecosystems on Earth, contributing to substantial biodiversity loss across taxonomic, genetic and functional dimensions, from the intraspecific to the ecosystem scale. Yet some components of biodiversity remain hidden or underappreciated, including behavioural diversity. Behaviour is often among the earliest whole‐organism responses to environmental change, and diversity in behaviour can occur within individuals, among individuals, among populations and across communities and ecosystems. This variation may influence growth, survival, reproduction, ecological interactions and responses to anthropogenic pressures, although its effects on population stability and resilience are likely context‐, scale‐ and component‐dependent. In this review, we examine behavioural diversity in fishes, defined here as variation in behavioural traits across levels of biological organisation, from individuals to ecosystems. Our review has two complementary aims. First, we provide a conceptual overview of behavioural diversity, clarify how it differs from related constructs such as personality, plasticity, and behavioural syndromes, and summarise the evolutionary, ontogenetic, ecological, stochastic and anthropogenic processes that generate or erode it. Second, we evaluate why behavioural diversity matters for fish ecology, fisheries management, aquaculture, restoration and conservation. We conclude by identifying key research needs, including improved quantification, stronger empirical links between behavioural diversity and ecological outcomes, and the development of management approaches sensitive to behavioural diversity. More explicit consideration of behavioural diversity should improve our ability to predict fish behavioural diversity responses and to design conservation and management measures that account for variation rather than only average behavioural responses.

Power performance and loads characterization of laboratory-scale cross-flow rotors fabricated using additive manufacturing - James R. McVey; Abigale C. Snortland; Christopher R. Rumple; John T. Zaengle; Robert J. Cavagnaro; Michelle D. Fenn; Gregory Talpey; Emma N. Geon (Ocean Engineering, 2026)

Detection of seizurogenic compounds in human and rat neurons in vitro: A multi-laboratory, multi-model assessment - Ruth Roberts; Ksenia Blinova; Coby Carlson; Matthew Cato; Katherine Czysz; Tromondae K. Feaster; Xiaobo Han; Yuto Ishibashi; Yasunari Kanda; Mohamed Kreir; Paul Levesque; Norimasa Miyamoto; et al. (NeuroToxicology, 2026)

A diverse new omomyid primate fauna from the early Eocene of southern Wyoming with implications for interpreting macroevolutionary patterns among anaptomorphines - Parker D. Rhinehart; Robert L. Anemone; K. Christopher Beard (Journal of Human Evolution, 2026)

Restoration of a Mid-Atlantic Coastal Bay Scallop Population (Argopecten irradians) - Richard A. Snyder; Rebecca T. Smith; Darian M. Kelley; Sean Fate; Robert J. Orth; Bowdoin Lusk; Christopher J. Patrick; Stacy A. Krueger-Hadfield; Jan McDowell; Fredrick C. Holbert; John C. Lewis; John P. Richardson; et al. (Estuaries and Coasts, 2026)
We have attempted to re-establish bay scallops to the Virginia, U.S.A. coastal bays and document the dynamics of the restoration effort. Bay scallops ( Argopecten irradians ) once flourished in the eelgrass ( Zostera marina ) of the Virginia coastal bays. Eelgrass wasting disease led to declines, and both eelgrass and scallops were completely lost after a 1933 hurricane. The Virginia Institute of Marine Science (VIMS) led a successful eelgrass restoration effort beginning in 1997, with eelgrass beds expanding at 204 ha per year since 2012 and covering over 4,800 ha in 2025. From 2009 to 2025, bay scallops were brought in from North Carolina, New York, and Florida to the VIMS Eastern Shore Laboratory (VIMS ESL) in Wachapreague, VA and used to raise bay scallops for restoration. Progeny were released to the eelgrass beds and held in spawning cages. Annual census data documented low and fluctuating scallop densities from 2012 to 2018. From 2019 to 2025, we have observed continued exponential growth with a current (2024–2025) specific growth rate of µ = 0.468 year − 1 and a population doubling time of 1.48 years. The carrying capacity of the system for the new Virginia bay scallop population remains unknown with the population still in the exponential growth phase. In 2025 the annual census documented an average density of 0.114 scallops m − 2 and maximum recorded local density within 50 m − 2 sampling stations of 0.52 scallops m − 2 . Aggregation within the population was anticipated as necessary for reproductive success and was observed in population data with increasing density.

Observer coverage and interaction rates determine the choice between design‐based and machine learning bycatch estimators for rare species - Christopher Long; Robert Ahrens; T. Todd Jones; Zachary Siders (Conservation Biology, 2026)
Robust estimates of the magnitude of protected species bycatch are essential for effective fisheries management and marine conservation. Existing bycatch estimation methods typically struggle to accurately and precisely estimate the bycatch of rare species as a result of the statistical assumptions necessary to overcome infrequent encounters and, often, low observer coverage. We compared the widely used Horvitz–Thompson design‐based estimator with a machine learning framework for estimating protected species bycatch based on ensemble random forests. We simulated reduced observer coverage in the 100% observed Hawaii shallow‐set pelagic longline fishery and compared the two estimation methods for five species: oceanic whitetip sharks ( Carcharhinus longimanus ), Laysan albatross ( Phoebastria immutabilis ), black‐footed albatross ( Phoebastria nigripes ), loggerhead sea turtles ( Caretta caretta ), and leatherback sea turtles ( Dermochelys coriacea ). Machine learning‐based estimates were more precise than design‐based estimates for all species, but annual and long‐term accuracy varied with bycatch rates and spatial clustering of interactions. The machine learning approach improved the precision of bycatch estimates for oceanic whitetip sharks (3.5% of sets with interaction) without reducing long‐term accuracy. As interaction rates declined below this level, the ensemble random forests method introduced increasing bias and resulted in a preference for the design‐based estimator in real‐world applications. The ensemble random forests approach relaxed the trade‐off between accurate, precise bycatch estimates and observer coverage for species with greater than 3% interaction rates. However, high observer coverage remains irreplaceable for effectively estimating bycatch for the rarest species, and the imprecision of design‐based estimates should be accounted for in management decisions.

The ripple effect of surface water on dryland ecosystems - Amanda L. Subalusky; Christopher L. Dutton; Robert A. McCleery (Trends in Ecology & Evolution, 2026)

Leveraging Pharmacy Education through a Train-the-Trainer Model to Enhance Breast Cancer Literacy in Rural Communities - Christopher L. Farrell; Melanie R. Ginzburg; Morgan B. Enlow; Missouri M. Jenkins; Alexus N. Hames; Cayla R. Adams; Marlana A. Roberts; Hillary E. Stamps; Natalie A. Paxton; Courtney N. Addison; Austin Y. Shull (Journal of Cancer Education, 2026)
Rural versus urban communities experience disproportionate challenges in breast cancer outcomes, with higher breast cancer mortality and later stage disease presentation, despite similar diagnosis rates. These disparities are driven by structural barriers, including rural hospital closures, transportation difficulties, and limited access to oncology specialists. This study evaluated a train-the-trainer program designed to equip PharmD students located at a pharmacy school in a rural county in South Carolina with breast cancer education training, leveraging the pharmacists’ position as accessible healthcare professionals in rural communities. Training focused on breast cancer risk factors, prevention, screening, genetics, staging, and treatment options. Effectiveness was measured through pre- and post-workshop confidence surveys and knowledge assessments. Results showed significant improvement in student confidence across educational domains, with average scores increasing from 6.30 to 8.59 ( p < 0.0001). Understanding of screening guidelines (mean difference: 4.30; p -value: < .0001) and target therapy options showed the greatest improvement (mean difference: 3.65; p -value: < .0001), while knowledge of BRCA gene inheritance showed the smallest change (mean difference: 0.369; p -value: ns), suggesting some pre-existing awareness but limited understanding of its clinical applications. Overall, this pilot program demonstrates how pharmacy education can address healthcare disparities in rural communities. By preparing pharmacists to deliver accurate breast cancer education and to increase rural patient agency, this model creates a sustainable approach to improving health literacy in medically underserved areas. Future research could further expand this model to include diverse healthcare professionals and incorporate long-term impact assessments in community settings.

From Genes to Greens: How Diet, Climate and Phylogeny Shape Freshwater Turtle Microbiotas - T. Franciscus Scheelings; Thi Thu Hao Van; Anthony Santoro; Louise M. Streeting; Christopher T. Ormond; James U. Van Dyke; Lee F. Skerratt; Robert J. Moore (Environmental Microbiology, 2026)
Reptile microbiotas remain poorly understood despite their importance for host ecology and evolution. This study investigated how diet, climate and evolutionary history shape the gut microbiota of 234 Australian freshwater turtles spanning 10 species, four climatic zones and contrasting trophic strategies. It was found that turtles' microbiotas were dominated by Pseudomonadota, Actinobacteriota and Bacteroidota. Microbial richness and evenness varied significantly among species, diets and climates. Carnivorous turtles exhibited greater bacterial diversity than omnivores, while individuals from oceanic and humid subtropical zones had higher diversity than those from semi‐arid and Mediterranean regions. Canonical Correspondence Analysis confirmed diet and climate as significant predictors of community composition, together explaining 2.76% of total variation. Omnivorous turtles were enriched in Bacteroidota, Myxococcota, Cyanobacteriota and Bacillota, whereas climatic effects drove distinct phylum‐level signatures across habitats. Host phylogeny showed a weak but significant signal of phylosymbiosis, indicating an evolutionary imprint on microbial structure. Collectively, these findings reveal that turtle microbiotas are shaped by a complex interplay between ecological and evolutionary forces, underscoring the importance of integrating microbial data into conservation strategies for Australia's increasingly threatened freshwater turtles.

Potato Disease Prevalence and Quality Performance Under Four Soil Health-Related Practices - Kate Binzen Fuller; Kusum Adhikari; Alexander Maas; Christopher McIntosh; Carl Rosen; James E. Crants; Robert P. Larkin; Kim Zitnick Anderson; Anna Stasko; Julie Pasche; Kenneth Frost; Jeff Miller; et al. (American Journal of Potato Research, 2026)

Emergence of heartbeat frailty in advanced age II: individual cardiovascular aging trajectories revealed by lifelong echocardiography in male mice - Ismayil Ahmet; Nolan M. Winicki; Jacob S. Roberts; Christopher H. Morrell; Edward G. Lakatta (GeroScience, 2026)

Generative diffusion models for agricultural AI: Plant image generation, indoor-to-outdoor translation, and expert preference alignment - Da Tan; Michael Beck; Christopher P. Bidinosti; Robert H. Gulden; Christopher J. Henry (Computers and Electronics in Agriculture, 2026)

Plastitar and pyroplastics as emerging vectors of coastal pollution: Chemical identification from Panjang Island (Java Sea) and Palm Beach, Florida - Dwi Amanda Utami; Lars Reuning; Lorenz Schwark; Robert K. Nelson; Bryan D. James; Robert F. Swarthout; Diane Buhler; Eliete Zanardi-Lamardo; Christopher M. Reddy (Marine Pollution Bulletin, 2026)

Biomass and composition of Atlantic menhaden schools in winter on the continental shelf offshore of New Jersey: Application of a novel hydroacoustic survey with midwater trawl sampling - Geneviève Nesslage; James Gartland; Robert J. Latour; Christopher Gurshin; Dong Liang; Dustin Gregg; Stefan Axelsson; Leif Axelsson; Wayne Reichle; Jeff Kaelin; J. Michael Jech; Ray Mroch; et al. (Fisheries Research, 2026)

Oceanographic and climatic controls of meteoric 10Be fluxes to seafloor sediments: A global synthesis - Jennifer Middleton; Frank Pavia; Robert Anderson; Roseanne Schwartz; Martin Fleisher; Yong Lao; Yuxin Zhou; Christopher Kinsley; Joerg Schaefer; Martin Frank; Gisela Winckler (Quaternary Science Reviews, 2026)

Prioritizing chemicals for developmental neurotoxicity by integrating data from a new approach methods (NAMs) battery covering key cellular events in neurodevelopment - Laura A. Hall; Jui-Hua Hsieh; Skylar W. Marvel; Mamta Behl; Ellen Fritsche; Katharina Koch; Anna Kreutz; Marcel Leist; Arantza Muriana; Timothy J. Shafer; Jason P. Stanko; Robert C. Sills; et al. (NeuroToxicology, 2026)

Twelve distinct laboratory methods used to measure SARS-CoV-2 in wastewaters throughout a three-year Ontario-wide, Canada study: Impact on public health interpretation of disease incidence - Nada Hegazy; K. Ken Peng; Johanna de Haan-Ward; Elizabeth Renouf; Elizabeth Mercier; Shen Wan; X. Joan Hu; Charmaine Dean; Mark Servos; Elizabeth Edwards; Gustavo Ybazeta; Marc Habash; et al. (Journal of Water Process Engineering, 2026)

Investigation of a novel, variable-orientation, pilot-scale mill using positron emission particle tracking - Daniel Rhymer; Andy Ingram; Christopher Robert Kit (Chemical Engineering Journal, 2026)

Sources and biodegradation potential of naphthenic acids in an oil sands pit-lake - Mohamed El-Waraky; David Bowman; Robert K. Nelson; Christopher M. Reddy; Lesley Warren; Gregory F. Slater (Applied Geochemistry, 2026)

Advancing Ecological Understanding and Sustainable Management of Small Pelagic Fish - Myron A. Peck; Ignacio A. Catalán; Ryan R. Rykaczewski; Akinori Takasuka; Susana Garrido; Rebecca G. Asch; Matthew R. Baker; Noelle M. Bowlin; Jennifer Boldt; Richard D. Brodeur; Cecilie Hansen; Salvador E. Lluch‐Cota; et al. (Fish and Fisheries, 2026)
Small pelagic fish (SPF) are critical to the trophodynamic structure and function of marine systems and support some of the most valuable and socially important fisheries worldwide. Their “boom and bust” population dynamics, shifts in distribution, and importance as forage resources for other fish stocks place unique challenges to assessing and managing SPF. In response to these challenges, an international working group was formed in 2019 to foster collaboration aimed at closing key knowledge gaps in the ecology and sustainable management of SPF. Here, that group reviews progress made over the last ~10 years and identifies priorities for the next stage of coordinated international collaboration. Key research needs include: (i) enhancing monitoring programs to capture shifts in SPF distribution and incorporating new technologies, from molecular tools and digital imaging to biophysical and ecological modelling, (ii) improving data sharing to better understand life‐history bottlenecks and cross‐regional population dynamics, (iii) advancing process‐based studies on oceanic and trophodynamic interactions to clarify the ecological roles of SPF as both predators and prey, and (iv) conducting bioeconomic and risk analyses to assess the vulnerability of fishing‐dependent human communities to environmental and fish population fluctuations. A key pathway forward involves integrating mechanistic ecological knowledge, ecosystem and bioeconomic modelling, and social‐ecological frameworks into real‐time, adaptive, and equitable management approaches. This integration will be essential for developing resilient, ecosystem‐based fisheries management capable of anticipating tipping points, accommodating non‐stationary population dynamics, and ensuring sustainability under future climate and socio‐economic uncertainties.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Short-term mechanisms, long-term consequences: transcriptomic insights into ocean acidification tolerance and stress in juvenile snow crab - Laura H. Spencer; Ingrid Spies; Jennifer L. Gardner; Steven B. Roberts; W. Christopher Long (Frontiers in Marine Science, 2026)
Understanding how marine species tolerate ocean acidification (OA) is critical for predicting biological responses to ocean change, as well as impacts on the ecosystems and industries that rely upon them. Snow crab ( Chionoecetes opilio ) are both a major fishery resource in the Bering Sea and an important component of high-latitude marine food webs. Experimental work suggests that snow crab are relatively tolerant of OA, but that this tolerance has limits. In a recent study, juveniles maintained growth and molting during a year-long exposure to moderate OA (pH 7.8) and severe OA (pH 7.5), while survival declined in the severe OA treatment after 250 days. In this companion study, we applied RNA-seq to characterize transcriptomic responses to OA using individual whole-body juvenile snow crab. Expression profiles were characterized in OA treatments (pH 7.8, pH 7.5) at two time points: after 8 hours to identify molecular mechanisms underlying short-term tolerance; and after 88 days to understand chronic effects of severe OA (10–14 crabs per treatment and time point). The 8 h transcriptional response involved strong activation of genes associated with mitochondrial protein repair, cuticle maintenance, and immune modulation, processes shared between OA treatments but of substantially greater magnitude under severe OA (616 versus 148 differentially expressed genes). After 88 days of OA exposure, differential expression among the two OA treatments (186 genes) revealed sustained upregulation of stress- and damage-mitigation pathways in severe OA (pH 7.5). These findings suggest that juvenile snow crab tolerate OA through flexible molecular responses that maintain energy production capacity, cellular, and protective barrier function. However, persistent activation of these pathways under severe OA indicates a chronic stress state that precedes outward physiological effects and likely contributes to increased mortality under long-term exposure. We further highlight potential early indicators of chronic acidification stress in snow crab, among which a gene likely coding for carbonic anhydrase 7 (CA7) appears to be the most promising biomarker candidate.

No differences in inhibitory control or prefrontal activation during a cannabis cue stop-signal task across CUDIT-R-defined CUD-risk groups - Christopher R. Pickering; Valentina Lorenzetti; Andrew Jones; Martin Guest; Paul Christiansen; Carl A. Roberts (Psychopharmacology, 2026)
Rationale Cannabis use continues to increase globally, with a growing proportion of users exhibiting problematic patterns of use. Although neural differences in reward and inhibitory control systems are commonly reported in individuals who use cannabis relative to individuals not reporting cannabis use, findings using behavioural tasks are inconsistent. This is possibly due to lack of differentiation between regular and more problematic patterns of use. Objectives This study investigated whether inhibitory control performance and associated prefrontal and orbitofrontal activation differed across CUDIT-R-stratified levels of CUD risk. Methods Participants ( N = 81) were divided into three groups based on CUDIT-R scores: 30 high-CUD-risk individuals who use cannabis (≥ 12), 21 low-CUD-risk individuals who use cannabis (< 8), and 30 individuals not reporting cannabis use. Individuals with a current substance use disorder, including cannabis use disorder, were excluded from participation. All completed a cannabis-cue specific Stop-Signal Task (SST) while functional near-infrared spectroscopy (fNIRS) was used to measure oxygenated (oxyHb) and deoxygenated haemoglobin (deoxyHb) concentrations in the prefrontal cortices. Behavioural performance and neural activation were compared across groups. Results No significant behavioural or neural differences were found between the groups. Conclusions The study found no evidence of impaired inhibitory control or differential prefrontal activation across CUDIT-R-stratified levels of CUD risk. The results suggest incorporating further diagnostic stratification, multimodal imaging, and ecologically valid methods in future research to better characterise cannabis-related neural adaptations and inform clinical practice.

Mesoscale eddies in the subpolar North Atlantic: their ecological importance and conservation significance - Lea-Anne Henry; Jason Cleland; Anna Gebruk; René Schubert; Alice Della Penna; Peter Gaube; Christian Mohn; Brynn Devine; Arne Biastoch; Camille M.L.S. Pagniello; Keno Ferter; George Wolff; et al. (Progress in Oceanography, 2026)

Iron and zinc isotopic insights into the formation of Archean continental crust - Jianfeng Ma; Hamed Gamaleldien; Robert H. Smithies; Tim Johnson; Yuan-Ru Qu; Sheng-Ao Liu; Christopher L. Kirkland (Earth and Planetary Science Letters, 2026)

Multi-frequency signatures of space-leader evolution in negative cloud-to-ground lightning stepped leaders - Dylan J. Goldberg; Amitabh Nag; Kenneth L. Cummins; Mathieu N. Plaisir; Alex Tempert; A. Tyler Brower; Christopher J. Biagi; Robert G. Brown; Hamid K. Rassoul (Atmospheric Research, 2026)

Direct Versus Indirect Bypass in Early-Stage Moyamoya (Suzuki I-III): A Propensity Score-Weighted Study - Basel Musmar; Joanna M. Roy; Hammam Abdalrazeq; Victor Gabriel El-Hajj; Michael Rizzuto; Matthews Lan; Pious Patel; Michael Baldassari; Arbaz Momin; Yazan Shamli Oghli; Marissa Tucci; Joseph Schaefer; et al. (Translational Stroke Research, 2026)

Does farming make us human? a report on two Australian public deliberations - Angie Sassano; Robert Sparrow; Christopher Mayes; Cheryl Travers; Megan Moss; Ashley Rootsey; Leland Glenna; Chris Degeling (Precision Agriculture, 2026)
Purpose Farmers in Australia are currently facing profound challenges due to soil degradation, biodiversity loss, climate change, biosecurity threats, and difficulties in securing labour; farmers elsewhere face similar challenges. Increased use of robotics and artificial intelligence (AI) has been proposed as a possible solution to these problems. These technologies have the potential to radically transform the practice of farming: according to some authorities they hold out the prospect of a future in which, at least in some forms of farming, human farmers are no longer necessary. There is a strong case that such a radical transformation of the nature of agriculture would require social license. Methods In this paper, we report on the conduct and outcomes of public deliberations conducted in community juries in metropolitan and regional communities in Victoria, Australia, on the question: Under what conditions (if any) should we fully automate food and fibre production without human labour and decision-making? Findings The two juries came to different verdicts: full automation was rejected by consensus in metropolitan Melbourne but seen as being acceptable (under specific conditions) by a clear majority of jurors in the regional town of Mildura. Conclusion These findings, the existential concerns expressed by participants about the prospect of “farmerless farms”, and the quality of the deliberations in the juries, demonstrate the value of engaging with the public about technological trajectories and are highly relevant to the project of attempting to ensure that the use of robots and AI in agriculture has a social license.

Brightness, colour, polarisation: a multi-instrument observation campaign of the Gorizont-6 satellite - Robert J.S. Airey; Paul Chote; Klaas Wiersema; Ioannis Apergis; James McCormac; James A. Blake; Benjamin F. Cooke; Isobel S. Lockley; Peter J. Wheatley; Daniel Bayliss; Samuel Gill; Christopher A. Watson; et al. (Advances in Space Research, 2026)

Species‐specific processing of fluorescent dissolved organic matter by Caribbean sponges - Jacqueline G. Keleher; Cole G. Easson; Christopher J. Freeman; Robert W. Thacker; Craig E. Nelson; Alicia M. Reigel; Cara L. Fiore (Limnology and Oceanography, 2026)
Coral reefs are biodiverse and productive ecosystems that are found in typically oligotrophic environments. Many studies have attempted to explain this paradox by demonstrating that microbial symbionts expand metabolic capabilities of host animals. However, few studies have determined if and how coexisting organisms and their symbiotic microbial communities partition available dissolved organic matter. To address this question, we built an artificial reef near the Florida Keys using dominant emergent sponges found in the Caribbean. Fluorescent dissolved organic matter (fDOM) components were measured in incurrent and excurrent water samples of 5–7 biological replicates for each of 10 sponge species. Sponges generally consumed more fDOM as incurrent concentrations increased, but there were also species‐level differences in their responses. We found that microbial abundance (i.e., high and low microbial abundance HMA/LMA classification) explained less variation in fDOM processing than sponge species. Additionally, fDOM analysis revealed both a separation of sponges into two groups based on whether they were net producers or consumers of fDOM, as well as their responses to fDOM concentrations in ambient seawater across species. Differential consumption of fDOM components also yielded species‐specific fluxes of fDOM. This observation contrasts with broad uptake of all fDOM components, which would be expected if net consumption of fDOM was simply concentration dependent and the same for all species. These results provide the first support for species‐level resource partitioning of fluorescent dissolved organic matter across coexisting sponge species and provide additional support for the evolutionary importance of microbial communities in sponges.

Nature vs. nurture? Light availability drives phenotypic plasticity within a reef coral species - Hugo Ducret; Christopher R. Suchocki; Claire J. Lewis; Heidi M. Dierssen; Eric J. Hochberg; Daniel W. H. Schar; Marc Kochzius; Isabelle F. George; Robert J. Toonen; Jean‐François Flot (Limnology and Oceanography, 2026)
Scleractinian corals exhibit wide intra‐specific phenotypic variations. However, the extent to which these variations are explained by genotypic variation or phenotypic plasticity remains unclear. To elucidate this question, we devised a replicated experiment in which nine Montipora capitata coral colonies were cut into six pieces each, three of which were placed in shaded conditions (with a 73% reduction in light intensity) whereas the other three were kept in natural conditions as a control. After 1 year, we detected statistically significant morphological differences between corals of the same genotypes grown in different light environments, but no significant change in symbiont community structure. Colonies kept in control conditions exhibited a high surface complexity and converged toward more digitate or corymbose morphs compared to shaded corals, which exhibited planar‐like surfaces and converged toward laminar and foliose forms. Our data demonstrate the high level of light‐driven phenotypic plasticity of M. capitata and suggest a trade‐off between the amount of biomass per space area and the amount of absorption of incident light.

Mangrove sediments reveal drivers of Late Holocene sea-level change in the equatorial Pacific Ocean - Juliet P. Sefton; Andrew C. Kemp; Simon E. Engelhart; Matthew J. Brain; Joanna C. Ellison; Roger Creel; Christopher G. Piecuch; Robert E. Kopp; Blair Charley; Saimon Lihpai (Quaternary Science Reviews, 2026)

Archean tectonics resembled modern-style plate tectonics? Pre-Columbia early plate tectonics in the São Francisco-Congo Craton - Rodrigo I. Cerri; Richard M. Palin; David Chew; Nick M.W. Roberts; Fabrício A. Caxito; Renato Moraes; George L. Luvizotto; Silvia Volante; Christopher Spencer; Claudio Riccomini (Earth and Planetary Science Letters, 2026)

Population Genomics of a Cosmopolitan Weed Provides Insights Into Its Local Adaptation and Recent Demographic History - Marilia Souza Lucas; Christoph Rosche; Isabell Hensen; Stefan G. Michalski; Dávid U. Nagy; Diana Gamba; Renske E. Onstein; Karime Abidkulova; Mohammad Al‐Gharaibeh; Ali A. Al‐Namazi; Sirwan Babaei; Fernando Bastida; et al. (Molecular Ecology, 2026)
Invasive plant species present a growing ecological and economic challenge, and often adapt rapidly to their novel environments through complex demographic and evolutionary processes. Invasion genomics offers powerful tools to disentangle these processes, but most studies rely on geographically narrow sampling across native and non‐native ranges. Erigeron canadensis is a cosmopolitan weed native to North America that has successfully invaded diverse climates worldwide. We used double‐digest restriction site‐associated DNA sequencing (ddRADseq) to investigate the genetic diversity and structure of 280 E. canadensis populations across the Northern Hemisphere. We found that native and non‐native populations maintained comparable genetic diversity. Population structure analyses revealed four genetic clusters that were mainly differentiated along latitudinal and aridity gradients. However, one cluster was strongly overrepresented in the non‐native compared to the native range. In the native range, genetic differentiation was shaped by spatial and environmental gradients, while in non‐native regions human‐mediated dispersal and repeated introductions disrupted environmentally driven genetic structure. Migration network analyses revealed limited intercontinental connectivity and a possible role of long‐distance dispersal in within‐range expansions. Genomic offset analyses showed that genotype‐environment mismatches in non‐native populations associated with reduced growth and reproduction. Together, our results indicate that the invasion dynamics of E. canadensis were driven by multiple introductions, population admixture, and lineage sorting, while some genotypes contributed disproportionately to the spread of this invader. The presence of apparent maladaptation suggests that even long‐established invaders may still be evolving in response to their novel environment, raising concerns about potential future expansions.

Landscape Connectivity and Wildlife Access to Water Across an International Border: Barriers and Opportunities for Facilitating Transboundary Movement - Bogdan Chivoiu; Erin L. Koen; Michael J. Osland; Christopher A. Gabler; Jerald T. Garrett; Ernesto Reyes; Stephanie A. Bilodeau; Mitch A. Sternberg; Miguel L. Villarreal; Eric K. Waller; Samuel N. Chambers; Jude A. Benavides; et al. (Global Change Biology, 2026)
Rapid global acceleration in the construction of physical barriers along international borders has greatly influenced biodiversity and animal movement. Physical barriers can fragment landscapes, hinder access to essential resources, impact long‐distance migrations, and inhibit dispersal and gene flow. The effects of physical barriers on animal movement and landscape connectivity can be exacerbated in dryland environments where access to water is a limiting factor. In recent decades, the construction of border barrier infrastructure has accelerated along the international boundary between the United States and Mexico. Here, we used a landscape connectivity model to investigate the effects of barriers on wildlife access to the river in the Lower Rio Grande Valley. We used a modified omnidirectional connectivity model to compare access to the river for three large, terrestrial mammal species across three border barrier scenarios: (1) a landscape without border barriers; (2) a landscape with the existing barrier system; and (3) a potential future landscape with a continuous barrier system. The existing barrier system includes many discrete sections of barrier within tracts of the Lower Rio Grande Valley National Wildlife Refuge or on lands associated with the region's flood control system. Our results indicate that the existing border barriers can impede connectivity and wildlife access to the river in some areas, while some existing gaps between border barrier sections can serve as conduits for wildlife movement and river access. Our future scenario results show how a potential continuous border barrier system could further impede wildlife access to the river. We discuss management and landscape conservation options for enhancing wildlife access to water and riverine habitats. Collectively, our results illustrate the potential effects of border barriers on wildlife movement and access to water, providing information that can be used to better anticipate and lessen the ecological impacts of transboundary barriers.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

The Hirnantian-Rhuddanian succession in East Central United States: New implications for latest Ordovician to early Silurian sea level - Cole F. Farnam; Carlton E. Brett; Lincoln Shoemaker; Jisuo Jin; Robert J. Elias; Christopher B.T. Waid (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Evolutionary history of Ridge-nosed Rattlesnakes (Crotalus willardi): A specialized and diverse montane species - Michael J. Buontempo; Philip Lavretsky; Rhett M. Rautsaw; Lauren M. McFarland; Ramses Alejandro Rosales-García; Jason L. Strickland; Miguel Borja; Jason Jones; Ricardo Ramírez Chaparro; Robert W. Bryson; Christopher L. Parkinson; Michael G. Harvey (Molecular Phylogenetics and Evolution, 2026)

Not all that's high is sediment: Conflicting evidence for sediment assimilation in intrusive rocks of the Frontenac terrane, Grenville province - Gideon Asomani-Darko; Christopher J. Spencer; Nick M.W. Roberts; Evelyne Leduc; Emma Pluister (Lithos, 2026)

Emerging hydrogen spot indices: Price taker or maker? - Chaewon Kim; Scott M.R. Mahadeo; Keiron P. Roberts; Christopher R. Jones (Journal of Environmental Management, 2026)

Enhancing Bayesian methods for radioactive source localization: a parameter study, prior construction and signal smoothing - Aliaksandr Dvornik; Robert Finck; Christopher Rääf (Journal of Environmental Radioactivity, 2026)

A laboratory-based spectrometer intercomparison for the measurement of snow spectra - Benjamin M. Roberts-Pierel; Christopher J. Crawford; Steven W. Brown; Raymond F. Kokaly; Kelly E. Gleason; Anne W. Nolin; Edward H. Bair; Brenton A. Wilder; Anton J. Surunis; S. McKenzie K. Skiles; Joachim Meyer; Allyson E. Fitts; et al. (Cold Regions Science and Technology, 2026)

Suburban land management impacts bee community composition and cucumber (Cucumis sativus) pollination - Sheryl C. Hosler; Megan Garfinkel; Michael Roberts; Christopher J. Whelan; Emily S. Minor (Urban Ecosystems, 2026)
Urban green spaces can provide quality habitat for insect pollinators. However, few studies have investigated the quality of pollination services provided by urban insect pollinator communities or compared pollination services between different types of urban green spaces. We evaluated both the taxonomic and functional trait diversity of flowering plant and bee communities in two common types of suburban green space: residential backyards and electric powerline corridors. We also quantified seed set from sentinel cucumber plants as a measure of pollination services. We analyzed the response of the flowering plant community to site type and impervious surface cover, as well as the response of the bee community to flowering plant taxonomic and functional diversity and impervious surface cover. Seed set was analyzed in response to bee abundance, species diversity, and the community-weighted mean of bee body size. Site type affected floral resource diversity. Bee abundance was negatively affected by both impervious surface cover and floral resource functional evenness, and pollination services were negatively affected by bee total abundance. Our findings suggest that certain suburban management practices and site characteristics can lead to bee communities with highly abundant but mostly ineffective pollinators. Ultimately, these results also reinforce the need for more urban ecology studies that directly measure ecosystem functions and attempt to trace the mechanistic relationships between those functions and the organisms facilitating them.

Improvements in tropical cyclone forecasting using CCAM compared with the operational Unified Model: A case study of tropical cyclone Idai - Lebogang N. Makgati; Mary-Jane M. Bopape; Elelwani Phaduli; Gift Rambuwani; Robert Maisha; Christopher J. C. Reason (Natural Hazards, 2026)
Tropical cyclones are among the most destructive weather systems, yet prediction skill in the South-west Indian Ocean (SWIO) lags due to limited observations and modelling constraints. This study evaluates the Conformal-Cubic Atmospheric Model (CCAM) in simulating track and intensity of Tropical Cyclone Idai, relative to the operational Unified Model (UM) at the South African Weather Service (SAWS). Simulations were performed at multiple resolutions (CCAM: 25 km, 6 km; UMGA: 10 km; UM: 4.4 km) and lead times (72 h, 48 h, 24 h), validated against independent observational and reanalysis datasets. Both models reproduced Idai’s track more accurately at finer resolution and shorter lead times. CCAM exhibited a southward track bias, while UM deviated northward. Landfall position and timing were generally captured, with position errors reduced to < 30 km at 24 h, although CCAM 6 km showed a late landfall bias of ~3 h at 72 h. Intensity was underestimated by all simulations, however, CCAM 6 km better matched best-track winds and central pressures, while UM 4.4 km aligned more closely with ERA5. Rainfall patterns differed, with CCAM overestimating rainfall extent and intensity, whereas UM 4.4 km more realistically captured IMERG and CHIRPS patterns, though with weaker magnitudes. Results show that high horizontal resolution is crucial for representing TC characteristics, with microphysical processes becoming increasingly influential at convection-permitting scales. Differences in model initialisation also contributed to track and intensity biases. These findings underscore the value of high-resolution modelling, improved initialisation and observations to advance TC forecasting and early warning in the SWIO.

Estimating mercury exposure in amphibians using non-lethal tissue sampling - Caitlin T. Rumrill; Kelly L. Smalling; Colleen Emery; Blake R. Hossack; Brian J. Halstead; Michael J. Adams; Adam R. Backlin; Adrianne B. Brand; Jon M. Davenport; Robert N. Fisher; Jill Fleming; Brad M. Glorioso; et al. (Ecotoxicology, 2026)

Diversification and Colonisation in the Indo‐Australian Archipelago: Genomic Insights From Colubrid Snakes - Justin M. Bernstein; Christopher C. Austin; J. Angel Soto‐Centeno; Tianqi Huang; Jackson R. Roberts; Jimmy A. McGuire; Djoko T. Iskandar; Bulisa Iova; Jeffrey H. Frederick; Marites B. Sanguila; Jeffrey L. Weinell; Rafe M. Brown; et al. (Journal of Biogeography, 2026)
Aim The Indo‐Australian Archipelago (IAA) is one of the most geologically complex and species‐rich regions on Earth. However, our knowledge of the geological processes and dispersal mechanisms that generate archipelago‐wide distributions across the IAA is limited to a few vertebrate groups and often solely attributed to Plio‐Pleistocene sea‐level fluctuations. In this study, we use phylogenomics‐based analyses to investigate two speciose and closely related genera of snakes, Lycodon and Stegonotus (Serpentes: Colubridae), which are widely distributed across the IAA to identify which biogeographic and environmental processes have shaped snake diversity in this region. Location South Asia and the Indo‐Australian Archipelago (Indochina, Sundaland, Philippines, Wallacea, Australasia). Taxon Snakes (Colubridae: Lycodon, Stegonotus ). Methods We inferred a phylogeny using a genomic dataset consisting of ultraconserved elements, anchored hybrid enrichment loci, and protein‐coding genes (~5400 nuclear loci) from 38 species (154 samples) of Lycodon and Stegonotus . We used ancestral range estimation analysis to identify dispersal patterns across the IAA. Additionally, we implemented ensemble species distribution models to identify potential hotspots of Lycodon and Stegonotus species richness and determined the environmental influence on geographic distributions and species diversity. Results We find that these snakes comprise six deeply divergent lineages (genera) that initially originated in Mainland Southeast Asia during the Oligocene. Diversification of these lineages is influenced not by Plio‐Pleistocene sea‐level fluctuations but by multiple historical processes, including in situ diversification, island hopping, long‐distance rafting, possible microcontinental block drifting, Cenozoic land bridge migrations and founder events. The species distribution models do not consistently estimate lower or higher species richness in any particular region within the IAA, but precipitation overall is considered an important factor in estimated species richness. Main Conclusion Although Plio‐Pleistocene sea‐level fluctuations are notorious species pump diversification paradigms in the IAA, multiple and more ancient geological processes and environmental factors contributed to current diversity levels and distributions. Our approach expands future investigations of alternative hypotheses of biodiversity sources in the IAA and greatly expands the diversity of causal mechanisms for discussions of terrestrial Southeast Asian biodiversity beyond dispersal versus vicariance hypotheses.

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Carbon capture from ArcelorMittal hot briquetted Iron plant using air liquide cryocap™ FG technology – FEED study - Sebastiano Giardinella; Varun Gopalakrishnan; Vincent Gueret; Lindsey Turney; Vincent Lu; Chris Tovee; David Zybko; Marcelo Andrade; Christopher Harris; Pierre-Philippe Guerif; Timothy Henderson; Anderson Morelato; et al. (International Journal of Greenhouse Gas Control, 2026)

Impact of geometry on 1D molecular-kinetics simulations of acoustic-gravity wave propagation into the exosphere - Jose A. Perez Chavez; Orenthal J. Tucker; Shane R. Carberry Mogan; Robert E. Johnson; Christopher Blaszczak-Boxe (Icarus, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Environmental and socio-ecological performance of greening at household and street level - Hao Sun; Akash Biswal; Isabelle Bray; Owen Cranshaw; Thomas Rodding Kjeldsen; Christopher C. Pain; Thomas Roberts; Danielle Sinnett; Tom Wild; Jannis Wenk; Prashant Kumar (Science of The Total Environment, 2026)

Outcomes of Bypass Surgery in Patients with Moyamoya Syndrome Secondary To Sickle Cell Disease: a Multicenter Study - Basel Musmar; Joanna M. Roy; Hammam Abdalrazeq; Celine Yacoub; Nimer Adeeb; Antony A. Fuleihan; Sravanthi Koduri; Michael Baldassari; Matthews Lan; Pious Patel; Arbaz A. Momin; Elias Atallah; et al. (Translational Stroke Research, 2026)

Shading does not lower thermal tolerance in the coral Montipora capitata - Hugo Ducret; Christopher R. Suchocki; Claire E. Bardin; Claire J. Lewis; Tristan Permentier; Madeleine Hardt; Robert J. Toonen; Marc Kochzius; Jean-François Flot (Coral Reefs, 2026)

Conservation genomics of the imperiled Leon springs pupfish, Cyprinodon bovinus, across temporal and spatial scales - Robert J. Bretzing-Tungate; Kevin W. Conway; Megan G. Bean; Ryan K. Smith; Christopher M. Hollenbeck; Andrew T. Fields; Elizabeth P. Dolan; Steven M. Mussmann; David S. Portnoy (Conservation Genetics, 2026)
The Leon Springs pupfish, Cyprinodon bovinus , is federally listed as endangered and currently confined to spring-fed pools on the Diamond Y Spring Preserve in Pecos County, Texas, USA. A refuge population is maintained by U.S. Fish and Wildlife Service in Dexter, New Mexico, USA because of ongoing threats from hybridization with the introduced congener, the sheepshead minnow, C. variegatus. To inform continued conservation and management planning for this species, a comprehensive conservation genomics study using double digest restriction-site associated DNA sequencing was performed. No evidence of contemporary hybridization or recent introgression between C. bovinus and C. variegatus was found. The refuge population was significantly differentiated from wild samples collected at two locations, and the two wild populations (less than 1 km apart) also exhibited significant heterogeneity in allele frequencies. Estimates of within population diversity were smaller for wild locations than the refuge population. Correspondingly, the wild populations’ contemporary effective population size estimates were smaller than the refuge’s effective population size estimates (145–262 versus 679). Temporal analyses, involving genetic data collected from samples obtained in 2013, suggest an increased magnitude of drift acting on the wild populations relative to the reserve population. Based on the results of this study, it appears that steps taken in the early 2000s to eradicate genetically admixed individuals from the wild populations were successful. However, habitat fragmentation and small effective population sizes of the wild populations have led to accelerated drift and decreasing levels of within population genetic diversity. This may jeopardize the long-term persistence of C. bovinus .

Exploring the fluorinome of PFAS-impacted groundwater using 21 tesla FT-ICR mass spectrometry - Wenchao Lu; Lydia Babcock-Adams; Hamidreza Sharifan; John J. Kornuc; Shilai Hao; Christopher P. Higgins; Robert B. Young; Amy M. McKenna; Jens Blotevogel (Water Research, 2026)

deadtrees.earth — An open-access and interactive database for centimeter-scale aerial imagery to uncover global tree mortality dynamics - Clemens Mosig; Janusch Vajna-Jehle; Miguel D. Mahecha; Yan Cheng; Henrik Hartmann; David Montero; Samuli Junttila; Stéphanie Horion; Mirela Beloiu Schwenke; Michael J. Koontz; Khairul Nizam Abdul Maulud; Stephen Adu-Bredu; et al. (Remote Sensing of Environment, 2026)

Air quality at mass gatherings: assessing ventilation and occupancy in marquees to evaluate airborne infection risk during the COVID-19 pandemic - Ben M. Roberts; Filipa Adzic; Ailsa Hamilton-Smith; Christopher Iddon; Oliver Wild; Malcolm Cook; Steve Gwynne; Aoife Hunt; Liora Malki-Epshtein (Building and Environment, 2026)

Seascape diversity and configuration shape habitat selection across multiple coastal ecosystems - Jesse D. Mosman; Hayden P. Borland; Ashley J. Rummell; Christopher J. Henderson; Sam Allan; Alec Bannam; Stacy L. Bierwagen; Michael J. Bradley; Alex B. Carter; Daniela M. Ceccarelli; Robert Coles; Michael J. Emslie; et al. (Biological Conservation, 2026)

96-h methamphetamine self-administration elicits striatal dopamine depletion in male and female rats: a model of binge-like use - Bo Jarrett Wood; Ethan D. Brackett; Nicole M. Hall; Christopher E. Cannon; Robert D. Dayton; Courtney M. Keller; Nicholas E. Goeders; Kevin S. Murnane (Psychopharmacology, 2026)
Background Methamphetamine is a psychostimulant with significant public health implications. Chronic methamphetamine use is linked to profound dysregulation of the dopaminergic system, cognitive deficits, and psychiatric symptoms. While traditional experimenter administered “binge” dosing models reliably produce dopaminergic neurotoxicity, they fail to capture the volitional, drug intake characteristic of human methamphetamine use. Although self-administration paradigms better reflect human drug-taking behavior, they have yet to consistently reproduce the neurochemical deficits seen in the non-contingent models. Methods In this study, we employed a very long-access (96-h) methamphetamine self-administration model over eight weeks to evaluate whether contingent, volitional drug intake produces dopaminergic neurotoxicity. Male and female rats were given extended access to methamphetamine (0.06 mg/kg/infusion) for 96-h sessions weekly, with saline-yoked controls. Neurochemical analysis focused on striatal dopamine and metabolites to assess drug-induced alterations. Results Rats exhibited significant escalation in methamphetamine intake over eight weeks, with no sex differences in total intake. Importantly, striatal dopamine levels were significantly reduced in both male and female methamphetamine self-administering rats compared to saline-yoked controls, representing the first demonstration of dopamine depletion following voluntary administration methamphetamine self-administration. Dopamine depletion was significantly correlated with total methamphetamine intake. Interestingly, no significant changes were observed in dopamine metabolites (DOPAC, HVA). Conclusions These findings demonstrate that volitional methamphetamine intake under a 96-h access model induces robust dopaminergic deficits, paralleling those seen in non-contingent binge dosing. This model provides a translationally relevant paradigm, capturing both the behavioral and neurobiological aspects of human methamphetamine use, supporting its utility for investigating neurotoxicity and potential treatments.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Development of 3D printed microchips with encapsulated channels as miniaturized separation devices for bioanalysis - Christopher T. Desire; R. Dario Arrua; Billy Michalatos; Jing Zhang; Xanthe L. Venn; Michael Breadmore; Zlatko Kopecki; Neil McMillan; Robert Fitridge; Emily F. Hilder; Allison J. Cowin (Analytica Chimica Acta, 2026)

Biomechanical Analysis of the Effects of Knee Savers on Knee Joint Loading During High Knee-Flexion Tasks - Liying Zheng; John Z. Wu; Kevin D. Moore; Ashley L. Hawke; Robert E. Carey; Christopher M. Warren; Scott P. Breloff (Annals of Biomedical Engineering, 2026)

Ciguatera poisoning trends in Florida using a predictive hybrid model - Daniel Breininger; Christopher Ryzowicz; Motti Goldberger; Michael Splitt; Robert van Woesik; Nezamoddin N. Kachouie (Regional Studies in Marine Science, 2025)

Transportation in net-zero emissions futures: Insights from the EMF-37 model intercomparison study - Christopher Hoehne; Matteo Muratori; John Bistline; Carol Lenox; David L. McCollum; Morgan Browning; Kara Podkaminer; Robert H. Beach; Robbie Orvis; Shiqi Ou; Page Kyle; Sharyn Lie; et al. (Energy and Climate Change, 2025)

Bioenergy pathways within United States net-zero CO2 emissions scenarios in the Energy Modeling Forum 37 study - Ronald D. Sands; Liz Wachs; Patrick Lamers; Olivier Bahn; Robert H. Beach; Matthew Binsted; Geoffrey Blanford; Yongxia Cai; Francisco De La Chesnaye; James A. Edmonds; Leonard Göke; Chioke Harris; et al. (Energy and Climate Change, 2025)

How Do Patient Outcomes in Mechanical Thrombectomy for Large-Core Stroke Vary Based on Neuroimaging Modalities Used for Patient Selection? A Multicenter Multinational Study - Omar Alwakaa; Rahim Abo Kasem; Felipe Ramirez-Velandia; Aryan Wadhwa; Kimberly Han; Michael R. Levitt; Ali Alaraj; Pascal Jabbour; Joon-Tae Kim; Brian Howard; Ali Alawieh; Stacey Quintero Wolfe; et al. (Translational Stroke Research, 2025)

Extracorporeal photopheresis induces the release of anti-inflammatory fatty acids and oxylipins and suppresses pro-inflammatory sphingosine-1-phosphate - Gerhard Hagn; Ara Cho; Nina Zila; Barbara Sterniczky; Christian Jantschitsch; Dexin Dong; Andrea Bileck; Mariia Koren; Philipp Paulitschke; Thomas Mohr; Robert Knobler; Wolfgang Peter Weninger; et al. (Inflammation Research, 2025)
Aims Extracorporeal photopheresis (ECP) is a UVA-based phototherapy of whole blood and well established as a first line or combination therapy for the treatment of cutaneous T-cell lymphoma, systemic sclerosis, graft-versus-host disease and is used to control organ transplant rejection. While the proapoptotic activity on activated T-cells is evident, the clinical efficacy of this treatment also appears to be based on other yet unknown mechanisms. In this study, we aimed to identify novel mechanisms of ECP regardless of the patient’s background situation. Main methods To better understand the immediate consequences of ECP, we analyzed blood plasma of patients with different ECP indications immediately before and after treatment with regard to proteins and lipid mediators. Key findings While proteome profiling identified substantial inter-individual differences in the protein composition, no significant alteration was detectable upon treatment. In contrast, several fatty acids and lipid mediators were found to be significantly altered by ECP. Remarkably, upregulated lipid mediators including polyunsaturated fatty acids, 12-HEPE and 13-OxoODE have been described to be anti-inflammatory, while the downregulated molecules sphingosine-1-phosphate (S1P) and stearic acid are potent pro-inflammatory mediators. A selective sphingosine-1-phosphate-1 receptor (S1P1) modulator AUY954, which decreases S1P1 and experimentally reduces transplant rejection in vivo, showed greater anti-proliferative activity in human lung fibroblasts from COPD patients compared to normal lung fibroblasts, confirming that this pathway may be important in ECP and its mode of action. Significance and outlook In conclusion, we suggest that the ECP-induced changes in lipid mediators may contribute to the remarkable anti-inflammatory effects of the treatment. Depending on their lipid status, patients may benefit from novel treatment regimens combining ECP with lipid modulators. This could be used for the prevention of transplant organ rejection, the treatment of acute or chronic GvHD or transplant organ rejection and the long-term treatment of various skin diseases. This study uncovers novel mechanisms of ECP, that can be used to establish clinically relevant lipid profiles of patients to support patient stratification, predictive or prognostic purposes and thus personalized medical care in the framework of PPPM practice. A combination with S1P modulators may therefore have beneficial effects.

Statistical Surgical Process Modeling: Analysis of Workflow and Performance of Emerging Technologies in Image-Guided Spine Surgery - Anshuj Deva; Tatiana A. Rypinski; Parvathy Sudhir Pillai; Bhavin Soni; Owais Sarwar; Aaron C. Milhorn; Aaron K. Jones; Claudio E. Tatsui; Laurence D. Rhines; Robert Y. North; Christopher Alvarez-Breckenridge; Justin E. Bird; et al. (Annals of Biomedical Engineering, 2025)

Predictions of southern migration timing in coastal sharks under future ocean warming - Maria H. Manz; Oliver N. Shipley; Robert M. Cerrato; Robert E. Hueter; Alisa L. Newton; John P. Tyminski; Bryan R. Franks; Tobey H. Curtis; Christopher Fischer; Joshua P. Zacharias; Christopher Scott; Keith J. Dunton; et al. (Conservation Biology, 2025)
Projected redistribution of marine species due to ocean warming may undermine current conservation efforts. Yet, there have been few studies on how ocean warming may alter migration timing. Across 5 years of acoustic telemetry data (2018–2022), we determined environmental drivers of southward migration timing for 6 migratory shark species from summer habitats in the Northwest Atlantic Ocean. We then forecasted how migratory timing from 3 regions, between the New England shelf and Mid‐Atlantic Bight, would respond under future sea surface temperatures (SSTs). Photoperiod and SST were strong predictors of southern migration in sharks, but the strength of these effects varied latitudinally. Overall, we found delayed departure dates from summer habitats under future elevated SSTs, indicating prolonged residency in northern habitats (median = ∼12 days). Sandbar sharks ( Carcharhinus plumbeus ) exhibited the largest delay in the onset of southern migrations (median = 29 days), whereas sand tiger sharks ( Carcharias taurus ) and white sharks ( Carcharodon carcharias ) exhibited the smallest delay (median = 1 day). Delays in migration timing of coastal shark species may alter local ecosystem dynamics and challenge current management strategies. These findings illustrate the utility of collaborative data‐sharing networks to expand understanding of broadscale animal movements and contribute to effective species management under a changing climate.

Angiotensin II, miR-34a, and AGTRAP crosstalk in arterial smooth muscle cells - Maria Cristina Florio; Sara Sileno; Liqun Jiang; Marco D’Agostino; Sunayana Begum Syed; Laura Monteonofrio; Mirko Baranzini; Chiara Prampolini; Federica Macrì; Manuel Casaburo; Nadia Fanotti; Stefania Castiglione; et al. (GeroScience, 2025)
Arterial aging is associated with enhanced angiotensin II (Ang II) signaling via Ang II type 1 receptor (AT1R) and with microRNA-34a (miR-34a) increased expression. AT1R-associated protein (ATRAP/Agtrap) binds to AT1R, promotes its internalization, and inhibits Ang II signaling. This study addresses the hypothesis that miR-34a targets ATRAP/Agtrap and enhances Ang II pro-inflammatory signaling via AT1R in arterial vascular smooth muscle cells (VSMC). Our results show that miR-34a exhibits an age-associated increase in Rhesus monkey’s common carotid artery and rat aorta. Further, AGTRAP protein expression is lower in old rat VSMC and in old mice aorta. Ang II enhances miR-34a in old rat VSMC and human aortic smooth muscle cells (HASMC), and inhibits AGTRAP and sirtuin 1 (SIRT1) mRNA/protein expression. In miR-34a-overexpressing HASMC, AGTRAP and SIRT1 mRNA/protein decrease, and these effects are rescued by AGTRAP forced expression. Moreover, miR-34a directly targets AGTRAP and AGTRAP downmodulation further enhances miR-34a expression decreasing SIRT1 in HASMC. Finally, Ang II and miR-34a induce the upregulation of pro-inflammatory genes, interleukin (IL)-6, cyclooxygenase 2 (COX2), monocyte chemoattractant protein-1 (MCP-1), and milk fat globule-epidermal growth factor 8 (MFGE8) in HASMC, and this effect is abolished by AGTRAP forced expression. In conclusion, Ang II upregulates miR-34a, activating a negative feedback loop on AGTRAP that reinforces Ang II signaling. The age-associated AGTRAP downmodulation in central arteries and VSMC underlies a potential miR-34a/AGTRAP role in vascular aging.

An expert elicitation to inform coastal management decision-making for mitigating future hazards - Davina L. Passeri; Matthew Richardson; Julien Martin; Simeon Yurek; Karim Alizad; Matthew V. Bilskie; James Flocks; Donya Frank-Gilchrist; Robert L. Jenkins; Rangley C. Mickey; Margaret L. Palmsten; Christopher G. Smith; et al. (Journal of Environmental Management, 2025)

Reef-scale variation in larval supply and settlement: validating Lagrangian dispersal predictions with observations of coral larvae - Robert A.B. Mason; Clothilde Langlais; Julian Uribe-Palomino; Mark Tonks; Frank Coman; Severine Choukroun; Javier Porobic; Christopher Doropoulos (Estuarine, Coastal and Shelf Science, 2025)

Sedimentation and deformation in oblique continental rifts: The role of climate-tectonic interactions - Liang Xue; Robert Moucha; Christopher A. Scholz; John Naliboff (Earth and Planetary Science Letters, 2025)

Antitrypanosomal secondary metabolites from medicinal plants: a review - Robert Christopher (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Flood hazard assessment due to dam breaching considering river morphodynamics - Andrea Antonella Graziano; Matthew Christopher Halso; Robert Michael Boes; Francesco Macchione; David Florian Vetsch (Natural Hazards, 2025)
The failure of a dam is a catastrophic event, which is expected to induce drastic changes to the downstream bed morphology. However, knowledge about channel response due to dam-breach flood wave and its impact on flood hydrodynamics and hazard assessment is still poor. Therefore, we studied the river morphodynamics associated with dam-breach floods, in order to understand the possible extent and distribution of the erosion depths and deposition heights, as well as the consequences of these changes on the flood hydrodynamics and, above all, on the hazard assessment. In this work, these impacts were investigated by simulating the hypothetical failure of a real embankment dam, using a simplified physically based model for the computation of the dam-breach hydrograph, and a two-dimensional morphodynamic model for the downstream wave propagation. To account for some of the uncertainties related to both models, two breach shape scenarios and three mobile bed configurations were considered. It was found that bed erodibility affected the flood hazard much more than the breach shape. Furthermore, the mobile bed configuration significantly affected river morphology in the narrow and steep part of the river, where both erosion depths and deposition heights were very high, while bed elevation changes in the downstream plain part of the river were significantly less. Finally, consideration of river morphodynamics in dam-breach flood wave propagation has been shown to shorten the arrival times of the flood wave and lead to more intense flood hazard due to a remarkable increase in the unit discharge.

Challenges and Strategic Recommendations for Enhancing Quantification and Projection of Forest Carbon Dynamics - Holly L. Munro; Christopher W. Woodall; William R. L. Anderegg; Jeff W. Atkins; Colin M. Beier; Bronson P. Bullock; Kendall DeLyser; David D. Diaz; Bianca N.I. Eskelson; Margaret E. K. Evans; John D. Foppert; Bryan C. Foster; et al. (Journal of Forestry, 2025)

Revealing Chronotypes Across Aquatic Species Using Acoustic Telemetry - Martina Martorell‐Barceló; David Abecasis; Mourad Akaarir; Alexandre Alonso‐Fernández; Robert Arlinghaus; Eneko Aspillaga; Margarida Barcelo‐Serra; Niels W. P. Brevé; Jan G. Davidsen; Antoni Gamundí; Amalia Grau; Bernat Hereu; et al. (Fish and Fisheries, 2025)
Acoustic telemetry offers valuable opportunities to investigate individual variability in circadian‐related and other behaviours and how environmental cues shape these patterns in wild fish populations. However, this potential has not yet been fully exploited. We conducted a meta‐analysis on 44 datasets from 34 distinct marine and freshwater species and different types of data (acoustic detections, depth, acceleration and positioning). Our aim was to explore the potential of acoustic telemetry in identifying chronotypes as consistent among‐individual differences in circadian‐related behaviours. First, we applied hidden semi‐Markov models to classify individual time series into active and rest states. Subsequently, we computed two classical circadian‐related behavioural traits: awakening time (as the activity onset) and rest onset (as the activity offset). Subsequently, we identified distinct phenotypes by decomposing behavioural variation into within‐ and among‐individual components based on repeatability scores. We found evidence of distinct chronotypes in 17 species, with average repeatability scores of 0.52 for awakening time and 0.43 for rest onset, revealing that chronotypes are common in aquatic species. Our findings highlight that both the data type, particularly acceleration sensors, and the number of detections are effective tools for exploring chronotypes. Our study proposes a novel approach to characterising daily activity patterns in aquatic species, predominantly in fishes, and provides guidelines for investigating chronotypes across diverse taxa. We emphasise the promise of biotelemetry and advanced statistical models for improving our understanding of the behaviour of aquatic species and highlight the value of synthesising across large data sets collected in networks of biotelemetryprojects.

Sex specific gut bacterial community structure: implications for frailty risk in people with HIV - Aline Zaparte; John W. Lammons; Christopher M. Taylor; Meng Luo; Hui-Yi Lin; Robert W. Siggins; Patricia E. Molina; David A. Welsh (GeroScience, 2025)

Best bang for your buck: Considerations for cost-efficiency in knowledge co-production - Denis B. Karcher; Christopher Cvitanovic; Alistair J. Hobday; Rebecca Shellock; Robert L. Stephenson; Ingrid van Putten (Marine Policy, 2025)

Projecting stream water quality using Weighted Regression on Time, Discharge, and Season (WRTDS): An example with drought conditions in the Delaware River Basin - Christopher T. Green; Robert M. Hirsch; Hedeff I. Essaid; Ward E. Sanford (Science of The Total Environment, 2025)

One for all and all for one health: Harmonizing SARS-CoV-2 wastewater surveillance results across a laboratory network - Alex H.S. Chik; Christopher Adam; Jane J.Y. Ho; Taylor Aris; Eric J. Arts; R. Stephen Brown; David Bulir; Ryland Corchis-Scott; Christopher T. DeGroot; Robert Delatolla; Philip Dennis; Hadi A. Dhiyebi; et al. (Science of The Total Environment, 2025)

Wildlife of tidal forested wetlands in the southeastern Atlantic United States - James T. Anderson; Andrew P. Hopkins; Crystal Anderson; Miriam Boucher; Rene Brown; Aruã de Castro; Sindupa De Silva; Robert M. Greco; Jordan E. McCall; Oluwatobi Emmanuel Olaniyi; Christopher Pettengill; Akshit R. Suthar; et al. (Estuarine, Coastal and Shelf Science, 2025)

Untangling parasite epidemiology of mountain gorillas through historical samples: Strongylid nematodes are friends or foe? - Bethan Mason; Vladislav Ilík; Barbora Červená; Michael Cranfield; Julius Nziza; Benard Ssebide; Kirsten Gilardi; Carine Uwamahoro; Winnie Eckardt; Felix Ndagijimana; Richard Muvunyi; Prosper Uwingeli; et al. (Biological Conservation, 2025)

Having a gander at goose behaviour. Evaluating time-activity of captive and wild geese at two different wetland sites - Paul Rose; Amelia Roper; Christopher Giorgio; Joe Thomas; Robert Kelly; Michelle F. O’Brien (Applied Animal Behaviour Science, 2025)

Whole Genome Sequencing Reveals How Plasticity and Genetic Differentiation Underlie Sympatric Morphs of Arctic Charr - Khrystyna Kurta; Mariano Olivera Fedi; Kendall Baker; Tom Barker; Leah Catchpole; Claudio Ciofi; Arianna Cocco; Joanna Collins; Genevieve Diedericks; Maria Angela Diroma; Alex Durrant; Kjetil Hindar; et al. (Molecular Ecology, 2025)
Salmonids have a remarkable ability to form sympatric morphs after postglacial colonisation of freshwater lakes. These morphs often differ in morphology, feeding and spawning behaviour. Here, we explored the genetic basis of morph differentiation in Arctic charr ( n = 283) by first establishing a high‐quality reference genome and then using this in whole genome sequencing of distinct morphs present in two Norwegian and two Icelandic lakes. The four lakes represent the spectrum of genetic differentiation between morphs from one lake with no genetic differentiation between morphs, implying phenotypic plasticity, to two lakes with locus‐specific genetic differentiation, implying incomplete reproductive isolation, and one lake with strong genome‐wide divergence consistent with complete reproductive isolation. As many as 12 putative inversions ranging from 0.45 to 3.25 Mbp in size segregated among the four morphs present in one lake, Thingvallavatn, and these contributed significantly to the genetic differentiation among morphs. None of the putative inversions were found in any of the other lakes, but there were cases of partial haplotype sharing in similar morph contrasts in other lakes. Our findings are consistent with a highly polygenic basis of morph differentiation with population‐specific selection on alleles linked to the development of similar morph phenotypes. The results support a model where morph differentiation is first established through phenotypic plasticity, leading to niche expansion and separation. This may be followed by gradual development of reproductive isolation, locus‐specific differentiation and eventually complete reproductive isolation and genome‐wide divergence.

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Well-posed boundary conditions and energy stable discontinuous Galerkin spectral element method for the linearized Serre equations - Kenny Wiratama; Kenneth Duru; Stephen Roberts; Christopher Zoppou (Wave Motion, 2025)

The discovery and preclinical pharmacology of JNJ-10450232 (NTM-006), a centrally penetrant, non-opioid structural analog of acetaminophen with comparable analgesic and anti-pyretic properties but no evidence of hepatotoxicity - Christopher M. Flores; John R. Carson; Ellen E. Codd; Scott L. Dax; Edwin K. Kuffner; Paul L. Stahle; Robert A. Neff; Gary E. Eichenbaum (Regulatory Toxicology and Pharmacology, 2025)

Secular compositional changes in granitoids and felsic volcanics: the tectonic setting control - Kent C. Condie; Stephen J. Puetz; Christopher J. Spencer; Nick M.W. Roberts (Chemical Geology, 2025)

Dual-strain detection of norovirus GI.1 and GII.4 in food samples using epitope-imprinted polymers - Amy Dann; Pankaj Singla; Jake McClements; Minji Kim; Sloane Stoufer; Robert D. Crapnell; Craig E. Banks; Shayan Seyedin; Mark Geoghegan; Christopher F. Blanford; Matthew D. Moore; Marloes Peeters (Analytica Chimica Acta, 2025)

Nicotinamide riboside combined with exercise to treat hypertension in middle-aged and older adults: a pilot randomized clinical trial - Yi Lin; Rola S. Zeidan; Stephanie Lapierre-Nguyen; Hannah M. Costello; Stephen D. Anton; Thomas W. Buford; Demetra D. Christou; Michelle L. Gumz; Christiaan Leeuwenburgh; Christopher R. Martens; Mary M. McDermott; Marie E. Migaud; et al. (GeroScience, 2025)
Aerobic exercise lowers blood pressure (BP) with varying effects in hypertensive adults, potentially due to age-related nicotinamide adenine dinucleotide (NAD) metabolism dysregulation. This pilot randomized clinical trial (RCT) tested the efficacy of combining aerobic exercise with the NAD booster nicotinamide riboside (NR) to enhance BP control. In this double-blinded RCT, 54 sedentary adults (≥ 55 years) with mean daytime systolic BP (SBP) ≥ 130 mmHg were randomized to 6 weeks of 1000 mg/day of NR combined with 3 days/week of supervised 30-min walking exercise (NR + Ex), Placebo combined with the same exercise regimen (PL + Ex), or NR alone (NR). The primary outcome was daytime SBP. Other outcomes included pulse wave velocity (PWV), NAD catabolites, and nighttime BP. The primary comparison was between NR + Ex and PL + Ex. Of 54 participants (mean age 67 years, 61% female), 49 (NR + Ex: n = 15, PL + Ex: n = 16, NR: n = 18) completed all study visits (93% adherence to exercise and 90% to supplementation). NR + Ex (mean change = 5.19 ± 13.2 mmHg) did not reduce SBP more than PL + Ex (− 2.71 ± 10.5 mmHg). NR + Ex (− 0.31 ± 0.77 m/s) showed a trend toward a greater reduction in PWV. Levels of NAD catabolites were higher in NR groups. In a post hoc analysis, NR + Ex showed a trend toward greater nighttime BP reductions (systolic: − 9.6 ± 9.22; diastolic: − 4.51 ± 7.12 mmHg) in participants without antihypertensive medications. NR + Ex was not superior to PL + Ex in reducing BP in hypertensive middle-aged and older. However, trends toward greater nighttime BP reduction in NR + Ex in participants without antihypertensive medication warrant further investigation in a Phase IIb RCT. Graphical Abstract

Digital monitoring of fish-trade for valuing bycatch and characterizing data-poor fisheries in Tanintharyi, Myanmar - Iris Segura-García; Robert Pomeroy; Michael McCoy; Christopher Moore; Krista McCoy; Stephen Box (Ocean & Coastal Management, 2025)

Seasonal variation of trifluoroacetic acid (TFA) in Antarctic ice cores analysed by direct injection non-suppressed ion chromatography-mass spectrometry (nsIC-MS) - Estrella Sanz Rodriguez; Mingxia Lai; Harrison Stevens; Meredith K. Nation; Christopher T. Plummer; Lenneke M. Jong; Jason L. Roberts; Andrew D. Moy; Andrew R. Bowie; Mark A. Curran; Brett Paull (Science of The Total Environment, 2025)

Environmental contamination predicts mammal diversity and mesocarnivore activity in the Seattle-Tacoma metro area - Yasmine Hentati; Cesar O. Estien; Zachary Hawn; Mark J. Jordan; Robert A. Long; Rachael Mueller; Katie R. Remine; Laura R. Prugh; Christopher J. Schell (Urban Ecosystems, 2025)

A time course analysis through diapause reveals dynamic temporal patterns of microRNAs associated with endocrine regulation in the butterfly Pieris napi - Kevin T. Roberts; Rachel A. Steward; Philip Süess; Philipp Lehmann; Christopher W. Wheat (Molecular Ecology, 2025)
Organisms inhabiting highly seasonal environments must cope with a wide range of environmentally induced challenges. Many seasonal challenges require extensive physiological modification to survive. In winter, to survive extreme cold and limited resources, insects commonly enter diapause, which is an endogenously derived dormant state associated with minimized cellular processes and low energetic expenditure. Due to the high degree of complexity involved in diapause, substantial cellular regulation is required, of which our understanding primarily derives from the transcriptome via messenger RNA expression dynamics. Here we aim to advance our understanding of diapause by investigating microRNA (miRNA) expression in diapausing and direct developing pupae of the butterfly Pieris napi. We identified coordinated patterns of miRNA expression throughout diapause in both head and abdomen tissues of pupae, and via miRNA target identification, found several expression patterns to be enriched for relevant diapause‐related physiological processes. We also identified two candidate miRNAs, miR‐14‐5p and miR‐2a‐3p, that are likely involved in diapause progression through their activity in the ecdysone pathway, a critical regulator of diapause termination. miR‐14‐5p targets phantom , a gene in the ecdysone synthesis pathway, and is upregulated early in diapause. miR‐2a‐3p has been found to be expressed in response to ecdysone, and is upregulated during diapause termination. Together, the expression patterns of these two miRNAs match our current understanding of the timing of hormonal regulation of diapause in P. napi and provide interesting candidates to further explore the mechanistic role of microRNAs in diapause regulation.

Coral calcification mechanisms across a natural environmental mosaic in Hawai'i - Verena Schoepf; Andréa G. Grottoli; Rowan H. McLachlan; James T. Price; Christopher P. Jury; Robert J. Toonen; Eric H. De Carlo; Malcolm T. McCulloch (Limnology and Oceanography, 2025)
Coral calcification is key to coral reef growth and function but may be compromised under increasing global and local stressors. Corals modify the carbonate chemistry of their calcifying fluid to facilitate calcification, but little is known about how these mechanisms vary across the substantial differences in reef seawater conditions that can occur over as little as a few kilometers. Here, we used boron‐based geochemical proxies (δ 11 B, B/Ca) to investigate how three common Hawaiian coral species ( Montipora capitata , Porites compressa , Porites lobata ) regulate the carbonate chemistry of the calcifying fluid along a natural environmental mosaic of seawater carbonate chemistry and significant wave height. We found that calcification mechanisms were governed by complex species and site interactions: while all species generally differed from each other in their calcifying fluid chemistry, they also responded differently to site‐specific environmental conditions. These results highlight that there are varying degrees of calcification mechanism plasticity in response to changing environmental conditions. Furthermore, species‐specific patterns of pH upregulation inside the calcifying fluid were good predictors of calcification responses to ocean acidification and warming in at least two of the three species, with M. capitata being a clear winner under future ocean conditions. Our findings provide important insights into how corals calcify across a natural environmental mosaic and highlight the differential potential for an adaptive capacity in calcification mechanisms in the face of intensifying climate change.

Chemical fingerprinting and weathering assessment of Sanchi oil tanker spill residues that impacted the southern Japanese islands - Gerald F. John; Robert K. Nelson; Ryuichiro Nishi; Jagoš R. Radović; Christopher M. Reddy (Marine Pollution Bulletin, 2025)

Exploring the role of building codes in protecting occupants from overheating—A Canadian perspective - Chun Yin Siu; Sarah Brown; Sébastien Brideau; Lili Ji; William O’Brien; Alex Ferguson; Erin Greco; Marianne Touchie; Christopher Mclellan; Robert Lepage; Nina Dmytrenko (Energy and Buildings, 2025)

The Cost of Antivenom: A Cost Minimization Study using the North American Snakebite Registry - Benjamin Herzel; Neev Batavia; Paul Gavaza; Tammy Phan; Emmelyn Samones; Anne-Michelle Ruha; Jakub Furmaga; Christopher Hoyte; Brian J. Wolk; Peter Akpunonu; Adam Algren; Alexandra Amaducci; et al. (Journal of Medical Toxicology, 2025)
Envenomation is a global health issue, with over 9,000 encounters managed in the United States yearly. The introduction of immunoglobulin fragment antivenom has reduced the risk of hypersensitivity. This study compares treatment costs of crotaline envenomation using the Fab and F(ab’) 2 antivenoms as reported to the North American Snakebite Registry (NASBR), a nationwide surveillance tool. Methods This was a retrospective analysis of NASBR data between 2018 and 2020. The following data points were assessed: patient demographics (age, gender, race), snake species, type of antivenom used, and treatment costs. Unit costs were estimated based on United States Centers for Medicare and Medicaid Services data. Average (mean) per patient costs from the payer perspective were calculated by multiplying resources by the unit costs. Sensitivity analyses were performed regarding cost variance and snake species. All costs reported in this study are in U.S. dollars. Results The average total cost of treatment was $31,343 per person, with medications contributing 72% of the total. Average total cost among patients who received Fab treatments was $33,347 per person compared to $19,747 among patients who received F(ab’) 2 . Antivenom costs accounted for 75% of the total cost in the Fab group and 42% in the F(ab’) 2 group. F(ab’) 2 required more vials than Fab (median 18 versus 10). Non-antivenom costs such as hospitalizations were higher in the F(ab’) 2 group. Using average sale prices increased average total cost to $52,572; Fab remained more expensive. Conclusion Antivenom is the primary cost driver in snakebite treatment in North America. Treatment with F(ab’) 2 resulted in lower overall costs, driven by lower cost of antivenom. F(ab’) 2 did not significantly lower overall resource use except for blood product administration.

Cross‐Continental Analysis Shows That Disturbance Effects on Reptile Body Condition Do Not Predict Abundance Responses - Kristina J. Macdonald; Don A. Driscoll; Michael D. Craig; Robert A. Davis; Steven J. Hromada; C. M. Gienger; Lee A. Fitzgerald; Daniel J. Leavitt; Danielle K. Walkup; Rickard Abom; Adrian F. Wayne; Gordon R. Friend; et al. (Global Change Biology, 2025)
Ecological disturbances are discrete events that alter or transform the physical, chemical, or biological characteristics of ecosystems. Disturbance can cause animal populations to decline and, according to the risk‐disturbance hypothesis and population collapse framework, these declines can be predicted by declines in animal body condition. However, no research has empirically examined the general relationship between body condition and abundance, nor their relationship in response to disturbance. We used a combined dataset representing 33 studies and > 42,000 observations of 75 species from Australia, New Zealand, Spain and the United States of America to test predictions relating to the relationship between reptile body condition and abundance. We first investigated the relationship at the site level and then used meta‐analytical models to test whether populations showed linked changes in abundance and body condition in response to disturbance. We further tested whether key environmental and species traits influenced this relationship and whether there was a time‐lagged effect of body condition responses on abundance. We found a positive relationship between mean reptile body condition and abundance at the site level. However, the relationship was largely lost when investigating population responses to disturbance. As such, our results provided no support for the risk‐disturbance hypothesis and limited support for the population collapse framework. Therefore, the impacts of disturbance on reptile body condition cannot be assumed to reflect or predict abundance responses. We provide a new conceptual framework that shows how disturbances can modify or uncouple the relationship between abundance and body condition by influencing underlying drivers, such as predation, competition and resource availability. Monitoring programs that infer population impacts based on changes in body condition should first confirm the relationship between these two variables in the relevant study system.

International Consortium on Ageing-Related Pathologies (ICCARP) Audiovestibular Group: fostering international consensus to refine International Classification of Diseases (ICD-11) codes for hearing loss across the life course - Dialechti Tsimpida; Michael A. Akeroyd; Barry L. Bentley; Shuvarthi Bhattacharjee; Michael R. Bowl; Emma Broome; Stuart R. G. Calimport; Sian Calvert; Gary Christopher; Tom Dening; Silvia Di Bonaventura; Ankita Goswami; et al. (GeroScience, 2025)

Subcortical white matter hyperintensities and motor function in parkinson’s disease: findings from the ONDRI study - Daniela Cristina Carvalho de Abreu; Frederico Pieruccini-Faria; Anthony E. Lang; Benjamin Cornish; William McIlroy; Mandar Jog; Mario Masellis; Joel Ramirez; Christopher Scott; Sean Symons; Sandra E. Black; Stephen R. Arnott; et al. (GeroScience, 2025)

Adsorption of MC-LR enabled by customizable 3D printed graphene-coated structures - Justin D. Puhnaty; Jacob M. Lalley; Alan J. Kennedy; Jaylen A. Davis; Angela M. Evans; Sarah Grace Zetterholm; Connor C. Clark; Jesse L. Roberts; Christopher S. Griggs; Benjamin S. Magbanua (Journal of Environmental Chemical Engineering, 2025)

Overexpression of the WWE domain of RNF146 modulates poly-(ADP)-ribose dynamics at sites of DNA damage - Rasha Q. Al-Rahahleh; Wynand P. Roos; Kate M. Saville; Joel F. Andrews; Zhijin Wu; Christopher A. Koczor; Aishwarya Prakash; Robert W. Sobol (DNA Repair, 2025)

Subduction and melting of biogenic and ferromanganese sediments as evidenced by sub-Moho granitoids - Tiago Valim Angelo; Christopher J. Spencer; Hong-Yan Li; Derek Knaack; Ziyi Zhu; Marina Seraine; Nick M.W. Roberts; Evelyne Leduc; Sophie Divilek; Anna Ren; Brian Joy; Gui-Mei Lu (Chemical Geology, 2025)

Harnessing genotype and phenotype data for population-scale variant classification using large language models and bayesian inference - Toby R. Manders; Christopher A. Tan; Yuya Kobayashi; Alexander Wahl; Carlos Araya; Alexandre Colavin; Flavia M. Facio; Hillery Metz; Jason Reuter; Laure Frésard; Samskruthi R. Padigepati; David A. Stafford; et al. (Human Genetics, 2025)

Regeneration Response to Shelterwood-Burn Treatments in a Dry Oak-Dominated Forest - Sarah J. Rademacher; Daniel C. Dey; John M. Kabrick; Robert W. E. Quackenbush; Michael R. Saunders; J. Travis Swaim; Christopher D. Thornton; Michael A. Jenkins (Forest Science, 2025)

An energy balance climate model for Mars represented by 4002 Goldberg polyhedrals with applications to ground ice re-distribution driven by obliquity cycles - Robert Olszewski; Piotr Pałka; Agnieszka Wendland; Alison F.C. Bridger; Melinda A. Kahre; Christopher P. McKay (Planetary and Space Science, 2025)

Field Note: Learning from Early Application of a Transition Forest Climate Adaptation Planting Strategy Incorporating Assisted Migration in Southern New England - Christopher C. Riely; Robert W. MacMillan; Maria K. Janowiak; Richard H. Blodgett (Journal of Forestry, 2025)
This field note presents an early example of a forest climate adaptation tree planting project incorporating assisted migration in southern New England which is valuable in providing lessons that can inform future work in this region and elsewhere. This effort is notable for moving forward through the implementation and monitoring stages during a period when many similar projects encountered barriers. The project is located on watershed protection forestland owned by the Providence Water Supply Board, a public utility in Rhode Island. Using a suite of tools developed through the Climate Change Response Framework, watershed forest managers carried out a “transition” strategy climate adaptation planting in 2015, seeking to improve regeneration in an area of forest near the state’s main drinking water reservoir. Seedlings of both native and assisted migration tree species projected to be adapted to future climate conditions were planted in adjacent areas that had experienced oak regeneration failure. Half of the seedlings of each species were planted within a deer exclosure fence and half were planted in an unfenced area. Annual monitoring has allowed for comparison of survival and growth of a subset of planted trees at these two sites for 10 growing seasons. Deer herbivory is believed to be the most significant factor contributing to differences in tree survival rates between the fenced and unfenced areas. Both native and non-native species have been able to survive when protected from deer browse, while differences are inconclusive after nearly a decade. This informal experimental planting provides a case study illustrating some of the opportunities and challenges associated with implementing assisted migration in a non-research, operational-scale setting.

Development of a Detailed Finite Element Model of the BIPED MK2 and Verification of Fidelity in Two Cases of Blunt Impact - Robert Chauvet; Ashton Martin; Jennifer Rovt; Oren Petel; Simon Ouellet; Lindsey Westover; Christopher R. Dennison (Annals of Biomedical Engineering, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Tropical Land‐Use Change Disrupts Zeta‐Diversity Across Taxa - Edicson Parra‐Sanchez; Guillaume Latombe; Simon C. Mills; Jacob B. Socolar; Felicity A. Edwards; Diego Martinez‐Revelo; Oscar A. Perez‐Escobar; Robert W. Davies; Christopher G. Bousfield; Gianluca R. Cerullo; Jose Manuel Ochoa‐Quintero; Torbjørn Haugaasen; et al. (Global Change Biology, 2025)
Land‐use change causes community turnover via local extinction and colonisation of species, driving biotic homogenization or heterogenization at larger spatial scales. Quantification of these processes has focused on beta‐diversity metrics, which upweight rarity and overlook the role of widespread species. A key knowledge gap is understanding the impact of land‐use change on both rare and widespread species—zeta‐diversity—allowing the detection of statistical patterns and drivers based on community turnover across space. We sampled bird, dung beetle, and orchid communities in 341 plots across natural (Andean forests and paramo) and transformed habitats (pasturelands) spanning ~270 km north‐to‐south in the Colombian Andes. We detected major losses in species richness following land‐use conversion, which disrupts zeta‐diversity across elevation in two ways. First, biodiversity patterns are rewired such that bird and dung beetle communities become structured by dispersal ability, overriding the effects of natural biogeographical drivers (i.e., elevation) and landscape conditions (i.e., canopy cover). Second, land‐use change causes biotic homogenization across bird communities, with pasture retaining twice as many widespread species than natural habitats, and a four‐fold reduction in widespread dung beetle species pointing to subtractive heterogenization. Orchid communities show high community turnover in both natural and transformed habitat. Our results show that the effect of local deforestation has a doubly devastating impact simplifying communities and reducing widespread species. Transforming natural habitats into anthropogenic landscapes may substantially raise extinction risk for communities composed of both widespread and rare species, especially in orchids as the most sensitive taxon.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Systemic toxicity after rattlesnake envenomation in patients using angiotensin converting enzyme inhibitors: A North American Snakebite Registry study - A.M. Ruha; M.B. Spyres; R. Culbreth; B. Wolk; C. Hoyte; S. Campleman; Peter Akpunonu; Adam Algren; Alexandra Amaducci; Sukhshant Atti; Connie Aubin; Kevin Baumgartner; et al. (Toxicon, 2025)

Mortality and diurnal temperature range in Virginia - Robert E. Davis; Owen Himmel; Parker K. Sims; Christopher M. Fuhrmann (International Journal of Biometeorology, 2025)
The relationship between diurnal temperature range (DTR) and daily mortality from 2005 to 2020 is examined for seven large metropolitan areas in Virginia using distributed lag non-linear models that control for temperature and humidity. The relative risk of mortality increases for very high DTR, and there is a short lag effect of several days. High risk DTR days are rare, typically occurring less than 1% of the time at most locations. These days primarily occur in spring and are characterized by high pressure and low humidity that allow overnight temperatures to drop substantially. High DTR days are often associated with elevated respiratory and cardiovascular mortality and tend to impact the elderly. The similarity between the mortality response to high DTR and that of high temperatures alone, coupled with the lack of clear physiological underpinnings, challenges the notion that these responses are independent. The prevalent spring peak in dangerous DTR days suggests that lack of acclimatization to hot and humid conditions may impose strain on the cardiovascular and respiratory systems.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Positive Feedback on Climate Warming by Stream Microbial Decomposers Indicated by a Global Space‐For‐Time Substitution Study - Javier Pérez; Luz Boyero; Richard G. Pearson; Mark O. Gessner; Alan Tonin; Naiara López‐Rojo; Juan Rubio‐Ríos; Francisco Correa‐Araneda; Alberto Alonso; Aydeé Cornejo; Ricardo J. Albariño; Sankarappan Anbalagan; et al. (Global Change Biology, 2025)
Decomposition of plant litter is a key ecological process in streams, whose contribution to the global carbon cycle is large relative to their extent on Earth. We examined the mechanisms underlying the temperature sensitivity (TS) of instream decomposition and forecast effects of climate warming on this process. Comparing data from 41 globally distributed sites, we assessed the TS of microbial and total decomposition using litter of nine plant species combined in six mixtures. Microbial decomposition conformed to the metabolic theory of ecology and its TS was consistently higher than that of total decomposition, which was higher than found previously. Litter quality influenced the difference between microbial and total decomposition, with total decomposition of more recalcitrant litter being more sensitive to temperature. Our projections suggest that (i) warming will enhance the microbial contribution to decomposition, increasing CO 2 outgassing and intensifying the warming trend, especially in colder regions; and (ii) riparian species composition will have a major influence on this process.

Particulate matter concentrations in UK schools: A nationwide study into the influence of ambient PM2.5 and the resulting exposure potentials - Alice E.E. Handy; Samuel G.A. Wood; Katherine Roberts; Christopher S. Malley; Henry C. Burridge (Science of The Total Environment, 2025)

Evaluating rainfall and graupel retrieval performance of the NASA TROPICS pathfinder through the NOAA MiRS system - John Xun Yang; Yong-Keun Lee; Shuyan Liu; Christopher Grassotti; Quanhua Liu; William Blackwell; Robert Vincent Leslie; Tom Greenwald; Ralf Bennartz; Scott Braun (Remote Sensing of Environment, 2025)

Adaptive sampling with PIXL on the Mars Perseverance rover - Peter R. Lawson; Tanya V. Kizovski; Michael M. Tice; Benton C. Clark; Scott J. VanBommel; David R. Thompson; Lawrence A. Wade; Robert W. Denise; Christopher M. Heirwegh; W. Timothy Elam; Mariek E. Schmidt; Yang Liu; et al. (Icarus, 2025)

Applying fuzzy logic cognitive modeling to integrate socio-ecological knowledge for carnivore conflict management - Vasavi Prakash; Robert A. Gitzen; Christopher A. Lepczyk (Biological Conservation, 2025)

Trace element and isotope composition of calcite, apatite, and zircon associated with magmatic sulfide globules - Maria Cherdantseva; Marco L. Fiorentini; Christopher M. Fisher; Antony I. S. Kemp; Laure A. J. Martin; Matvei Aleshin; Malcolm P. Roberts (Mineralium Deposita, 2025)
The formation of volatile-rich phases in magmatic sulfide systems has been interpreted at least in six different ways. The most popular model attributes their origin to secondary processes, mostly due to the presence of serpentine, chlorite, phlogopite, amphibole, and calcite. While chlorite and serpentine are likely to form as alteration products, the other volatile-rich minerals have the potential to originate in a range of ways, including by primary magmatic processes. Based on mineralogical and petrological studies, it was recently suggested that volatile- and incompatible element-rich halos around sulfide globules may form due to the interaction between three immiscible liquids: silicate, carbonate, and sulfide. This hypothesis was confirmed by experimental data revealing the systematic envelopment of sulfide globules by carbonate melt, indicating their mutual affinity. In this study, we present data on isotopic signatures and trace element distributions of three minerals commonly found in spatial association with sulfides—calcite, apatite, and zircon—to address the question of the source and nature of volatiles and other incompatible elements involved in the formation of the halos. Here we compare our new hypothesis with all the previously proposed explanations to show if they can be consistent with obtained results. Our findings indicate that both mantle and crustal sources play a role in the formation of volatile- and incompatible element-rich halos, strongly correlating with sulfur isotope data previously reported for the sulfide globules in the same intrusions. This correlation confirms the shared origin of sulfides, carbonate and fluids during ore-forming processes, ruling out the secondary origin of volatile-rich phases. The isotope and trace element signatures support the newly proposed hypothesis that volatile- and incompatible element-rich halos could have been formed due to the interaction of immiscible sulfide, carbonate, and silicate melts. The volatile-rich carbonate melt could be sourced from the mantle or it could be added from the crust. Regardless of the origin, carbonate melt and sulfide liquid both immiscible with mafic magma tend to stick to each other resulting in the formation of volatile- and incompatible element-rich halos commonly documented in magmatic sulfide deposits.

Mortality in a cohort of WTC-exposed law-enforcement officers compared to non-WTC law-enforcement officers - Ankura Singh; Malak Khalifeh; John Violanti; Rachel Zeig-Owens; Andrew C. Todd; Moshe Z. Shapiro; Madeline E. Carwile; Christopher R. Dasaro; Jiehui Li; Janette Yung; Mark R. Farfel; Robert M. Brackbill; et al. (International Archives of Occupational and Environmental Health, 2025)
Purpose World Trade Center (WTC) rescue/recovery workers were exposed to materials hazardous to health. Previous studies found lower than expected mortality among WTC rescue/recovery workers when compared to general populations, possibly due to healthy worker effects, better healthcare access and/or incomparability of the groups. We compared mortality rates in WTC-exposed law enforcement officers (LEOs) with rates in LEOs employed by the Buffalo, NY, Police Department. We also compared both cohorts to the general population. Methods Follow-up began at the later of one year after enrollment date or 1/1/2005 and ended at the earlier of death date or 12/31/2018. Analyses were restricted to ages 40–79 years (N = 11,476 WTC LEOs, N = 1668 non-WTC LEOs). We estimated standardized mortality ratios (SMRs) in each cohort using stratum-specific US mortality rates. Relative rates (RRs) and 95% CIs were estimated for the WTC vs. the Buffalo cohort using Poisson regression models adjusted for sex, race, age-group, and calendar-period. Results 185 deaths were observed in the WTC cohort and 186 in the Buffalo cohort. All-cause and cause-specific SMRs were significantly lower in the WTC cohort. Similarly, the adjusted all-cause mortality RR for the WTC vs. Buffalo cohorts was 0.30 (95% CI = 0.23–0.40). The cause-specific mortality RRs were all significantly < 1. Conclusion We found lower overall and cause-specific mortality rates in WTC LEOs compared with both the general population and Buffalo LEOs. These results suggest that factors other than healthy worker effects, such as access to healthcare via the WTC Health Program, contribute to lower mortality rates in WTC rescue/recovery workers.

A field test on the hydromechanical behaviour of flowing and nonflowing fractures in the 2.5 km COSC-1 borehole in crystalline rock, Sweden - Yves Guglielmi; Auli Niemi; Chin-Fu Tsang; Patrick Dobson; Paul Cook; Christopher Juhlin; Benoît Dessirier; Alexandru Tatomir; Farzad Basirat; Henning Lorenz; Jan-Erik Rosberg; Emil Lundberg; et al. (Hydrogeology Journal, 2025)

International Consortium to Classify Ageing-related Pathologies (ICCARP) senescence definitions: achieving international consensus - Emma Short; Robert T. R. Huckstepp; Kambiz Alavian; Winfried M. K. Amoaku; Thomas M. Barber; Edwin J. R. van Beek; Emyr Benbow; Sunil Bhandari; Phillip Bloom; Carlo Cota; Paul Chazot; Gary Christopher; et al. (GeroScience, 2025)

Brainstem Substructure Atrophy in Late-Onset GM2-Gangliosidosis Imaging Using Automated Segmentation - Olivia E. Rowe; D. Rangaprakash; Florian S. Eichler; Jeremy D. Schmahmann; Robert L. Barry; Christopher D. Stephen (The Cerebellum, 2025)

Pharmaceutical Sciences: Insights and Observations from Academic Chairs and Vice Chairs - Kristy M. Ainslie; Albert A Bowers; Robert H. Chichewicz; Lara S. Collier; Jonathan A. Doorn; Christopher R. Frei; Hamidreza Ghandehari; Robert B. Gibbs; David S. Lawrence; Craig R. Lee; Donald E. Mager; Paul Marker; et al. (The AAPS Journal, 2025)

Enriching OpenStreetMap network data for transportation applications: Insights into the impact of urban congestion on accessibility - Sailesh Acharya; Venu M. Garikapati; Michael Allen; Mingdong Lyu; Christopher Hoehne; Shivam Sharda; Robert Fitzgerald (Journal of Transport Geography, 2025)

The transport and vertical distribution of microplastics in the Mekong River, SE Asia - Freija Mendrik; Christopher R. Hackney; Vivien M. Cumming; Catherine Waller; Danet Hak; Robert Dorrell; Nguyen Nghia Hung; Daniel R. Parsons (Journal of Hazardous Materials, 2025)

Shifts in marsh erosion, migration, and wave exposure over nearly two centuries of sea-level rise in the Gulf of Mexico - Kathryn E.L. Smith; Joseph F. Terrano; Robert L. Jenkins; Jonathan L. Pitchford; Davina L. Passeri; Christopher G. Smith (Estuarine, Coastal and Shelf Science, 2025)

Bayesian networks facilitate updating of species distribution and habitat suitability models - Adam Duarte; Robert S. Spaan; James T. Peterson; Christopher A. Pearl; Michael J. Adams (Ecological Modelling, 2025)

The MOOSE fluid properties module - Guillaume Giudicelli; Christopher Green; Joshua Hansel; David Andrs; April Novak; Sebastian Schunert; Benjamin Spaude; Steven Isaacs; Matthias Kunick; Robert Salko; Shane Henderson; Lise Charlot; et al. (Computer Physics Communications, 2025)

Organic alkalinity distributions, characteristics, and application to carbonate system calculations in estuarine and coastal systems - Christopher W. Hunt; Joseph E. Salisbury; Xuewu Liu; Robert H. Byrne (Limnology and Oceanography, 2025)
The capacity of aquatic systems to buffer acidification depends on the sum contributions of various chemical species to total alkalinity (TA). Major TA contributors are inorganic, with carbonate and bicarbonate considered the most important. However, growing evidence shows that many rivers, estuaries, and coastal waters contain dissolved organic molecules with charge sites that create organic alkalinity (OrgAlk). This study describes the first comparison of (1) OrgAlk distributions and (2) acid–base properties in contrasting estuary‐plume systems: the Pleasant (Maine, USA) and the St. John (New Brunswick, CA). The substantial concentrations of OrgAlk in each estuary were sometimes not conservative with salinity and typically associated with very low pH. Two approaches to OrgAlk measurement showed consistent differences, indicating acid–base characteristics inconsistent with the TA definition. The OrgAlk fraction of TA ranged from 78% at low salinity to less than 0.4% in the coastal ocean endmember. Modeling of titration data identified three groups of organic charge sites, with mean acid–base dissociation constants (pK a ) of 4.2 (± 0.5), 5.9 (± 0.7) and 8.5 (± 0.2). These represented 21% (± 9%), 8% (± 5%), and 71% (± 11%) of titrated organic charge groups. Including OrgAlk, pK a , and titrated organic charge groups in carbonate system calculations improved estimates of pH. However, low and medium salinity, organic‐rich samples demonstrated persistent offsets in calculated pH, even using dissolved inorganic carbon and CO 2 partial pressure as inputs. These offsets show the ongoing challenge of carbonate system intercomparisons in organic rich systems whereby new techniques and further investigations are needed to fully account for OrgAlk in TA titrations.

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

The effect of replacing prolonged sitting with intermittent standing during a simulated workday on the subsequent night’s sleep - Christopher E. Kline; Andrew G. Kubala; Robert J. Kowalsky; Bethany Barone Gibbs (Sleep and Biological Rhythms, 2025)

Management scale drives bee and forb biodiversity patterns in suburban green spaces - Sheryl C. Hosler; Megan B. Garfinkel; Michael Roberts; Christopher Whelan; Emily Minor (Biodiversity and Conservation, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Site‐Specific Nutrient Data Reveal the Importance of Soils in Driving the Mycorrhizal Make‐Up of Woody Vegetation Worldwide - Xiaobin Hua; Christopher H. Lusk; Ian A. Dickie; Stephen Adu‐Bredu; Kathryn J. Allen; Viviana Araus; Laurent Augusto; Pavel Barsukov; David Bauman; Félix Brédoire; David F. R. P. Burslem; James W. Dalling; et al. (Global Ecology and Biogeography, 2025)
Aim Arbuscular mycorrhizas (AM) and ectomycorrhizas (ECM) have different impacts on nutrient cycling, carbon storage, community dynamics and enhancement of photosynthesis by rising CO 2 . Recent global analyses have concluded that patterns of AM/ECM dominance in forests worldwide are shaped by climate, with soil nutrients contributing negligible additional explanatory power. However, their reliance on nutrient data from GIS surfaces masks important local influences of parent material, topography and soil age on soil nutrient status. We asked if use of site‐specific nutrient data reveals a more important role for nutrients. Time Period Present day. Location Global dataset comprising 703 sites, encompassing forests, savanna/woodlands, shrublands and deserts on all continents except Antarctica. Taxa Studied Arborescent plants, including angiosperms, gymnosperms and tree ferns. Methods Generalised Additive Models for Location, Scale and Shape (GAMLSS) to determine the effects of climate variables, soil nitrogen and soil phosphorus on the proportional representation of ECM and of non‐mycorrhizal species (NM) in woody vegetation. Results GAMLSS showed a strong negative relationship of ECM representation with mean annual temperature (MAT), and a strong negative relationship with soil total nitrogen. NM representation was highest on dry sites and phosphorus‐poor sites. Reanalysis showed that GIS‐derived soil nutrient data had less explanatory power than site‐specific nutrient data, and resulted in poorer model fits. Conclusions Our results support the long‐held belief that soil nutrients as well as climate influence the relative fitness of different mycorrhizal syndromes worldwide, and demonstrate the value of using site‐specific nutrient data. Soil nutrients should be considered when predicting the impact of climate change on the mycorrhizal composition of vegetation and resulting shifts in ecosystem processes.

Rectifying a century of misidentifications: a taxonomic re-evaluation of sipo snakes (Colubridae: Chironius ) on Trinidad - Robert C. Jadin; Michael J. Jowers; Christopher Blair; Rickaela K. Ludwig; Xabier Salgado-Irazabal; John C. Murphy (Systematics and Biodiversity, 2024)

Very low sulfur fuel oil spilled from the MV Wakashio in 2020 remains in sediments in a Mauritius mangrove ecosystem nearly three years after the grounding - Alan G. Scarlett; Robert K. Nelson; Marthe Monique Gagnon; Christopher M. Reddy; Kliti Grice (Marine Pollution Bulletin, 2024)

Spatial model of groundwater contamination risks from pit-latrines in a low-income country - Rebekah G.K. Hinton; Robert M. Kalin; Modesta B. Kanjaye; Prince Mleta; Christopher J.A. Macleod; Mads Troldborg (Water Research, 2024)

Mixed method analysis of anthropogenic groundwater contamination of drinking water sources in Malawi - Rebekah G.K. Hinton; Robert M. Kalin; Limbikani C. Banda; Modesta B. Kanjaye; Christopher J.A. Macleod; Mads Troldborg; Peaches Phiri; Sydney Kamtukule (Science of The Total Environment, 2024)

Controls on spatial variation in porewater methane concentrations across United States tidal wetlands - Erika L. Koontz; Sarah M. Parker; Alice E. Stearns; Brian J. Roberts; Caitlin M. Young; Lisamarie Windham-Myers; Patricia Y. Oikawa; J. Patrick Megonigal; Genevieve L. Noyce; Edward J. Buskey; R. Kyle Derby; Robert P. Dunn; et al. (Science of The Total Environment, 2024)

Archaeopteris trees at high southern latitudes in the late Devonian - Robert W. Gess; Christopher Berry (Review of Palaeobotany and Palynology, 2024)

Geographic bias effects on interpretations of secular trends of Hf isotope times series in zircons - Kent C. Condie; Stephen J. Puetz; Kurt E. Sundell; Sergei A. Pisarevsky; Christopher J. Spencer; Nick M.W. Roberts (Lithos, 2024)

Do affluent neighbourhoods pay more for transit access? Exploring the capitalization of employment accessibility within different housing submarkets in Vancouver - Robert Nutifafa Arku; Christopher D. Higgins; Jaimy Fischer; Steven Farber (Journal of Transport Geography, 2024)

Health and air pollutant emission impacts of net zero CO2 by 2050 scenarios from the energy modeling forum 37 study - Daniel H. Loughlin; Alexander R. Barron; Charavee Basnet Chettri; Abigail O'Meara; Luis Sarmiento; Danni Dong; David L. McCollum; Sharon Showalter; Robert H. Beach; John Bistline; G. Joyce Kim; Christopher G. Nolte; et al. (Energy and Climate Change, 2024)

Winners and Losers From Climate Change: An Analysis of Climate Thresholds for Tree Growth and Survival for Roughly 150 Species Across the Contiguous United States - Christopher M. Clark; Justin G. Coughlin; Jennifer Phelan; Gray Martin; Kemen Austin; Marwa Salem; Robert D. Sabo; Kevin Horn; R. Quinn Thomas; Rebecca M. Dalton (Global Change Biology, 2024)
Changes in temperature and precipitation are already influencing US forests and that will continue in the future even as we mitigate climate change. Using spatiotemporally matched data for mean annual temperature (MAT) and mean annual precipitation (MAP), we used simulated annealing to estimate critical thresholds for changes in the growth and survival of roughly 150 tree species (153 spp. for growth, 159 spp. for survival) across the conterminous United States (CONUS). We found that growth of nearly one‐third of tree species assessed (44 spp.) decreased with any increase in MAT (42–49 species), whereas fewer responded negatively to projected regional trends in MAP (

Model Sensitivity Analysis for Coastal Morphodynamics: Investigating Sediment Parameters and Bed Composition in Delft3D - Robert L. Jenkins; Christopher G. Smith; Davina L. Passeri; Alisha M. Ellis (Journal of Marine Science and Engineering, 2024)
Numerical simulation of sediment transport and subsequent morphological evolution rely on accurate parameterizations of sediment characteristics. However, these data are often not available or are spatially and/or temporally limited. This study approaches the problem of limited sediment grain-size data with a series of simulations assessing model sensitivity to sediment parameters and initial bed composition configurations in Delft3D, leading to improved modeling practices. A previously validated Delft3D sediment transport and morphology model for Dauphin Island, Alabama, USA, is used as the benchmark case. A method for the generation of representative sediment grain sizes and their spatially varying distributions is presented via end-member analysis of in situ surficial sediment samples. Derived sediment classes and their spatial distributions are applied to two sensitivity case simulations with increasing bed composition complexity. First, multiple sediment classes are applied in a single fully mixed layer, regardless of sediment type. Second, multiple sediment classes are applied in a thin, fully mixed transport layer with underlayers containing only the non-cohesive sediment classes below. Simulations were carried out in a probabilistic, Delft3D MorMerge configuration to capture long-term morphology change for 10 years. We found there is sensitivity to the inclusion of additional sediment classes and sediment distribution made evident in bed level and morphology change. Inclusion of highly mobile fine sediments altered model results in each sensitivity case. The model was also found to be sensitive to initial bed composition in terms of bed level and morphology change, with notable differences between sensitivity cases on decadal timescales, indicating an armoring effect in the second sensitivity case, which used the transport and underlayer bed configuration. The results of this study offer guidance for numerical modelers concerned with sediment behavior in coastal and estuarine environments.

The influence of the strength of pre-existing weak zones on rift geometry and strain localization - Liang Xue; Robert Moucha; Folarin Kolawole; James D. Muirhead; Christopher A. Scholz (Tectonophysics, 2024)

Resolving the paradox of conflicting glacial chronologies: Reconstructing the pattern of deglaciation of the Magellan cordilleran ice dome (53–54°S) during the last glacial – interglacial transition - Robert D. McCulloch; Michael J. Bentley; Derek Fabel; Hans Fernández-Navarro; Juan-Luis García; Andrew S. Hein; Carla Huynh; Stewart S.R. Jamieson; María-Paz Lira; Christopher Lüthgens; Grace A. Nield; Manuel San Román; et al. (Quaternary Science Reviews, 2024)

A molecular phylogeny of the Petaluridae (Odonata: Anisoptera): A 160-Million-Year-Old story of drift and extinction - Ethan R. Tolman; Christopher D. Beatty; Manpreet K. Kohli; John Abbott; Seth M. Bybee; Paul B. Frandsen; J. Stephen Gosnell; Robert Guralnick; V.J. Kalkman; Lacie G. Newton; Anton Suvorov; Jessica L. Ware (Molecular Phylogenetics and Evolution, 2024)

Intra-uterine injection of amnion-derived acellular bioscaffold product in mares, a description of systemic and intra-uterine effects over 21 days - Dale Kelley; Stephanie Walbornn; Christine Bartley; Jamie Kaczor; Christopher Premanandan; Nathaniel Newton; Robert Holland; Maria Schnobrich (Journal of Equine Veterinary Science, 2024)

Climatic drought and trophic disruption in an endemic subalpine Hawaiian forest bird - Kyle S. Van Houtan; Tyler O. Gagné; Paul Banko; Molly E. Hagemann; Robert W. Peck; Christopher T. Yarnes (Biological Conservation, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Re-anchoring of failed in-situ grouted post-tension anchor rods with high rod to duct area ratios - Christopher M. Abela; Robert Lindyberg; Eric Landis (Engineering Structures, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

RGD-coated polymeric microbubbles promote ultrasound-mediated drug delivery in an inflamed endothelium-pericyte co-culture model of the blood-brain barrier - Christopher Hark; Junlin Chen; Julia Blöck; Eva Miriam Buhl; Harald Radermacher; Robert Pola; Michal Pechar; Tomáš Etrych; Quim Peña; Anne Rix; Natascha I. Drude; Fabian Kiessling; et al. (Drug Delivery and Translational Research, 2024)
Drug delivery to central nervous pathologies is compromised by the blood-brain barrier (BBB). A clinically explored strategy to promote drug delivery across the BBB is sonopermeation, which relies on the combined use of ultrasound (US) and microbubbles (MB) to induce temporally and spatially controlled opening of the BBB. We developed an advanced in vitro BBB model to study the impact of sonopermeation on the delivery of the prototypic polymeric drug carrier pHPMA as a larger molecule and the small molecule antiviral drug ribavirin. This was done under standard and under inflammatory conditions, employing both untargeted and RGD peptide-coated MB. The BBB model is based on human cerebral capillary endothelial cells and human placental pericytes, which are co-cultivated in transwell inserts and which present with proper transendothelial electrical resistance (TEER). Sonopermeation induced a significant decrease in TEER values and facilitated the trans-BBB delivery of fluorescently labeled pHPMA (Atto488-pHPMA). To study drug delivery under inflamed endothelial conditions, which are typical for e.g. tumors, neurodegenerative diseases and CNS infections, tumor necrosis factor (TNF) was employed to induce inflammation in the BBB model. RGD-coated MB bound to and permeabilized the inflamed endothelium-pericyte co-culture model, and potently improved Atto488-pHPMA and ribavirin delivery. Taken together, our work combines in vitro BBB bioengineering with MB-mediated drug delivery enhancement, thereby providing a framework for future studies on optimization of US-mediated drug delivery to the brain. Graphical abstract

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Diverse source materials contributed to a secular increase in δ18O for the Paleo-Mesoproterozoic A2-type granites - Gui-Mei Lu; Yi-Gang Xu; Wei Wang; Christopher J. Spencer; Nick M.W. Roberts; Kent C. Condie (Earth and Planetary Science Letters, 2024)

Multirotor UAV icing correlated to liquid water content measurements in natural supercooled clouds - Anna J. Miller; Christopher Fuchs; Nadja Omanovic; Fabiola Ramelli; Patric Seifert; Robert Spirig; Huiying Zhang; Emilie Fons; Ulrike Lohmann; Jan Henneberger (Cold Regions Science and Technology, 2024)

Research and educational applications of the Aerojet General Nucleonics 201-M at the University of New Mexico - Rowdy Davis; Christopher M. Perfetti; Robert D. Busch; Larry L. Wetzel; Carl A. Willis (Annals of Nuclear Energy, 2024)

Cerebellar Theta Burst Stimulation Impairs Working Memory - Nasem Raies; Jean-François Nankoo; Christopher R. Madan; Robert Chen (The Cerebellum, 2024)

Corrigendum: Ocean surface radiation measurement best practices - Laura D. Riihimaki; Meghan F. Cronin; Raja Acharya; Nathan Anderson; John A. Augustine; Kelly A. Balmes; Patrick Berk; Roberto Bozzano; Anthony Bucholtz; Kenneth J. Connell; Christopher J. Cox; Alcide G. di Sarra; et al. (Frontiers in Marine Science, 2024)

Identifying drivers of non-stationary climate-growth relationships of European beech - Christopher Leifsson; Allan Buras; Stefan Klesse; Claudia Baittinger; Banzragch Bat-Enerel; Giovanna Battipaglia; Franco Biondi; Branko Stajić; Marius Budeanu; Vojtěch Čada; Liam Cavin; Hugues Claessens; et al. (Science of The Total Environment, 2024)

Subduction and loss of continental crust during the Mesoproterozoic Sveconorwegian Orogeny - Trond Slagstad; Øyvind Skår; Gina Bjerkan; Nolwenn Coint; Anette Granseth; Christopher L. Kirkland; Evgeniy Kulakov; Eduardo Mansur; Alf André Orvik; Andreas Petersson; Nick M.W. Roberts (Precambrian Research, 2024)

Red king crab larval survival and development are resilient to ocean acidification - W. Christopher Long; Alexandra L. Conrad; Jennifer L. Gardner; Robert J. Foy (Journal of Experimental Marine Biology and Ecology, 2024)

Oncometabolite 2-hydroxyglutarate suppresses basal protein levels of DNA polymerase beta that enhances alkylating agent and PARG inhibition induced cytotoxicity - Kate M. Saville; Rasha Q. Al-Rahahleh; Aisha H. Siddiqui; Morgan E. Andrews; Wynand P. Roos; Christopher A. Koczor; Joel F. Andrews; Faisal Hayat; Marie E. Migaud; Robert W. Sobol (DNA Repair, 2024)

Evolution of white matter hyperintensity segmentation methods and implementation over the past two decades; an incomplete shift towards deep learning - Maryam Rahmani; Donna Dierker; Lauren Yaeger; Andrew Saykin; Patrick H. Luckett; Andrei G. Vlassenko; Christopher Owens; Hussain Jafri; Kyle Womack; Jurgen Fripp; Ying Xia; Duygu Tosun; et al. (Brain Imaging and Behavior, 2024)
This systematic review examines the prevalence, underlying mechanisms, cohort characteristics, evaluation criteria, and cohort types in white matter hyperintensity (WMH) pipeline and implementation literature spanning the last two decades. Following Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines, we categorized WMH segmentation tools based on their methodologies from January 1, 2000, to November 18, 2022. Inclusion criteria involved articles using openly available techniques with detailed descriptions, focusing on WMH as a primary outcome. Our analysis identified 1007 visual rating scales, 118 pipeline development articles, and 509 implementation articles. These studies predominantly explored aging, dementia, psychiatric disorders, and small vessel disease, with aging and dementia being the most prevalent cohorts. Deep learning emerged as the most frequently developed segmentation technique, indicative of a heightened scrutiny in new technique development over the past two decades. We illustrate observed patterns and discrepancies between published and implemented WMH techniques. Despite increasingly sophisticated quantitative segmentation options, visual rating scales persist, with the SPM technique being the most utilized among quantitative methods and potentially serving as a reference standard for newer techniques. Our findings highlight the need for future standards in WMH segmentation, and we provide recommendations based on these observations.

Impact of ocean in-situ observations on ECMWF sub-seasonal forecasts - Beena Balan-Sarojini; Magdalena Alonso Balmaseda; Frédéric Vitart; Christopher David Roberts; Hao Zuo; Steffen Tietsche; Michael Mayer (Frontiers in Marine Science, 2024)
We assess for the first time the impact of in-situ ocean observations on European Centre for Medium-Range Weather Forecasts (ECMWF) sub-seasonal forecasts of both ocean and atmospheric conditions. A series of coupled reforecasts have been conducted for the period 1993-2015, in which different sets of ocean observations were withdrawn in the production of the ocean initial conditions. Removal of all ocean in-situ observations in the initial conditions leads to significant degradation in the forecasts of ocean surface and subsurface mean state at lead times from week 1 to week 4. The negative impact is predominantly caused by the removal of the Argo observing system in recent decades. Changes in the mean state of atmospheric variables are comparatively small but significant in the forecasts of lower and upper atmospheric circulation over large regions. Our results highlight the value of continuous, real-time in-situ observations of the surface and subsurface ocean for coupled forecasts in the sub-seasonal range.

The deglacial history of 79N glacier and the Northeast Greenland Ice Stream - David H. Roberts; Timothy P. Lane; Richard S. Jones; Michael J. Bentley; Christopher M. Darvill; Angel Rodes; James A. Smith; Stewart S.R. Jamieson; Brice R. Rea; Derek Fabel; Delia Gheorghiu; Allan Davidson; et al. (Quaternary Science Reviews, 2024)

Associations between neighborhood characteristics and child well-being before and during the COVID-19 pandemic: A repeated cross-sectional study in the Environmental influences on Child Health Outcomes (ECHO) program - Xueying Zhang; Courtney K. Blackwell; Janet Moore; Shelley H. Liu; Chang Liu; Christopher B. Forrest; Jody Ganiban; Annemarie Stroustrup; Judy L. Aschner; Leonardo Trasande; Sean C.L. Deoni; Amy J. Elliott; et al. (Environmental Research, 2024)

A model for evaluation of sediment exposure and burial for freshwater mussels from heavy particle sedimentation - Binbin Wang; Brandon J. Sansom; Wenyu Zhu; James Kunz; M. Christopher Barnhart; Henry Brown; Stephen McMurray; Andrew D. Roberts; Christopher Shulse; Caleb J. Knerr; Kathleen Trauth; Jeffery A. Steevens; et al. (Ecological Modelling, 2024)

City divided: Unveiling family ties and genetic structuring of coyotes in Seattle - Samantha E. S. Kreling; Ellen M. Reese; Olivia M. Cavalluzzi; Natalee B. Bozzi; Riley Messinger; Christopher J. Schell; Robert A. Long; Laura R. Prugh (Molecular Ecology, 2024)
Linear barriers pose significant challenges for wildlife gene flow, impacting species persistence, adaptation, and evolution. While numerous studies have examined the effects of linear barriers (e.g., fences and roadways) on partitioning urban and non‐urban areas, understanding their influence on gene flow within cities remains limited. Here, we investigated the impact of linear barriers on coyote ( Canis latrans ) population structure in Seattle, Washington, where major barriers (i.e., interstate highways and bodies of water) divide the city into distinct quadrants. Just under 1000 scats were collected to obtain genetic data between January 2021 and December 2022, allowing us to identify 73 individual coyotes. Notably, private allele analysis underscored limited interbreeding among quadrants. When comparing one quadrant to each other, there were up to 16 private alleles within a single quadrant, representing nearly 22% of the population allelic diversity. Our analysis revealed weak isolation by distance, and despite being a highly mobile species, genetic structuring was apparent between quadrants even with extremely short geographic distance between individual coyotes, implying that Interstate 5 and the Ship Canal act as major barriers. This study uses coyotes as a model species for understanding urban gene flow and its consequences in cities, a crucial component for bolstering conservation of rarer species and developing wildlife friendly cities.

Deliberately introduced dung beetles in A ustralia: 12 years of occurrence and abundance records from 2001 to 2022 - Jacob D. Berson; Penelope B. Edwards; T. James Ridsdill‐Smith; Christopher K. Taylor; Daniel J. Anderson; Nigel R. Andrew; Russell A. Barrow; David A. Cousins; Robert N. Emery; Laura L. Fagan; Rhiannon M. Foster; Lucas G. Harwood; et al. (Ecology, 2024)
Since 1968, the Australian Dung Beetle Project has carried out field releases of 43 deliberately introduced dung beetle species for the biological control of livestock dung and dung‐breeding pests. Of these, 23 species are known to have become established. For most of these species, sufficient time has elapsed for population expansion to fill the extent of their potential geographic range through both natural and human‐assisted dispersal. Consequently, over the last 20 years, extensive efforts have been made to quantify the current distribution of these introduced dung beetles, as well as the seasonal and spatial variation in their activity levels. Much of these data and their associated metadata have remained unpublished, and they have not previously been synthesized into a cohesive dataset. Here, we collate and report data from the three largest dung beetle monitoring projects from 2001 to 2022. Together, these projects encompass data collected from across Australia, and include records for all 23 species of established dung beetles introduced for biocontrol purposes. In total, these data include 22,718 presence records and 213,538 absence records collected during 10,272 sampling events at 546 locations. Most presence records (97%) include abundance data. In total, 1,752,807 dung beetles were identified as part of these data. The distributional occurrence and abundance data can be used to explore questions such as factors influencing dung beetle species distributions, dung beetle biocontrol, and insect‐mediated ecosystem services. These data are provided under a CC‐BY‐NC 4.0 license and users are encouraged to cite this data paper when using the data.

Developing simple indicators of nitrogen and phosphorus removal in constructed stormwater wetlands - Christopher Szota; Alistair Danger; Peter J. Poelsma; Belinda E. Hatt; Robert B. James; Alison Rickard; Matthew J. Burns; Frédéric Cherqui; Vaughn Grey; Rhys A. Coleman; Tim D. Fletcher (Science of The Total Environment, 2024)

Dislocation-mediated interfacial re-equilibration of pyrite: An alternative model to interface-coupled dissolution-reprecipitation and gold remobilisation - Denis Fougerouse; Steven M. Reddy; Sumail; Joël Brugger; Nicolas Thébaud; William D.A. Rickard; Lin Yang; Zakaria Quadir; Malcolm P. Roberts; Andrew G. Tomkins; Laure Martin; Laura Petrella; et al. (Geochimica et Cosmochimica Acta, 2024)

Long-Term Follow-Up of Cerebral Aneurysms Completely Occluded at 6 Months After Intervention with the Woven EndoBridge (WEB) Device: a Retrospective Multicenter Observational Study - Kareem El Naamani; Panagiotis Mastorakos; Nimer Adeeb; Mathews Lan; James Castiglione; Omaditya Khanna; Jose Danilo Bengzon Diestro; Rachel M. McLellan; Mahmoud Dibas; Justin E. Vranic; Assala Aslan; Hugo H. Cuellar-Saenz; et al. (Translational Stroke Research, 2024)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Combining camera trap surveys and IUCN range maps to improve knowledge of species distributions - Cheng Chen; Alys Granados; Jedediah F. Brodie; Roland Kays; T. Jonathan Davies; Runzhe Liu; Jason T. Fisher; Jorge Ahumada; William McShea; Douglas Sheil; Jayasilan Mohd‐Azlan; Bernard Agwanda; et al. (Conservation Biology, 2024)
Reliable maps of species distributions are fundamental for biodiversity research and conservation. The International Union for Conservation of Nature (IUCN) range maps are widely recognized as authoritative representations of species’ geographic limits, yet they might not always align with actual occurrence data. In recent area of habitat (AOH) maps, areas that are not habitat have been removed from IUCN ranges to reduce commission errors, but their concordance with actual species occurrence also remains untested. We tested concordance between occurrences recorded in camera trap surveys and predicted occurrences from the IUCN and AOH maps for 510 medium‐ to large‐bodied mammalian species in 80 camera trap sampling areas. Across all areas, cameras detected only 39% of species expected to occur based on IUCN ranges and AOH maps; 85% of the IUCN only mismatches occurred within 200 km of range edges. Only 4% of species occurrences were detected by cameras outside IUCN ranges. The probability of mismatches between cameras and the IUCN range was significantly higher for smaller‐bodied mammals and habitat specialists in the Neotropics and Indomalaya and in areas with shorter canopy forests. Our findings suggest that range and AOH maps rarely underrepresent areas where species occur, but they may more often overrepresent ranges by including areas where a species may be absent, particularly at range edges. We suggest that combining range maps with data from ground‐based biodiversity sensors, such as camera traps, provides a richer knowledge base for conservation mapping and planning.

Ocean surface radiation measurement best practices - Laura D. Riihimaki; Meghan F. Cronin; Raja Acharya; Nathan Anderson; John A. Augustine; Kelly A. Balmes; Patrick Berk; Roberto Bozzano; Anthony Bucholtz; Kenneth J. Connell; Christopher J. Cox; Alcide G. di Sarra; et al. (Frontiers in Marine Science, 2024)
Ocean surface radiation measurement best practices have been developed as a first step to support the interoperability of radiation measurements across multiple ocean platforms and between land and ocean networks. This document describes the consensus by a working group of radiation measurement experts from land, ocean, and aircraft communities. The scope was limited to broadband shortwave (solar) and longwave (terrestrial infrared) surface irradiance measurements for quantification of the surface radiation budget. Best practices for spectral measurements for biological purposes like photosynthetically active radiation and ocean color are only mentioned briefly to motivate future interactions between the physical surface flux and biological radiation measurement communities. Topics discussed in these best practices include instrument selection, handling of sensors and installation, data quality monitoring, data processing, and calibration. It is recognized that platform and resource limitations may prohibit incorporating all best practices into all measurements and that spatial coverage is also an important motivator for expanding current networks. Thus, one of the key recommendations is to perform interoperability experiments that can help quantify the uncertainty of different practices and lay the groundwork for a multi-tiered global network with a mix of high-accuracy reference stations and lower-cost platforms and practices that can fill in spatial gaps.

Lunar Flashlight science ground and flight measurements and operations using a multi-band laser reflectometer - Barbara A. Cohen; Ryan R. Petersburg; Daniel R. Cremons; Patrick S. Russell; Paul O. Hayne; Benjamin T. Greenhagen; David A. Paige; Jose Martinez Camacho; Nathan Cheek; Mark T. Sullivan; Valeria Lopez Robles; Jessica Ban; et al. (Icarus, 2024)

Revisiting the discrimination and distribution of S-type granites from zircon trace element composition - Nick M W Roberts; Chris Yakymchuk; Christopher J Spencer; C. Brenhin Keller; Simon R Tapster (Earth and Planetary Science Letters, 2024)

The influence of gene flow on population viability in an isolated urban caracal population - Christopher C. Kyriazis; Laurel E. K. Serieys; Jacqueline M. Bishop; Marine Drouilly; Storme Viljoen; Robert K. Wayne; Kirk E. Lohmueller (Molecular Ecology, 2024)
Wildlife populations are becoming increasingly fragmented by anthropogenic development. Small and isolated populations often face an elevated risk of extinction, in part due to inbreeding depression. Here, we examine the genomic consequences of urbanization in a caracal ( Caracal caracal ) population that has become isolated in the Cape Peninsula region of the City of Cape Town, South Africa, and is thought to number ~50 individuals. We document low levels of migration into the population over the past ~75 years, with an estimated rate of 1.3 effective migrants per generation. As a consequence of this isolation and small population size, levels of inbreeding are elevated in the contemporary Cape Peninsula population (mean F ROH = 0.20). Inbreeding primarily manifests as long runs of homozygosity >10 Mb, consistent with the effects of isolation due to the rapid recent growth of Cape Town. To explore how reduced migration and elevated inbreeding may impact future population dynamics, we parameterized an eco‐evolutionary simulation model. We find that if migration rates do not change in the future, the population is expected to decline, though with a low projected risk of extinction. However, if migration rates decline or anthropogenic mortality rates increase, the potential risk of extinction is greatly elevated. To avert a population decline, we suggest that translocating migrants into the Cape Peninsula to initiate a genetic rescue may be warranted in the near future. Our analysis highlights the utility of genomic datasets coupled with computational simulation models for investigating the influence of gene flow on population viability.

Spatio‐temporal integrated Bayesian species distribution models reveal lack of broad relationships between traits and range shifts - Joris H. Wiethase; Philip S. Mostert; Christopher R. Cooney; Robert B. O'Hara; Colin M. Beale (Global Ecology and Biogeography, 2024)
Aim Climate change and habitat loss or degradation are some of the greatest threats that species face today, often resulting in range shifts. Species traits have been discussed as important predictors of range shifts, with the identification of general trends being of great interest to conservation efforts. However, studies reviewing relationships between traits and range shifts have questioned the existence of such generalized trends, due to mixed results and weak correlations, as well as analytical shortcomings. The aim of this study was to test this relationship empirically, using analytical approaches that account for common sources of bias when assessing range trends. Location Tanzania, East Africa. Time period 1980–1999 and 2000–2020. Major taxa studied 57 savannah specialist birds found in Tanzania, belonging to 26 families and 11 orders. Methods We applied recently developed integrated spatio‐temporal species distribution models in R‐INLA, combining citizen science and bird Atlas data to estimate ranges of species, quantify range shifts, and test the predictive power of traditional trait groups, as well as exposure‐related and sensitivity traits. We based our study on 40 years of bird observations in East African savannahs, a biome that has experienced increasing climatic and non‐climatic pressures over recent decades. We correlated patterns of change with species traits using linear regression models. Results We find indications of relationships identified by previous research, but low average explanatory power of traits from an ecological perspective, confirming the lack of meaningful general associations. However, our analysis finds compelling species‐specific results. Main conclusions We highlight the importance of individual assessments while demonstrating the usefulness of our analytical approach for analyses of range shifts.

A machine learning approach for protected species bycatch estimation - Christopher A. Long; Robert N. M. Ahrens; T. Todd Jones; Zachary A. Siders (Frontiers in Marine Science, 2024)
Introduction Monitoring bycatch of protected species is a fisheries management priority. In practice, protected species bycatch is difficult to precisely or accurately estimate with commonly used ratio estimators or parametric, linear model-based methods. Machine-learning algorithms have been proposed as means of overcoming some of the analytical hurdles in estimating protected species bycatch. Methods Using 17 years of set-specific bycatch data derived from 100% observer coverage of the Hawaii shallow-set longline fishery and 25 aligned environmental predictors, we evaluated a new approach for protected species bycatch estimation using Ensemble Random Forests (ERFs). We tested the ability of ERFs to predict interactions with five protected species with varying levels of bycatch in the fishery and methods for correcting these predictions using Type I and Type II error rates from the training data. We also assessed the amount of training data needed to inform a ERF approach by mimicking the sequential addition of new data in each subsequent fishing year. Results We showed that ERF bycatch estimation was most effective for species with greater than 2% interaction rates and error correction improved bycatch estimates for all species but introduced a tendency to regress estimates towards mean rates in the training data. Training data needs differed among species but those above 2% interaction rates required 7-12 years of bycatch data. Discussion Our machine learning approach can improve bycatch estimates for rare species but comparisons are needed to other approaches to assess which methods perform best for hyperrare species.

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Characterising differences between self-reported and wastewater-identified drug use at two consecutive years of an Australian music festival - Cheneal Puljević; Benjamin Tscharke; Ellen Leslie Wessel; Cameron Francis; Rory Verhagen; Jake W. O'Brien; Richard Bade; Dhayaalini Nadarajan; Fiona Measham; M.J. Stowe; Timothy Piatkowski; Jason Ferris; et al. (Science of The Total Environment, 2024)

A novel in vitro model of clinical cryoablation to investigate the transition zone for focal tumor ablation - Maura R. Vrabel; Christopher C. Fesmire; Matthew J. Rich; Robert L. Kobrin; Michael B. Sano; David A. Zaharoff (Cryobiology, 2024)

Estimation of ammonia deposition to forest ecosystems in Scotland and Sri Lanka using wind-controlled NH3 enhancement experiments - Ajinkya G. Deshpande; Matthew R. Jones; Netty van Dijk; Neil J. Mullinger; Duncan Harvey; Robert Nicoll; Galina Toteva; Gothamie Weerakoon; Sarath Nissanka; Buddhika Weerakoon; Maude Grenier; Agata Iwanicka; et al. (Atmospheric Environment, 2024)

Assessment of length-of-day and universal time predictions based on the results of the Second Earth Orientation Parameters Prediction Comparison Campaign - Justyna Śliwińska-Bronowicz; Tomasz Kur; Małgorzata Wińska; Henryk Dobslaw; Jolanta Nastula; Aleksander Partyka; Santiago Belda; Christian Bizouard; Dale Boggs; Sara Bruni; Lue Chen; Mike Chin; et al. (Journal of Geodesy, 2024)
Predicting Earth Orientation Parameters (EOP) is crucial for precise positioning and navigation both on the Earth’s surface and in space. In recent years, many approaches have been developed to forecast EOP, incorporating observed EOP as well as information on the effective angular momentum (EAM) derived from numerical models of the atmosphere, oceans, and land-surface dynamics. The Second Earth Orientation Parameters Prediction Comparison Campaign (2nd EOP PCC) aimed to comprehensively evaluate EOP forecasts from many international participants and identify the most promising prediction methodologies. This paper presents the validation results of predictions for universal time and length-of-day variations submitted during the 2nd EOP PCC, providing an assessment of their accuracy and reliability. We conduct a detailed evaluation of all valid forecasts using the IERS 14 C04 solution provided by the International Earth Rotation and Reference Systems Service (IERS) as a reference and mean absolute error as the quality measure. Our analysis demonstrates that approaches based on machine learning or the combination of least squares and autoregression, with the use of EAM information as an additional input, provide the highest prediction accuracy for both investigated parameters. Utilizing precise EAM data and forecasts emerges as a pivotal factor in enhancing forecasting accuracy. Although several methods show some potential to outperform the IERS forecasts, the current standard predictions disseminated by IERS are highly reliable and can be fully recommended for operational purposes.

Potential of dynamic ocean management strategies for western Pacific leatherback sea turtle bycatch mitigation in New Zealand - Zachary A. Siders; Campbell Murray; Charity Puloka; Shelton Harley; Clinton Duffy; Christopher A. Long; Robert N. M. Ahrens; T. Todd Jones (Frontiers in Marine Science, 2024)
Western Pacific leatherback sea turtles ( Dermochelys coriacea ) are a priority bycatch mitigation concern due to the projected extinction of the population before the end of the 21st century. The species regularly occurs as bycatch in gillnet and surface longline fisheries. Here, we explore the potential for dynamic ocean management in an emerging hotspot of leatherback sea turtle bycatch in the New Zealand pelagic longline fishery. We compared spatial areas of different sizes built from single oceanographic covariates as well as built from a composite risk surface developed through ensemble random forests. We found that, individually, the Okubo–Weiss parameter, sea surface temperature (SST) anomaly, SST, moon phase, and distance to the SST front were important oceanographic covariates for leatherback sea turtle bycatch. However, the spatial areas built from the composite risk surface were the most effective at discriminating sets with and without bycatch across a range of risk cutoffs. When we also considered implementation metrics of spatial area and coherence as part of performance, the area derived from the composite risk surface with a risk of interaction per set greater than 52% performed best. This spatial area was ephemeral, occurring 1 or 2 weeks each year, and localized, occurring along the north coast of East Cape in the North Island of New Zealand. The apparent presence of discrete spatial areas with elevated risk may be useful to inform future management in the area. Considering implementation metrics in defining utility was useful for identifying tradeoffs between the total size and the underlying covariates delineating a spatial area. As such, we recommend these types of metrics to be included when designing spatial bycatch mitigation strategies elsewhere.

Reclassifying historical disasters: From single to multi-hazards - Ryan Lee; Christopher J. White; Mohammed Sarfaraz Gani Adnan; John Douglas; Miguel D. Mahecha; Fiachra E. O'Loughlin; Edoardo Patelli; Alexandre M. Ramos; Matthew J. Roberts; Olivia Martius; Enrico Tubaldi; Bart van den Hurk; et al. (Science of The Total Environment, 2024)

Microplastic trapping efficiency and hydrodynamics in model coral reefs: A physical experimental investigation - Freija Mendrik; Robert C. Houseago; Christopher R. Hackney; Daniel R. Parsons (Environmental Pollution, 2024)

Metrics and Considerations for Evaluating How Forest Treatments Alter Wildfire Behavior and Effects - Anthony G Vorster; Camille Stevens-Rumann; Nicholas Young; Brian Woodward; Christopher Tsz Hin Choi; Marin E Chambers; Antony S Cheng; Michael Caggiano; Courtney Schultz; Matthew Thompson; Michelle Greiner; Greg Aplet; et al. (Journal of Forestry, 2024)
The influence of forest treatments on wildfire effects is challenging to interpret. This is, in part, because the impact forest treatments have on wildfire can be slight and variable across many factors. Effectiveness of a treatment also depends on the metric considered. We present and define human–fire interaction, fire behavior, and ecological metrics of forest treatment effects on wildfire and discuss important considerations and recommendations for evaluating treatments. We demonstrate these concepts using a case study from the Cameron Peak Fire in Colorado, USA. Pre-fire forest treatments generally, but not always, experienced reduced burn severity, particularly when surface fuels were reduced. Treatments in the Cameron Peak Fire have also been documented as increasing tree survivorship, aiding suppression efforts, promoting firefighter safety, and influencing fire spread. However, the impacts of pre-fire management on primary landscape-scale objectives, like watershed protection, are unknown. Discussions about the influence of pre-fire treatments on fire effects must define the indicator(s) being assessed, as the same treatment may be considered successful under one measure but not others. Thus, it is critical to bring a common language and understanding to conversations about treatment effects and advance efforts to evaluate the range of treatment effects, thus supporting treatment planning.

Reasons to Be Skeptical about Sentience and Pain in Fishes and Aquatic Invertebrates - Benjamin K. Diggles; Robert Arlinghaus; Howard I. Browman; Steven J. Cooke; Robin L. Cooper; Ian G. Cowx; Charles D. Derby; Stuart W. Derbyshire; Paul JB Hart; Brian Jones; Alexander O. Kasumyan; Brian Key; et al. (Reviews in Fisheries Science & Aquaculture, 2024)

Context-dependent changes in maritime traffic activity during the first year of the COVID-19 pandemic - Alexandra Loveridge; Christopher D. Elvidge; David A. Kroodsma; Timothy D. White; Karen Evans; Akiko Kato; Yan Ropert-Coudert; Julia Sommerfeld; Akinori Takahashi; Robert Patchett; Benjamin Robira; Christian Rutz; et al. (Global Environmental Change, 2024)

Duration-sensitive association between air pollution exposure and changes in cardiometabolic biomarkers: Evidence from a predominantly African American cohort - Jiajun Luo; Muhammad G. Kibriya; Farzana Jasmine; Afzal Shaikh; Zhihao Jin; Robert Sargis; Karen Kim; Christopher O. Olopade; Jayant Pinto; Habibul Ahsan; Briseis Aschebrook-Kilfoy (Environmental Research, 2024)

Four billion years of secular compositional change in granitoids - Kent C. Condie; Stephen J. Puetz; Christopher J. Spencer; Nick M.W. Roberts (Chemical Geology, 2024)

Observing Ocean Boundary Currents: Lessons Learned from Six Regions with Mature Observational and Modeling Systems - Nadia Ayoub; María Chidichimo; Edward Dever; Xinyu Guo; Marjolaine Krug; Belén Míguez; Tamaryn Morris; Janet Sprintall; Kiyoshi Tanaka; Robert Todd; John Wilkin; Enrique Álvarez-Fanjul; et al. (Oceanography, 2024)
Ocean boundary currents are complex and highly variable systems that play key roles in connecting the open and coastal ocean through cross-slope circulation and upwelling of nutrient-rich water. The structure, strength, and variability of boundary currents are associated with a broad range of spatial and temporal scales. For that reason, long-term boundary current monitoring is challenging and requires the use of complementary observing platforms and sensors coupled with numerical simulations. The Ocean Observations Physics and Climate Panel Boundary Systems Task Team recently held a virtual dialogue series to discuss six mature boundary current monitoring systems. The goal of the series was to examine strategies for developing a conceptual design for sustained observing activities applicable to a wide range of boundary current systems. This article provides a brief overview of the six systems, including users and the observational and modeling components needed to achieve scientific, operational, and societal goals. Ocean observing best practices and recommendations are shared to provide guidance for the coordination and sustainability of observing systems at ocean boundaries and to strengthen and integrate partnerships across and within the global observing networks.

Essential omega‐3 fatty acids are depleted in sea ice and pelagic algae of the Central Arctic Ocean - Katrin Schmidt; Martin Graeve; Clara J. M. Hoppe; Sinhué Torres‐Valdes; Nahid Welteke; Laura M. Whitmore; Philipp Anhaus; Angus Atkinson; Simon T. Belt; Tina Brenneis; Robert G. Campbell; Giulia Castellani; et al. (Global Change Biology, 2024)
Microalgae are the main source of the omega‐3 fatty acids eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), essential for the healthy development of most marine and terrestrial fauna including humans. Inverse correlations of algal EPA and DHA proportions (% of total fatty acids) with temperature have led to suggestions of a warming‐induced decline in the global production of these biomolecules and an enhanced importance of high latitude organisms for their provision. The cold Arctic Ocean is a potential hotspot of EPA and DHA production, but consequences of global warming are unknown. Here, we combine a full‐seasonal EPA and DHA dataset from the Central Arctic Ocean (CAO), with results from 13 previous field studies and 32 cultured algal strains to examine five potential climate change effects; ice algae loss, community shifts, increase in light, nutrients, and temperature. The algal EPA and DHA proportions were lower in the ice‐covered CAO than in warmer peripheral shelf seas, which indicates that the paradigm of an inverse correlation of EPA and DHA proportions with temperature may not hold in the Arctic. We found no systematic differences in the summed EPA and DHA proportions of sea ice versus pelagic algae, and in diatoms versus non‐diatoms. Overall, the algal EPA and DHA proportions varied up to four‐fold seasonally and 10‐fold regionally, pointing to strong light and nutrient limitations in the CAO. Where these limitations ease in a warming Arctic, EPA and DHA proportions are likely to increase alongside increasing primary production, with nutritional benefits for a non‐ice‐associated food web.

Retention and export of planktonic fish eggs in the northeastern Gulf of Mexico - Bich Vi Viviane Nguyen; Yonggang Liu; Christopher D. Stallings; Mya Breitbart; Steven A. Murawski; Robert H. Weisberg; Makenzie Kerr; Eva‐Maria S. Bønnelycke; Ernst B. Peebles (Fisheries Oceanography, 2024)
To help determine whether planktonic eggs of fishes on the West Florida Shelf (WFS) are retained locally or exported elsewhere, we collected fish eggs by plankton net from 17 locations (stations) and identified them using DNA barcoding. We then entered the station coordinates into the West Florida Coastal Ocean Model (WFCOM) and simulated the trajectories of the passively drifting eggs over 2 weeks at three depths (surface, midwater, and near bottom). The results indicated there were two groups of trajectories: a nearshore group that tended to be retained and an offshore group that tended toward export and potential long‐distance dispersal. We also found evidence of a relationship between retention and higher fish‐egg abundance; nearshore stations were associated with higher fish‐egg abundances and higher retention. We suggest this is the result of (1) increased spawning in high‐retention areas, (2) increased drift convergence in high‐retention areas, or both processes acting together. Community analysis using SIMPROF indicated the presence of a depth‐related (retention‐related) difference in species assemblages. Fish‐egg species were also categorized as pelagics or non‐pelagics; there was no evidence of pelagic species being more likely to be exported.

Revision of the Indo-West Pacific crab genus Soliella (Brachyura: Xanthidae: Etisinae): ‘pseudocryptic species’ and basinal speciation - Robert M. Lasley; Jose Christopher E. Mendoza; Gustav Paulay (Systematics and Biodiversity, 2023)

Hydrocarbon markers for assessing the influence of human activities in the tropical semi-arid region (Acaraú River, state of Ceará, Brazil) - Gabrielle M. Fernandes; Davi de A. Martins; Andre H.B. de Oliveira; Marcielly F.B. de Lima; Christopher M. Reddy; Robert K. Nelson; Rivelino M. Cavalcante (Chemosphere, 2023)

Impacts of acute and chronic suspended solids exposure on juvenile freshwater mussels - Wenyu Zhu; James Kunz; Eric Brunson; Chris Barnhart; Henry Brown; Stephen McMurray; Andrew D. Roberts; Christopher Shulse; Kathleen Trauth; Binbin Wang; Jeffery A. Steevens; Baolin Deng (Science of The Total Environment, 2023)

Bridging the gap between airborne and spaceborne imaging spectroscopy for mountain glacier surface property retrievals - Christopher P. Donahue; Brian Menounos; Nick Viner; S. McKenzie Skiles; Steven Beffort; Taylor Denouden; Santiago Gonzalez Arriola; Robert White; Derek Heathfield (Remote Sensing of Environment, 2023)

Restoring areas after a radioactive fallout: A multidisciplinary study on decontamination - Christopher Rääf; Johan Martinsson; Mats Eriksson; Jens Ewald; Reza G. Javid; Martin Hjellström; Mats Isaksson; Joel Rasmussen; Thomas Sterner; Robert Finck (Journal of Environmental Radioactivity, 2023)

Correction to: The Woven EndoBridge (WEB) Device for the Treatment of Intracranial Aneurysms: Ten Years of Lessons Learned and Adjustments in Practice from the WorldWideWEB Consortium - Adam A. Dmytriw; Mahmoud Dibas; Sherief Ghozy; Nimer Adeeb; Jose Danilo Bengzon Diestro; Kevin Phan; Hugo H. Cuellar-Saenz; Ahmad Sweid; Sovann V. Lay; Adrien Guenego; Leonardo Renieri; Ali Al Balushi; et al. (Translational Stroke Research, 2023)

Production of secondary metabolites in regenerated Southern wormwood (Artemisia abrotanum L.) under various experimental conditions - Adna Alihodzic; Jimmy Davis; Christopher Roberts; Sally Henrie; Mark Bolyard (In Vitro Cellular & Developmental Biology - Plant, 2023)

Genetic risk prediction in Hispanics/Latinos: milestones, challenges, and social-ethical considerations - Betzaida L. Maldonado; Daniel G. Piqué; Robert C. Kaplan; Katrina G. Claw; Christopher R. Gignoux (Journal of Community Genetics, 2023)
Genome-wide association studies (GWAS) have allowed the identification of disease-associated variants, which can be leveraged to build polygenic scores (PGSs). Even though PGSs can be a valuable tool in personalized medicine, their predictive power is limited in populations of non-European ancestry, particularly in admixed populations. Recent efforts have focused on increasing racial and ethnic diversity in GWAS, thus, addressing some of the limitations of genetic risk prediction in these populations. Even with these efforts, few studies focus exclusively on Hispanics/Latinos. Additionally, Hispanic/Latino populations are often considered a single population despite varying admixture proportions between and within ethnic groups, diverse genetic heterogeneity, and demographic history. Combined with highly heterogeneous environmental and socioeconomic exposures, this diversity can reduce the transferability of genetic risk prediction models. Given the recent increase of genomic studies that include Hispanics/Latinos, we review the milestones and efforts that focus on genetic risk prediction, summarize the potential for improving PGS transferability, and highlight the challenges yet to be addressed. Additionally, we summarize social-ethical considerations and provide ideas to promote genetic risk prediction models that can be implemented equitably.

Beech bark disease does not reduce the long-term wood production of two forests contrasting in age, productivity, and structure - Ellen Stuart-Haëntjens; Jeff W. Atkins; Alexander T. Fotis; Robert T. Fahey; Brady S. Hardiman; Brandon C. Alveshere; Christoph Vogel; Christopher M. Gough (Forest Ecology and Management, 2023)

Impact of fixture purging on water age and excess water usage, considering stochastic water demands - Emily Clements; Christopher Irwin; Alexandros Taflanidis; Kyle Bibby; Robert Nerenberg (Water Research, 2023)

Bio-physical determinants of sediment accumulation on an offshore coral reef: A snapshot study - Sterling B. Tebbett; Jodie A. Schlaefer; Casey L. Bowden; William P. Collins; Christopher R. Hemingson; Scott D. Ling; Juliano Morais; Renato A. Morais; Alexandre C. Siqueira; Robert P. Streit; Sam Swan; David R. Bellwood (Science of The Total Environment, 2023)

A Ceratopteris EXCESS MICROSPOROCYTES1 suppresses reproductive transition in the fern vegetative leaves - Kelley A. Withers; Kevin Falls; Christopher E. Youngstrom; Tommy Nguyen; Anika DeWald; Rebekah M. Yarvis; Gabriel P. Simons; Robert Flanagan; Linh T. Bui; Erin E. Irish; Chi-Lien Cheng (Plant Science, 2023)

A generic approach to construct pseudo components for oil weathering models - Xiaolong Geng; Christopher H. Barker; Amy MacFadyen; Michel C. Boufadel; Dalina L. Thrift-Viveros; Robert K. Jones; Caitlin O’Connor; Kenneth Lee (Journal of Hazardous Materials, 2023)

Integrating risk assessment methods for carbon storage: A case study for the quest carbon capture and storage facility - Christopher F. Brown; Greg Lackey; Nate Mitchell; Seunghwan Baek; Brandon Schwartz; Marcella Dean; Robert Dilmore; Hein Blanke; Simon O'Brien; Carrie Rowe (International Journal of Greenhouse Gas Control, 2023)

An experimental approach to identify drivers of tree regeneration diversity, composition, and heterogeneity in northern hardwood forests - Claudia I. Bartlick; Julia I. Burton; Christopher R. Webster; Robert E. Froese; Yvette L. Dickinson (Forest Ecology and Management, 2023)

Sustainability of bioenergy – Mapping the risks & benefits to inform future bioenergy systems - Andrew James Welfle; Alberto Almena; Muhammad Naveed Arshad; Scott William Banks; Isabela Butnar; Katie Jane Chong; SamuelJ.G. Cooper; Helen Daly; Samira Garcia Freites; Fatih Güleç; Christopher Hardacre; Robert Holland; et al. (Biomass and Bioenergy, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Mercury in Neotropical birds: a synthesis and prospectus on 13 years of exposure data - Christopher J. Sayers; David C. Evers; Viviana Ruiz-Gutierrez; Evan Adams; Claudia M. Vega; Jessica N. Pisconte; Vania Tejeda; Kevin Regan; Oksana P. Lane; Abidas A. Ash; Reynold Cal; Stevan Reneau; et al. (Ecotoxicology, 2023)
Environmental mercury (Hg) contamination of the global tropics outpaces our understanding of its consequences for biodiversity. Knowledge gaps of pollution exposure could obscure conservation threats in the Neotropics: a region that supports over half of the world’s species, but faces ongoing land-use change and Hg emission via artisanal and small-scale gold mining (ASGM). Due to their global distribution and sensitivity to pollution, birds provide a valuable opportunity as bioindicators to assess how accelerating Hg emissions impact an ecosystem’s ability to support biodiversity, and ultimately, global health. We present the largest database on Neotropical bird Hg concentrations ( n = 2316) and establish exposure baselines for 322 bird species spanning nine countries across Central America, South America, and the West Indies. Patterns of avian Hg exposure in the Neotropics broadly align with those in temperate regions: consistent bioaccumulation across functional groups and high spatiotemporal variation. Bird species occupying higher trophic positions and aquatic habitats exhibited elevated Hg concentrations that have been previously associated with reductions in reproductive success. Notably, bird Hg concentrations were over four times higher at sites impacted by ASGM activities and differed by season for certain trophic niches. We developed this synthesis via a collaborative research network, the Tropical Research for Avian Conservation and Ecotoxicology (TRACE) Initiative, which exemplifies inclusive, equitable, and international data-sharing. While our findings signal an urgent need to assess sampling biases, mechanisms, and consequences of Hg exposure to tropical avian communities, the TRACE Initiative provides a meaningful framework to achieve such goals. Ultimately, our collective efforts support and inform local, scientific, and government entities, including Parties of the United Nations Minamata Convention on Mercury, as we continue working together to understand how Hg pollution impacts biodiversity conservation, ecosystem function, and public health in the tropics.

Infection prevalence, intensity, and gill coverage by the parasitic flatworm, Bdelloura candida, in the American horseshoe crab (Limulus polyphemus) - Christopher J. Brianik; Justin Bopp; Camilla Piechocki; Nancy Liang; Sabrina O’Reilly; Robert M. Cerrato; Bassem Allam (Hydrobiologia, 2023)

Extreme weather events and public attention to climate change in Australia - Christopher Crellin; Robert MacNeil (Climatic Change, 2023)

Future climate change effects on US forest composition may offset benefits of reduced atmospheric deposition of N and S - Christopher M. Clark; Jennifer Phelan; Jeremy Ash; John Buckley; James Cajka; Kevin Horn; R. Quinn Thomas; Robert D. Sabo (Global Change Biology, 2023)
Climate change and atmospheric deposition of nitrogen (N) and sulfur (S) are important drivers of forest demography. Here we apply previously derived growth and survival responses for 94 tree species, representing >90% of the contiguous US forest basal area, to project how changes in mean annual temperature, precipitation, and N and S deposition from 20 different future scenarios may affect forest composition to 2100. We find that under the low climate change scenario (RCP 4.5), reductions in aboveground tree biomass from higher temperatures are roughly offset by increases in aboveground tree biomass from reductions in N and S deposition. However, under the higher climate change scenario (RCP 8.5) the decreases from climate change overwhelm increases from reductions in N and S deposition. These broad trends underlie wide variation among species. We found averaged across temperature scenarios the relative abundance of 60 species were projected to decrease more than 5% and 20 species were projected to increase more than 5%; and reductions of N and S deposition led to a decrease for 13 species and an increase for 40 species. This suggests large shifts in the composition of US forests in the future. Negative climate effects were mostly from elevated temperature and were not offset by scenarios with wetter conditions. We found that by 2100 an estimated 1 billion trees under the RCP 4.5 scenario and 20 billion trees under the RCP 8.5 scenario may be pushed outside the temperature record upon which these relationships were derived. These results may not fully capture future changes in forest composition as several other factors were not included. Overall efforts to reduce atmospheric deposition of N and S will likely be insufficient to overcome climate change impacts on forest demography across much of the United States unless we adhere to the low climate change scenario.

A–Z of cost-effective adaptation strategies to the impact of climate change among crop farmers in West Africa - NwaJesus Anthony Onyekuru; Robert Marchant; Julia M. Touza; Chukwuma Ume; Chinedu Chiemela; Chukwemeka Onyia; Eric C. Eboh; Christopher C. Eze (Environment, Development and Sustainability, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Modeling the effects of interior headland restoration on estuarine sediment transport processes in a marine-dominant estuary - Robert L. Jenkins; Davina L. Passeri; Christopher G. Smith; David M. Thompson; Kathryn E. L. Smith (Frontiers in Marine Science, 2023)
The effects of interior headland restoration on estuarine sediment transport processes were assessed through process-based numerical modeling. Three proposed interior headland restoration scenarios in the Grand Bay estuary (Mississippi/Alabama) were modeled using Delft3D to understand impacts on suspended sediment concentrations, bed level morphology, and sediment fluxes under present-day conditions and a sea level rise (SLR) of 0.5 m, representing a high projection of SLR by the year 2050. Model results showed localized differences in bed levels near the restored features after a year of simulated morphologic change. The restored headland features acted as a sediment source to the immediate surroundings while also providing some non-significant sheltering effect of backshore shoals and marsh shorelines. Sediment fluxes were sensitive to wind directions and the presence of the restored headlands. However, regardless of wind direction, mean sea level, or restoration action, the greatest sediment fluxes were always export fluxes from the estuary, which were further increased with increased sea level. Suspended sediment concentrations were highly influenced by SLR in a non-linear manner. Sediment concentrations both increased and decreased depending on depth under SLR. Furthermore, SLR allowed for the suspension and deposition of sediments on the marsh platform. Overall, the influence of SLR was more impactful to changing sediment dynamics than the influence of the restoration features.

Age, Growth, and Functional Gonochorism with a Twist of Diandric Protogyny in Goliath Grouper from the Atlantic Coast of Florida - Debra J. Murie; Daryl C. Parkyn; Christopher C. Koenig; Felicia C. Coleman; Christopher R. Malinowski; Jessica A. Cusick; Robert D. Ellis (Fishes, 2023)
The lack of data on the age, growth, and reproduction of the Atlantic Goliath Grouper Epinephelus itajara off the coasts of Florida (USA) makes it difficult to estimate the extent of their population recovery following the 1990 fishery closure, as well as the potential effects of the recent (2023) opening of a fishery for juveniles. Goliath Grouper from the Atlantic coast of Florida were non-lethally sampled for size (total length, TL), age (via fin rays), and sex and reproductive stage (via gonad biopsies, milt/egg expression, gonopores) from May to October 2010–2016. Of 653 unique fish captured (not including 118 recaptures), 257 (39.4%) were females (122–228 cm TL; 5–20 years old), 264 (40.0%) were males (104–225 cm TL; 4–22 years old), 100 (15.3%) were unsexed (82–211 cm TL; 3–15 years old), and 32 (4.9%) were protogynous hermaphrodites (108–209 cm TL; 5–20 years old). Protogyny was conclusively determined in two fish recaptured and re-biopsied that had transitioned from female to male. However, an overlap in the age and size of males and females, a 1:1 sex ratio, and the presence of relatively small, young, mature males, in combination with an apparently low functional sex change rate, all indicated that the sexual pattern of Goliath Grouper was functionally gonochoristic with the potential for diandric protogyny. Females > 10 years old were larger-at-age than males, and Goliath Grouper from the Atlantic coast were larger-at-age than fish from the Gulf of Mexico. These differences in age, growth, and reproductive strategy—as well as the nascent fishery for juveniles—need to be monitored closely so that the current and future reproductive capacity of the population continues to ensure growth and sustainability.

Physicochemical and immunological effects of adjuvant formulations with snake venom antigens for immunization of horses for antivenom production - Christopher B. Fox; Amit P. Khandhar; Lisa Khuu; Tony Phan; Robert Kinsey; Daniel Cordero; José María Gutiérrez; Guillermo León (Toxicon, 2023)

The Woven EndoBridge (WEB) Device for the Treatment of Intracranial Aneurysms: Ten Years of Lessons Learned and Adjustments in Practice from the WorldWideWEB Consortium - Adam A. Dmytriw; Mahmoud Dibas; Sherief Ghozy; Nimer Adeeb; Jose Danilo Bengzon Diestro; Kevin Phan; Hugo H. Cuellar-Saenz; Ahmad Sweid; Sovann V. Lay; Adrien Guenego; Leonardo Renieri; Ali Al Balushi; et al. (Translational Stroke Research, 2023)

Evapotranspiration regulates leaf temperature and respiration in dryland vegetation - Christopher L. Kibler; Anna T. Trugman; Dar A. Roberts; Christopher J. Still; Russell L. Scott; Kelly K. Caylor; John C. Stella; Michael Bliss Singer (Agricultural and Forest Meteorology, 2023)

Drivers and timing of grass carp movement within the Sandusky River, Ohio: implications to potential spawning barrier response strategy - Justin J. Bopp; Travis O. Brenden; Matthew D. Faust; Christopher S. Vandergoot; Richard T. Kraus; James J. Roberts; Lucas R. Nathan (Biological Invasions, 2023)

Spawning Migrations of the Atlantic Goliath Grouper along the Florida Atlantic Coast - Robert D. Ellis; Christopher C. Koenig; James V. Locascio; Christopher R. Malinowski; Felicia C. Coleman (Fishes, 2023)
Atlantic goliath grouper (Epinephelus itajara), the largest reef fish in the Western Atlantic, exhibit high site fidelity to home reefs but also undertake annual migrations to distant spawning sites. Once relatively common throughout Florida and the Caribbean, the species; is now considered vulnerable (i.e., threatened with extinction) due to overfishing and loss of juvenile mangrove habitat. Goliath grouper in the southeastern US form annual spawning aggregations on high-relief reefs located offshore of both the Gulf and Atlantic coasts of Florida, US. To determine spawning site fidelity and describe migration patterns to aggregations, we implanted 50 adult goliath grouper with acoustic transmitter tags from 2010 to 2013. Fish were tagged at known spawning sites off the Florida Atlantic coast and tracked as they moved through the FACT Network array of acoustic receivers. From 2010 to 2020, we collected ~7 million detections from tagged goliath grouper at 153 sites along the southeastern US Atlantic coast. Results of this long-term tracking indicate that adult goliath grouper are relatively sedentary during non-spawning months (Nov to June) but move significantly more prior to, during, and immediately after spawning (July to Oct). Inter-annual spawning site fidelity was high: between 80–93% of tagged fish returned to the same spawning sites each year. Arrival timing at spawning sites coincided with the August new moon, with males arriving earlier than females. Some individuals migrated distances greater than 400-km per year, with observed migration rates of up to 44-km per day prior to spawning. Long-term tagging data are critical for understanding movement patterns and developing management strategies for this species of special conservation concern.

Design and redesign of a bottom trawl survey in Chesapeake Bay, USA - Robert J. Latour; James Gartland; Christopher F. Bonzek (Frontiers in Marine Science, 2023)
Fisheries-independent surveys that reliably sample a broad size range of exploited and ecologically important species provide valuable data in support of fisheries management and ecosystem science. The operational consistency of surveys over time and space is fundamental to the interpretation of data in the contexts of population dynamics processes, community interactions, policy impacts, and environmental forcing. However, the need to maintain historic sampling protocols over extended time periods limits the utilization of new technologies that could lead to improved data collection. Survey vessel replacements also become inevitable as the maturity of sampling programs becomes multidecadal. This case study describes the motivational origin, initial design, and redesign of a bottom trawl survey operating in Chesapeake Bay, the largest estuary in the United States. Regional aspirations to consider ecosystem principles in fisheries management aided initial development of the survey, and the need to collect specific data types to support that endeavor impacted several early design elements. Following the beginning years of full-scale survey operations, a consistently evolving awareness of potential areas of improvement for the survey grew from formal efforts to engage with scientific and industry partners on trawl gear design, leverage the program for additional survey opportunities, utilize gear testing technology, and analyze extant data. When the delivery of a new, state-of-the-art research vessel forced the transfer of survey operations to a new platform, all potential changes were incorporated simultaneously. A subsequent paired-tow experiment was conducted to build a calibration database that successfully provided estimates of relative selectivity for routinely sampled taxa. This experience yielded several lessons learned that are intended to aid investigators faced with adopting structural changes to fisheries-independent surveys in the future.

Length-based assessment of an exploited coastal pike (Esox lucius) stock (Rügen, southern Baltic Sea) underscores the crucial relevance of growth and natural mortality for assessment outcomes - Colm J. Fitzgerald; Jan S. Droll; Samuel Shephard; Christopher T. Monk; Timo Rittweg; Robert Arlinghaus (Fisheries Research, 2023)

PFAS adsorbent selection: The role of adsorbent use rate, water quality, and cost - Conner C. Murray; Andrew Safulko; Hooman Vatankhah; Charlie J. Liu; Bahareh Tajdini; Robert E. Marshall; Christopher Bellona (Journal of Hazardous Materials, 2023)

Rapidly Changing Range Limits in a Warming World: Critical Data Limitations and Knowledge Gaps for Advancing Understanding of Mangrove Range Dynamics in the Southeastern USA - Rémi Bardou; Michael J. Osland; Steven Scyphers; Christine Shepard; Karen E. Aerni; Jahson B. Alemu I; Robert Crimian; Richard H. Day; Nicholas M. Enwright; Laura C. Feher; Sarah L. Gibbs; Kiera O’Donnell; et al. (Estuaries and Coasts, 2023)
Climate change is altering species’ range limits and transforming ecosystems. For example, warming temperatures are leading to the range expansion of tropical, cold-sensitive species at the expense of their cold-tolerant counterparts. In some temperate and subtropical coastal wetlands, warming winters are enabling mangrove forest encroachment into salt marsh, which is a major regime shift that has significant ecological and societal ramifications. Here, we synthesized existing data and expert knowledge to assess the distribution of mangroves near rapidly changing range limits in the southeastern USA. We used expert elicitation to identify data limitations and highlight knowledge gaps for advancing understanding of past, current, and future range dynamics. Mangroves near poleward range limits are often shorter, wider, and more shrublike compared to their tropical counterparts that grow as tall forests in freeze-free, resource-rich environments. The northern range limits of mangroves in the southeastern USA are particularly dynamic and climate sensitive due to abundance of suitable coastal wetland habitat and the exposure of mangroves to winter temperature extremes that are much colder than comparable range limits on other continents. Thus, there is need for methodological refinements and improved spatiotemporal data regarding changes in mangrove structure and abundance near northern range limits in the southeastern USA. Advancing understanding of rapidly changing range limits is critical for foundation plant species such as mangroves, as it provides a basis for anticipating and preparing for the cascading effects of climate-induced species redistribution on ecosystems and the human communities that depend on their ecosystem services.

Hummingbird blood traits track oxygen availability across space and time - Jessie L. Williamson; Ethan B. Linck; Emil Bautista; Ashley Smiley; Jimmy A. McGuire; Robert Dudley; Christopher C. Witt (Ecology Letters, 2023)
Predictable trait variation across environments suggests shared adaptive responses via repeated genetic evolution, phenotypic plasticity or both. Matching of trait–environment associations at phylogenetic and individual scales implies consistency between these processes. Alternatively, mismatch implies that evolutionary divergence has changed the rules of trait–environment covariation. Here we tested whether species adaptation alters elevational variation in blood traits. We measured blood for 1217 Andean hummingbirds of 77 species across a 4600‐m elevational gradient. Unexpectedly, elevational variation in haemoglobin concentration ([Hb]) was scale independent, suggesting that physics of gas exchange, rather than species differences, determines responses to changing oxygen pressure. However, mechanisms of [Hb] adjustment did show signals of species adaptation: Species at either low or high elevations adjusted cell size, whereas species at mid‐elevations adjusted cell number. This elevational variation in red blood cell number versus size suggests that genetic adaptation to high altitude has changed how these traits respond to shifts in oxygen availability.

The DynaDeep observatory – a unique approach to study high-energy subterranean estuaries - Gudrun Massmann; Grace Abarike; Kojo Amoako; Felix Auer; Thomas H. Badewien; Cordula Berkenbrink; Michael Ernst Böttcher; Simone Brick; Iris Valeria Medina Cordova; Jairo Cueto; Thorsten Dittmar; Bert Engelen; et al. (Frontiers in Marine Science, 2023)
Subterranean estuaries are connective zones between inland aquifers and the open sea where terrestrial freshwater and circulating seawater mix and undergo major biogeochemical changes. They are biogeochemical reactors that modify groundwater chemistry prior to discharge into the sea. We propose that subterranean estuaries of high-energy beaches are particularly dynamic environments, where the effect of the dynamic boundary conditions propagates tens of meters into the subsurface, leading to strong spatio-temporal variability of geochemical conditions. We hypothesize that they form a unique habitat with an adapted microbial community unlike other typically more stable subsurface environments. So far, however, studies concerning subterranean estuaries of high-energy beaches have been rare and therefore their functioning, and their importance for coastal ecosystems, as well as for carbon, nutrient and trace element cycling, is little understood. We are addressing this knowledge gap within the interdisciplinary research project DynaDeep by studying the combined effect of surface (hydro- and morphodynamics) on subsurface processes (groundwater flow and transport, biogeochemical reactions, microbiology). A unique subterranean estuary observatory was established on the northern beach of the island of Spiekeroog facing the North Sea, serving as an exemplary high-energy research site and model system. It consists of fixed and permanent infrastructure such as a pole with measuring devices, multi-level groundwater wells and an electrode chain. This forms the base for autonomous measurements, regular repeated sampling, interdisciplinary field campaigns and experimental work, all of which are integrated via mathematical modelling to understand and quantify the functioning of the biogeochemical reactor. First results show that the DynaDeep observatory is collecting the intended spatially and temporally resolved morphological, sedimentological and biogeochemical data. Samples and data are further processed ex-situ and combined with experiments and modelling. Ultimately, DynaDeep aims at elucidating the global relevance of these common but overlooked environments.

Edge computing at sea: high-throughput classification of in-situ plankton imagery for adaptive sampling - Moritz S. Schmid; Dominic Daprano; Malhar M. Damle; Christopher M. Sullivan; Su Sponaugle; Charles Cousin; Cedric Guigand; Robert K. Cowen (Frontiers in Marine Science, 2023)
The small sizes of most marine plankton necessitate that plankton sampling occur on fine spatial scales, yet our questions often span large spatial areas. Underwater imaging can provide a solution to this sampling conundrum but collects large quantities of data that require an automated approach to image analysis. Machine learning for plankton classification, and high-performance computing (HPC) infrastructure, are critical to rapid image processing; however, these assets, especially HPC infrastructure, are only available post-cruise leading to an ‘after-the-fact’ view of plankton community structure. To be responsive to the often-ephemeral nature of oceanographic features and species assemblages in highly dynamic current systems, real-time data are key for adaptive oceanographic sampling. Here we used the new In-situ Ichthyoplankton Imaging System-3 (ISIIS-3) in the Northern California Current (NCC) in conjunction with an edge server to classify imaged plankton in real-time into 170 classes. This capability together with data visualization in a heavy.ai dashboard makes adaptive real-time decision-making and sampling at sea possible. Dual ISIIS-Deep-focus Particle Imager (DPI) cameras sample 180 L s -1 , leading to >10 GB of video per min. Imaged organisms are in the size range of 250 µm to 15 cm and include abundant crustaceans, fragile taxa (e.g., hydromedusae, salps), faster swimmers (e.g., krill), and rarer taxa (e.g., larval fishes). A deep learning pipeline deployed on the edge server used multithreaded CPU-based segmentation and GPU-based classification to process the imagery. AVI videos contain 50 sec of data and can contain between 23,000 - 225,000 particle and plankton segments. Processing one AVI through segmentation and classification takes on average 3.75 mins, depending on biological productivity. A heavyDB database monitors for newly processed data and is linked to a heavy.ai dashboard for interactive data visualization. We describe several examples where imaging, AI, and data visualization enable adaptive sampling that can have a transformative effect on oceanography. We envision AI-enabled adaptive sampling to have a high impact on our ability to resolve biological responses to important oceanographic features in the NCC, such as oxygen minimum zones, or harmful algal bloom thin layers, which affect the health of the ecosystem, fisheries, and local communities.

A Bayesian model for multivariate discrete data using spatial and expert information with application to inferring building attributes - Christopher Krapu; Nolan Hayes; Robert Stewart; Kuldeep Kurte; Amy Rose; Alex Sorokine; Marie Urban (Spatial Statistics, 2023)

Chronic toxicity and carcinogenicity study of dietary gardenia blue in Sprague Dawley rats - Robert Maronpot; Yuval Ramot; Abraham Nyska; Christopher Sproul; Rebecca Moore; Mihoko Koyanagi; Shuichi Chiba; Masayuki Nishino; Shim-mo Hayashi (Food and Chemical Toxicology, 2023)

Comprehensive ECG reference intervals in C57BL/6N substrains provide a generalizable guide for cardiac electrophysiology studies in mice - Manuela A. Oestereicher; Janine M. Wotton; Shinya Ayabe; Ghina Bou About; Tsz Kwan Cheng; Jae-Hoon Choi; Dave Clary; Emily M. Dew; Lahcen Elfertak; Alain Guimond; Hamed Haseli Mashhadi; Jason D. Heaney; et al. (Mammalian Genome, 2023)
Reference ranges provide a powerful tool for diagnostic decision-making in clinical medicine and are enormously valuable for understanding normality in pre-clinical scientific research that uses in vivo models. As yet, there are no published reference ranges for electrocardiography (ECG) in the laboratory mouse. The first mouse-specific reference ranges for the assessment of electrical conduction are reported herein generated from an ECG dataset of unprecedented scale. International Mouse Phenotyping Consortium data from over 26,000 conscious or anesthetized C57BL/6N wildtype control mice were stratified by sex and age to develop robust ECG reference ranges. Interesting findings include that heart rate and key elements from the ECG waveform (RR-, PR-, ST-, QT-interval, QT corrected, and QRS complex) demonstrate minimal sexual dimorphism. As expected, anesthesia induces a decrease in heart rate and was shown for both inhalation (isoflurane) and injectable (tribromoethanol) anesthesia. In the absence of pharmacological, environmental, or genetic challenges, we did not observe major age-related ECG changes in C57BL/6N-inbred mice as the differences in the reference ranges of 12-week-old compared to 62-week-old mice were negligible. The generalizability of the C57BL/6N substrain reference ranges was demonstrated by comparison with ECG data from a wide range of non-IMPC studies. The close overlap in data from a wide range of mouse strains suggests that the C57BL/6N-based reference ranges can be used as a robust and comprehensive indicator of normality. We report a unique ECG reference resource of fundamental importance for any experimental study of cardiac function in mice.

Correction to: Coupled climate response to Atlantic Multidecadal Variability in a multi-model multi-resolution ensemble - Daniel L. R. Hodson; Pierre-Antoine Bretonnière; Christophe Cassou; Paolo Davini; Nicholas P. Klingaman; Katja Lohmann; Jorge Lopez-Parages; Marta Martín-Rey; Marie-Pierre Moine; Paul-Arthur Monerie; Dian A. Putrasahan; Christopher D. Roberts; et al. (Climate Dynamics, 2023)

US regulations to curb alleged cancer causes are ineffectual and compromised by scientific, constitutional and ethical violations - Gio B. Gori; Michael Aschner; Christopher J. Borgert; Samuel M. Cohen; Daniel R. Dietrich; Corrado L. Galli; Helmut Greim; John S. Heslop-Harrison; Sam Kacew; Norbert E. Kaminski; James E. Klaunig; Hans W.J. Marquardt; et al. (Archives of Toxicology, 2023)
The 1958 Delaney amendment to the Federal Food Drug and Cosmetics Act prohibited food additives causing cancer in animals by appropriate tests. Regulators responded by adopting chronic lifetime cancer tests in rodents, soon challenged as inappropriate, for they led to very inconsistent results depending on the subjective choice of animals, test design and conduct, and interpretive assumptions. Presently, decades of discussions and trials have come to conclude it is impossible to translate chronic animal data into verifiable prospects of cancer hazards and risks in humans. Such conclusion poses an existential crisis for official agencies in the US and abroad, which for some 65 years have used animal tests to justify massive regulations of alleged human cancer hazards, with aggregated costs of $trillions and without provable evidence of public health advantages. This article addresses suitable remedies for the US and potentially worldwide, by critically exploring the practices of regulatory agencies vis-á-vis essential criteria for validating scientific evidence. According to this analysis, regulations of alleged cancer hazards and risks have been and continue to be structured around arbitrary default assumptions at odds with basic scientific and legal tests of reliable evidence. Such practices raise a manifold ethical predicament for being incompatible with basic premises of the US Constitution, and with the ensuing public expectations of testable truth and transparency from government agencies. Potential remedies in the US include amendments to the US Administrative Procedures Act, preferably requiring agencies to justify regulations compliant with the Daubert opinion of the Daubert ruling of the US Supreme Court, which codifies the criteria defining reliable scientific evidence . International reverberations are bound to follow what remedial actions may be taken in the US, the origin of current world regulatory procedures to control alleged cancer causing agents.

Mechanisms underpinning community stability along a latitudinal gradient: Insights from a niche‐based approach - Luke Christopher Evans; Yolanda Melero; Reto Schmucki; Philipp H. Boersch‐Supan; Lluís Brotons; Colin Fontaine; Frédéric Jiguet; Mikko Kuussaari; Dario Massimino; Robert A. Robinson; David B. Roy; Oliver Schweiger; et al. (Global Change Biology, 2023)
At large scales, the mechanisms underpinning stability in natural communities may vary in importance due to changes in species composition, mean abundance, and species richness. Here we link species characteristics (niche positions) and community characteristics (richness and abundance) to evaluate the importance of stability mechanisms in 156 butterfly communities monitored across three European countries and spanning five bioclimatic regions. We construct niche‐based hierarchical structural Bayesian models to explain first differences in abundance, population stability, and species richness between the countries, and then explore how these factors impact community stability both directly and indirectly (via synchrony and population stability). Species richness was partially explained by the position of a site relative to the niches of the species pool, and species near the centre of their niche had higher average population stability. The differences in mean abundance, population stability, and species richness then influenced how much variation in community stability they explained across the countries. We found, using variance partitioning, that community stability in Finnish communities was most influenced by community abundance, whereas this aspect was unimportant in Spain with species synchrony explaining most variation; the UK was somewhat intermediate with both factors explaining variation. Across all countries, the diversity–stability relationship was indirect with species richness reducing synchrony which increased community stability, with no direct effects of species richness. Our results suggest that in natural communities, biogeographical variation observed in key drivers of stability, such as population abundance and species richness, leads to community stability being limited by different factors and that this can partially be explained due to the niche characteristics of the European butterfly assemblage.

Oral chronic toxicity and carcinogenicity study of alpha-glycosyl isoquercitrin (AGIQ) in Sprague Dawley rats - Robert Maronpot; Yuval Ramot; Abraham Nyska; Christopher Sproul; Rebecca Moore; Brad Bolon; Shim-mo Hayashi (Regulatory Toxicology and Pharmacology, 2023)

Straining to find the permeability - Bryan Euser; Christopher W. Johnson; Robert A. Guyer; Esteban Rougier; Carly M. Donahue; George D. Guthrie; Antonio Munjiza; Paul A. Johnson (Earth and Planetary Science Letters, 2023)

A-type granites in space and time: Relationship to the supercontinent cycle and mantle events - Kent C. Condie; Sergei A. Pisarevsky; Stephen J. Puetz; Nick M.W. Roberts; Christopher J. Spencer (Earth and Planetary Science Letters, 2023)

Adult snow crab, Chionoecetes opilio, display body-wide exoskeletal resistance to the effects of long-term ocean acidification - Tait Algayer; Ahmed Mahmoud; Sanjana Saksena; W. Christopher Long; Katherine M. Swiney; Robert J. Foy; Brittan V. Steffel; Kathryn E. Smith; Richard B. Aronson; Gary H. Dickinson (Marine Biology, 2023)

Subgrid Variability of Atmospheric Surface-Layer Parameters in Complex Terrain - Sebastian F. Otarola Bustos; Harindra J. S. Fernando; James M. Wilczak; Andrey A. Grachev; Christopher Hocut; Robert Dumais (Boundary-Layer Meteorology, 2023)

Sorghum in foods: Functionality and potential in innovative products - Ali Khoddami; Valeria Messina; Komala Vadabalija Venkata; Asgar Farahnaky; Christopher L. Blanchard; Thomas H. Roberts (Critical Reviews in Food Science and Nutrition, 2023)

Middle platform carbonate depositional systems and lithofacies patterns in the Lower Ordovician Ellenburger Group, Tobosa Basin in West Texas, U.S.A., and subsequent Sauk-Tippecanoe megasequence boundary meteoric karsting - Robert G. Loucks; Christopher K. Zahm; Kelly E. Hattori; Taylor Sanchez (Marine and Petroleum Geology, 2023)

Aflatoxins in stored maize, maize flours, and stiff porridge consumed in schools: A case study of Dodoma region, Tanzania - Mariamu Kibwana; Fikira Kimbokota; Robert Christopher; Juma A. Mmongoyo (Food Control, 2023)

Highly socially vulnerable communities exhibit disproportionately increased viral loads as measured in community wastewater - William M. Baldwin; Robert D. Dayton; Aaron W. Bivins; Rona S. Scott; Andrew D. Yurochko; John A. Vanchiere; Terry Davis; Connie L. Arnold; Jose.E.T. Asuncion; Mohammad A.N. Bhuiyan; Brandon Snead; William Daniel; et al. (Environmental Research, 2023)

Climate-driven shifts in pelagic fish distributions in a rapidly changing Pacific Arctic - Robert M. Levine; Alex De Robertis; Daniel Grünbaum; Sharon Wildes; Edward V. Farley; Phyllis J. Stabeno; Christopher D. Wilson (Deep Sea Research Part II: Topical Studies in Oceanography, 2023)

Integrating management of marine activities in Australia - Robert L. Stephenson; Alistair J. Hobday; Ian Butler; Toni Cannard; Mel Cowlishaw; Ian Cresswell; Christopher Cvitanovic; Jon C. Day; Kirstin Dobbs; Leo X.C. Dutra; Stewart Frusher; Maree Fudge; et al. (Ocean & Coastal Management, 2023)

Reexamining one-trial learning in common carp (Cyprinus carpio) through private and social cues: No evidence for hook avoidance lasting more than seven months - Philipp Czapla; Magnus Lovén Wallerius; Christopher T. Monk; Steven J. Cooke; Robert Arlinghaus (Fisheries Research, 2023)

Actinium and radium fluxes from the seabed in the northeast Pacific Basin - Nathaniel Kemnitz; Douglas E. Hammond; Paul Henderson; Emilie Le Roy; Matthew Charette; Willard Moore; Robert F. Anderson; Martin Q. Fleisher; Anne Leal; Erin Black; Christopher T. Hayes; Jess Adkins; et al. (Marine Chemistry, 2023)

Balancing the management of powerline right-of-way corridors for humans and nature - Megan Garfinkel; Sheryl Hosler; Michael Roberts; Jess Vogt; Christopher Whelan; Emily Minor (Journal of Environmental Management, 2023)

Human health risk and food safety implications of microplastic consumption by fish from coastal waters of the eastern equatorial Atlantic Ocean - Edem Mahu; Wise Goodluck Datsomor; Regina Folorunsho; Jerome Fisayo; Richard Crane; Robert Marchant; Judith Montford; Mario Charles Boateng; Maurice Edusei Oti; Margret Ngozi Oguguah; Christopher Gordon (Food Control, 2023)

Polβ/XRCC1 heterodimerization dictates DNA damage recognition and basal Polβ protein levels without interfering with mouse viability or fertility - Christopher A. Koczor; Marlo K. Thompson; Nidhi Sharma; Aishwarya Prakash; Robert W. Sobol (DNA Repair, 2023)

The impacts of a global pandemic on the efficacy and stability of contemporary wildlife conservation: South Africa as a case study - David A. Ehlers Smith; Yvette C. Ehlers Smith; Harriet T. Davies-Mostert; Lindy J. Thompson; Daniel M. Parker; Deon de Villiers; Dean Ricketts; Brent Coverdale; Peter J. Roberts; Christopher Kelly; Duncan N. Macfadyen; Nomthandazo S. Manqele; et al. (Ambio, 2023)
Conservationists speculated on potential benefits to wildlife of lockdown restrictions because of the COVID-19 pandemic but voiced concern that restrictions impeded nature conservation. We assessed the effects of lockdown restrictions on biodiversity conservation in South Africa, a biodiverse country with economic inequality and reliance on wildlife resources. We solicited expert opinion using the IUCN’s Threats Classification Scheme to structure a questionnaire and illustrated responses with individual case studies from government parastatal and non-governmental conservation organisations. The most highly reported threats were biological resource use, residential/commercial developments, invasive species, and human intrusions. The trends reported by 90 survey respondents were supported by case studies using environmental compliance data from parastatal conservation organisations. Lack of tourism revenue and funding were cited as hindrances to conservation. Mechanisms to prevent environmental degradation in the face of global emergencies must be implemented and ‘ring-fenced’ to ensure conservation is not a casualty during future global crises.

Spatial analysis of mercury and stable isotopes in the vulnerable Dusky Grouper Epinephelus marginatus along the Brazilian coast - Mario V. Condini; Christopher R. Malinowski; David J. Hoeinghaus; Brittany L. Harried; Aaron P. Roberts; Brianne K. Soulen; Kathleen J. Roark; Alexis J. Khursigara; Luciano G. Fischer; Bianca Possamai; Maurício Hostim-Silva; Alexandre M. Garcia (Marine Pollution Bulletin, 2023)

An early Miocene (∼20 Ma) paleogeographic reconstruction for paleoclimate modelling - Zhilin He; Zhongshi Zhang; Zhengtang Guo; Christopher Robert Scotese; Chenglong Deng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Laminar Flame Speed modeling for Low Carbon Fuels using methods of Machine Learning - Saeid Shahpouri; Armin Norouzi; Christopher Hayduk; Alexander Fandakov; Reza Rezaei; Charles Robert Koch; Mahdi Shahbakhti (Fuel, 2023)

A 15-year follow-up study of mortality in a pooled cohort of World Trade Center rescue and recovery workers - Jiehui Li; Charles B. Hall; Janette Yung; Rebecca D. Kehm; Rachel Zeig-Owens; Ankura Singh; James E. Cone; Robert M. Brackbill; Mark R. Farfel; Baozhen Qiao; Maria J. Schymura; Moshe Z. Shapiro; et al. (Environmental Research, 2023)

Modifying a pelagic trawl to better retain small Arctic fishes - Alex De Robertis; Robert Levine; Kresimir Williams; Christopher Wilson (Deep Sea Research Part II: Topical Studies in Oceanography, 2023)

Average uranium bedrock concentration in Swedish municipalities predicts male lung cancer incidence rate when adjusted for smoking prevalence: Indication of a cumulative radon induced detriment - Christopher L. Rääf; Martin Tondel; Mats Isaksson; Robert Wålinder (Science of The Total Environment, 2023)

Lava-ice interactions during historical eruptions of Veniaminof Volcano, Alaska and the potential for meltwater floods and lahars - Christopher F. Waythomas; Benjamin R. Edwards; Thomas P. Miller; Robert G. McGimsey (Natural Hazards, 2023)
Veniaminof Volcano on the Alaska Peninsula of southwest Alaska is one of a small group of ice-clad volcanoes globally that erupts lava flows in the presence of glacier ice. Here, we describe the nature of lava-ice-snow interactions that have occurred during historical eruptions of the volcano since 1944. Lava flows with total volumes on the order of 0.006 km 3 have been erupted in 1983–1984, 1993–1994, 2013, and 2018. Smaller amounts of lava (1 × 10 −4 km 3 or less) were generated during eruptions in 1944 and 2021. All known historical eruptions have occurred at a 300-m-high cinder cone (informally named cone A) within the 8 × 10-km-diameter ice-filled caldera that characterizes Veniaminof Volcano. Supraglacial lava flows erupted at cone A, resulted in minor amounts of melting and did not lead to any significant outflows of water in nearby drainages. Subglacial effusion of lava in 1983–1984, 2021 and possibly in 1944 and 1993–1994 resulted in more significant melting including a partially water-filled melt pit, about 0.8 km 2 in area, that developed during the 1983–1984 eruption. The 1983–1984 event created an impression that meltwater floods from Mount Veniaminof’s ice-filled caldera could be significant and hazardous given the large amount of glacier ice resident within the caldera (ice volume about 8 km 3 ). To date, no evidence supporting catastrophic outflow of meltwater from lava-ice interactions at cone A has been found. Analysis of imagery from the 1983–1984 eruption shows that the initial phase erupted englacial lavas that melted ice/snow/firn from below, producing surface subsidence outward from the cone with no discernable surface connection to the summit vent on cone A. This also happened during the 2021 eruption, and possibly during the 1993–1994 eruption although meltwater lakes did not form during these events. Thus, historical eruptions at Veniaminof Volcano appear to have two different modes of effusive eruptive behavior, where lava reaches the ice subglacially from flank vents, or where lava flows are erupted subaerially from vents near the summit of cone A and flow down the cone on to the ice surface. When placed in the context of global lava-ice eruptions, in cases where lava flows melt the ice from the surface downward, the main hazards are from localized phreatic explosions as opposed to potential flood/lahar hazards. However, when lava effusion/emplacement occurs beneath the ice surface, melting is more rapid and can produce lakes whose drainage could plausibly produce localized floods and lahars.

Genomic analyses reveal range‐wide devastation of sea otter populations - Annabel C. Beichman; Pooneh Kalhori; Christopher C. Kyriazis; Amber A. DeVries; Sergio Nigenda‐Morales; Gisela Heckel; Yolanda Schramm; Andrés Moreno‐Estrada; Douglas J. Kennett; Mark Hylkema; James Bodkin; Klaus‐Peter Koepfli; et al. (Molecular Ecology, 2023)
The genetic consequences of species‐wide declines are rarely quantified because the timing and extent of the decline varies across the species’ range. The sea otter ( Enhydra lutris ) is a unique model in this regard. Their dramatic decline from thousands to fewer than 100 individuals per population occurred range‐wide and nearly simultaneously due to the 18th–19th century fur trade. Consequently, each sea otter population represents an independent natural experiment of recovery after extreme population decline. We designed sequence capture probes for 50 Mb of sea otter exonic and neutral genomic regions. We sequenced 107 sea otters from five populations that span the species range to high coverage (18–76×) and three historical Californian samples from ~1500 and ~200 years ago to low coverage (1.5–3.5×). We observe distinct population structure and find that sea otters in California are the last survivors of a divergent lineage isolated for thousands of years and therefore warrant special conservation concern. We detect signals of extreme population decline in every surviving sea otter population and use this demographic history to design forward‐in‐time simulations of coding sequence. Our simulations indicate that this decline could lower the fitness of recovering populations for generations. However, the simulations also demonstrate how historically low effective population sizes prior to the fur trade may have mitigated the effects of population decline on genetic health. Our comprehensive approach shows how demographic inference from genomic data, coupled with simulations, allows assessment of extinction risk and different models of recovery.

Relative Condition Parameters for Fishes of Montana, USA - Robert W. Eckelbecker; Nathaniel M. Heili; Christopher S. Guy; David A. Schmetterling (Fishes, 2022)
Body condition indices are commonly used in the management of fish populations and are a surrogate to physiological attributes such as tissue-energy reserves. Relative condition factor (Kn) describes the condition of species relative to populations in a geographic area. We developed models to allow for the calculation of Kn in Montana, USA by using the weight–length data collected by Montana Fish, Wildlife & Parks. We generated log10weight–log10length relationships to obtain Montana specific parameter estimates for relative condition equations (W′) for 51 species and three subspecies. We developed separate models by water type (e.g., lotic and lentic) and sex for five species due to varying growth based on sexual dimorphism and varying ecosystem types. Relative condition offers the advantage of describing body condition relative to species in Montana, provides a condition index for species that do not have standard-weight models developed for relative weight (Wr), and affords more information for the global database on weight–length relationships of fishes.

Untargeted metabolomics reveals differences between commercial and non-commercial Camellia sinensis cultivars used in black tea production - Christopher Nyarukowa; Mari van Reenen; Robert Koech; Shayne Mason; Zander Lindeque; Samson Kamunya; Richard Mose; Zeno Apostolides (Journal of Plant Biochemistry and Biotechnology, 2022)

Trends in Bark Beetle Impacts in North America During a Period (2000–2020) of Rapid Environmental Change - Christopher J Fettig; Christopher Asaro; John T Nowak; Kevin J Dodds; Kamal J K Gandhi; Jason E Moan; Jeanne Robert (Journal of Forestry, 2022)
Of the more than five hundred and fifty species of North American bark beetles (Coleoptera: Curculionidae, Scolytinae), approximately twenty species occasionally cause large amounts of tree mortality in conifer forests. During 2000–2020, trends in bark beetle impacts changed dramatically across North America compared to those observed during the mid- to late 20th century. We review tools and tactics available for bark beetle suppression and prevention and provide an overview of temporal and spatial trends in bark beetle impacts in North American forests during 2000–2020. Higher impacts were observed for several bark beetle species in western North America accompanied by substantial declines in eastern North America driven by large reductions in southern pine beetle (Dendroctonus frontalis) activity in the southeastern United States. Regional differences likely result from a higher species richness of both bark beetles and their hosts in western North America, stronger direct and indirect effects of climate change (warming and drying) on bark beetles in western North America, and differences in forest composition, management history, and other abiotic stressors and disturbances. Study Implications Compared to the mid- to late 20th century, bark beetles have had increased impacts in western North America and reduced impacts in eastern North America, the latter driven by large reductions in southern pine beetle (Dendroctonus frontalis) activity in the southeastern United States. We review tools and tactics available to foresters and other natural resource managers to reduce the negative impacts of bark beetles on forests. Furthermore, we provide several potential explanations for recent trends in bark beetle impacts between eastern and western North America.

A novel method for identifying coded tags recorded on aquatic acoustic monitoring systems - Christopher D. Lowe; Nicolas J. C. Tregenza; Claudia J. Allen; Georgina E. Blow; Hanna Nuuttila; Chiara M. Bertelli; Anouska F. Mendzil; Thomas Stamp; Emma V. Sheehan; Peter Davies; Jonathan C. D. Gordon; Jonathan D. Bolland; et al. (Environmental Monitoring and Assessment, 2022)
Aquatic biotelemetry increasingly relies on using acoustic transmitters (‘tags’) that enable passive detection of tagged animals using fixed or mobile receivers. Both tracking methods are resource-limited, restricting the spatial area in which movements of highly mobile animals can be measured using proprietary detection systems. Transmissions from tags are recorded by underwater noise monitoring systems designed for other purposes, such as cetacean monitoring devices, which have been widely deployed in the marine environment; however, no tools currently exist to decode these detections, and thus valuable additional information on animal movements may be missed. Here, we describe simple hybrid methods, with potentially wide application, for obtaining information from otherwise unused data sources. The methods were developed using data from moored, acoustic cetacean detectors (C-PODs) and towed passive receiver arrays, often deployed to monitor the vocalisations of cetaceans, but any similarly formatted data source could be used. The method was applied to decode tag detections that were found to have come from two highly mobile fish species, bass ( Dicentrarchus labrax ) and Twaite shad ( Alosa fallax ), that had been tagged in other studies. Decoding results were validated using test tags; range testing data were used to demonstrate the relative efficiency of these receiver methods in detecting tags. This approach broadens the range of equipment from which acoustic tag detections can be decoded. Novel detections derived from the method could add significant value to past and present tracking studies at little additional cost, by providing new insights into the movement of mobile animals at sea.

Predictors of muscle hypertrophy responsiveness to electrically evoked resistance training after spinal cord injury - Ashraf S. Gorgey; Jacob A. Goldsmith; Refka E. Khalil; Xin-hua Liu; Jiangping Pan; Christopher Cardozo; Robert A. Adler (European Journal of Applied Physiology, 2022)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Quantifying spatial extents of artificial versus natural reefs in the seascape - D’amy N. Steward; Avery B. Paxton; Nathan M. Bacheler; Christina M. Schobernd; Keith Mille; Jeffrey Renchen; Zach Harrison; Jordan Byrum; Robert Martore; Cameron Brinton; Kenneth L. Riley; J. Christopher Taylor; et al. (Frontiers in Marine Science, 2022)
With increasing human uses of the ocean, existing seascapes containing natural habitats, such as biogenic reefs or plant-dominated systems, are supplemented by novel, human-made habitats ranging from artificial reefs to energy extraction infrastructure and shoreline installments. Despite the mixture of natural and artificial habitats across seascapes, the distribution and extent of these two types of structured habitats are not well understood but are necessary pieces of information for ocean planning and resource management decisions. Through a case study, we quantified the amount of seafloor in the southeastern US (SEUS; 103,220 km 2 in the Atlantic Ocean; 10 – 200 m depth) covered by artificial reefs and natural reefs. We developed multiple data-driven approaches to quantify the extent of artificial reefs within state-managed artificial reef programs, and then drew from seafloor maps and published geological and predictive seafloor habitat models to develop three estimates of natural reef extent. Comparisons of the extent of natural and artificial reefs revealed that artificial reefs account for substantially less habitat (average of two estimates 3 km 2 ; <0.01% of SEUS) in the region than natural reefs (average of three estimates 2,654 km 2 ; 2.57% of SEUS) and that this pattern holds across finer regional groupings (e.g., states, depth bins). Our overall estimates suggest that artificial reef coverage is several orders of magnitude less than natural reef coverage. While expansive seafloor mapping and characterization efforts are still needed in SEUS waters, our results fill information gaps regarding the extent of artificial and natural reef habitats in the region, providing support for ecosystem-based management, and demonstrating an approach applicable to other regions.

Conspecific cues, not starvation, mediate barren urchin response to predation risk - Christopher J. Knight; Robert P. Dunn; Jeremy D. Long (Oecologia, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

A fly GWAS for purine metabolites identifies human FAM214 homolog medusa, which acts in a conserved manner to enhance hyperuricemia-driven pathologies by modulating purine metabolism and the inflammatory response - Tyler A. U. Hilsabeck; Ru Liu-Bryan; Tracy Guo; Kenneth A. Wilson; Neelanjan Bose; Daniel Raftery; Jennifer N. Beck; Sven Lang; Kelly Jin; Christopher S. Nelson; Tal Oron; Marshall Stoller; et al. (GeroScience, 2022)

Coupled climate response to Atlantic Multidecadal Variability in a multi-model multi-resolution ensemble - Daniel L. R. Hodson; Pierre-Antoine Bretonnière; Christophe Cassou; Paolo Davini; Nicholas P. Klingaman; Katja Lohmann; Jorge Lopez-Parages; Marta Martín-Rey; Marie-Pierre Moine; Paul-Arthur Monerie; Dian A. Putrasahan; Christopher D. Roberts; et al. (Climate Dynamics, 2022)
North Atlantic sea surface temperatures (SSTs) underwent pronounced multidecadal variability during the twentieth and early twenty-first century. We examine the impacts of this Atlantic Multidecadal Variability (AMV), also referred to as the Atlantic Multidecadal Oscillation (AMO), on climate in an ensemble of five coupled climate models at both low and high spatial resolution. We use a SST nudging scheme specified by the Coupled Model Intercomparision Project’s Decadal Climate Prediction Project Component C (CMIP6 DCPP-C) to impose a persistent positive/negative phase of the AMV in the North Atlantic in coupled model simulations; SSTs are free to evolve outside this region. The large-scale seasonal mean response to the positive AMV involves widespread warming over Eurasia and the Americas, with a pattern of cooling over the Pacific Ocean similar to the Pacific Decadal Oscillation (PDO), together with a northward displacement of the inter-tropical convergence zone (ITCZ). The accompanying changes in global atmospheric circulation lead to widespread changes in precipitation. We use Analysis of Variance (ANOVA) to demonstrate that this large-scale climate response is accompanied by significant differences between models in how they respond to the common AMV forcing, particularly in the tropics. These differences may arise from variations in North Atlantic air-sea heat fluxes between models despite a common North Atlantic SST forcing pattern. We cannot detect a widespread effect of increased model horizontal resolution in this climate response, with the exception of the ITCZ, which shifts further northwards in the positive phase of the AMV in the higher resolution configurations.

Correction to: Probing the multimodal fungiform papilla: complex peripheral nerve endings of chorda tympani taste and mechanosensitive fibers before and after Hedgehog pathway inhibition - Christopher R. Donnelly; Archana Kumari; Libo Li; Iva Vesela; Robert M. Bradley; Charlotte M. Mistretta; Brian A. Pierchala (Cell and Tissue Research, 2022)

Bioclimatic context of species' populations determines community stability - Luke Christopher Evans; Yolanda Melero; Reto Schmucki; Philipp H. Boersch‐Supan; Lluís Brotons; Colin Fontaine; Frédéric Jiguet; Mikko Kuussaari; Dario Massimino; Robert A. Robinson; David B. Roy; Oliver Schweiger; et al. (Global Ecology and Biogeography, 2022)
Aim It is important to understand the factors affecting community stability because ecosystem function is increasingly at risk from biodiversity loss. Here, we evaluate how a key factor, the position of local environmental conditions within the thermal range of the species, influences the stability of butterfly communities at a continental scale. Location Spain, UK and Finland. Time period 1999–2017. Major taxa studied Butterflies. Methods We tested the following hypotheses about how species responses to temperature anomalies aggregate to influence stability: Hypothesis 1, species have contrasting responses to local temperature anomalies at opposing edges of their thermal range; hypothesis 2, communities with central thermal range positions have higher community stability; and the impacts of thermal range position on community stability are driven by hypothesis 3, population asynchrony, or hypothesis 4, additive population stability. Data were analysed at 876 sites for 157 species. Results We found some support for hypothesis 1, because there were interactions between thermal range and response to temperature anomalies such that species at different range edges could provide weak compensatory dynamics. However, responses were nonlinear, suggesting strong declines with extreme anomalies, particularly at the hot range edge. Hypothesis 2 was supported in part, because community stability increased with central thermal range positions and declined at the edges, after accounting for species richness and community abundance. Thermal range position was weakly correlated with asynchrony (hypothesis 3) and population stability (hypothesis 4), although species richness and population abundance had larger impacts. Main conclusions Future extreme heat events will be likely to impact species negatively across their thermal range, but might be particularly impactful on populations at the hottest end of the thermal range. Thermal range position influenced community stability because range edge communities were stable. However, the prediction of community stability from thermal range position is challenging because of nonlinear responses to temperature, with small temperature anomalies producing weak compensatory dynamics, but large extreme events synchronizing dynamics.

Evaluating expert‐based habitat suitability information of terrestrial mammals with GPS‐ tracking data - Maarten J. E. Broekman; Jelle P. Hilbers; Mark A. J. Huijbregts; Thomas Mueller; Abdullahi H. Ali; Henrik Andrén; Jeanne Altmann; Malin Aronsson; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; Jerrold L. Belant; et al. (Global Ecology and Biogeography, 2022)
Aim Macroecological studies that require habitat suitability data for many species often derive this information from expert opinion. However, expert‐based information is inherently subjective and thus prone to errors. The increasing availability of GPS tracking data offers opportunities to evaluate and supplement expert‐based information with detailed empirical evidence. Here, we compared expert‐based habitat suitability information from the International Union for Conservation of Nature (IUCN) with habitat suitability information derived from GPS‐tracking data of 1,498 individuals from 49 mammal species. Location Worldwide. Time period 1998–2021. Major taxa studied Forty‐nine terrestrial mammal species. Methods Using GPS data, we estimated two measures of habitat suitability for each individual animal: proportional habitat use (proportion of GPS locations within a habitat type), and selection ratio (habitat use relative to its availability). For each individual we then evaluated whether the GPS‐based habitat suitability measures were in agreement with the IUCN data. To that end, we calculated the probability that the ranking of empirical habitat suitability measures was in agreement with IUCN's classification into suitable, marginal and unsuitable habitat types. Results IUCN habitat suitability data were in accordance with the GPS data (> 95% probability of agreement) for 33 out of 49 species based on proportional habitat use estimates and for 25 out of 49 species based on selection ratios. In addition, 37 and 34 species had a > 50% probability of agreement based on proportional habitat use and selection ratios, respectively. Main conclusions We show how GPS‐tracking data can be used to evaluate IUCN habitat suitability data. Our findings indicate that for the majority of species included in this study, it is appropriate to use IUCN habitat suitability data in macroecological studies. Furthermore, we show that GPS‐tracking data can be used to identify and prioritize species and habitat types for re‐evaluation of IUCN habitat suitability data.

Effect of Aquaculture-Related Diets on the Long-Term Performance and Condition of the Rock Crab, Cancer irroratus - David Drolet; Cyrena Riley; Sonia Robert; Rafael Estrada; Bruno L. Gianasi; Christopher W. McKindsey (Frontiers in Marine Science, 2022)
Shellfish and salmonid aquaculture operations in Eastern Canada attract several mobile epibenthic species as a result of added structural complexity and increased food availability (bivalve fall-off and waste salmonid feed). It is not clear whether the aggregation of predators and scavengers below coastal farms contributes positively or negatively to their population dynamics, due to concerns about the quality of food items found under farms. We conducted an 18-month laboratory study to investigate the effect of diets composed of 1) mixed items, 2) mussels ( Mytilus edulis ), and 3) salmonid feed on the performance and condition of the rock crab, Cancer irroratus . Diet had no impact on crab survival but several negative consequences were observed in crabs fed the salmonid feed diet when compared to the mixed diet: reduced 1) moulting rates during the second growing season, 2) inter-molt growth, 3) gonad and hepatopancreas indices, 4) hemolymph dissolved compounds, 5) hepatopancreatic glycogen, and 6) shell hardness. Crabs fed the mussel diet had similar performance and condition when compared to the mixed diet. Fatty acid composition of muscle, gonad, and hepatopancreas tissues revealed that a salmonid feed diet decreased n3/n6 ratio when compared to a mixed or a mussel diet; those differences were mostly due to increases in the proportions of terrestrial (18:1n9 and 18:2n6) and decreases in proportions of marine essential (20:5n3 and 22:6n3) fatty acids. Together, these results point to a minimal impact of a mussel-only diet on crabs, whereas the salmonid feed diet resulted in negative impacts on condition. Our experimental results explored the consequences of a ‘worst-case scenario’ in which crabs were forced to feed on a single item for a long period of time; the realized impact in field settings will depend on other factors such as consumption of alternate food items underneath a farm, proportion of time spent in farms, and level of overlap between crab habitat and aquaculture facilities.

Spatiotemporal Overlap of Baleen Whales and Krill Fisheries in the Western Antarctic Peninsula Region - Ryan R. Reisinger; Philip N. Trathan; Christopher M. Johnson; Trevor W. Joyce; John W. Durban; Robert L. Pitman; Ari S. Friedlaender (Frontiers in Marine Science, 2022)
In Antarctica, abundant consumers rely on Antarctic krill for food, but krill are also the subject of a commercial fishery. The fishery overlaps in time and space with the foraging areas of these consumers, thus potential competition between krill fisheries and krill consumers is a major management concern. The fishery is managed by the Commission for the Conservation of Antarctic Marine Living Resources with an ecosystem approach, according to which fishing should not interfere with either the population growth of krill, or krill-dependent consumers. Krill catches have become increasingly spatially concentrated in a small number of hotspots, raising concerns about how local depletion of krill impacts consumers. Such concentrated fishing demonstrates that there is a mismatch between the spatial and temporal scale at which krill fisheries are currently managed, and that at which fisheries operate and consumers forage. Information on the seasonal dynamics of predator abundance and their foraging behaviour is fundamental to future precautionary management of the krill fishery. We analysed the spatiotemporal distribution of two major krill consumers – humpback and minke whales – and that of krill fishing, off the Western Antarctic Peninsula. We used whale tracking data (58 humpback whale tracks and 19 minke whale tracks) to develop spatial random forest models predicting the monthly distribution of whale foraging areas from January-July. Using these predictions, we calculated spatiotemporally-explicit geographic overlap between whales and fisheries, the latter represented by krill fishing effort and catch data. Over the krill fishing season, fishing effort and catch hotspots shifted to the southwest, into the Bransfield Strait where effort and catch was highest. Predicted humpback whale foraging areas increased in the Bransfield Strait over the same period, while predicted minke whale foraging areas showed an opposite trend. For both we predicted a whale-fishing interaction hotspot in the Bransfield Strait, strongest in April and May. Our results illustrate the fine spatial scale of likely interactions between baleen whales and the krill fishery, and their concentration over the season, underlining the need for fishery management more closely aligned to the spatiotemporal scale of likely predator-fishery interactions.

Spatial Ecology of Atlantic Halibut across the Northwest Atlantic: A Recovering Species in an Era of Climate Change - Nancy L. Shackell; Jonathan A. D. Fisher; Cornelia E. den Heyer; Daniel R. Hennen; Andrew C. Seitz; Arnault Le Bris; Dominique Robert; Michael E. Kersula; Steven X. Cadrin; Richard S. McBride; Christopher H. McGuire; Tony Kess; et al. (Reviews in Fisheries Science & Aquaculture, 2022)

Relationship between gene expression networks and muscle contractile physiology differences in Anolis lizards - Luke B. Smith; Christopher V. Anderson; Miyuraj H. Hikkaduwa Withangage; Andrew Koch; Thomas J. Roberts; Andrea L. Liebl (Journal of Comparative Physiology B, 2022)

Content-Aware Segmentation of Objects Spanning a Large Size Range: Application to Plankton Images - Thelma Panaïotis; Louis Caray–Counil; Ben Woodward; Moritz S. Schmid; Dominic Daprano; Sheng Tse Tsai; Christopher M. Sullivan; Robert K. Cowen; Jean-Olivier Irisson (Frontiers in Marine Science, 2022)
As the basis of oceanic food webs and a key component of the biological carbon pump, planktonic organisms play major roles in the oceans. Their study benefited from the development of in situ imaging instruments, which provide higher spatio-temporal resolution than previous tools. But these instruments collect huge quantities of images, the vast majority of which are of marine snow particles or imaging artifacts. Among them, the In Situ Ichthyoplankton Imaging System (ISIIS) samples the largest water volumes (> 100 L s -1 ) and thus produces particularly large datasets. To extract manageable amounts of ecological information from in situ images, we propose to focus on planktonic organisms early in the data processing pipeline: at the segmentation stage. We compared three segmentation methods, particularly for smaller targets, in which plankton represents less than 1% of the objects: (i) a traditional thresholding over the background, (ii) an object detector based on maximally stable extremal regions (MSER), and (iii) a content-aware object detector, based on a Convolutional Neural Network (CNN). These methods were assessed on a subset of ISIIS data collected in the Mediterranean Sea, from which a ground truth dataset of > 3,000 manually delineated organisms is extracted. The naive thresholding method captured 97.3% of those but produced ~340,000 segments, 99.1% of which were therefore not plankton (i.e. recall = 97.3%, precision = 0.9%). Combining thresholding with a CNN missed a few more planktonic organisms (recall = 91.8%) but the number of segments decreased 18-fold (precision increased to 16.3%). The MSER detector produced four times fewer segments than thresholding (precision = 3.5%), missed more organisms (recall = 85.4%), but was considerably faster. Because naive thresholding produces ~525,000 objects from 1 minute of ISIIS deployment, the more advanced segmentation methods significantly improve ISIIS data handling and ease the subsequent taxonomic classification of segmented objects. The cost in terms of recall is limited, particularly for the CNN object detector. These approaches are now standard in computer vision and could be applicable to other plankton imaging devices, the majority of which pose a data management problem.

Plant species of the genus Uvaria : ethnobotanical uses, biological activities and phytochemistry - Robert Christopher (Natural Product Research, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Investigating the contribution of white matter hyperintensities and cortical thickness to empathy in neurodegenerative and cerebrovascular diseases - Miracle Ozzoude; Brenda Varriano; Derek Beaton; Joel Ramirez; Melissa F. Holmes; Christopher J. M. Scott; Fuqiang Gao; Kelly M. Sunderland; Paula McLaughlin; Jennifer Rabin; Maged Goubran; Donna Kwan; et al. (GeroScience, 2022)

Long-term Annual Aerial Surveys of Submersed Aquatic Vegetation (SAV) Support Science, Management, and Restoration - Robert J. Orth; William C. Dennison; Cassie Gurbisz; Michael Hannam; Jeni Keisman; J. Brooke Landry; Jonathan S. Lefcheck; Kenneth A. Moore; Rebecca R. Murphy; Christopher J. Patrick; Jeremy Testa; Donald E. Weller; et al. (Estuaries and Coasts, 2022)
Aerial surveys of coastal habitats can uniquely inform the science and management of shallow, coastal zones, and when repeated annually, they reveal changes that are otherwise difficult to assess from ground-based surveys. This paper reviews the utility of a long-term (1984–present) annual aerial monitoring program for submersed aquatic vegetation (SAV) in Chesapeake Bay, its tidal tributaries, and nearby Atlantic coastal bays, USA. We present a series of applications that highlight the program’s importance in assessing anthropogenic impacts, gauging water quality status and trends, establishing and evaluating restoration goals, and understanding the impact of commercial fishing practices on benthic habitats. These examples demonstrate how periodically quantifying coverage of this important foundational habitat answers basic research questions locally, as well as globally, and provides essential information to resource managers. New technologies are enabling more frequent and accurate aerial surveys at greater spatial resolution and lower cost. These advances will support efforts to extend the applications described here to similar issues in other areas.

Unveiling hidden sponge biodiversity within the Hawaiian reef cryptofauna - Jan Vicente; Maryann K. Webb; Gustav Paulay; Wachirawit Rakchai; Molly A. Timmers; Christopher P. Jury; Keisha Bahr; Robert J. Toonen (Coral Reefs, 2022)

Compound urban crises - Linda Westman; James Patterson; Rachel Macrorie; Christopher J. Orr; Catherine M. Ashcraft; Vanesa Castán Broto; Dana Dolan; Mukesh Gupta; Jeroen van der Heijden; Thomas Hickmann; Robert Hobbins; Marielle Papin; et al. (Ambio, 2022)
The crises that cities face—such as climate change, pandemics, economic downturn, and racism—are tightly interlinked and cannot be addressed in isolation. This paper addresses compound urban crises as a unique type of problem, in which discrete solutions that tackle each crisis independently are insufficient. Few scholarly debates address compound urban crises and there is, to date, a lack of interdisciplinary insights to inform urban governance responses. Combining ideas from complex adaptive systems and critical urban studies, we develop a set of boundary concepts (unsettlement, unevenness, and unbounding) to understand the complexities of compound urban crises from an interdisciplinary perspective. We employ these concepts to set a research agenda on compound urban crises, highlighting multiple interconnections between urban politics and global dynamics. We conclude by suggesting how these entry points provide a theoretical anchor to develop practical insights to inform and reform urban governance.

Globally, tree fecundity exceeds productivity gradients - Valentin Journé; Robert Andrus; Marie‐Claire Aravena; Davide Ascoli; Roberta Berretti; Daniel Berveiller; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Rafael Calama; Jesús Julio Camarero; et al. (Ecology Letters, 2022)
Lack of tree fecundity data across climatic gradients precludes the analysis of how seed supply contributes to global variation in forest regeneration and biotic interactions responsible for biodiversity. A global synthesis of raw seedproduction data shows a 250‐fold increase in seed abundance from cold‐dry to warm‐wet climates, driven primarily by a 100‐fold increase in seed production for a given tree size. The modest (threefold) increase in forest productivity across the same climate gradient cannot explain the magnitudes of these trends. The increase in seeds per tree can arise from adaptive evolution driven by intense species interactions or from the direct effects of a warm, moist climate on tree fecundity. Either way, the massive differences in seed supply ramify through food webs potentially explaining a disproportionate role for species interactions in the wet tropics.

Synthesizing Empirical and Modelling Studies to Predict Past and Future Primary Production in the North Sea - Michael A. Spence; Christopher P. Lynam; Robert B. Thorpe; Ryan F. Heneghan; Paul J. Dolder (Frontiers in Marine Science, 2022)
Understanding change at the base of the marine foodwebs is fundamental to understanding how climate change can impact fisheries. However, there is a shortage of empirical measurements of primary productivity, and models estimates often disagree with each other by an order of magnitude or more. In this study we incorporate information from empirical studies and a suite of Earth system models statistically downscaled using an ensemble model to produce estimates of North Sea primary production with robust quantification of uncertainties under two different climate scenarios. The results give a synthesised estimate of primary production that can feed into regional fisheries models. We found that Earth system models describe the dynamics of primary production in the North Sea poorly, and therefore the effects of climate change on future primary production are uncertain. The methods demonstrated here can be applied to other geographical locations and are not limited in application to primary production.

Utilizing Marine Cultural Heritage for the Preservation of Coastal Systems in East Africa - Georgia Holly; Arturo Rey da Silva; Jon Henderson; Caesar Bita; Wes Forsythe; Zacarias Alexandre Ombe; Christopher Poonian; Hayley Roberts (Journal of Marine Science and Engineering, 2022)
This paper presents the key contributions of marine cultural heritage to the survival of coastal ecosystems and the communities that rely on them in East Africa. Marine cultural heritage (MCH) describes the evidence of past human interactions with coastal and marine space, encompassing tangible material culture remains and associated intangible cultural expressions within coastal communities. By incorporating the protection of MCH into local and regional environmental frameworks, we gain an essential indicator to monitor change dynamics in natural habitats, the cumulative impacts of climate change, and the development of social adaptation strategies. An essential aspect of this development is the move away from global sustainability strategies towards community-centric management and stewardship. Such processes utilise a combination of traditional knowledge systems and scientific approaches designed to harness targeted economic, ecological, and social sustainable development. To argue for the incorporation of MCH into local and regional environmental frameworks in the area, this paper presents four case studies from the Rising from the Depths Network, a challenge-led research network focusing on harnessing the potential of MCH to bring sustainable development strategies to East Africa.

Transport Processes in the Gulf of Mexico Along the River-Estuary-Shelf-Ocean Continuum: a Review of Research from the Gulf of Mexico Research Initiative - Dubravko Justić; Villy Kourafalou; Giulio Mariotti; Songjie He; Robert Weisberg; Yannis Androulidakis; Christopher Barker; Annalisa Bracco; Brian Dzwonkowski; Chuanmin Hu; Haosheng Huang; Gregg Jacobs; et al. (Estuaries and Coasts, 2022)
Estuarine and coastal geomorphology, biogeochemistry, water quality, and coastal food webs in river-dominated shelves of the Gulf of Mexico (GoM) are modulated by transport processes associated with river inputs, winds, waves, tides, and deep-ocean/continental shelf interactions. For instance, transport processes control the fate of river-borne sediments, which in turn affect coastal land loss. Similarly, transport of freshwater, nutrients, and carbon control the dynamics of eutrophication, hypoxia, harmful algal blooms, and coastal acidification. Further, freshwater inflow transports pesticides, herbicides, heavy metals, and oil into receiving estuaries and coastal systems. Lastly, transport processes along the continuum from the rivers and estuaries to coastal and shelf areas and adjacent open ocean (abbreviated herein as “river-estuary-shelf-ocean”) regulate the movements of organisms, including the spatial distributions of individuals and the exchange of genetic information between distinct subpopulations. The Gulf of Mexico Research Initiative (GoMRI) provided unprecedented opportunities to study transport processes along the river-estuary-shelf-ocean continuum in the GoM. The understanding of transport at multiple spatial and temporal scales in this topographically and dynamically complex marginal sea was improved, allowing for more accurate forecasting of the fate of oil and other constituents. For this review, we focus on five specific transport themes: (i) wetland, estuary, and shelf exchanges; (ii) river-estuary coupling; (iii) nearshore and inlet processes; (iv) open ocean transport processes; and (v) river-induced fronts and cross-basin transport. We then discuss the relevancy of GoMRI findings on the transport processes for ecological connectivity and oil transport and fate. We also examine the implications of new findings for informing the response to future oil spills, and the management of coastal resources and ecosystems. Lastly, we summarize the research gaps identified in the many studies and offer recommendations for continuing the momentum of the research provided by the GoMRI effort. A number of uncertainties were identified that occurred in multiple settings. These include the quantification of sediment, carbon, dissolved gasses and nutrient fluxes during storms, consistent specification of the various external forcings used in analyses, methods for smooth integration of multiscale advection mechanisms across different flow regimes, dynamic coupling of the atmosphere with sub-mesoscale and mesoscale phenomena, and methods for simulating finer-scale dynamics over long time periods. Addressing these uncertainties would allow the scientific community to be better prepared to predict the fate of hydrocarbons and their impacts to the coastal ocean, rivers, and marshes in the event of another spill in the GoM.

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

The Response of North Sea Ecosystem Functional Groups to Warming and Changes in Fishing - Robert B. Thorpe; Nina L. Arroyo; Georges Safi; Nathalie Niquil; Izaskun Preciado; Michael Heath; Matthew C. Pace; Christopher P. Lynam (Frontiers in Marine Science, 2022)
Achieving Good Environmental Status (GES) requires managing ecosystems subject to a variety of pressures such as climate change, eutrophication, and fishing. However, ecosystem models are generally much better at representing top-down impacts from fishing than bottom-up impacts due to warming or changes in nutrient loading. Bottom-up processes often have to be parameterised with little data or worse still taken as a system input rather than being represented explicitly. In this study we use an end-to-end ecosystem model (StrathE2E2) for the North Sea with 18 broad functional groups, five resource pools, and representations of feeding, metabolism, reproduction, active migrations, advection, and mixing. Environmental driving data include temperature, irradiance, hydrodynamics, and nutrient inputs from rivers, atmosphere, and ocean boundaries, so the model is designed to evaluate rigorously top-down and bottom-up impacts and is ideal for looking at possible changes in energy flows and “big picture” ecosystem function. In this study we considered the impacts of warming (2 and 4°C) and various levels of fishing, by demersal and pelagic fleets, on the structure and function of the foodweb. A key aim is to demonstrate whether monitoring of broad ecosystem groups could assist in deciding whether GES was being achieved. We found that warming raised primary productivity and increased the size (total biomass) of the ecosystem. Warming raised metabolic demands on omnivorous zooplankton and reduced their abundance, thus favouring benthivorous and piscivorous demersal fish at the expense of planktivorous pelagic fish but otherwise had modest effects on energy pathways and top predators, whereas changes in fishing patterns could materially alter foodweb function and the relative outcomes for top predators. We suggest that GES should be defined in terms of an unfished state and that abundances of broad groupings and the balance between them can help to assess whether indicator outcomes were consistent with GES. Our findings underwrite the need for an ecosystem approach for the management of human activities supported by relevant monitoring. We also highlight the need to improve our basic understanding of bottom-up processes, improve their representation within models, and ensure that our ecosystem models can capture growth limitation by nitrogen and other elements, and not just food/energy uptake.

Genetic analysis of sucrose concentration in soybean seeds using a historical soybean genomic panel - Alexandra Ficht; Robert Bruce; Davoud Torkamaneh; Christopher M. Grainger; Milad Eskandari; Istvan Rajcan (Theoretical and Applied Genetics, 2022)

Sea Ice and Substratum Shape Extensive Kelp Forests in the Canadian Arctic - Karen Filbee-Dexter; Kathleen A. MacGregor; Camille Lavoie; Ignacio Garrido; Jesica Goldsmit; Laura Castro de la Guardia; Kimberly L. Howland; Ladd E. Johnson; Brenda Konar; Christopher W. McKindsey; Christopher J. Mundy; Robert W. Schlegel; et al. (Frontiers in Marine Science, 2022)
The coastal zone of the Canadian Arctic represents 10% of the world’s coastline and is one of the most rapidly changing marine regions on the planet. To predict the consequences of these environmental changes, a better understanding of how environmental gradients shape coastal habitat structure in this area is required. We quantified the abundance and diversity of canopy forming seaweeds throughout the nearshore zone (5–15 m) of the Eastern Canadian Arctic using diving surveys and benthic collections at 55 sites distributed over 3,000 km of coastline. Kelp forests were found throughout, covering on average 40.4% (±29.9 SD) of the seafloor across all sites and depths, despite thick sea ice and scarce hard substrata in some areas. Total standing macroalgal biomass ranged from 0 to 32 kg m –2 wet weight and averaged 3.7 kg m –2 (±0.6 SD) across all sites and depths. Kelps were less abundant at depths of 5 m compared to 10 or 15 m and distinct regional assemblages were related to sea ice cover, substratum type, and nutrient availability. The most common community configuration was a mixed assemblage of four species: Agarum clathratum (14.9% benthic cover ± 12.0 SD), Saccharina latissima (13% ± 14.7 SD), Alaria esculenta (5.4% ± 1.2 SD), and Laminaria solidungula (3.7% ± 4.9 SD). A. clathratum dominated northernmost regions and S. latissima and L. solidungula occurred at high abundance in regions with more open water days. In southeastern areas along the coast of northern Labrador, the coastal zone was mainly sea urchin barrens, with little vegetation. We found positive relationships between open water days (days without sea ice) and kelp biomass and seaweed diversity, suggesting kelp biomass could increase, and the species composition of kelp forests could shift, as sea ice diminishes in some areas of the Eastern Canadian Arctic. Our findings demonstrate the high potential productivity of this extensive coastal zone and highlight the need to better understand the ecology of this system and the services it provides.

Supplementing the Forest Health National Aerial Survey Program with Remote Sensing during the COVID-19 Pandemic: Lessons Learned from a Collaborative Approach - Ryan P Hanavan; Aaron G Kamoske; Abigail N Schaaf; Tom Eager; Haans Fisk; Jim Ellenwood; Kayanna Warren; Christopher Asaro; Brian Vanderbilt; Karen Hutten; Lila Leatherman; Mark Finco; et al. (Journal of Forestry, 2022)
The COVID-19 pandemic has created unprecedented challenges in the way the USDA Forest Service conducts business. Standard data collection methods were immediately challenged due to travel restrictions and due to uncertainty regarding when it would be safe to return to a “business as usual” approach. These challenges were met with an inspiring collaboration between forest health specialists directly involved in the annual Aerial Detection Survey (ADS) program and remote sensing specialists from the Forest Service and academia. This group worked together to generate informative training materials, new workflows, and weekly help sessions to directly address problems that arose during this capacity building exercise. Small ad hoc teams were created to identify regionally specific program resources to enhance remote sensing utilization while supplementing information gaps where aerial detection surveys were either limited or not possible. The lessons learned from this challenge provide an opportunity to continue the exploration of combining ADS, remote sensing, and field data to deliver comprehensive information for managing the nation’s forests, while applying what is working and learning and growing from both successes and limitations.

Aortic haemodynamics: the effects of habitual endurance exercise, age and muscle sympathetic vasomotor outflow in healthy men - Denis J. Wakeham; Tony G. Dawkins; Rachel N. Lord; Jack S. Talbot; Freya M. Lodge; Bryony A. Curry; Lydia L. Simpson; Christopher J. A. Pugh; Robert E. Shave; Jonathan P. Moore (European Journal of Applied Physiology, 2022)
Purpose We determined the effect of habitual endurance exercise and age on aortic pulse wave velocity (aPWV), augmentation pressure (AP) and systolic blood pressure (aSBP), with statistical adjustments of aPWV and AP for heart rate and aortic mean arterial pressure, when appropriate. Furthermore, we assessed whether muscle sympathetic nerve activity (MSNA) correlates with AP in young and middle-aged men. Methods Aortic PWV, AP, aortic blood pressure (applanation tonometry; SphygmoCor) and MSNA (peroneal microneurography) were recorded in 46 normotensive men who were either young or middle-aged and endurance-trained runners or recreationally active nonrunners (10 nonrunners and 13 runners within each age-group). Between-group differences and relationships between variables were assessed via ANOVA/ANCOVA and Pearson product-moment correlation coefficients, respectively. Results Adjusted aPWV and adjusted AP were similar between runners and nonrunners in both age groups (all, P > 0.05), but higher with age (all, P < 0.001), with a greater effect size for the age-related difference in AP in runners (Hedges’ g , 3.6 vs 2.6). aSBP was lower in young ( P = 0.009; g = 2.6), but not middle-aged ( P = 0.341; g = 1.1), runners compared to nonrunners. MSNA burst frequency did not correlate with AP in either age group (young: r = 0.00, P = 0.994; middle-aged: r = − 0.11, P = 0.604). Conclusion There is an age-dependent effect of habitual exercise on aortic haemodynamics, with lower aSBP in young runners compared to nonrunners only. Statistical adjustment of aPWV and AP markedly influenced the outcomes of this study, highlighting the importance of performing these analyses. Further, peripheral sympathetic vasomotor outflow and AP were not correlated in young or middle-aged normotensive men.

Many cameras make light work: opportunistic photographs of rare species in iNaturalist complement structured surveys of reef fish to better understand species richness - Christopher J. Roberts; Adriana Vergés; Corey T. Callaghan; Alistair G. B. Poore (Biodiversity and Conservation, 2022)
Citizen science is on the rise, with growing numbers of initiatives, participants and increasing interest from the broader scientific community. iNaturalist is an example of a successful citizen science platform that enables users to opportunistically capture and share biodiversity observations. Understanding how data from such opportunistic citizen science platforms compare with and complement data from structured surveys will improve their use in future biodiversity research. We compared the opportunistic fish photographs from iNaturalist to those obtained from structured surveys at eight study reefs in Sydney, Australia over twelve years. iNaturalist recorded 1.2 to 5.5 times more fish species than structured surveys resulting in significantly greater annual species richness at half of the reefs, with the remainder showing no significant difference. iNaturalist likely recorded more species due to having simple methods, which allowed for broad participation with substantially more iNaturalist observation events (e.g., dives) than structured surveys over the same period. These results demonstrate the value of opportunistic citizen science platforms for documenting fish species richness, particularly where access and use of the marine environment is common and communities have the time and resources for expensive recreational activities (i.e., underwater photography). The datasets also recorded different species composition with iNaturalist recording many rare, less abundant, or cryptic species while the structured surveys captured many common and abundant species. These results suggest that integrating data from both opportunistic and structured data sources is likely to have the best outcome for future biodiversity monitoring and conservation activities.

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Probing the multimodal fungiform papilla: complex peripheral nerve endings of chorda tympani taste and mechanosensitive fibers before and after Hedgehog pathway inhibition - Christopher R. Donnelly; Archana Kumari; Libo Li; Iva Vesela; Robert M. Bradley; Charlotte M. Mistretta; Brian A. Pierchala (Cell and Tissue Research, 2022)
The fungiform papilla (FP) is a gustatory and somatosensory structure incorporating chorda tympani (CT) nerve fibers that innervate taste buds (TB) and also contain somatosensory endings for touch and temperature. Hedgehog (HH) pathway inhibition eliminates TB, but CT innervation remains in the FP. Importantly, after HH inhibition, CT neurophysiological responses to taste stimuli are eliminated, but tactile responses remain. To examine CT fibers that respond to tactile stimuli in the absence of TB, we used Phox2b-Cre; Rosa26 LSL−TdTomato reporter mice to selectively label CT fibers with TdTomato. Normally CT fibers project in a compact bundle directly into TB, but after HH pathway inhibition, CT fibers reorganize and expand just under the FP epithelium where TB were. This widened expanse of CT fibers coexpresses Synapsin-1, β-tubulin, S100, and neurofilaments. Further, GAP43 expression in these fibers suggests they are actively remodeling. Interestingly, CT fibers have complex terminals within the apical FP epithelium and in perigemmal locations in the FP apex. These extragemmal fibers remain after HH pathway inhibition. To identify tactile end organs in FP, we used a K20 antibody to label Merkel cells. In control mice, K20 was expressed in TB cells and at the base of epithelial ridges outside of FP. After HH pathway inhibition, K20 + cells remained in epithelial ridges but were eliminated in the apical FP without TB. These data suggest that the complex, extragemmal nerve endings within and disbursed under the apical FP are the mechanosensitive nerve endings of the CT that remain after HH pathway inhibition.

Best Practice Data Standards for Discrete Chemical Oceanographic Observations - Li-Qing Jiang; Denis Pierrot; Rik Wanninkhof; Richard A. Feely; Bronte Tilbrook; Simone Alin; Leticia Barbero; Robert H. Byrne; Brendan R. Carter; Andrew G. Dickson; Jean-Pierre Gattuso; Dana Greeley; et al. (Frontiers in Marine Science, 2022)
Effective data management plays a key role in oceanographic research as cruise-based data, collected from different laboratories and expeditions, are commonly compiled to investigate regional to global oceanographic processes. Here we describe new and updated best practice data standards for discrete chemical oceanographic observations, specifically those dealing with column header abbreviations, quality control flags, missing value indicators, and standardized calculation of certain properties. These data standards have been developed with the goals of improving the current practices of the scientific community and promoting their international usage. These guidelines are intended to standardize data files for data sharing and submission into permanent archives. They will facilitate future quality control and synthesis efforts and lead to better data interpretation. In turn, this will promote research in ocean biogeochemistry, such as studies of carbon cycling and ocean acidification, on regional to global scales. These best practice standards are not mandatory. Agencies, institutes, universities, or research vessels can continue using different data standards if it is important for them to maintain historical consistency. However, it is hoped that they will be adopted as widely as possible to facilitate consistency and to achieve the goals stated above.

A dual compartment cuvette system for correcting scattering in whole-cell absorbance spectroscopy of photosynthetic microorganisms - John R. D. Hervey; Paolo Bombelli; David J. Lea-Smith; Alan K. Hulme; Nathan R. Hulme; Atvinder K. Rullay; Robert Keighley; Christopher J. Howe (Photosynthesis Research, 2022)
Absorption spectroscopy is widely used to determine absorption and transmission spectra of chromophores in solution, in addition to suspensions of particles, including micro-organisms. Light scattering, caused by photons deflected from part or all of the cells or other particles in suspension, results in distortions to the absorption spectra, lost information and poor resolution. A spectrophotometer with an integrating sphere may be used to alleviate this problem. However, these instruments are not universally available in biology laboratories, for reasons such as cost. Here, we describe a novel, rapid, and inexpensive technique that minimises the effect of light scattering when performing whole-cell spectroscopy. This method involves using a custom made dual compartment cuvette containing titanium dioxide in one chamber as a scattering agent. Measurements were conducted of a range of different photosynthetic micro-organisms of varying cell size and morphology, including cyanobacteria, eukaryotic microalgae and a purple non-sulphur bacterium. A concentration of 1 mg ml −1 titanium dioxide, using a spectrophotometer with a slit width of 5 nm, produced spectra for cyanobacteria and microalgae similar (1–4% difference) to those obtained using an integrating sphere. The spectrum > 520 nm was similar to that with an integrating sphere with the purple non-sulphur bacterium. This system produced superior results to those obtained using a recently reported method, the application of the diffusing agent, Scotch™ Magic tape, to the side of the cuvette. The protocol can be completed in an equivalent period of time to standard whole-cell absorbance spectroscopy techniques, and is, in principle, suitable for any dual-beam spectrophotometer.

Opening Doors to Training Medical Toxicology Fellows from All Residency Backgrounds - Louise Kao; Michele Burns; Christine Murphy; Evan Schwarz; Steve Aks; Kavita Babu; Gillian Beauchamp; Rana Biary; Michele Burns; Nathan Charlton; Cathleen Clancy; Jonathan Ford; et al. (Journal of Medical Toxicology, 2022)

Correction to: Deep mixed ocean volume in the Labrador Sea in HighResMIP models - Torben Koenigk; Ramon Fuentes-Franco; Virna L. Meccia; Oliver Gutjahr; Laura C. Jackson; Adrian L. New; Pablo Ortega; Christopher D. Roberts; Malcolm J. Roberts; Thomas Arsouze; Doroteaciro Iovino; Marie-Pierre Moine; et al. (Climate Dynamics, 2022)

Early musical training shapes cortico-cerebellar structural covariation - Joseph J. Shenker; Christopher J. Steele; M. Mallar Chakravarty; Robert J. Zatorre; Virginia B. Penhune (Brain Structure and Function, 2022)

Warming increased bark beetle‐induced tree mortality by 30% during an extreme drought in California - Zachary J. Robbins; Chonggang Xu; Brian H. Aukema; Polly C. Buotte; Rutuja Chitra‐Tarak; Christopher J. Fettig; Michael L. Goulden; Devin W. Goodsman; Alexander D. Hall; Charles D. Koven; Lara M. Kueppers; Gavin D. Madakumbura; et al. (Global Change Biology, 2022)
Quantifying the responses of forest disturbances to climate warming is critical to our understanding of carbon cycles and energy balances of the Earth system. The impact of warming on bark beetle outbreaks is complex as multiple drivers of these events may respond differently to warming. Using a novel model of bark beetle biology and host tree interactions, we assessed how contemporary warming affected western pine beetle ( Dendroctonus brevicomis ) populations and mortality of its host, ponderosa pine ( Pinus ponderosa ), during an extreme drought in the Sierra Nevada, California, United States. When compared with the field data, our model captured the western pine beetle flight timing and rates of ponderosa pine mortality observed during the drought. In assessing the influence of temperature on western pine beetles, we found that contemporary warming increased the development rate of the western pine beetle and decreased the overwinter mortality rate of western pine beetle larvae leading to increased population growth during periods of lowered tree defense. We attribute a 29.9% (95% CI: 29.4%–30.2%) increase in ponderosa pine mortality during drought directly to increases in western pine beetle voltinism (i.e., associated with increased development rates of western pine beetle) and, to a much lesser extent, reductions in overwintering mortality. These findings, along with other studies, suggest each degree (°C) increase in temperature may have increased the number of ponderosa pine killed by upwards of 35%–40% °C −1 if the effects of compromised tree defenses (15%–20%) and increased western pine beetle populations (20%) are additive. Due to the warming ability to considerably increase mortality through the mechanism of bark beetle populations, models need to consider climate's influence on both host tree stress and the bark beetle population dynamics when determining future levels of tree mortality.

Climate change research and action must look beyond 2100 - Christopher Lyon; Erin E. Saupe; Christopher J. Smith; Daniel J. Hill; Andrew P. Beckerman; Lindsay C. Stringer; Robert Marchant; James McKay; Ariane Burke; Paul O’Higgins; Alexander M. Dunhill; Bethany J. Allen; et al. (Global Change Biology, 2022)
Anthropogenic activity is changing Earth's climate and ecosystems in ways that are potentially dangerous and disruptive to humans. Greenhouse gas concentrations in the atmosphere continue to rise, ensuring that these changes will be felt for centuries beyond 2100, the current benchmark for projection. Estimating the effects of past, current, and potential future emissions to only 2100 is therefore short‐sighted. Critical problems for food production and climate‐forced human migration are projected to arise well before 2100, raising questions regarding the habitability of some regions of the Earth after the turn of the century. To highlight the need for more distant horizon scanning, we model climate change to 2500 under a suite of emission scenarios and quantify associated projections of crop viability and heat stress. Together, our projections show global climate impacts increase significantly after 2100 without rapid mitigation. As a result, we argue that projections of climate and its effects on human well‐being and associated governance and policy must be framed beyond 2100.

Comparison of Machine Learning Approaches for Tsunami Forecasting from Sparse Observations - Christopher M. Liu; Donsub Rim; Robert Baraldi; Randall J. LeVeque (Pure and Applied Geophysics, 2021)

Pilot study to investigate the effect of long-term exposure to high pCO2 on adult cod (Gadus morhua) otolith morphology and calcium carbonate deposition - Clara Coll-Lladó; Felix Mittermayer; Paul Brian Webb; Nicola Allison; Catriona Clemmesen; Martina Stiasny; Christopher Robert Bridges; Gwendolin Göttler; Daniel Garcia de la serrana (Fish Physiology and Biochemistry, 2021)
To date the study of ocean acidification on fish otolith formation has been mainly focused on larval and juvenile stages. In the present pilot study, wild-captured adult Atlantic cod ( Gadus morhua ) were exposed to two different levels of p CO 2, 422µatm (ambient, low p CO 2 ) or 1091µatm (high p CO 2 ), for a period of 30 weeks (from mid-October to early April 2014–2015) in order to study the effects on otolith size, shape and CaCO 3 crystallization amongst other biological parameters. We found that otoliths from cod exposed to high p CO 2 were slightly smaller (− 3.4% in length; − 3.3% in perimeter), rounder (− 2.9% circularity and + 4% roundness) but heavier (+ 5%) than the low p CO 2 group. Interestingly, there were different effects in males and females; for instance, male cods exposed to high p CO 2 exhibited significant changes in circularity (− 3%) and roundness (+ 4%) compared to the low p CO 2 males, but without significant changes on otolith dimensions, while females exposed to high p CO 2 had smaller otoliths as shown for length (− 5.6%), width (− 2%), perimeter (− 3.5%) and area (− 4.8%). Furthermore, while the majority of the otoliths analysed showed normal aragonite deposition, 10% of fish exposed to 1091µatm of p CO 2 had an abnormal accretion of calcite, suggesting a shift on calcium carbonate polymorph crystallization in some individuals under high p CO 2 conditions. Our preliminary results indicate that high levels of p CO 2 in adult Atlantic cod might affect otolith growth in a gender-specific way. Our findings reveal that otoliths from adult cod are affected by ocean acidification, and we believe that the present study will prompt further research into this currently under-explored area.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Global exposure of population and land‐use to meteorological droughts under different warming levels and SSPs : A CORDEX ‐based study - Jonathan Spinoni; Paulo Barbosa; Edoardo Bucchignani; John Cassano; Tereza Cavazos; Alessandro Cescatti; Jens H. Christensen; Ole B. Christensen; Erika Coppola; Jason P. Evans; Giovanni Forzieri; Beate Geyer; et al. (International Journal of Climatology, 2021)
Global warming is likely to cause a progressive drought increase in some regions, but how population and natural resources will be affected is still underexplored. This study focuses on global population, forests, croplands and pastures exposure to meteorological drought hazard in the 21st century, expressed as frequency and severity of drought events. As input, we use a large ensemble of climate simulations from the Coordinated Regional Climate Downscaling Experiment (CORDEX), population projections from the NASA‐SEDAC dataset and land‐use projections from the Land‐Use Harmonization 2 project for 1981–2100. The exposure to drought hazard is presented for five Shared Socioeconomic Pathways (SSP1‐SSP5) at four Global Warming Levels (GWLs: 1.5°C to 4°C). Results show that considering only Standardized Precipitation Index (SPI; based on precipitation), the SSP3 at GWL4 projects the largest fraction of the global population (14%) to experience an increase in drought frequency and severity (versus 1981–2010), with this value increasing to 60% if temperature is considered (indirectly included in the Standardized Precipitation‐Evapotranspiration Index, SPEI). With SPEI, considering the highest GWL for each SSP, 8 (for SSP2, SSP4, SSP5) and 11 (SSP3) billion people, that is, more than 90%, will be affected by at least one unprecedented drought. For SSP5 at GWL4, approximately 2 × 10 6 km 2 of forests and croplands (respectively, 6% and 11%) and 1.5 × 10 6 km 2 of pastures (19%) will be exposed to increased drought frequency and severity according to SPI, but for SPEI this extent will rise to 17 × 10 6 km 2 of forests (49%), 6 × 10 6 km 2 of pastures (78%) and 12 × 10 6 km 2 of croplands (67%), being mid‐latitudes the most affected. The projected likely increase of drought frequency and severity significantly increases population and land‐use exposure to drought, even at low GWLs, thus extensive mitigation and adaptation efforts are needed to avoid the most severe impacts of climate change.

Landscape-Scale Forest Reorganization Following Insect Invasion and Harvest Under Future Climate Change Scenarios - Stacey K. Olson; Erica A. H. Smithwick; Melissa S. Lucash; Robert M. Scheller; Robert E. Nicholas; Kelsey L. Ruckert; Christopher M. Caldwell (Ecosystems, 2021)
Emerald ash borer (EAB; Agrilus planipennis Farimaire) has been found in 35 US states and five Canadian provinces. This invasive beetle is causing widespread mortality to ash trees ( Fraxinus spp.), which are an important timber product and ornamental tree, as well as a cultural resource for some Tribes. The damage will likely continue despite efforts to impede its spread. Further, widespread and rapid ash mortality as a result of EAB is expected to alter forest composition and structure, especially when coupled with the regional effects of climate change in post-ash forests. Thus, we forecasted the long-term effects of EAB-induced ash mortality and preemptive ash harvest (a forest management mitigation strategy) on forested land across a 2-million-hectare region in northern Wisconsin. We used a spatially explicit and spatially interactive forest simulation model, LANDIS-II, to estimate future species dominance and biodiversity assuming continued widespread ash mortality. We ran forest disturbance and succession simulations under historic climate conditions and three downscaled CMIP5 climate change projections representing the upper bound of expected changes in precipitation and temperature. Our results suggest that although ash loss from EAB or harvest resulted in altered biodiversity patterns in some stands, climate change will be the major driver of changes in biodiversity by the end of century, causing increases in the dominance of southern species and homogenization of species composition across the landscape.

Wealth and urbanization shape medium and large terrestrial mammal communities - Seth B. Magle; Mason Fidino; Heather A. Sander; Adam T. Rohnke; Kelli L. Larson; Travis Gallo; Cria A. M. Kay; Elizabeth W. Lehrer; Maureen H. Murray; Solny A. Adalsteinsson; Adam A. Ahlers; Whitney J. B. Anthonysamy; et al. (Global Change Biology, 2021)
Urban biodiversity provides critical ecosystem services and is a key component to environmentally and socially sustainable cities. However, biodiversity varies greatly within and among cities, leading to human communities with changing and unequal experiences with nature. The “luxury effect,” a hypothesis that predicts a positive correlation between wealth, typically measured by per capita income, and species richness may be one indication of these inequities. While the luxury effect is well studied for some taxa, it has rarely been investigated for mammals, which provide unique ecosystem services (e.g., biological pest control) and exhibit significant potential for negative human–wildlife interactions (e.g., nuisances or conflicts). We analyzed a large dataset of mammal detections across 20 North American cities to test whether the luxury effect is consistent for medium‐ to large‐sized terrestrial mammals across diverse urban contexts. Overall, support for the luxury effect, as indicated by per capita income, was inconsistent; we found evidence of a luxury effect in approximately half of our study cities. Species richness was, however, highly and negatively correlated with urban intensity in most cities. We thus suggest that economic factors play an important role in shaping urban mammal communities for some cities and species, but that the strongest driver of urban mammal diversity is urban intensity. To better understand the complexity of urban ecosystems, ecologists and social scientists must consider the social and political factors that drive inequitable human experiences with nature in cities.

Anticipating and Adapting to the Future Impacts of Climate Change on the Health, Security and Welfare of Low Elevation Coastal Zone (LECZ) Communities in Southeastern USA - Thomas Allen; Joshua Behr; Anamaria Bukvic; Ryan S. D. Calder; Kiki Caruson; Charles Connor; Christopher D’Elia; David Dismukes; Robin Ersing; Rima Franklin; Jesse Goldstein; Jonathon Goodall; et al. (Journal of Marine Science and Engineering, 2021)
Low elevation coastal zones (LECZ) are extensive throughout the southeastern United States. LECZ communities are threatened by inundation from sea level rise, storm surge, wetland degradation, land subsidence, and hydrological flooding. Communication among scientists, stakeholders, policy makers and minority and poor residents must improve. We must predict processes spanning the ecological, physical, social, and health sciences. Communities need to address linkages of (1) human and socioeconomic vulnerabilities; (2) public health and safety; (3) economic concerns; (4) land loss; (5) wetland threats; and (6) coastal inundation. Essential capabilities must include a network to assemble and distribute data and model code to assess risk and its causes, support adaptive management, and improve the resiliency of communities. Better communication of information and understanding among residents and officials is essential. Here we review recent background literature on these matters and offer recommendations for integrating natural and social sciences. We advocate for a cyber-network of scientists, modelers, engineers, educators, and stakeholders from academia, federal state and local agencies, non-governmental organizations, residents, and the private sector. Our vision is to enhance future resilience of LECZ communities by offering approaches to mitigate hazards to human health, safety and welfare and reduce impacts to coastal residents and industries.

A new indole alkaloid and other constituents from Monodora minor and Uvaria tanzaniae : their antitrypanosomal and antiplasmodial evaluation - Robert Christopher; Quintino A. Mgani; Stephen S. Nyandoro; Amanda L. Rousseau; Michelle Isaacs; Heinrich C. Hoppe (Natural Product Research, 2021)

Kelp in the Eastern Canadian Arctic: Current and Future Predictions of Habitat Suitability and Cover - Jesica Goldsmit; Robert W. Schlegel; Karen Filbee-Dexter; Kathleen A. MacGregor; Ladd E. Johnson; Christopher J. Mundy; Amanda M. Savoie; Christopher W. McKindsey; Kimberly L. Howland; Philippe Archambault (Frontiers in Marine Science, 2021)
Climate change is transforming marine ecosystems through the expansion and contraction of species’ ranges. Sea ice loss and warming temperatures are expected to expand habitat availability for macroalgae along long stretches of Arctic coastlines. To better understand the current distribution of kelp forests in the Eastern Canadian Arctic, kelps were sampled along the coasts for species identifications and percent cover. The sampling effort was supplemented with occurrence records from global biodiversity databases, searches in the literature, and museum records. Environmental information and occurrence records were used to develop ensemble models for predicting habitat suitability and a Random Forest model to predict kelp cover for the dominant kelp species in the region – Agarum clathratum , Alaria esculenta , and Laminariaceae species ( Laminaria solidungula and Saccharina latissima ). Ice thickness, sea temperature and salinity explained the highest percentage of kelp distribution. Both modeling approaches showed that the current extent of arctic kelps is potentially much greater than the available records suggest. These modeling approaches were projected into the future using predicted environmental data for 2050 and 2100 based on the most extreme emission scenario (RCP 8.5). The models agreed that predicted distribution of kelp in the Eastern Canadian Arctic is likely to expand to more northern locations under future emissions scenarios, with the exception of the endemic arctic kelp L. solidungula , which is more likely to lose a significant proportion of suitable habitat. However, there were differences among species regarding predicted cover for both current and future projections. Notwithstanding model-specific variation, it is evident that kelps are widespread throughout the area and likely contribute significantly to the functioning of current Arctic ecosystems. Our results emphasize the importance of kelp in Arctic ecosystems and the underestimation of their potential distribution there.

Improved Segmentation of the Intracranial and Ventricular Volumes in Populations with Cerebrovascular Lesions and Atrophy Using 3D CNNs - Emmanuel E. Ntiri; Melissa F. Holmes; Parisa M. Forooshani; Joel Ramirez; Fuqiang Gao; Miracle Ozzoude; Sabrina Adamo; Christopher J. M. Scott; Dar Dowlatshahi; Jane M. Lawrence-Dewar; Donna Kwan; Anthony E. Lang; et al. (Neuroinformatics, 2021)

Effect of species, provenance, and coral physiology on the composition of Hawaiian coral-associated microbial communities - James T. Price; Rowan H. McLachlan; Christopher P. Jury; Robert J. Toonen; Michael J. Wilkins; Andréa G. Grottoli (Coral Reefs, 2021)

Environmental gradients drive physiological variation in Hawaiian corals - Rowan H. McLachlan; James T. Price; Agustí Muñoz-Garcia; Noah L. Weisleder; Christopher P. Jury; Robert J. Toonen; Andréa G. Grottoli (Coral Reefs, 2021)

Deep mixed ocean volume in the Labrador Sea in HighResMIP models - Torben Koenigk; Ramon Fuentes-Franco; Virna L. Meccia; Oliver Gutjahr; Laura C. Jackson; Adrian L. New; Pablo Ortega; Christopher D. Roberts; Malcolm J. Roberts; Thomas Arsouze; Doroteaciro Iovino; Marie-Pierre Moine; et al. (Climate Dynamics, 2021)
Simulations from seven global coupled climate models performed at high and standard resolution as part of the high resolution model intercomparison project (HighResMIP) are analyzed to study deep ocean mixing in the Labrador Sea and the impact of increased horizontal resolution. The representation of convection varies strongly among models. Compared to observations from ARGO-floats and the EN4 data set, most models substantially overestimate deep convection in the Labrador Sea. In four out of five models, all four using the NEMO-ocean model, increasing the ocean resolution from 1° to 1/4° leads to increased deep mixing in the Labrador Sea. Increasing the atmospheric resolution has a smaller effect than increasing the ocean resolution. Simulated convection in the Labrador Sea is mainly governed by the release of heat from the ocean to the atmosphere and by the vertical stratification of the water masses in the Labrador Sea in late autumn. Models with stronger sub-polar gyre circulation have generally higher surface salinity in the Labrador Sea and a deeper convection. While the high-resolution models show more realistic ocean stratification in the Labrador Sea than the standard resolution models, they generally overestimate the convection. The results indicate that the representation of sub-grid scale mixing processes might be imperfect in the models and contribute to the biases in deep convection. Since in more than half of the models, the Labrador Sea convection is important for the Atlantic Meridional Overturning Circulation (AMOC), this raises questions about the future behavior of the AMOC in the models.

Biochemical inhibition of acid phosphatase activity in two mountain spruce forest soils - Petr Čapek; Christopher P. Kasanke; Robert Starke; Qian Zhao; Karolina Tahovská (Biology and Fertility of Soils, 2021)

Differential household vulnerability to climatic and non-climatic stressors in semi-arid areas of Mali, West Africa - Alcade C. Segnon; Edmond Totin; Robert B. Zougmoré; Jourdain C. Lokossou; Mary Thompson-Hall; Benjamin O. Ofori; Enoch G. Achigan-Dako; Christopher Gordon (Climate and Development, 2021)

Metals and Metalloids in Feathers of Neotropic Cormorants (Phalacrocorax brasilianus) Nesting in Lake Livingston and Richland Creek, Texas, USA - Miguel A. Mora; Christopher Sandoval; Robert Taylor (Bulletin of Environmental Contamination and Toxicology, 2021)

Benthic iron flux influenced by climate‐sensitive interplay between organic carbon availability and sedimentation rate in Arctic fjords - Lisa C. Herbert; Qingzhi Zhu; Alexander B. Michaud; Katja Laufer‐Meiser; Christopher K. Jones; Natascha Riedinger; Zachery S. Stooksbury; Robert C. Aller; Bo Barker Jørgensen; Laura M. Wehrmann (Limnology and Oceanography, 2021)
Benthic iron (Fe) fluxes from continental shelf sediments are an important source of Fe to the global ocean, yet the magnitude of these fluxes is not well constrained. Processing of Fe in sediments is of particular importance in the Arctic Ocean, which has a large shelf area and Fe limitation of primary productivity. In the Arctic fjords of Svalbard, glacial weathering delivers high volumes of Fe‐rich sediment to the fjord benthos. Benthic redox cycling of Fe proceeds through multiple pathways of reduction (i.e., dissimilatory iron reduction and reduction by hydrogen sulfide) and re‐oxidation. There are few estimates of the magnitude and controlling factors of the benthic Fe flux in Arctic fjords. We collected cores from two Svalbard fjords (Kongsfjorden and Lilliehöökfjorden), measured dissolved Fe 2+ concentrations using a two‐dimensional sensor, and analyzed iron, manganese, carbon, and sulfur species to study benthic Fe fluxes. Benthic fluxes of Fe 2+ vary throughout the fjords, with a “sweet spot” mid‐fjord controlled by the availability of organic carbon linked to sedimentation rates. The flux is also impacted by fjord circulation and sea ice cover, which influence overall mineralization rates in the sediment. Due to ongoing Arctic warming, we predict an increase in the benthic Fe 2+ flux with reduced sea ice cover in some fjords and a decrease in the Fe 2+ flux with the retreat of tidewater glaciers in other regions. Decreasing benthic Fe 2+ fluxes in fjords may exacerbate Fe limitation of primary productivity in the Arctic Ocean.

Resource availability and heterogeneity shape the self‐organisation of regular spatial patterning - Jessica A. Castillo Vardaro; Juan A. Bonachela; Christopher C. M. Baker; Malin L. Pinsky; Daniel F. Doak; Robert M. Pringle; Corina E. Tarnita (Ecology Letters, 2021)
Explaining large‐scale ordered patterns and their effects on ecosystem functioning is a fundamental and controversial challenge in ecology. Here, we coupled empirical and theoretical approaches to explore how competition and spatial heterogeneity govern the regularity of colony dispersion in fungus‐farming termites. Individuals from different colonies fought fiercely, and inter‐nest distances were greater when nests were large and resources scarce—as expected if competition is strong, large colonies require more resources and foraging area scales with resource availability. Building these principles into a model of inter‐colony competition showed that highly ordered patterns emerged under high resource availability and low resource heterogeneity. Analysis of this dynamical model provided novel insights into the mechanisms that modulate pattern regularity and the emergent effects of these patterns on system‐wide productivity. Our results show how environmental context shapes pattern formation by social‐insect ecosystem engineers, which offers one explanation for the marked variability observed across ecosystems.

Effects of ocean acidification on young-of-the-year golden king crab (Lithodes aequispinus) survival and growth - W. Christopher Long; Katherine M. Swiney; Robert J. Foy (Marine Biology, 2021)

Opportunities and challenges applying gene editing to specialty crops - Nicholas J. Bate; Christopher D. Dardick; Ruud A. de Maagd; Robert W. Williams (In Vitro Cellular & Developmental Biology - Plant, 2021)

Fine root dynamics across pantropical rainforest ecosystems - Walter Huaraca Huasco; Terhi Riutta; Cécile A. J. Girardin; Fernando Hancco Pacha; Beisit L. Puma Vilca; Sam Moore; Sami W. Rifai; Jhon del Aguila‐Pasquel; Alejandro Araujo Murakami; Renata Freitag; Alexandra C. Morel; Sheleme Demissie; et al. (Global Change Biology, 2021)
Fine roots constitute a significant component of the net primary productivity (NPP) of forest ecosystems but are much less studied than aboveground NPP. Comparisons across sites and regions are also hampered by inconsistent methodologies, especially in tropical areas. Here, we present a novel dataset of fine root biomass, productivity, residence time, and allocation in tropical old‐growth rainforest sites worldwide, measured using consistent methods, and examine how these variables are related to consistently determined soil and climatic characteristics. Our pantropical dataset spans intensive monitoring plots in lowland (wet, semi‐deciduous, and deciduous) and montane tropical forests in South America, Africa, and Southeast Asia ( n = 47). Large spatial variation in fine root dynamics was observed across montane and lowland forest types. In lowland forests, we found a strong positive linear relationship between fine root productivity and sand content, this relationship was even stronger when we considered the fractional allocation of total NPP to fine roots, demonstrating that understanding allocation adds explanatory power to understanding fine root productivity and total NPP. Fine root residence time was a function of multiple factors: soil sand content, soil pH, and maximum water deficit, with longest residence times in acidic, sandy, and water‐stressed soils. In tropical montane forests, on the other hand, a different set of relationships prevailed, highlighting the very different nature of montane and lowland forest biomes. Root productivity was a strong positive linear function of mean annual temperature, root residence time was a strong positive function of soil nitrogen content in montane forests, and lastly decreasing soil P content increased allocation of productivity to fine roots. In contrast to the lowlands, environmental conditions were a better predictor for fine root productivity than for fractional allocation of total NPP to fine roots, suggesting that root productivity is a particularly strong driver of NPP allocation in tropical mountain regions.

Sponge–Microbe Interactions on Coral Reefs: Multiple Evolutionary Solutions to a Complex Environment - Christopher J. Freeman; Cole G. Easson; Cara L. Fiore; Robert W. Thacker (Frontiers in Marine Science, 2021)
Marine sponges have been successful in their expansion across diverse ecological niches around the globe. Pioneering work attributed this success to both a well-developed aquiferous system that allowed for efficient filter feeding on suspended organic matter and the presence of microbial symbionts that can supplement host heterotrophic feeding with photosynthate or dissolved organic carbon. We now know that sponge-microbe interactions are host-specific, highly nuanced, and provide diverse nutritional benefits to the host sponge. Despite these advances in the field, many current hypotheses pertaining to the evolution of these interactions are overly generalized; these over-simplifications limit our understanding of the evolutionary processes shaping these symbioses and how they contribute to the ecological success of sponges on modern coral reefs. To highlight the current state of knowledge in this field, we start with seminal papers and review how contemporary work using higher resolution techniques has both complemented and challenged their early hypotheses. We outline different schools of thought by discussing evidence of symbiont contribution to both host ecological divergence and convergence, nutritional specificity and plasticity, and allopatric and sympatric speciation. Based on this synthesis, we conclude that the evolutionary pressures shaping these interactions are complex, with influences from both external (nutrient limitation and competition) and internal (fitness trade-offs and evolutionary constraints) factors. We outline recent controversies pertaining to these evolutionary pressures and place our current understanding of these interactions into a broader ecological and evolutionary framework. Finally, we propose areas for future research that we believe will lead to important new developments in the field.

Correction to: Dimethyl sulfoxide acutely enhances regulated insulin secretion in the MIN6-K8 mouse insulinoma cell line - Christopher M. Carmean; Lidan Zhao; Michael Landeche; Bijoy Chellan; Robert M. Sargis (Histochemistry and Cell Biology, 2021)

Dimethyl sulfoxide acutely enhances regulated insulin secretion in the MIN6-K8 mouse insulinoma cell line - Christopher M. Carmean; Lidan Zhao; Michael Landeche; Bijoy Chellan; Robert M. Sargis (Histochemistry and Cell Biology, 2021)

Tropical cyclone precipitation in the HighResMIP atmosphere-only experiments of the PRIMAVERA Project - Wei Zhang; Gabriele Villarini; Enrico Scoccimarro; Malcolm Roberts; Pier Luigi Vidale; Benoıt Vanniere; Louis-Philippe Caron; Dian Putrasahan; Christopher Roberts; Retish Senan; Marie-Pierre Moine (Climate Dynamics, 2021)

The evolution of the terrestrial‐terminating Irish Sea glacier during the last glaciation - Richard Christopher Chiverrell; Geoff Stephen Powell Thomas; Matthew Burke; Alicia Medialdea; Rachel Smedley; Mark Bateman; Chris Clark; Geoffrey A. T. Duller; Derek Fabel; Geraint Jenkins; Xianjiao Ou; Helen Marie Roberts; et al. (Journal of Quaternary Science, 2021)
Here we reconstruct the last advance to maximum limits and retreat of the Irish Sea Glacier (ISG), the only land‐terminating ice lobe of the western British Irish Ice Sheet. A series of reverse bedrock slopes rendered proglacial lakes endemic, forming time‐transgressive moraine‐ and bedrock‐dammed basins that evolved with ice marginal retreat. Combining, for the first time on glacial sediments, optically stimulated luminescence (OSL) bleaching profiles for cobbles with single grain and small aliquot OSL measurements on sands, has produced a coherent chronology from these heterogeneously bleached samples. This chronology constrains what is globally an early build‐up of ice during late Marine Isotope Stage 3 and Greenland Stadial (GS) 5, with ice margins reaching south Lancashire by 30 ± 1.2 ka, followed by a 120‐km advance at 28.3 ± 1.4 ka reaching its 26.5 ± 1.1 ka maximum extent during GS‐3. Early retreat during GS‐3 reflects piracy of ice sources shared with the Irish‐Sea Ice Stream (ISIS), starving the ISG. With ISG retreat, an opportunistic readvance of Welsh ice during GS‐2 rode over the ISG moraines occupying the space vacated, with ice margins oscillating within a substantial glacial over‐deepening. Our geomorphological chronosequence shows a glacial system forced by climate but mediated by piracy of ice sources shared with the ISIS, changing flow regimes and fronting environments.

How flexible are habitat specialists? Short-term space use in obligate coral-dwelling damselfishes - Robert P. Streit; Christopher R. Hemingson; Graeme S. Cumming; David R. Bellwood (Reviews in Fish Biology and Fisheries, 2021)

Environmental Drivers of Forage Fishes and Benthic Invertebrates at Multiple Spatial Scales in a Large Temperate Estuary - Ryan J. Woodland; Andre Buchheister; Robert J. Latour; Carlos Lozano; Edward Houde; Christopher J. Sweetman; Mary C. Fabrizio; Troy D. Tuckey (Estuaries and Coasts, 2021)

Observing Life in the Sea Using Environmental DNA - Francisco Chavez; Markus Min; Kathleen Pitz; Nathan Truelove; Jacoby Baker; Diana LaScala-Grunewald; Marguerite Blum; Kristine Walz; Charles Nye; Anni Djurhuus; Robert Miller; Kelly Goodwin; et al. (Oceanography, 2021)
The use of environmental DNA (eDNA) for studying the ecology and variability of life in the sea is reviewed here in the context of US interagency Marine Biodiversity Observation Network (MBON) projects. Much of the information in this paper comes from samples collected within US National Marine Sanctuaries. The field of eDNA is relatively new but growing rapidly, and it has the potential to disrupt current paradigms developed on the basis of existing measurement methods. After a general review of the field, we provide specific examples of the type of information that eDNA provides regarding the changing distribution of life in the sea over space (horizontally and vertically) and time. We conclude that eDNA analyses yield results that are similar to those collected using traditional observation methods, are complementary to them, and because of the breadth of information provided, have the potential to improve conservation and management practices. Moreover, through technology development and standardization of methods, eDNA offers a means to scale biological observations globally to a level similar to those currently made for ocean physics and biogeochemistry. This scaling can ultimately result in a far better understanding of global marine biodiversity and contribute to better management and sustainable use of the world ocean. Improved information management systems that track methods and associated metadata, together with international coordination, will be needed to realize a global eDNA observation network.

Isotopic approaches to estimating the contribution of heterotrophic sources to Hawaiian corals - James T. Price; Rowan H. McLachlan; Christopher P. Jury; Robert J. Toonen; Andréa G. Grottoli (Limnology and Oceanography, 2021)
Corals obtain nutrition from the photosynthetic products of their algal endosymbionts and the ingestion of organic material and zooplankton from the water column. Here, we use stable carbon (δ 13 C) and nitrogen (δ 15 N) isotopes to assess the proportionate contribution of photoautotrophic and heterotrophic sources to seven Hawaiian coral species collected from six locations around the island of O‘ahu, Hawaiʻi. We analyzed the δ 13 C and δ 15 N of coral tissues and their algal endosymbionts, as well as that of dissolved inorganic matter, particulate organic matter, and zooplankton from each site. Estimates of heterotrophic contribution varied among coral species and sites. Bayesian mixing models revealed that heterotrophic sources (particulate organic material and zooplankton) contributed the most to Pocillopora acuta and Montipora patula coral tissues at 49.3% and 48.0%, respectively, and the least to Porites lobata at 28.7%, on average. Estimates of heterotrophic contribution based on the difference between δ 13 C of the host and algal endosymbiont (δ 13 C h–e ) and isotopic niche overlap often differed, while estimates based on δ 15 N h–e were slightly more aligned with the estimates produced using Bayesian mixing models. These findings suggest that the utility of each approach may vary with coral health status, regions, and coral species. Overall, we find that the mean heterotrophic contribution to Hawaiian coral tissues ranges from 20% to 50%, suggesting a variety of trophic strategies. However, these findings did not always match past direct measurements of heterotrophic feeding, indicating that heterotrophically acquired nutrition does not necessarily get incorporated into tissues but can be respired or exuded in mucus.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Sex differences in changes of protein synthesis with rapamycin treatment are minimized when metformin is added to rapamycin - Christopher A. Wolff; Marcus M. Lawrence; Hunter Porter; Qian Zhang; Justin J. Reid; Jaime L. Laurin; Robert V. Musci; Melissa A. Linden; Frederick F. Peelor; Jonathan D. Wren; Joseph S. Creery; Kyle J. Cutler; et al. (GeroScience, 2021)

Forest Structural Complexity and Biomass Predict First-Year Carbon Cycling Responses to Disturbance - Christopher M. Gough; Jeff W. Atkins; Ben Bond-Lamberty; Elizabeth A. Agee; Kalyn R. Dorheim; Robert T. Fahey; Maxim S. Grigri; Lisa T. Haber; Kayla C. Mathes; Stephanie C. Pennington; Alexey N. Shiklomanov; Jason M. Tallant (Ecosystems, 2021)

Evaluation of trends in extreme temperatures simulated by HighResMIP models across Europe - Antonello A. Squintu; Gerard van der Schrier; Else van den Besselaar; Eveline van der Linden; Dian Putrasahan; Christopher Roberts; Malcolm Roberts; Enrico Scoccimarro; Retish Senan; Albert Klein Tank (Climate Dynamics, 2021)
Simulation of past climate is an important tool for the validation of climate models. The comparison with observed daily values allows us to assess the reliability of their projections on climatic extremes in a future climate. The frequency and amplitude of extreme events are fundamental aspects that climate simulations need to reproduce as they have high impacts on economy and society. The ability to simulate them will help policy makers in taking better measures to face climate change. This work aims at evaluating how six models within the High Resolution Model Intercomparison Project reproduce the trends on extreme indices as they have been observed over Europe in the 1970–2014 period. Observed values are provided by the new homogenized version of the E-OBS gridded dataset. The comparison is performed through the use of indices based on seasonal averages and on exceedances of percentile-based thresholds, focusing on six subregions. Winter-average minimum temperature is generally underestimated by models (down to − 4 °C difference over Italy and Norway) while simulated trends in seasonal averages and extreme values are found to be too cold on Eastern Europe and too warm on Iberia and Southern Europe (e.g. up to a difference of − 4% per decade on the number of Cold Nights over Spain). On the other hand the models tend to overestimate summer maximum temperatures averages in the Mediterranean Area (up to + 5 °C over the Balkans) and underestimate these at higher latitudes. Iberia, Southern and Eastern Europe are simulated with too low trends in average summer temperatures. The simulated trends are too strong on the North West part and too weak on the South East part of Europe (down to − 3%/decade on the number of Warm Days over Italy and Western Balkans). These results corroborate the findings of previous studies about the underestimation of the warming trends of summer temperatures in Southern Europe, where these are more intense and have more impacts. The high-resolution versions of the models are compared to their lower-resolution counterparts, similar to those used in the CMIP5, showing a slight improvement for the simulation of extreme winter minimum temperatures, while no significant progresses have been found for extreme summer maximum temperatures.

Challenges and opportunities for neuroimaging in young patients with traumatic brain injury: a coordinated effort towards advancing discovery from the ENIGMA pediatric moderate/severe TBI group - Emily L Dennis; Karen Caeyenberghs; Robert F Asarnow; Talin Babikian; Brenda Bartnik-Olson; Erin D Bigler; Anthony Figaji; Christopher C Giza; Naomi J Goodrich-Hunsaker; Cooper B Hodges; Kristen R Hoskinson; Marsh Königs; et al. (Brain Imaging and Behavior, 2021)

North Atlantic Basin-Scale Multi-Criteria Assessment Database to Inform Effective Management and Protection of Vulnerable Marine Ecosystems - Telmo Morato; Christopher K. Pham; Laurence Fauconnet; Gerald H. Taranto; Giovanni Chimienti; Erik Cordes; Carlos Dominguez-Carrió; Pablo Durán Muñoz; Hronn Egilsdottir; José-Manuel González-Irusta; Anthony Grehan; Dierk Hebbeln; et al. (Frontiers in Marine Science, 2021)

The Quilt of Sustainable Ocean Governance: Patterns for Practitioners - Robert L. Stephenson; Alistair J. Hobday; Edward H. Allison; Derek Armitage; Kate Brooks; Alida Bundy; Christopher Cvitanovic; Mark Dickey-Collas; Natalia de Miranda Grilli; Catalina Gomez; Astrid Jarre; Laura Kaikkonen; et al. (Frontiers in Marine Science, 2021)
In recent decades, scientists and practitioners have increasingly focused on identifying and codifying the best ways to manage activities in marine systems, leading to the development and implementation of concepts such as the social-ecological systems approach, ecosystem-based management, integrated management, marine spatial planning, participatory co-management, and the precautionary approach. To date, these concepts appear as separate entities: they have parallel literature streams; have been applied most often individually in attempts to improve governance and management; and in many ways, seem to be competing for attention. This patchwork of approaches may be hindering effective ocean governance. We propose that desirable features from these frameworks could be woven together to form the basis of more effective and equitable ocean governance arrangements across contexts, sectors, and scales. This article synthesizes the efforts of an IMBeR (Integrated Marine Biosphere Research Project) conference session and working group, that brought together experts in these diverse concepts with the objective of producing a synthesis of how they could be more effectively integrated for improved ocean sustainability outcomes. We reviewed and compared the concepts in terms of (a) the need to achieve a comprehensive suite of sustainability objectives, (b) similarities and differences in their scope, and (c) their place in practical management, policy and regulation. Achieving greater cross-sectoral integration, or a more holistic perspective on management for sustainability is at the core of each concept. All deal with aspects of governance and most, with improved participation in governance. The major differences in the origin and historical application of each concept are reflected in the degree of implicit or explicit focus given to different objectives of sustainability. Overall, the concepts are especially strong for ecological and institutional or governance considerations, moderately strong for economic aspects, and weakest for the social-cultural pillar of full spectrum sustainability. There is no panacea, and no emergent hierarchy among concepts. Some concepts fit better with top-down legislation-based efforts, others with more bottom-up stakeholder driven efforts. The selection of the core concepts for a situation will depend in a large part on which concepts are specified, or demand focus, in the legal and policy context of the situation (or area) of interest. No matter how influential or dominant a single concept might be, pragmatically, different concepts will be used in different areas, and there may always be the need for a combination of concepts and objectives woven together to achieve a cohesive quilt of sustainability.

Global data set for nitrogen and carbon stable isotopes of tunas - Nathalie Bodin; Heidi Pethybridge; Leanne M. Duffy; Anne Lorrain; Valérie Allain; John M. Logan; Frédéric Ménard; Brittany Graham; C. Anela Choy; Christopher J. Somes; Robert J. Olson; Jock W. Young (Ecology, 2021)
Nitrogen and carbon stable isotope data sets are commonly used to assess complex population to ecosystem responses to natural or anthropogenic changes at regional to global spatial scales, and monthly to decadal timescales. Measured in the tissues of consumers, nitrogen isotopes (δ 15 N) are primarily used to estimate trophic position while carbon isotopes (δ 13 C) describe habitat associations and feeding pathways. Models of both δ 15 N and δ 13 C values and their associated variance can be used to estimate likely dietary contributions and niche width and provide inferences about consumer movement and migration. Stable isotope data have added utility when used in combination with other empirical data sets (e.g., stomach content, movement tracking, bioregionalization, contaminant, or fisheries data) and are increasingly relied upon in food web and ecosystem models. While numerous regional studies publish tables of mean δ 15 N and δ 13 C values, limited individual records have been made available for wider use. Such a deficiency has impeded full utility of the data, which otherwise would facilitate identification of macroscale patterns. The data provided here consist of 4,498 records of individuals of three tuna species, Thunnus alalunga , T. obesus , and T. albacares sampled from all major ocean basins from 2000 to 2015. For each individual tuna, we provide a record of the following: species name, sampling date, sampling location, tuna length, muscle bulk and baseline corrected δ 15 N values, and muscle bulk and, where available, lipid corrected δ 13 C values. We provide these individual records to support comparative studies and more robust modeling projects seeking to improve understanding of complex marine ecosystem dynamics and their responses to a changing environment. There are no copyright restrictions for research and/or teaching purposes. Users are requested to acknowledge their use of the data in publications, research proposals, websites, and other outlets following the citation instructions in Class III, Section B.

Minding the Data-Gap Trap: Exploring Dynamics of Abundant Dolphin Populations Under Uncertainty - Erin Ashe; Rob Williams; Christopher Clark; Christine Erbe; Leah R. Gerber; Ailsa J. Hall; Philip S. Hammond; Robert C. Lacy; Randall Reeves; Nicole L. Vollmer (Frontiers in Marine Science, 2021)
Preventing declines in common species is key to sustaining the structure and function of marine ecosystems. Yet for many common marine mammals, including oceanic dolphins, statistical power to detect declines remains low due to patchy distribution and large variability in group sizes. In this study, population viability analyses (PVA) were used to model the dynamics of four oceanic dolphin populations off the United States West Coast: eastern North Pacific long-beaked common dolphins ( Delphinus delphis capensis ), short-beaked common dolphins ( D. delphis delphis ), Pacific white-sided dolphins ( Lagenorhynchus obliquidens ), and “offshore” common bottlenose dolphins ( Tursiops truncatus ). We calibrated the PVA with life-history tables, studies on proxy species, and stock assessment reports. We explored the sensitivity of populations to demographic variation and projected how they may respond to changes in three sublethal threats (prey limitation, ocean noise, and chemical pollution) and one lethal threat (fisheries bycatch). We found the most serious projected declines in long-beaked common dolphins, which showed the lowest birth rate. Most threat scenarios resulted in declines that would not be detected by existing monitoring programs in the United States, which are among the most data-rich surveys of their kind. The cumulative effects of the three sublethal stressors exceeded the effect of the one lethal stressor (fisheries bycatch). To implement pro-active management and monitoring programs, anticipating which cetaceans are more at risk and which anthropogenic threats could cause declines is paramount. Our study highlights the value of model testing with PVA when monitoring data are poor, thereby identifying priorities for future research, monitoring, and management.

Scenarios for Global Aquaculture and Its Role in Human Nutrition - Jessica A. Gephart; Christopher D. Golden; Frank Asche; Ben Belton; Cecile Brugere; Halley E. Froehlich; Jillian P. Fry; Benjamin S. Halpern; Christina C. Hicks; Robert C. Jones; Dane H. Klinger; David C. Little; et al. (Reviews in Fisheries Science & Aquaculture, 2021)

Molybdenum, phosphorus, and pH do not constrain nitrogen fixation in a tropical forest in the southeastern Amazon - Michelle Y. Wong; Christopher Neill; Roxanne Marino; Divino Silvério; Robert W. Howarth (Ecology, 2021)
High rates of biological nitrogen fixation (BNF) are commonly reported for tropical forests, but most studies have been conducted in regions that receive substantial inputs of molybdenum (Mo) from atmospheric dust and sea‐salt aerosols. Even in these regions, the low availability of Mo can constrain free‐living BNF catalyzed by heterotrophic bacteria and archaea. We hypothesized that in regions where atmospheric inputs of Mo are low and soils are highly weathered, such as the southeastern Amazon, Mo would constrain BNF. We also hypothesized that the high soil acidity, characteristic of the Amazon Basin, would further constrain Mo availability and therefore soil BNF. We conducted two field experiments across the wet and dry seasons, adding Mo, phosphorus (P), and lime alone and in combination to the forest floor in the southeastern Amazon. We sampled soils and litter immediately, and then weeks and months after the applications, and measured Mo and P availability through resin extractions and BNF with the acetylene reduction assay. The experimental additions of Mo and P increased their availability and the lime increased soil pH. While the combination of Mo and P increased BNF at some time points, BNF rates did not increase strongly or consistently across the study as a whole, suggesting that Mo, P, and soil pH are not the dominant controls over BNF. In a separate short‐term laboratory experiment, BNF did not respond strongly to Mo and P even when labile carbon was added. We postulate that high nitrogen (N) availability in this area of the Amazon, as indicated by the stoichiometry of soils and vegetation and the high nitrate soil stocks, likely suppresses BNF at this site. These patterns may also extend across highly weathered soils with high N availability in other topographically stable regions of the tropics.

The First Cut Is the Deepest: Trawl Effects on a Deep-Sea Sponge Ground Are Pronounced Four Years on - Katelin M. Morrison; Heidi Kristina Meyer; Emyr Martyn Roberts; Hans Tore Rapp; Ana Colaço; Christopher Kim Pham (Frontiers in Marine Science, 2020)
Few studies have described the effects of physical disturbance and post-recovery of deep-sea benthic communities. Here, we explore the status of deep-sea sponge ground communities four years after being impacted by an experimental bottom trawl. The diversity and abundance of epibenthic megafauna of two distinct benthic communities in disturbed versus control areas were surveyed using a remotely operated vehicle on the Schulz Bank, Arctic Ocean. Four years after disturbance, megafaunal densities of the shallow (∼600 m depth) and deep (∼1,400 m depth) sites were significantly lower on the disturbed patches compared to the control areas. Multivariate analyses revealed a distinct separation between disturbed and control communities for both sites, with trawling causing 29–58% of the variation. Many epibenthic morphotypes were significantly impacted by the trawl, including ascidians, Geodia parva , Hexactinellida spp., Craniella infrequens , Lissodendoryx complicata , Haliclonia sp. Stylocordyla borealis , Gersemia rubiformis and Actiniaria sp. However, we found some smaller morphospecies to be equally abundant with control transects, including Polymastia thielei , Geodia hentscheli , and Stelletta rhaphidiophora , reflecting lower trawl impact for these morphotypes. Overall, our results suggest that these are fragile ecosystems that require much more time than four years to recover from physical disturbance typical of trawling activities.

The Utility of Satellites and Autonomous Remote Sensing Platforms for Monitoring Offshore Aquaculture Farms: A Case Study for Canopy Forming Kelps - Tom W. Bell; Nick J. Nidzieko; David A. Siegel; Robert J. Miller; Kyle C. Cavanaugh; Norman B. Nelson; Daniel C. Reed; Dmitry Fedorov; Christopher Moran; Jordan N. Snyder; Katherine C. Cavanaugh; Christie E. Yorke; et al. (Frontiers in Marine Science, 2020)
The emerging sector of offshore kelp aquaculture represents an opportunity to produce biofuel feedstock to help meet growing energy demand. Giant kelp represents an attractive aquaculture crop due to its rapid growth and production, however precision farming over large scales is required to make this crop economically viable. These demands necessitate high frequency monitoring to ensure outplant success, maximum production, and optimum quality of harvested biomass, while the long distance from shore and large necessary scales of production makes in person monitoring impractical. Remote sensing offers a practical monitoring solution and nascent imaging technologies could be leveraged to provide daily products of the kelp canopy and subsurface structures over unprecedented spatial scales. Here, we evaluate the efficacy of remote sensing from satellites and aerial and underwater autonomous vehicles as potential monitoring platforms for offshore kelp aquaculture farms. Decadal-scale analyses of the Southern California Bight showed that high offshore summertime cloud cover restricts the ability of satellite sensors to provide high frequency direct monitoring of these farms. By contrast, daily monitoring of offshore farms using sensors mounted to aerial and underwater drones seems promising. Small Unoccupied Aircraft Systems (sUAS) carrying lightweight optical sensors can provide estimates of canopy area, density, and tissue nitrogen content on the time and space scales necessary for observing changes in this highly dynamic species. Underwater color imagery can be rapidly classified using deep learning models to identify kelp outplants on a longline farm and high acoustic returns of kelp pneumatocysts from side scan sonar imagery signal an ability to monitor the subsurface development of kelp fronds. Current sensing technologies can be used to develop additional machine learning and spectral algorithms to monitor outplant health and canopy macromolecular content, however future developments in vehicle and infrastructure technologies are necessary to reduce costs and transcend operational limitations for continuous deployment in an offshore setting.

Open Data, Collaborative Working Platforms, and Interdisciplinary Collaboration: Building an Early Career Scientist Community of Practice to Leverage Ocean Observatories Initiative Data to Address Critical Questions in Marine Science - Robert M. Levine; Kristen E. Fogaren; Johna E. Rudzin; Christopher J. Russoniello; Dax C. Soule; Justine M. Whitaker (Frontiers in Marine Science, 2020)
Ocean observing systems are well-recognized as platforms for long-term monitoring of near-shore and remote locations in the global ocean. High-quality observatory data is freely available and accessible to all members of the global oceanographic community—a democratization of data that is particularly useful for early career scientists (ECS), enabling ECS to conduct research independent of traditional funding models or access to laboratory and field equipment. The concurrent collection of distinct data types with relevance for oceanographic disciplines including physics, chemistry, biology, and geology yields a unique incubator for cutting-edge, timely, interdisciplinary research. These data are both an opportunity and an incentive for ECS to develop the computational skills and collaborative relationships necessary to interpret large data sets. Here, we use observatory data to demonstrate the potential for these interdisciplinary approaches by presenting a case study on the water-column response to anomalous atmospheric events (i.e., major storms) on the shelf of the Mid-Atlantic Bight southwest of Cape Cod, United States. Using data from the Ocean Observatories Initiative (OOI) Pioneer Array, we applied a simple data mining method to identify anomalous atmospheric events over a four-year period. Two closely occurring storm events in late 2018 were then selected to explore the dynamics of water-column response using mooring data from across the array. The comprehensive ECS knowledge base and computational skill sets allowed identification of data issues in the OOI data streams and technologically sound characterization of data from multiple sensor packages to broadly characterize ocean-atmosphere interactions. An ECS-driven approach that emphasizes collaborative and interdisciplinary working practices adds significant value to existing datasets and programs such as OOI and has the potential to produce meaningful scientific advances. Future success in utilizing ocean observatory data requires continued investment in ECS education, collaboration, and research; in turn, the ECS community provides feedback, develops knowledge, and builds new tools to enhance the value of ocean observing systems. These findings present an argument for building a community of practice to augment ECS ocean scientist skills and foster collaborations to extend the context, reach, and societal utility of ocean science.

Not withering on the evolutionary vine: systematic revision of the Brown Vine Snake (Reptilia: Squamata: Oxybelis) from its northern distribution - Robert C. Jadin; Christopher Blair; Sarah A. Orlofske; Michael J. Jowers; Gilson A. Rivas; Laurie J. Vitt; Julie M. Ray; Eric N. Smith; John C. Murphy (Organisms Diversity & Evolution, 2020)

Author Correction: Resolving and Parameterising the Ocean Mesoscale in Earth System Models - Helene T. Hewitt; Malcolm Roberts; Pierre Mathiot; Arne Biastoch; Ed Blockley; Eric P. Chassignet; Baylor Fox-Kemper; Pat Hyder; David P. Marshall; Ekaterina Popova; Anne-Marie Treguier; Laure Zanna; et al. (Current Climate Change Reports, 2020)

Resolving and Parameterising the Ocean Mesoscale in Earth System Models - Helene T. Hewitt; Malcolm Roberts; Pierre Mathiot; Arne Biastoch; Ed Blockley; Eric P. Chassignet; Baylor Fox-Kemper; Pat Hyder; David P. Marshall; Ekaterina Popova; Anne-Marie Treguier; Laure Zanna; et al. (Current Climate Change Reports, 2020)
Purpose of Review Assessment of the impact of ocean resolution in Earth System models on the mean state, variability, and future projections and discussion of prospects for improved parameterisations to represent the ocean mesoscale. Recent Findings The majority of centres participating in CMIP6 employ ocean components with resolutions of about 1 degree in their full Earth System models (eddy-parameterising models). In contrast, there are also models submitted to CMIP6 (both DECK and HighResMIP) that employ ocean components of approximately 1/4 degree and 1/10 degree (eddy-present and eddy-rich models). Evidence to date suggests that whether the ocean mesoscale is explicitly represented or parameterised affects not only the mean state of the ocean but also the climate variability and the future climate response, particularly in terms of the Atlantic meridional overturning circulation (AMOC) and the Southern Ocean. Recent developments in scale-aware parameterisations of the mesoscale are being developed and will be included in future Earth System models. Summary Although the choice of ocean resolution in Earth System models will always be limited by computational considerations, for the foreseeable future, this choice is likely to affect projections of climate variability and change as well as other aspects of the Earth System. Future Earth System models will be able to choose increased ocean resolution and/or improved parameterisation of processes to capture physical processes with greater fidelity.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Dynamics of phosphorus exchange between sediment and water in a gravel‐bed river - Robert J. Wilcock; Richard W. McDowell; John M. Quinn; J. Christopher Rutherford; Roger G. Young; Craig V. Depree (New Zealand Journal of Marine and Freshwater Research, 2020)
Phosphorus (P) stores in gravel‐bed rivers are released for uptake by periphyton when pH levels exceed 8.5. The Tukituki River has low alkalinity water and frequently experiences periphyton blooms, and daytime pH > 9 during summer low‐flows. We measured dissolved reactive P (DRP) and EPC 0 , the water concentration of DRP at which no net release or sorption from the river bed occurs, in sediment samples from the Tukituki River subject to controlled pH levels before (2014) and after (2017) changes to two wastewater discharges that reduced P release to the river by 95%. DRP released from 2014 sediments at pH 8.5–10 were 30 ± 10 mg/m 3 above background (pH 8) whereas those released from 2017 sediments were 5 ± 3 mg/m 3 above background. EPC 0 levels in 2014 and 2017 were 11 ± 6 and 7 ± 2 mg/m 3 , respectively. Field estimates of released DRP calculated from continuous pH and the Redfield equation suggested that most of the readily available DRP released from sediments at elevated pH is derived from material attached to recently deposited sediment. Subsequently, a reduction in wastewater inputs or agricultural runoff should reduce sediment DRP stores, and hence sediment fluxes, within a few years and mitigate periphyton blooms in addition to directly lowering water column concentrations.

Community and structural constraints on the complexity of eastern North American forests - Christopher M. Gough; Jeff W. Atkins; Robert T. Fahey; Brady S. Hardiman; Elizabeth A. LaRue (Global Ecology and Biogeography, 2020)
Aim Canopy structural complexity, which describes the degree of heterogeneity in vegetation density, is strongly tied to a number of ecosystem functions, but the community and structural characteristics that give rise to variation in complexity at site to subcontinental scales are poorly defined. We investigated how woody plant taxonomic and phylogenetic diversity, maximum canopy height, and leaf area index (LAI) relate to canopy rugosity, a measure of canopy structural complexity that is correlated with primary production, light capture, and resource‐use efficiency. Location Our analysis used 122 plots distributed across 10 ecologically and climatically variable forests spanning a > 1,500 km latitudinal gradient within the National Ecological Observatory Network (NEON) of the USA. Time period 2016–2018. Taxa studied Woody plants. Methods We used univariate and multivariate modelling to examine relationships between canopy rugosity, and community and structural characteristics hypothesized to drive site and subcontinental variation in complexity. Results Spatial variation in canopy rugosity within sites and across the subcontinent was strongly and positively related to maximum canopy height ( r 2 = .87 subcontinent‐wide), with the addition of species richness in a multivariate model resolving another 2% of the variation across the subcontinent. Individually, woody plant species richness and phylogenetic diversity ( r 2 = .17 to .44, respectively) and LAI ( r 2 = .16) were weakly to moderately correlated with canopy rugosity at the subcontinental scale, and inconsistently explained spatial variation in canopy rugosity within sites. Main conclusions We conclude that maximum canopy height is a substantially stronger predictor of complexity than diversity or LAI within and across forests of eastern North America, suggesting that canopy volume places a primary constraint on the development of structural complexity. Management and land‐use practices that encourage and sustain tall temperate forest canopies may support greater complexity and associated increases in ecosystem functioning.

Spatial patterning of soil microbial communities created by fungus‐farming termites - Christopher C. M. Baker; Jessica A. Castillo Vardaro; Daniel F. Doak; Johan Pansu; Jérémy Puissant; Robert M. Pringle; Corina E. Tarnita (Molecular Ecology, 2020)
Spatially overdispersed mounds of fungus‐farming termites (Macrotermitinae) are hotspots of nutrient availability and primary productivity in tropical savannas, creating spatial heterogeneity in communities and ecosystem functions. These termites influence the local availability of nutrients in part by redistributing nutrients across the landscape, but the links between termite ecosystem engineering and the soil microbes that are the metabolic agents of nutrient cycling are little understood. We used DNA metabarcoding of soils from Odontotermes montanus mounds to examine the influence of termites on soil microbial communities in a semi‐arid Kenyan savanna. We found that bacterial and fungal communities were compositionally distinct in termite‐mound topsoils relative to the surrounding savanna, and that bacterial communities were more diverse on mounds. The higher microbial alpha and beta diversity associated with mounds created striking spatial patterning in microbial community composition, and boosted landscape‐scale microbial richness and diversity. Selected enzyme assays revealed consistent differences in potential enzymatic activity, suggesting links between termite‐induced heterogeneity in microbial community composition and the spatial distribution of ecosystem functions. We conducted a large‐scale field experiment in which we attempted to simulate termites’ effects on microbes by fertilizing mound‐sized patches; this altered both bacterial and fungal communities, but in a different way than natural mounds. Elevated levels of inorganic nitrogen, phosphorus and potassium may help to explain the distinctive fungal communities in termite‐mound soils, but cannot account for the distinctive bacterial communities associated with mounds.

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

An Application of NEMOVAR for Regional Wave Model Data Assimilation - Andrew N. Saulter; Christopher Bunney; Robert R. King; Jennifer Waters (Frontiers in Marine Science, 2020)

The importance of North Atlantic Ocean transports for seasonal forecasts - Steffen Tietsche; Magdalena Balmaseda; Hao Zuo; Christopher Roberts; Michael Mayer; Laura Ferranti (Climate Dynamics, 2020)
The Atlantic Meridional Overturning Circulation (AMOC) is a main driver for predictability at decadal time scales, but has been largely ignored in the context of seasonal forecasts. Here, we show compelling evidence that AMOC initialization can have a direct and strong impact on seasonal forecasts. Winter reforecasts with SEAS5, the current operational seasonal forecasting system by the European Centre for Medium-Range Weather Forecasts, exhibit errors of sea-surface temperature (SST) in the western part of the North Atlantic Subpolar Gyre that are strongly correlated with decadal variations in the AMOC initial conditions. In the early reforecast period 1981–1996, too warm SST coincide with an overly strong AMOC transporting excessive heat into the region. In the ocean reanalyses providing the forecast initial conditions, excessive heat transport is balanced by additional surface cooling from relaxing towards observed SST, and therefore the fit to observations is acceptable. However, the additional surface cooling contributes to enhanced deep convection and strengthens the AMOC, thereby establishing a feedback loop. In the forecasts, where the SST relaxation is absent, the balance is disrupted, and fast growth of SST errors ensues. The warm SST bias has a strong local impact on surface air temperature, mean sea-level pressure, and precipitation patterns, but remote impact is small. In the late reforecast period 2001–2016, neither the SST in the western North Atlantic nor the AMOC show large biases. The non-stationarity of the bias prevents an effective forecast calibration and causes an apparent loss of skill in the affected region. The case presented here demonstrates the importance of correctly initializing slowly varying aspects of the Earth System such as the AMOC in order to improve forecasts on seasonal and shorter time scales.

Boreal-winter teleconnections with tropical Indo-Pacific rainfall in HighResMIP historical simulations from the PRIMAVERA project - Franco Molteni; Christopher D. Roberts; Retish Senan; Sarah P. E. Keeley; Alessio Bellucci; Susanna Corti; Ramon Fuentes Franco; Rein Haarsma; Xavier Levine; Dian Putrasahan; Malcolm J. Roberts; Laurent Terray (Climate Dynamics, 2020)
This study investigates how teleconnections linking tropical rainfall anomalies and wintertime circulation in the northern extra-tropics are represented in historical simulations for the period 1950–2010 run by partners of the EU-funded PRIMAVERA project, following the HighResMIP protocol of CMIP6. The analysis focusses on teleconnections from the western/central Indian Ocean in mid-winter and from the NINO4 region in both the early and the late part of winter; this choice is justified by a substantial change in the relationship between ENSO and the North Atlantic Oscillation (NAO) in the two parts of the season. Model results for both coupled integrations and runs with prescribed sea-surface temperature (SST) are validated against data from the latest ECMWF 20th-century re-analysis, CERA20C. Simulations from six modelling groups are considered, comparing the impact of increasing atmospheric resolution in runs with prescribed SST, and of moving from uncoupled to coupled simulations in the high-resolution version of each model. Single runs were available for each model configurations at the time of writing, with one centre (ECMWF) also providing a 6-member ensemble. Results from this ensemble are compared with those of a 6-member multi-model ensemble (MME) formed by including one simulation from each model. Using only a single historical simulation from each model configuration, it is difficult to detect a consistent change in the fidelity of model-generated teleconnections when either atmospheric resolution is increased or ocean coupling is introduced. However, when simulations from six different models are pooled together in the MME, some improvements in teleconnection patterns can be seen when moving from uncoupled to coupled simulations. For the ECMWF ensemble, improvements in the coupled simulations are only apparent for the late-winter NINO4 teleconnection. While the Indian Ocean teleconnection and the late-winter NINO4 teleconnection appear equally robust in the re-analysis record, the latter is well simulated in the majority of both uncoupled and coupled runs, while the former is reproduced with (generally) much larger errors, and a high degree of variability between individual models and ensemble members. Most of the simulations with prescribed SST fail to produce a realistic estimate of multi-decadal changes between the first and the second part of the 60-year record. This is (at least partially) due to their inability to simulate an Indian Ocean rainfall change which, in observations, has a zonal gradient out of phase with SST changes. In coupled runs, at least one model run with both realistic teleconnections and a good simulation of the inter-decadal pattern of Indian Ocean rainfall also shows a realistic NAO signal in extratropical multi-decadal variability.

Erweitertes Entwurfskonzept für Entsanderanlagen an Wasserkraftwerken - Christopher Paschmann; Uwe Rieth; Robert Boes; David Vetsch (WASSERWIRTSCHAFT, 2020)

Tree canopy cover constrains the fertility–diversity relationship in plant communities of the southeastern United States - Christopher R. Hakkenberg; Robert K. Peet; Thomas R. Wentworth; Kai Zhu; Michael P. Schafale (Ecology, 2020)
The goal of elucidating the primary mechanisms constraining the assembly and distribution of biodiversity remains among the central unresolved challenges facing the field of ecology. Simulation studies and experimental manipulations have focused on how patterns in community assembly result from bivariate relationships along productivity or environmental gradients. However, the joint influence of multiple resource gradients on the distribution of species richness in natural communities remains understudied. Using data from a large network of multiscale vegetation plots across forests and woodlands of the southeastern United States, we find significant evidence for the scale‐dependent, joint constraints of forest structure and soil resources on the distribution of vascular plant species richness. In addition to their significant partial effects on species richness, understory light levels and soil fertility positively interact, suggesting a trade‐off between the two limiting resources with species richness peaking both in high‐light, low‐fertility conditions as well as low‐light, high‐fertility settings. This finding provides a novel perspective on the biodiversity–productivity relationship that suggests a transition in limiting resources from soil nutrients to light availability when enhanced productivity results in reduced light resources for subordinate individuals. Results likewise have meaningful implications for our understanding of scale‐dependent community assembly processes as size‐asymmetric competition replaces environmental filtering as the primary assembly mechanism structuring temperate forest communities along an increasing soil fertility gradient.

Molecular Mechanisms for Krüppel-Like Factor 13 Actions in Hippocampal Neurons - José Ávila-Mendoza; Arasakumar Subramani; Christopher J. Sifuentes; Robert J. Denver (Molecular Neurobiology, 2020)

The Effect of a Spatial Harvest Closure Area on the Abundance, Movement, and Demographics of an Intensively Fished Population of Dungeness Crabs (Cancer magister) Along Roberts Bank, British Columbia, Canada - Christopher W. Burns; David Robichaud; Elmar Plate; Travis G. Gerwing; Julio Novoa; Yury Bychkov; Robert Bocking (Estuaries and Coasts, 2020)

Nutrient attenuation in a shallow, gravel‐bed river. II. Spatial and temporal changes in nitrogen dynamics and community metabolism - J. Christopher Rutherford; Roger G. Young; John M. Quinn; Robert J. Wilcock (New Zealand Journal of Marine and Freshwater Research, 2020)
Instream processes alter the concentration and bioavailability of nutrients as they are transported downstream. By relating primary production and periphyton composition to changes in nutrient concentration in a gravel‐bed river this study made inferences about recycling and attenuation. Where dissolved inorganic nitrogen (DIN) was abundant, concentrations decreased linearly with distance but by less than required to meet the nitrogen demand of primary production. Where DIN was barely measurable photosynthesis was reduced but only by 50%. We infer that recycling sustained primary production even when DIN concentrations were negligibly small. One implication is that DIN removal underestimates attenuation. Further experimental research on recycling and improved modelling is required to better quantify the length of streams adversely affected by nutrients.

Continental‐scale tree‐ring‐based projection of Douglas‐fir growth: Testing the limits of space‐for‐time substitution - Stefan Klesse; Robert Justin DeRose; Flurin Babst; Bryan A. Black; Leander D. L. Anderegg; Jodi Axelson; Ailene Ettinger; Hardy Griesbauer; Christopher H. Guiterman; Grant Harley; Jill E. Harvey; Yueh‐Hsin Lo; et al. (Global Change Biology, 2020)
A central challenge in global change research is the projection of the future behavior of a system based upon past observations. Tree‐ring data have been used increasingly over the last decade to project tree growth and forest ecosystem vulnerability under future climate conditions. But how can the response of tree growth to past climate variation predict the future, when the future does not look like the past? Space‐for‐time substitution (SFTS) is one way to overcome the problem of extrapolation: the response at a given location in a warmer future is assumed to follow the response at a warmer location today. Here we evaluated an SFTS approach to projecting future growth of Douglas‐fir ( Pseudotsuga menziesii ), a species that occupies an exceptionally large environmental space in North America. We fit a hierarchical mixed‐effects model to capture ring‐width variability in response to spatial and temporal variation in climate. We found opposing gradients for productivity and climate sensitivity with highest growth rates and weakest response to interannual climate variation in the mesic coastal part of Douglas‐fir's range; narrower rings and stronger climate sensitivity occurred across the semi‐arid interior. Ring‐width response to spatial versus temporal temperature variation was opposite in sign, suggesting that spatial variation in productivity, caused by local adaptation and other slow processes, cannot be used to anticipate changes in productivity caused by rapid climate change. We thus substituted only climate sensitivities when projecting future tree growth. Growth declines were projected across much of Douglas‐fir's distribution, with largest relative decreases in the semiarid U.S. Interior West and smallest in the mesic Pacific Northwest. We further highlight the strengths of mixed‐effects modeling for reviving a conceptual cornerstone of dendroecology, Cook's 1987 aggregate growth model, and the great potential to use tree‐ring networks and results as a calibration target for next‐generation vegetation models.

What and where? Predicting invasion hotspots in the Arctic marine realm - Jesica Goldsmit; Christopher W. McKindsey; Robert W. Schlegel; D. Bruce Stewart; Philippe Archambault; Kimberly L. Howland (Global Change Biology, 2020)
The risk of aquatic invasions in the Arctic is expected to increase with climate warming, greater shipping activity and resource exploitation in the region. Planktonic and benthic marine aquatic invasive species (AIS) with the greatest potential for invasion and impact in the Canadian Arctic were identified and the 23 riskiest species were modelled to predict their potential spatial distributions at pan‐Arctic and global scales. Modelling was conducted under present environmental conditions and two intermediate future (2050 and 2100) global warming scenarios. Invasion hotspots—regions of the Arctic where habitat is predicted to be suitable for a high number of potential AIS—were located in Hudson Bay, Northern Grand Banks/Labrador, Chukchi/Eastern Bering seas and Barents/White seas, suggesting that these regions could be more vulnerable to invasions. Globally, both benthic and planktonic organisms showed a future poleward shift in suitable habitat. At a pan‐Arctic scale, all organisms showed suitable habitat gains under future conditions. However, at the global scale, habitat loss was predicted in more tropical regions for some taxa, particularly most planktonic species. Results from the present study can help prioritize management efforts in the face of climate change in the Arctic marine ecosystem. Moreover, this particular approach provides information to identify present and future high‐risk areas for AIS in response to global warming.

Biological Nitrogen Fixation Does Not Replace Nitrogen Losses After Forest Fires in the Southeastern Amazon - Michelle Y. Wong; Christopher Neill; Roxanne Marino; Divino V. Silvério; Paulo M. Brando; Robert W. Howarth (Ecosystems, 2020)

Quantifying storm surge and risk reduction costs: a case study for Lafitte, Louisiana - Christopher G. Siverd; Scott C. Hagen; Matthew V. Bilskie; DeWitt H. Braud; Robert R. Twilley (Climatic Change, 2020)

Modification of the glycolytic pathway in Pyrococcus furiosus and the implications for metabolic engineering - Christopher T. Straub; Gerritt Schut; Jonathan K. Otten; Lisa M. Keller; Michael W. W. Adams; Robert M. Kelly (Extremophiles, 2020)

Habitat suitability modelling to predict the spatial distribution of cold‐water coral communities affected by the Deepwater Horizon oil spill - Samuel E. Georgian; Kody Kramer; Miles Saunders; William Shedd; Harry Roberts; Christopher Lewis; Chuck Fisher; Erik Cordes (Journal of Biogeography, 2020)
Aim The Deepwater Horizon disaster resulted in the largest accidental marine oil spill in history and caused extensive injury to deep‐sea habitats, including cold‐water coral communities dominated by Paramuricea species. One of the primary difficulties in assessing the full extent of the injury to cold‐water coral ecosystems is the extreme paucity of observational data and the subsequent lack of knowledge of their distribution within the affected region. The aim of this study was to use habitat suitability modelling to estimate the number of potentially affected Paramuricea sp. corals across the northern Gulf of Mexico. Location Northern Gulf of Mexico. Taxon Cold‐water corals in the genus Paramuricea. Methods High‐resolution (12.5 m) models were built using the maximum entropy (Maxent) approach using remotely sensed data including seafloor topography, seismic reflectivity, temperature and the amount of productivity exported from the surface. Model outputs were used to estimate the number of potential coral sites in the northern Gulf of Mexico, delineated as areas with both high habitat suitability scores and the presence of hard substrate. The number of coral sites was further adjusted using a ground‐truthing procedure using autonomous underwater vehicle‐transect data. Results Across the entire study area in the northern Gulf of Mexico, there were 558 predicted coral sites, covering an area of 14.2 km 2 . Within a 2,291 km 2 region shown to have been directly affected by the spill and subsequent oil plume, there were 66 predicted coral sites covering an area of 1.2 km 2 with an average of 63 corals per site. Main Conclusions Our results indicate that the magnitude of injury stemming from the spill was likely far higher than previously known, and will help quantify the full extent of the losses incurred as well as prioritize disturbed areas for future research and restoration efforts.

Yellowstone Lake Ecosystem Restoration: A Case Study for Invasive Fish Management - Todd M. Koel; Jeffery L. Arnold; Patricia E. Bigelow; Travis O. Brenden; Jeffery D. Davis; Colleen R. Detjens; Philip D. Doepke; Brian D. Ertel; Hayley C. Glassic; Robert E. Gresswell; Christopher S. Guy; Drew J. MacDonald; et al. (Fishes, 2020)
Invasive predatory lake trout Salvelinus namaycush were discovered in Yellowstone Lake in 1994 and caused a precipitous decrease in abundance of native Yellowstone cutthroat trout Oncorhynchus clarkii bouvieri. Suppression efforts (primarily gillnetting) initiated in 1995 did not curtail lake trout population growth or lakewide expansion. An adaptive management strategy was developed in 2010 that specified desired conditions indicative of ecosystem recovery. Population modeling was used to estimate effects of suppression efforts on the lake trout and establish effort benchmarks to achieve negative population growth (λ 46,800 100-m net nights; this effort level was achieved in 2012 and led to a reduction in lake trout biomass. Total lake trout biomass declined from 432,017 kg in 2012 to 196,675 kg in 2019, primarily because of a 79% reduction in adults. Total abundance declined from 925,208 in 2012 to 673,983 in 2019 but was highly variable because of recruitment of age-2 fish. Overall, 3.35 million lake trout were killed by suppression efforts from 1995 to 2019. Cutthroat trout abundance remained below target levels, but relative condition increased, large individuals (> 400 mm) became more abundant, and individual weights doubled, probably because of reduced density. Continued actions to suppress lake trout will facilitate further recovery of the cutthroat trout population and integrity of the Yellowstone Lake ecosystem.

Haplotype diversity underlying quantitative traits in Canadian soybean breeding germplasm - Robert W. Bruce; Davoud Torkamaneh; Christopher M. Grainger; François Belzile; Milad Eskandari; Istvan Rajcan (Theoretical and Applied Genetics, 2020)

Single-digit cold-induced vasodilation adaptations during an Antarctic expedition - Christopher James Tyler; Robert Lambert; Alexander Kumar; Mike Adrian Stroud; Stephen Sau-Shing Cheung (Polar Biology, 2020)
An increasing number of people are spending time in Polar Regions for work and tourism and this can increase the risk of tissue injuries, e.g. frostbite. The risk would be reduced if beneficial peripheral blood flow adaptions occurred but data regarding the trainability of the cold-induced vasodilation (CIVD) response are equivocal. Five healthy males spent almost 8 months in Antarctica; five of them at a semi-permanent camp (− 44 °C; 2752 m). CIVD tests (30 min index finger immersion into 0 °C water) were performed on the 12th, 39–40th, 67–68th, 179th and 234th days of the expedition in a climate-controlled caboose. Heart rate (HR), thermal sensation of the finger, pain sensation, and mean arterial pressure (MAP) were recorded. Minimum, maximum, and mean finger temperature were greater, onset time was earlier ( r = 0.34), and amplitude was greater ( r = 0.55) on day 234 than day 12 suggesting that adaptation occurred. Time-point data suggested that the adaptations were progressive. Cardiovascular and perceptual data also showed some adaptation. MAP was lower on day 234 than day 12 ( r = 0.47 and r = 0.47) but mean HR was higher ( r = 0.55). Mean and peak thermal sensation ( r = 0.31–0.59; r = 0.31) and perceived pain ( r = 0.58; r = 0.36) both improved over the course of the expedition. Of interest to Polar Region visitors, beneficial peripheral and perceptual adaptations to prolonged Antarctic exposure can occur with 2 h of daily outdoor exposure although the rates at which adaptation occurs differ.

Fungal and chemical diversity in hay and wrapped haylage for equine feed - Birgitte Andersen; Christopher Phippen; Jens C. Frisvad; Sue Emery; Robert A. Eustace (Mycotoxin Research, 2020)

Cancer-associated fibroblast-derived WNT2 increases tumor angiogenesis in colon cancer - Daniela Unterleuthner; Patrick Neuhold; Katharina Schwarz; Lukas Janker; Benjamin Neuditschko; Harini Nivarthi; Ilija Crncec; Nina Kramer; Christine Unger; Markus Hengstschläger; Robert Eferl; Richard Moriggl; et al. (Angiogenesis, 2020)
WNT2 acts as a pro-angiogenic factor in placental vascularization and increases angiogenesis in liver sinusoidal endothelial cells (ECs) and other ECs. Increased WNT2 expression is detectable in many carcinomas and participates in tumor progression. In human colorectal cancer (CRC), WNT2 is selectively elevated in cancer-associated fibroblasts (CAFs), leading to increased invasion and metastasis. However, if there is a role for WNT2 in colon cancer, angiogenesis was not addressed so far. We demonstrate that WNT2 enhances EC migration/invasion, while it induces canonical WNT signaling in a small subset of cells. Knockdown of WNT2 in CAFs significantly reduced angiogenesis in a physiologically relevant assay, which allows precise assessment of key angiogenic properties. In line with these results, expression of WNT2 in otherwise WNT2-devoid skin fibroblasts led to increased angiogenesis. In CRC xenografts, WNT2 overexpression resulted in enhanced vessel density and tumor volume. Moreover, WNT2 expression correlates with vessel markers in human CRC. Secretome profiling of CAFs by mass spectrometry and cytokine arrays revealed that proteins associated with pro-angiogenic functions are elevated by WNT2. These included extracellular matrix molecules, ANG-2, IL-6, G-CSF, and PGF. The latter three increased angiogenesis. Thus, stromal-derived WNT2 elevates angiogenesis in CRC by shifting the balance towards pro-angiogenic signals.

Opportunities for agent‐based modelling in human dimensions of fisheries - Matthew G. Burgess; Ernesto Carrella; Michael Drexler; Robert L. Axtell; Richard M. Bailey; James R. Watson; Reniel B. Cabral; Michaela Clemence; Christopher Costello; Chris Dorsett; Steven D. Gaines; Emily S. Klein; et al. (Fish and Fisheries, 2020)
Models of human dimensions of fisheries are important to understanding and predicting how fishing industries respond to changes in marine ecosystems and management institutions. Advances in computation have made it possible to construct agent‐based models (ABMs)—which explicitly describe the behaviour of individual people, firms or vessels in order to understand and predict their aggregate behaviours. ABMs are widely used for both academic and applied purposes in many settings including finance, urban planning and the military, but are not yet mainstream in fisheries science and management, despite a growing literature. ABMs are well suited to understanding emergent consequences of fisher interactions, heterogeneity and bounded rationality, especially in complex ecological, social and institutional contexts. For these reasons, we argue that ABMs of human behaviour can contribute significantly to human dimensions of fisheries in three areas: (a) understanding interactions between multiple management institutions; (b) incorporating cognitive and behavioural sciences into fisheries science and practice; and (c) understanding and projecting the social consequences of management institutions. We provide simple examples illustrating the potential for ABMs in each of these areas, using conceptual (“toy”) versions of the POSEIDON model. We argue that salient strategic advances in these areas could pave the way for increased tactical use of ABMs in fishery management settings. We review common ABM development and application challenges, with the aim of providing guidance to beginning ABM developers and users studying human dimensions of fisheries.

Adaptive capacity in social–ecological systems: a framework for addressing bark beetle disturbances in natural resource management - Stuart Cottrell; Katherine M. Mattor; Jesse L. Morris; Christopher J. Fettig; Pavlina McGrady; Dorothy Maguire; Patrick M. A. James; Jennifer Clear; Zach Wurtzebach; Yu Wei; Andrea Brunelle; Jessica Western; et al. (Sustainability Science, 2020)

Trends in tuna carbon isotopes suggest global changes in pelagic phytoplankton communities - Anne Lorrain; Heidi Pethybridge; Nicolas Cassar; Aurore Receveur; Valérie Allain; Nathalie Bodin; Laurent Bopp; C. Anela Choy; Leanne Duffy; Brian Fry; Nicolas Goñi; Brittany S. Graham; et al. (Global Change Biology, 2020)
Considerable uncertainty remains over how increasing atmospheric CO 2 and anthropogenic climate changes are affecting open‐ocean marine ecosystems from phytoplankton to top predators. Biological time series data are thus urgently needed for the world's oceans. Here, we use the carbon stable isotope composition of tuna to provide a first insight into the existence of global trends in complex ecosystem dynamics and changes in the oceanic carbon cycle. From 2000 to 2015, considerable declines in δ 13 C values of 0.8‰–2.5‰ were observed across three tuna species sampled globally, with more substantial changes in the Pacific Ocean compared to the Atlantic and Indian Oceans. Tuna recorded not only the Suess effect, that is, fossil fuel‐derived and isotopically light carbon being incorporated into marine ecosystems, but also recorded profound changes at the base of marine food webs. We suggest a global shift in phytoplankton community structure, for example, a reduction in 13 C‐rich phytoplankton such as diatoms, and/or a change in phytoplankton physiology during this period, although this does not rule out other concomitant changes at higher levels in the food webs. Our study establishes tuna δ 13 C values as a candidate essential ocean variable to assess complex ecosystem responses to climate change at regional to global scales and over decadal timescales. Finally, this time series will be invaluable in calibrating and validating global earth system models to project changes in marine biota.

The biology and biotechnology of the genus Caldicellulosiruptor: recent developments in ‘Caldi World’ - Laura L. Lee; James R. Crosby; Gabriel M. Rubinstein; Tunyaboon Laemthong; Ryan G. Bing; Christopher T. Straub; Michael W.W. Adams; Robert M. Kelly (Extremophiles, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Towards a cohesive strategy for the conservation of the United States’ diverse and highly endemic crayfish fauna - Christopher A. Taylor; Robert J. DiStefano; Eric R. Larson; James Stoeckel (Hydrobiologia, 2019)

Coastal Louisiana landscape and storm surge evolution: 1850–2110 - Christopher G. Siverd; Scott C. Hagen; Matthew V. Bilskie; DeWitt H. Braud; R. Hampton Peele; Madeline R. Foster-Martinez; Robert R. Twilley (Climatic Change, 2019)

Assessing North American multimodel ensemble (NMME) seasonal forecast skill to assist in the early warning of anomalous hydrometeorological events over East Africa - Shraddhanand Shukla; Jason Roberts; Andrew Hoell; Christopher C. Funk; Franklin Robertson; Ben Kirtman (Climate Dynamics, 2019)

Urbanization reduces genetic connectivity in bobcats ( Lynx rufus ) at both intra– and interpopulation spatial scales - Christopher P. Kozakiewicz; Christopher P. Burridge; W. Chris Funk; Patricia E. Salerno; Daryl R. Trumbo; Roderick B. Gagne; Erin E. Boydston; Robert N. Fisher; Lisa M. Lyren; Megan K. Jennings; Seth P. D. Riley; Laurel E. K. Serieys; et al. (Molecular Ecology, 2019)
Urbanization is a major factor driving habitat fragmentation and connectivity loss in wildlife. However, the impacts of urbanization on connectivity can vary among species and even populations due to differences in local landscape characteristics, and our ability to detect these relationships may depend on the spatial scale at which they are measured. Bobcats ( Lynx rufus ) are relatively sensitive to urbanization and the status of bobcat populations is an important indicator of connectivity in urban coastal southern California. We genotyped 271 bobcats at 13,520 SNP loci to conduct a replicated landscape resistance analysis in five genetically distinct populations. We tested urban and natural factors potentially influencing individual connectivity in each population separately, as well as study–wide. Overall, landscape genomic effects were most frequently detected at the study–wide spatial scale, with urban land cover (measured as impervious surface) having negative effects and topographic roughness having positive effects on gene flow. The negative effect of urban land cover on connectivity was also evident when populations were analyzed separately despite varying substantially in spatial area and the proportion of urban development, confirming a pervasive impact of urbanization largely independent of spatial scale. The effect of urban development was strongest in one population where stream habitat had been lost to development, suggesting that riparian corridors may help mitigate reduced connectivity in urbanizing areas. Our results demonstrate the importance of replicating landscape genetic analyses across populations and considering how landscape genetic effects may vary with spatial scale and local landscape structure.

Defining a spectrum of integrative trait‐based vegetation canopy structural types - Robert T. Fahey; Jeff W. Atkins; Christopher M. Gough; Brady S. Hardiman; Lucas E. Nave; Jason M. Tallant; Knute J. Nadehoffer; Christoph Vogel; Cynthia M. Scheuermann; Ellen Stuart‐Haëntjens; Lisa T. Haber; Alexander T. Fotis; et al. (Ecology Letters, 2019)
Vegetation canopy structure is a fundamental characteristic of terrestrial ecosystems that defines vegetation types and drives ecosystem functioning. We use the multivariate structural trait composition of vegetation canopies to classify ecosystems within a global canopy structure spectrum. Across the temperate forest sub‐set of this spectrum, we assess gradients in canopy structural traits, characterise canopy structural types (CST) and evaluate drivers and functional consequences of canopy structural variation. We derive CSTs from multivariate canopy structure data, illustrating variation along three primary structural axes and resolution into six largely distinct and functionally relevant CSTs. Our results illustrate that within‐ecosystem successional processes and disturbance legacies can produce variation in canopy structure similar to that associated with sub‐continental variation in forest types and eco‐climatic zones. The potential to classify ecosystems into CSTs based on suites of structural traits represents an important advance in understanding and modelling structure–function relationships in vegetated ecosystems.

Tropical Coastal Wetlands Ameliorate Nitrogen Export During Floods - Maria Fernanda Adame; Melanie E. Roberts; David P. Hamilton; Christopher E. Ndehedehe; Vanessa Reis; Jing Lu; Matthew Griffiths; Graeme Curwen; Mike Ronan (Frontiers in Marine Science, 2019)

Genome-wide genetic diversity is maintained through decades of soybean breeding in Canada - Robert W. Bruce; Davoud Torkamaneh; Christopher Grainger; François Belzile; Milad Eskandari; Istvan Rajcan (Theoretical and Applied Genetics, 2019)

Complete genome sequence of bovine herpesvirus type 1.1 (BoHV-1.1) Los Angeles (LA) strain and its genotypic relationship to BoHV-1.1 Cooper and more recently isolated wild-type field strains - Jean M. d’Offay; Robert W. Fulton; R. Eberle; Edward J. Dubovi; Christopher C. L. Chase (Archives of Virology, 2019)

Impact of model resolution on Arctic sea ice and North Atlantic Ocean heat transport - David Docquier; Jeremy P. Grist; Malcolm J. Roberts; Christopher D. Roberts; Tido Semmler; Leandro Ponsoni; François Massonnet; Dmitry Sidorenko; Dmitry V. Sein; Doroteaciro Iovino; Alessio Bellucci; Thierry Fichefet (Climate Dynamics, 2019)

Observation of irrigation‐induced climate change in the Midwest United States - Mallika A. Nocco; Robert A. Smail; Christopher J. Kucharik (Global Change Biology, 2019)
Irrigated agriculture alters near‐surface temperature and humidity, which may mask global climate change at the regional scale. However, observational studies of irrigation‐induced climate change are lacking in temperate, humid regions throughout North America and Europe. Despite unknown climate impacts, irrigated agriculture is expanding in the Midwest United States, where unconfined aquifers provide groundwater to support crop production on coarse soils. This is the first study in the Midwest United States to observe and quantify differences in regional climate associated with irrigated agricultural conversion from forests and rainfed agriculture. To this end, we established a 60 km transect consisting of 28 stations across varying land uses and monitored surface air temperature and relative humidity for 31 months in the Wisconsin Central Sands region. We used a novel approach to quantify irrigated land use in both space and time with a database containing monthly groundwater withdrawal estimates by parcel for the state of Wisconsin. Irrigated agriculture decreased maximum temperatures and increased minimum temperatures, thus shrinking the diurnal temperature range (DTR) by an average of 3°C. Irrigated agriculture also decreased the vapor pressure deficit (VPD) by an average of 0.10 kPa. Irrigated agriculture significantly decreased evaporative demand for 25% and 66% of study days compared to rainfed agriculture and forest, respectively. Differences in VPD across the land‐use gradient were highest (0.21 kPa) during the peak of the growing season, while differences in DTR were comparable year‐round. Interannual variability in temperature had greater impacts on differences in DTR and VPD across the land‐use gradient than interannual variability in precipitation. These regional climate changes must be considered together with increased greenhouse gas emissions, changes to groundwater quality, and surface water degradation when evaluating the costs and benefits of groundwater‐sourced irrigation expansion in the Midwest United States and similar regions around the world.

A highly resolved food web for insect seed predators in a species‐rich tropical forest - Sofia Gripenberg; Yves Basset; Owen T. Lewis; J. Christopher D. Terry; S. Joseph Wright; Indira Simón; D. Catalina Fernández; Marjorie Cedeño‐Sanchez; Marleny Rivera; Héctor Barrios; John W. Brown; Osvaldo Calderón; et al. (Ecology Letters, 2019)
The top‐down and indirect effects of insects on plant communities depend on patterns of host use, which are often poorly documented, particularly in species‐rich tropical forests. At Barro Colorado Island, Panama, we compiled the first food web quantifying trophic interactions between the majority of co‐occurring woody plant species and their internally feeding insect seed predators. Our study is based on more than 200 000 fruits representing 478 plant species, associated with 369 insect species. Insect host‐specificity was remarkably high: only 20% of seed predator species were associated with more than one plant species, while each tree species experienced seed predation from a median of two insect species. Phylogeny, but not plant traits, explained patterns of seed predator attack. These data suggest that seed predators are unlikely to mediate indirect interactions such as apparent competition between plant species, but are consistent with their proposed contribution to maintaining plant diversity via the Janzen–Connell mechanism.

High rates of primary production in structurally complex forests - Christopher M. Gough; Jeff W. Atkins; Robert T. Fahey; Brady S. Hardiman (Ecology, 2019)
Structure–function relationships are central to many ecological paradigms. Chief among these is the linkage of net primary production ( NPP ) with species diversity and canopy structure. Using the National Ecological Observatory Network ( NEON ) as a subcontinental‐scale research platform, we examined how temperate‐forest NPP relates to several measures of site‐level canopy structure and tree species diversity. Novel multidimensional canopy traits describing structural complexity, most notably canopy rugosity, were more strongly related to site NPP than were species diversity measures and other commonly characterized canopy structural features. The amount of variation in site‐level NPP explained by canopy rugosity alone was 83%, which was substantially greater than that explained individually by vegetation area index (31%) or Shannon's index of species diversity (30%). Forests that were more structurally complex, had higher vegetation‐area indices, or were more diverse absorbed more light and used light more efficiently to power biomass production, but these relationships were most strongly tied to structural complexity. Implications for ecosystem modeling and management are wide ranging, suggesting structural complexity traits are broad, mechanistically robust indicators of NPP that, in application, could improve the prediction and management of temperate forest carbon sequestration.

Conditioned stimuli affect ethanol-seeking by female alcohol-preferring (P) rats: the role of repeated-deprivations, cue-pretreatment, and cue-temporal intervals - Sheketha R. Hauser; Gerald A. Deehan; Christopher P. Knight; Robert A. Waeiss; William A. Truitt; Philip L. Johnson; Richard L. Bell; William J. McBride; Zachary A. Rodd (Psychopharmacology, 2019)

The provision and utility of earth science to decision-makers: synthesis and key findings - Mark C. Quigley; Luke G. Bennetts; Patricia Durance; Petra M. Kuhnert; Mark D. Lindsay; Keith G. Pembleton; Melanie E. Roberts; Christopher J. White (Environment Systems and Decisions, 2019)

The provision and utility of science and uncertainty to decision-makers: earth science case studies - Mark C. Quigley; Luke G. Bennetts; Patricia Durance; Petra M. Kuhnert; Mark D. Lindsay; Keith G. Pembleton; Melanie E. Roberts; Christopher J. White (Environment Systems and Decisions, 2019)

Global in situ Observations of Essential Climate and Ocean Variables at the Air–Sea Interface - Luca R. Centurioni; Jon Turton; Rick Lumpkin; Lancelot Braasch; Gary Brassington; Yi Chao; Etienne Charpentier; Zhaohui Chen; Gary Corlett; Kathleen Dohan; Craig Donlon; Champika Gallage; et al. (Frontiers in Marine Science, 2019)

Targeted Sampling by Autonomous Underwater Vehicles - Yanwu Zhang; John P. Ryan; Brian Kieft; Brett W. Hobson; Robert S. McEwen; Michael A. Godin; Julio B. Harvey; Benedetto Barone; James G. Bellingham; James M. Birch; Christopher A. Scholin; Francisco P. Chavez (Frontiers in Marine Science, 2019)

Investigating the predictability of North Atlantic sea surface height - Robert Fraser; Matthew Palmer; Christopher Roberts; Chris Wilson; Dan Copsey; Laure Zanna (Climate Dynamics, 2019)

Process-oriented assessment of RCA4 regional climate model projections over the Congo Basin under $$1.5 \ ^{° }{\text {C}}$$ 1.5 ∘ C and $$2 \ ^{° }{\text {C}}$$ 2 ∘ C global warming levels: influence of regional moisture fluxes - Alain T. Tamoffo; Wilfran Moufouma-Okia; Alessandro Dosio; Rachel James; Wilfried M. Pokam; Derbetini A. Vondou; Thierry C. Fotso-Nguemo; Guy Merlin Guenang; Pierre H. Kamsu-Tamo; Grigory Nikulin; Georges-Noel Longandjo; Christopher J. Lennard; et al. (Climate Dynamics, 2019)

Variation in egg mass within two Atlantic herring Clupea harengus stocks - Guðmundur J. Óskarsson; Christopher T. Taggart; Robert L. Stephenson (Journal of Fish Biology, 2019)
The main objective of this study was to investigate if egg size (mass) at spawning is invariant for Scotia‐Fundy summer and autumn (SFSH) and Icelandic summer (ISSH) spawning herring Clupea harengus . Oocyte dry mass measurements for SFSH females collected in 2001 and ISSH females collected in 1999 and 2000 showed a large variation. Difference in egg dry mass among fish was found to vary by as much as twofold in each stock. For ISSH, variation in egg mass was also apparent from oocyte volume measurements made jointly with a histological examination of the ovaries. Approximately 20% of the variation in egg mass could be explained by maternal whole‐body mass or total length, indicating that length or age composition in the stocks can potentially influence the recruitment success. This implies that fisheries management strategies should aim to maintain a broad range in age composition.

Effects of historic and projected climate change on the range and impacts of an emerging wildlife disease - Stephen J. Price; William T. M. Leung; Christopher J. Owen; Robert Puschendorf; Chris Sergeant; Andrew A. Cunningham; Francois Balloux; Trenton W. J. Garner; Richard A. Nichols (Global Change Biology, 2019)
The global trend of increasing environmental temperatures is often predicted to result in more severe disease epidemics. However, unambiguous evidence that temperature is a driver of epidemics is largely lacking, because it is demanding to demonstrate its role among the complex interactions between hosts, pathogens, and their shared environment. Here, we apply a three‐pronged approach to understand the effects of temperature on ranavirus epidemics in UK common frogs, combining in vitro, in vivo, and field studies. Each approach suggests that higher temperatures drive increasing severity of epidemics. In wild populations, ranavirosis incidents were more frequent and more severe at higher temperatures, and their frequency increased through a period of historic warming in the 1990s. Laboratory experiments using cell culture and whole animal models showed that higher temperature increased ranavirus propagation, disease incidence, and mortality rate. These results, combined with climate projections, predict severe ranavirosis outbreaks will occur over wider areas and an extended season, possibly affecting larval recruitment. Since ranaviruses affect a variety of ectothermic hosts (amphibians, reptiles, and fish), wider ecological damage could occur. Our three complementary lines of evidence present a clear case for direct environmental modulation of these epidemics and suggest management options to protect species from disease.

Constraining Southern Ocean Air-Sea-Ice Fluxes Through Enhanced Observations - Sebastiaan Swart; Sarah T. Gille; Bruno Delille; Simon Josey; Matthew Mazloff; Louise Newman; Andrew F. Thompson; Jim Thomson; Brian Ward; Marcel D. du Plessis; Elizabeth C. Kent; James Girton; et al. (Frontiers in Marine Science, 2019)

Model-Observations Synergy in the Coastal Ocean - Pierre De Mey-Frémaux; Nadia Ayoub; Alexander Barth; Robert Brewin; Guillaume Charria; Francisco Campuzano; Stefano Ciavatta; Mauro Cirano; Christopher A. Edwards; Ivan Federico; Shan Gao; Isabel Garcia Hermosa; et al. (Frontiers in Marine Science, 2019)

Taxonomy of the order Mononegavirales: update 2019 - Gaya K. Amarasinghe; María A. Ayllón; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Camila Chabi-Jesus; et al. (Archives of Virology, 2019)

Ten tips for developing interdisciplinary socio-ecological researchers - Rachel Kelly; Mary Mackay; Kirsty L. Nash; Christopher Cvitanovic; Edward H. Allison; Derek Armitage; Aletta Bonn; Steven J. Cooke; Stewart Frusher; Elizabeth A. Fulton; Benjamin S. Halpern; Priscila F. M. Lopes; et al. (Socio-Ecological Practice Research, 2019)

Therapeutic challenges for concurrent ethanol and nicotine consumption: naltrexone and varenicline fail to alter simultaneous ethanol and nicotine intake by female alcohol-preferring (P) rats - Robert A. Waeiss; Christopher P. Knight; Sheketha R. Hauser; Lauren A. Pratt; William J. McBride; Zachary A. Rodd (Psychopharmacology, 2019)

Contrasting NO3-N concentration patterns at two karst springs in Iowa (USA): insights on aquifer nitrogen storage and delivery - Keith E. Schilling; Christopher S. Jones; Ryan J. Clark; Robert D. Libra; Xiuyu Liang; You-Kuan Zhang (Hydrogeology Journal, 2019)

Multi-model evaluation of the sensitivity of the global energy budget and hydrological cycle to resolution - Benoît Vannière; Marie-Estelle Demory; Pier Luigi Vidale; Reinhard Schiemann; Malcolm J. Roberts; Christopher D. Roberts; Mio Matsueda; Laurent Terray; Torben Koenigk; Retish Senan (Climate Dynamics, 2019)

Measurement and correlation of displacements on the Severn Suspension Bridge using GPS - Gethin Wyn Roberts; Xu Tang; Christopher J. Brown (Applied Geomatics, 2019)

Correction to: Land Use and Salinity Drive Changes in SAV Abundance and Community Composition - Christopher J. Patrick; Donald E. Weller; Robert J. Orth; David J. Wilcox; Michael P. Hannam (Estuaries and Coasts, 2019)

Large birds travel farther in homogeneous environments - Marlee A. Tucker; Olga Alexandrou; Richard O. Bierregaard; Keith L. Bildstein; Katrin Böhning‐Gaese; Chloe Bracis; John N. Brzorad; Evan R. Buechley; David Cabot; Justin M. Calabrese; Carlos Carrapato; Andre Chiaradia; et al. (Global Ecology and Biogeography, 2019)
Aim Animal movement is an important determinant of individual survival, population dynamics and ecosystem structure and function. Nonetheless, it is still unclear how local movements are related to resource availability and the spatial arrangement of resources. Using resident bird species and migratory bird species outside the migratory period, we examined how the distribution of resources affects the movement patterns of both large terrestrial birds (e.g., raptors, bustards and hornbills) and waterbirds (e.g., cranes, storks, ducks, geese and flamingos). Location Global. Time period 2003–2015. Major taxa studied Birds. Methods We compiled GPS tracking data for 386 individuals across 36 bird species. We calculated the straight‐line distance between GPS locations of each individual at the 1‐hr and 10‐day time‐scales. For each individual and time‐scale, we calculated the median and 0.95 quantile of displacement. We used linear mixed‐effects models to examine the effect of the spatial arrangement of resources, measured as enhanced vegetation index homogeneity, on avian movements, while accounting for mean resource availability, body mass, diet, flight type, migratory status and taxonomy and spatial autocorrelation. Results We found a significant effect of resource spatial arrangement at the 1‐hr and 10‐day time‐scales. On average, individual movements were seven times longer in environments with homogeneously distributed resources compared with areas of low resource homogeneity. Contrary to previous work, we found no significant effect of resource availability, diet, flight type, migratory status or body mass on the non‐migratory movements of birds. Main conclusions We suggest that longer movements in homogeneous environments might reflect the need for different habitat types associated with foraging and reproduction. This highlights the importance of landscape complementarity, where habitat patches within a landscape include a range of different, yet complementary resources. As habitat homogenization increases, it might force birds to travel increasingly longer distances to meet their diverse needs.

Airway Exposure to Modified Multi-walled Carbon Nanotubes Perturbs Cardiovascular Adenosinergic Signaling in Mice - Leslie C. Thompson; Nicole L. Sheehan; Dianne M. Walters; Robert M. Lust; Jared M. Brown; Christopher J. Wingard (Cardiovascular Toxicology, 2019)

Regional entropy of functional imaging signals varies differently in sensory and cognitive systems during propofol-modulated loss and return of behavioral responsiveness - Xiaolin Liu; Kathryn K. Lauer; B. Douglas Ward; Christopher J. Roberts; Suyan Liu; Suneeta Gollapudy; Robert Rohloff; William Gross; Zhan Xu; Shanshan Chen; Lubin Wang; Zheng Yang; et al. (Brain Imaging and Behavior, 2019)

Taxonomy of the order Mononegavirales: second update 2018 - Piet Maes; Gaya K. Amarasinghe; María A. Ayllón; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Kartik Chandran; et al. (Archives of Virology, 2019)

Using fish landing sites and markets information towards quantification of the blue economy to enhance fisheries management - Christopher Mulanda Aura; Chrisphine S. Nyamweya; James M. Njiru; Cyprian Odoli; Safina Musa; Zachary Ogari; Richard Abila; Raphael Okeyo; Robert Oketch (Fisheries Management and Ecology, 2019)
Fisheries management uses important fish market information and information from Communication Technology ( ICT ) to improve fish trade by identifying inefficiencies, inequity and post‐harvest losses. The current study reports fisheries output using ICT at major landing sites and markets in Kenya and Uganda from the Kenya Marine and Fisheries Research Institute ( KMFRI ) Enhanced Fish Market Information Service ( EFMIS ) database for 2009 – 2017. Catch assessment survey data validated the use of market data in drawing conclusions. Regional Frame Survey data provided information before EFMIS , enabling comparisons of fish trade costings. The average quantity of fish traded in Kenya depended on seasons of active lake fishing, which occurs in January – March and August – October, while Uganda had an irregular pattern associated with fish trade throughout the year. The quantity of fish traded weekly depended on the average price of fish. Lower sales margins during the EFMIS project showed the merits of information sharing using ICT platforms for efficient and equitable fish trade. Such evaluation of fish market information is useful in fish trade policy formulation and for fisheries management and ecological sustainability in rural and peri‐urban communities.

Better Regional Ocean Observing Through Cross-National Cooperation: A Case Study From the Northeast Pacific - John A. Barth; Susan E. Allen; Edward P. Dever; Richard K. Dewey; Wiley Evans; Richard A. Feely; Jennifer L. Fisher; Jonathan P. Fram; Burke Hales; Debby Ianson; Jennifer Jackson; Kim Juniper; et al. (Frontiers in Marine Science, 2019)

Rising Sea Levels: Helping Decision-Makers Confront the Inevitable - John A. Hall; Christopher P. Weaver; Jayantha Obeysekera; Mark Crowell; Radley M. Horton; Robert E. Kopp; John Marburger; Douglas C. Marcy; Adam Parris; William V. Sweet; William C. Veatch; Kathleen D. White (Coastal Management, 2019)

Feeding Aquatic Ecosystems: Whole-Lake Experimental Addition of Angler’s Ground Bait Strongly Affects Omnivorous Fish Despite Low Contribution to Lake Carbon Budget - Thomas Mehner; Tobias Rapp; Christopher T. Monk; Mara E. Beck; Ashley Trudeau; Mikko Kiljunen; Sabine Hilt; Robert Arlinghaus (Ecosystems, 2019)

Taxonomy of the order Bunyavirales: second update 2018 - Piet Maes; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; Matthew J. Ballinger; Dennis A. Bente; Martin Beer; Éric Bergeron; Carol D. Blair; Thomas Briese; Michael J. Buchmeier; Felicity J. Burt; et al. (Archives of Virology, 2019)

Rockall and Hatton: Resolving a Super Wicked Marine Governance Problem in the High Seas of the Northeast Atlantic Ocean - David E. Johnson; Christopher Barrio Froján; Francis Neat; Dick Van Oevelen; David Stirling; Matthew J. Gubbins; J. Murray Roberts (Frontiers in Marine Science, 2019)

Challenges and Prospects in Ocean Circulation Models - Baylor Fox-Kemper; Alistair Adcroft; Claus W. Böning; Eric P. Chassignet; Enrique Curchitser; Gokhan Danabasoglu; Carsten Eden; Matthew H. England; Rüdiger Gerdes; Richard J. Greatbatch; Stephen M. Griffies; Robert W. Hallberg; et al. (Frontiers in Marine Science, 2019)

Effects of garden management practices, by different types of gardeners, on human wellbeing and ecological and soil sustainability in Swiss cities - Robert Home; Olivia Lewis; Nicole Bauer; Andreas Fliessbach; David Frey; Stéphanie Lichtsteiner; Marco Moretti; Simon Tresch; Christopher Young; Andrea Zanetta; Matthias Stolze (Urban Ecosystems, 2019)

Lack of consistent sex differences in d-amphetamine-induced dopamine release measured with [18F]fallypride PET - Christopher T. Smith; Linh C. Dang; Leah L. Burgess; Scott F. Perkins; M. Danica San Juan; Darcy K. Smith; Ronald L. Cowan; Nam T. Le; Robert M. Kessler; Gregory R. Samanez-Larkin; David H. Zald (Psychopharmacology, 2019)

Sex- and developmental-specific transcriptomic analyses of the Antarctic mite, Alaskozetes antarcticus, reveal transcriptional shifts underlying oribatid mite reproduction - Hannah E. Meibers; Geoffrey Finch; Robert T. Gregg; Sierra Glenn; Keavash D. Assani; Emily C. Jennings; Benjamin Davies; Andrew J. Rosendale; Christopher J. Holmes; J. D. Gantz; Drew E. Spacht; Richard E. Lee; et al. (Polar Biology, 2019)

Bonefish in South Florida: status, threats and research needs - Jacob W. Brownscombe; Andy J. Danylchuk; Aaron J. Adams; Brooke Black; Ross Boucek; Michael Power; Jennifer S. Rehage; Rolando O. Santos; Russ W. Fisher; Bill Horn; Christopher R. Haak; Sean Morton; et al. (Environmental Biology of Fishes, 2019)

Germline CDH1 mutations are a significant contributor to the high frequency of early-onset diffuse gastric cancer cases in New Zealand Māori - Christopher Hakkaart; Lis Ellison-Loschmann; Robert Day; Andrew Sporle; Jonathan Koea; Pauline Harawira; Soo Cheng; Michelle Gray; Tracey Whaanga; Neil Pearce; Parry Guilford (Familial Cancer, 2019)

Correction to: Impact of Channel Deepening on Tidal and Gravitational Circulation in a Highly Engineered Estuarine Basin - Robert J. Chant; Christopher K. Sommerfield; Stefan A. Talke (Estuaries and Coasts, 2018)

Ecosystem services of geoduck farming in South Puget Sound, USA: a modeling analysis - Alhambra Martínez Cubillo; João Gomes Ferreira; Christopher Michael Pearce; Robert Marshall; Dan Cheney; Bobbi Hudson (Aquaculture International, 2018)

Attraction and repulsion of mobile wild organisms to finfish and shellfish aquaculture: a review - Myriam D. Callier; Carrie J. Byron; David A. Bengtson; Peter J. Cranford; Stephen F. Cross; Ulfert Focken; Henrice M. Jansen; Pauline Kamermans; Anders Kiessling; Thomas Landry; Francis O'Beirn; Erik Petersson; et al. (Reviews in Aquaculture, 2018)
Knowledge of aquaculture–environment interactions is essential for the development of a sustainable aquaculture industry and efficient marine spatial planning. The effects of fish and shellfish farming on sessile wild populations, particularly infauna, have been studied intensively. Mobile fauna, including crustaceans, fish, birds and marine mammals, also interact with aquaculture operations, but the interactions are more complex and these animals may be attracted to (attraction) or show an aversion to (repulsion) farm operations with various degrees of effects. This review outlines the main mechanisms and effects of attraction and repulsion of wild animals to/from marine finfish cage and bivalve aquaculture, with a focus on effects on fisheries‐related species. Effects considered in this review include those related to the provision of physical structure (farm infrastructure acting as fish aggregating devices ( FAD s) or artificial reefs ( AR s), the provision of food (e.g. farmed animals, waste feed and faeces, fouling organisms associated with farm structures) and some farm activities (e.g. boating, cleaning). The reviews show that the distribution of mobile organisms associated with farming structures varies over various spatial (vertical and horizontal) and temporal scales (season, feeding time, day/night period). Attraction/repulsion mechanisms have a variety of direct and indirect effects on wild organisms at the level of individuals and populations and may have implication for the management of fisheries species and the ecosystem in the context of marine spatial planning. This review revealed considerable uncertainties regarding the long‐term and ecosystem‐wide consequences of these interactions. The use of modelling may help better understand consequences, but long‐term studies are necessary to better elucidate effects.

Impact of Gulf Stream SST biases on the global atmospheric circulation - Robert W. Lee; Tim J. Woollings; Brian J. Hoskins; Keith D. Williams; Christopher H. O’Reilly; Giacomo Masato (Climate Dynamics, 2018)

Vanishing refuge? Testing the forest refuge hypothesis in coastal East Africa using genome‐wide sequence data for seven amphibians - Christopher D. Barratt; Beryl A. Bwong; Robert Jehle; H. Christoph Liedtke; Peter Nagel; Renske E. Onstein; Daniel M. Portik; Jeffrey W. Streicher; Simon P. Loader (Molecular Ecology, 2018)
High‐throughput sequencing data have greatly improved our ability to understand the processes that contribute to current biodiversity patterns. The “vanishing refuge” diversification model is speculated for the coastal forests of eastern Africa, whereby some taxa have persisted and diversified between forest refugia, while others have switched to becoming generalists also present in non‐forest habitats. Complex arrangements of geographical barriers (hydrology and topography) and ecological gradients between forest and non‐forest habitats may have further influenced the region's biodiversity, but elucidation of general diversification processes has been limited by lack of suitable data. Here, we explicitly test alternative diversification modes in the coastal forests using genome‐wide single nucleotide polymorphisms, mtDNA, spatial and environmental data for three forest ( Arthroleptis xenodactyloides , Leptopelis flavomaculatus and Afrixalus sylvaticus ) and four generalist ( Afrixalus fornasini , A. delicatus , Leptopelis concolor and Leptopelis argenteus ) amphibians. Multiple analyses provide insight about divergence times, spatial population structure, dispersal barriers, environmental stability and demographic history. We reveal highly congruent intra‐specific diversity and population structure across taxa, with most divergences occurring during the late Pliocene and Pleistocene. Although stability models support the existence of some forest refugia, dispersal barriers and demographic models point towards idiosyncratic diversification modes across taxa. We identify a consistent role for riverine barriers in the diversification of generalist taxa, but mechanisms of diversification are more complex for forest taxa and potentially include topographical barriers, forest refugia and ecological gradients. Our work demonstrates the complexity of diversification processes in this region, which vary between forest and generalist taxa, but also for ecologically similar species with shared population boundaries.

Effects of canopy structure and species diversity on primary production in upper Great Lakes forests - Cynthia M. Scheuermann; Lucas E. Nave; Robert T. Fahey; Knute J. Nadelhoffer; Christopher M. Gough (Oecologia, 2018)

Genome-wide association study of primary open-angle glaucoma in continental and admixed African populations - Pieter W. M. Bonnemaijer; Adriana I. Iglesias; Girish N. Nadkarni; Anna J. Sanyiwa; Hassan G. Hassan; Colin Cook; Mark Simcoe; Kent D. Taylor; Claudia Schurmann; Gillian M. Belbin; Eimear E. Kenny; Erwin P. Bottinger; et al. (Human Genetics, 2018)

Habitat correlates of Eurasian Woodcock Scolopax rusticola abundance in a declining resident population - Christopher J. Heward; Andrew N. Hoodless; Greg J. Conway; Robert J. Fuller; Andrew D. C. MacColl; Nicholas J. Aebischer (Journal of Ornithology, 2018)

Annual Monitoring of US Timber Production: Rationale and Design - John W Coulston; James A Westfall; David N Wear; Christopher B Edgar; Steven P Prisley; Thomas B Treiman; Robert C Abt; W Brad Smith (Forest Science, 2018)

Impact of Channel Deepening on Tidal and Gravitational Circulation in a Highly Engineered Estuarine Basin - Robert J. Chant; Christopher K. Sommerfield; Stefan A. Talke (Estuaries and Coasts, 2018)

Land Use and Salinity Drive Changes in SAV Abundance and Community Composition - Christopher J. Patrick; Donald E. Weller; Robert J. Orth; David J. Wilcox; Michael P. Hannam (Estuaries and Coasts, 2018)
Conserving and restoring submerged aquatic vegetation (SAV) are key management goals for estuaries worldwide because SAV integrates many aspects of water quality and provides a wide range of ecosystem services. Management strategies are typically focused on aggregated abundance of several SAV species, because species cannot be easily distinguished in remotely sensed data. Human land use and shoreline alteration have been shown to negatively impact SAV abundance, but the effects have varied with study, spatial scale, and location. The differences in reported effects may be partly due to the focus on abundance, which overlooks within-community and among-community dynamics that generate total SAV abundance. We analyzed long-term SAV aerial survey data (1984–2009) and ground observations of community composition (1984–2012) in subestuaries of Chesapeake Bay to integrate variations in abundance with differences in community composition. We identified five communities (mixed freshwater, milfoil- Zannichellia , mixed mesohaline, Zannichellia , and Ruppia-Zostera ). Temporal variations in SAV abundance were more strongly related to community identity than to terrestrial stressors, and responses to stressors differed among communities and among species. In one fifth of the subestuaries, the community identity changed during the study, and the probability of such a change was positively related to the prevalence of riprapped shoreline in the subestuary. Mixed freshwater communities had the highest rates of recovery, and this may have been driven by Hydrilla verticillata , which was the single best predictor of SAV recovery rate. Additional species-specific and community-specific research will likely yield better understanding of the factors affecting community identity and SAV abundance, more accurate predictive models, and more effective management strategies.

Seasonal and latitudinal variations of surface fluxes at two Arctic terrestrial sites - Andrey A. Grachev; P. Ola G. Persson; Taneil Uttal; Elena A. Akish; Christopher J. Cox; Sara M. Morris; Christopher W. Fairall; Robert S. Stone; Glen Lesins; Alexander P. Makshtas; Irina A. Repina (Climate Dynamics, 2018)

Efficient Computational Modeling of Human Ventricular Activation and Its Electrocardiographic Representation: A Sensitivity Study - Jonathan P. Cranford; Thomas J. O’Hara; Christopher T. Villongco; Omar M. Hafez; Robert C. Blake; Joseph Loscalzo; Jean-Luc Fattebert; David F. Richards; Xiaohua Zhang; James N. Glosli; Andrew D. McCulloch; David E. Krummen; et al. (Cardiovascular Engineering and Technology, 2018)

A global meta‐analysis of marine predator nitrogen stable isotopes: Relationships between trophic structure and environmental conditions - Heidi Pethybridge; C. Anela Choy; John M. Logan; Valerie Allain; Anne Lorrain; Nathalie Bodin; Christopher J. Somes; Jock Young; Frederic Ménard; Clothilde Langlais; Leanne Duffy; Alistair J. Hobday; et al. (Global Ecology and Biogeography, 2018)
Aim We examined potential environmental drivers of broad‐scale spatial patterns in the trophic structure of marine ecosystems as represented by nitrogen stable isotopes in globally distributed marine predators. Additionally, we assessed the effects of spatial scale on the predictive capabilities of environmental variables. Location Global oceans. Time period 2000 to 2015. Major taxa studied Tunas: Thunnus albacares , Thunnus obesus , Thunnus alalunga . Methods We undertook a global compilation and meta‐analysis of the bulk nitrogen stable isotope ratios (δ 15 N values) of three tuna species ( n = 4,281). After adjusting for regional variations in baseline δ 15 N values using a global ocean biogeochemistry model, generalized additive mixed models were employed to infer global‐scale oceanographic controls of trophic structure, using cosmopolitan tuna species as a model. Results For the three tuna species, variation in trophic position estimated using bulk δ 15 N values was largely explained by geographical location and the corresponding oxygen minimum layer depth. Tuna trophic positions declined in areas with reduced oxygen at depth. Food‐chain length, as captured by maximum trophic position, was longer in areas of the western Pacific Ocean and shorter in the northern Atlantic and eastern Pacific Oceans. Trophic adaptability of the tuna predators, as indicated by intraspecific variability, was highest in the western and central Pacific Ocean and lowest in the northern Atlantic Ocean. Our analysis demonstrated that while tunas share similar functional trophic roles, deeper‐foraging tuna species had higher trophic positions globally. The predictive capacity of environmental variables decreased at finer (regional) spatial scales. Main conclusions Our work suggests that habitat compression resulting from the predicted global expansion of oxygen minimum zones with ocean warming will impact the trophic structure of marine food webs and the corresponding foraging habits of marine predators. Spatial scale analyses highlighted the importance of representing differences in regional ecological dynamics in global‐scale trophic and ecosystem models.

Taxonomy of the family Arenaviridae and the order Bunyavirales: update 2018 - Piet Maes; Sergey V. Alkhovsky; Yīmíng Bào; Martin Beer; Monica Birkhead; Thomas Briese; Michael J. Buchmeier; Charles H. Calisher; Rémi N. Charrel; Il Ryong Choi; Christopher S. Clegg; Juan Carlos de la Torre; et al. (Archives of Virology, 2018)

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Consensus guidelines for the use and interpretation of angiogenesis assays - Patrycja Nowak-Sliwinska; Kari Alitalo; Elizabeth Allen; Andrey Anisimov; Alfred C. Aplin; Robert Auerbach; Hellmut G. Augustin; David O. Bates; Judy R. van Beijnum; R. Hugh F. Bender; Gabriele Bergers; Andreas Bikfalvi; et al. (Angiogenesis, 2018)

Southern Hemisphere westerly wind influence on southern New Zealand hydrology during the Lateglacial and Holocene - Harris J. Anderson; Christopher M. Moy; Marcus J. Vandergoes; Jonathan E. Nichols; Christina R. Riesselman; Robert Van Hale (Journal of Quaternary Science, 2018)
The strength and latitudinal position of the southern westerly winds (SWW) influence mid‐latitude precipitation and carbon cycling in the Southern Ocean. Despite the important role the westerlies play in the global climate system, past variability is poorly constrained. Here, we present a geochemical record of hydroclimate change from Lake Von in south‐west New Zealand that spans the last 16 000 years. During the Lateglacial and early Holocene, we find stratigraphic and geochemical evidence for three distinct periods of low lake levels that occur during North Atlantic cold events when the Intertropical Convergence Zone is displaced southwards, Southern Ocean upwelling is enhanced and the Antarctic is rapidly warming. We attribute these hydrological changes to southward shifts of the SWW and associated storm tracks that cause arid conditions in southern New Zealand. During the early Holocene, we find evidence for an extended period of low lake levels that are caused by a combination of diminished wind strength, higher air temperatures and reduced seasonality. Finally, we interpret an overall intensification of the SWW after 5500 cal a bp. Our results support the idea that climate mechanisms originating in the high latitudes and the tropics work together to influence the SWW on millennial timescales.

The role of resveratrol on skeletal muscle cell differentiation and myotube hypertrophy during glucose restriction - Hannah F. Dugdale; David C. Hughes; Robert Allan; Colleen S. Deane; Christopher R. Coxon; James P. Morton; Claire E. Stewart; Adam P. Sharples (Molecular and Cellular Biochemistry, 2018)

Estimation of critical end-test torque using neuromuscular electrical stimulation of the quadriceps in humans - Natalie R. Janzen; Robert E. Hight; Darshit S. Patel; Jason A. Campbell; Rebecca D. Larson; Christopher D. Black (European Journal of Applied Physiology, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

The functional response and resilience in small waterbodies along land‐use and environmental gradients - Ian A. Thornhill; Jeremy Biggs; Matthew J. Hill; Robert Briers; David Gledhill; Paul J. Wood; John H. R. Gee; Mark Ledger; Christopher Hassall (Global Change Biology, 2018)
There is growing recognition of the essential services provided to humanity by functionally intact ecosystems. Freshwater ecosystems are found throughout agricultural and urban landscapes and provide a wide range of ecosystem services, but globally they are also amongst the most vulnerable. In particular, ponds (lentic waters typically less than 2 ha), provide natural flood management, sequester carbon and hold significant cultural value. However, to inform their management it is important to understand (1) how functional diversity varies in response to disturbance and (2) the link between biodiversity conservation and ecosystem function. In this study, a meta‐analysis of seven separate pond studies from across England and Wales was carried out to explore the effect of urban and agricultural land‐use gradients, shading, emergent vegetation, surface area and pH upon groups of functionally similar members of the macroinvertebrate fauna. Functional effect groups were first identified by carrying out a hierarchical cluster analysis using body size, voltinism and feeding habits (18 categories) that are closely related to biogeochemical processes (e.g. nutrient and carbon recycling). Secondly, the influence of the gradients upon effect group membership (functional redundancy— FR ) and the breadth of traits available to aid ecosystem recovery (response diversity) was assessed using species counts and functional dispersion (FDis) using 12 response traits. The effect of land‐use gradients was unpredictable, whilst there was a negative response in both FR and FD is to shading and positive responses to increases in emergent vegetation cover and surface area. An inconsistent association between FD is and FR suggested that arguments for taxonomic biodiversity conservation to augment ecosystem functioning are too simplistic. Thus, a deeper understanding of the response of functional diversity to disturbance could have greater impact with decision‐makers who may relate better to the loss of ecosystem function in response to environmental degradation than species loss alone.

Advancing Marine Biological Observations and Data Requirements of the Complementary Essential Ocean Variables (EOVs) and Essential Biodiversity Variables (EBVs) Frameworks - Frank E. Muller-Karger; Patricia Miloslavich; Nicholas J. Bax; Samantha Simmons; Mark J. Costello; Isabel Sousa Pinto; Gabrielle Canonico; Woody Turner; Michael Gill; Enrique Montes; Benjamin D. Best; Jay Pearlman; et al. (Frontiers in Marine Science, 2018)

Freedom from Tritrichomonas foetus infection in cattle in St. Kitts - Kimberly E. Coker; Joseph J. Lim; Rebecca L. Schleisman; Christopher Vosloo; Hilari M. French; Juan C. Samper; John J. Callanan; Robert O. Gilbert; Fortune Sithole; Chaoqun Yao; Aspinas Chapwanya (Tropical Animal Health and Production, 2018)

How ecology shapes exploitation: a framework to predict the behavioural response of human and animal foragers along exploration–exploitation trade‐offs - Christopher T. Monk; Matthieu Barbier; Pawel Romanczuk; James R. Watson; Josep Alós; Shinnosuke Nakayama; Daniel I. Rubenstein; Simon A. Levin; Robert Arlinghaus (Ecology Letters, 2018)
Understanding how humans and other animals behave in response to changes in their environments is vital for predicting population dynamics and the trajectory of coupled social‐ecological systems. Here, we present a novel framework for identifying emergent social behaviours in foragers (including humans engaged in fishing or hunting) in predator–prey contexts based on the exploration difficulty and exploitation potential of a renewable natural resource. A qualitative framework is introduced that predicts when foragers should behave territorially, search collectively, act independently or switch among these states. To validate it, we derived quantitative predictions from two models of different structure: a generic mathematical model, and a lattice‐based evolutionary model emphasising exploitation and exclusion costs. These models independently identified that the exploration difficulty and exploitation potential of the natural resource controls the social behaviour of resource exploiters. Our theoretical predictions were finally compared to a diverse set of empirical cases focusing on fisheries and aquatic organisms across a range of taxa, substantiating the framework's predictions. Understanding social behaviour for given social‐ecological characteristics has important implications, particularly for the design of governance structures and regulations to move exploited systems, such as fisheries, towards sustainability. Our framework provides concrete steps in this direction.

A pilot(less) study on the use of an unmanned aircraft system for studying polar bears (Ursus maritimus) - Andrew F. Barnas; Christopher J. Felege; Robert F. Rockwell; Susan N. Ellis-Felege (Polar Biology, 2018)

Modelling habitat and planning surveillance using Landsat imagery: a case study using Imported Red Fire ants - Clair L. Alston-Knox; Kerrie L. Mengersen; Robert Denham; Christopher M. Strickland (Biological Invasions, 2018)

Reducing production of fumonisin mycotoxins in Fusarium verticillioides by RNA interference - Eric T. Johnson; Robert H. Proctor; Christopher A. Dunlap; Mark Busman (Mycotoxin Research, 2018)

Pyramidal cell-selective GluN1 knockout causes impairments in salience attribution and related EEG activity - Alexandra D. Forrest; Jakyung Bang; Robert E. Featherstone; Jonathan H. Bloom; Matthew S. Luminais; Rebecca V. Zhang; Christopher R. Gajewski; Mary F. McMullen; Yuling Liang; Steven J. Siegel (Experimental Brain Research, 2018)

Current perspectives on bone metastases in castrate-resistant prostate cancer - Christopher Logothetis; Michael J. Morris; Robert Den; Robert E. Coleman (Cancer and Metastasis Reviews, 2018)

SeaView: Bringing Together an Ocean of Data - Karen Stocks; Steve Diggs; Christopher Olson; Anh Pham; Robert Arko; Adam Shepherd; Danie Kinkade (Oceanography, 2018)

Identification of novel QTL for black tea quality traits and drought tolerance in tea plants (Camellia sinensis) - Robert K. Koech; Pelly M. Malebe; Christopher Nyarukowa; Richard Mose; Samson M. Kamunya; Zeno Apostolides (Tree Genetics & Genomes, 2018)

Evaluating Current Practices in Shelf Life Estimation - Robert Capen; David Christopher; Patrick Forenzo; Kim Huynh-Ba; David LeBlond; Oscar Liu; John O’Neill; Nate Patterson; Michelle Quinlan; Radhika Rajagopalan; James Schwenke; Walter Stroup (AAPS PharmSciTech, 2018)

A new precipitation and drought climatology based on weather patterns - Douglas Richardson; Hayley J. Fowler; Christopher G. Kilsby; Robert Neal (International Journal of Climatology, 2018)
Weather‐pattern, or weather‐type, classifications are a valuable tool in many applications as they characterize the broad‐scale atmospheric circulation over a given region. This study analyses the aspects of regional UK precipitation and meteorological drought climatology with respect to a new set of objectively defined weather patterns. These new patterns are currently being used by the Met Office in several probabilistic forecasting applications driven by ensemble forecasting systems. Weather pattern definitions and daily occurrences are mapped to Lamb weather types (LWTs), and parallels between the two classifications are drawn. Daily precipitation distributions are associated with each weather pattern and LWT. Standardized precipitation index (SPI) and drought severity index (DSI) series are calculated for a range of aggregation periods and seasons. Monthly weather‐pattern frequency anomalies are calculated for SPI wet and dry periods and for the 5% most intense DSI‐based drought months. The new weather‐pattern definitions and daily occurrences largely agree with their respective LWTs, allowing comparison between the two classifications. There is also broad agreement between weather pattern and LWT changes in frequencies. The new data set is shown to be adequate for precipitation‐based analyses in the UK, although a smaller set of clustered weather patterns is not. Furthermore, intra‐pattern precipitation variability is lower in the new classification compared to the LWTs, which is an advantage in this context. Six of the new weather patterns are associated with drought over the entire UK, with several other patterns linked to regional drought. It is demonstrated that the new data set of weather patterns offers a new opportunity for classification‐based analyses in the UK.

Relationship between air mass type and emergency department visits for migraine headache across the Triangle region of North Carolina - Christopher Elcik; Christopher M. Fuhrmann; Andrew E. Mercer; Robert E. Davis (International Journal of Biometeorology, 2017)

Concomitant external pneumatic compression treatment with consecutive days of high intensity interval training reduces markers of proteolysis - Cody T. Haun; Michael D. Roberts; Matthew A. Romero; Shelby C. Osburn; James C. Healy; Angelique N. Moore; Christopher B. Mobley; Paul A. Roberson; Wesley C. Kephart; Petey W. Mumford; Michael D. Goodlett; David D. Pascoe; et al. (European Journal of Applied Physiology, 2017)

Remote sensing evidence of lava–ground ice interactions associated with the Lost Jim Lava Flow, Seward Peninsula, Alaska - Emma C. Marcucci; Christopher W. Hamilton; Robert R. Herrick (Bulletin of Volcanology, 2017)

Correlated evolution of sexually selected traits: interspecific variation in ejaculates, sperm morphology, copulatory mate guarding, and body size in two sympatric species of garter snakes - Christopher R. Friesen; Emily J. Uhrig; Ehren J. Bentz; Leslie A. Blakemore; Robert T. Mason (Behavioral Ecology and Sociobiology, 2017)

Climate Variability and Change: Response of a Coastal Ocean Ecosystem - Francisco Chavez; J. Timothy Pennington; Reiko Michisaki; Marguerite Blum; Gabriela Chavez; Jules Friederich; Brent Jones; Robert Herlien; Brian Kieft; Brett Hobson; Alice Ren; John Ryan; et al. (Oceanography, 2017)

Rapid recovery of nuclear and mitochondrial genes by genome skimming from Northern Hemisphere freshwater crayfish - Frederic Grandjean; Mun Hua Tan; Han Ming Gan; Yin Peng Lee; Tadashi Kawai; Robert J. Distefano; Martin Blaha; Angela J. Roles; Christopher M. Austin (Zoologica Scripta, 2017)
Molecular phylogenetics has benefited tremendously from the advent of next‐generation sequencing, enabling quick and cost‐effective recovery of whole mitogenomes via an approach referred to as ‘genome skimming’. Recently, genome skimming has been utilised to recover highly repetitive nuclear genes such as 18S and 28S ribosomal RNA genes that are useful for inferring deeper evolutionary relationships. To address some outstanding issues in the relationships among Northern Hemisphere freshwater crayfish (Astacoidea), we sequenced the partial genome of crayfish species from Asian, North American and European genera and report the successful recovery of whole mitogenome sequences in addition to three highly repetitive nuclear genes, namely histone H3, 18S and 28S ribosomal RNA . Consistent with some previous studies using short mt DNA and nuclear gene fragments, phylogenetic analyses based on the concatenation of recovered mitochondrial and/or nuclear sequences recovered the Asian cambarid lineage as basal to all astacids and North American cambarids, which conflicts with the current taxonomic classification based on morphological and reproduction‐related characters. Lastly, we show that complete H3, 18S and 28S ribosomal RNA genes can also be consistently recovered from a diverse range of animal taxa, demonstrating the potential wide utility of genome skimming for nuclear markers.

Ultrafine Particulate Matter Increases Cardiac Ischemia/Reperfusion Injury via Mitochondrial Permeability Transition Pore - Nathan A. Holland; Chad R. Fraiser; Ruben C. Sloan; Robert B. Devlin; David A. Brown; Christopher J. Wingard (Cardiovascular Toxicology, 2017)

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Fundamental Economic Irreversibilities Influence Policies for Enhancing International Forest Phytosanitary Security - Thomas P. Holmes; Will Allen; Robert G. Haight; E. Carina H. Keskitalo; Mariella Marzano; Maria Pettersson; Christopher P. Quine; E. R. Langer (Current Forestry Reports, 2017)

Leaf and canopy scale drivers of genotypic variation in soybean response to elevated carbon dioxide concentration - Álvaro Sanz‐Sáez; Robert P. Koester; David M. Rosenthal; Christopher M. Montes; Donald R. Ort; Elizabeth A. Ainsworth (Global Change Biology, 2017)
The atmospheric [ CO 2 ] in which crops grow today is greater than at any point in their domestication history and represents an opportunity for positive effects on seed yield that can counteract the negative effects of greater heat and drought this century. In order to maximize yields under future atmospheric [ CO 2 ], we need to identify and study crop cultivars that respond most favorably to elevated [ CO 2 ] and understand the mechanisms contributing to their responsiveness. Soybean ( Glycine max Merr.) is a widely grown oilseed crop and shows genetic variation in response to elevated [ CO 2 ]. However, few studies have studied the physiological basis for this variation. Here, we examined canopy light interception, photosynthesis, respiration and radiation use efficiency along with yield and yield parameters in two cultivars of soybean (Loda and HS 93‐4118) previously reported to have similar seed yield at ambient [ CO 2 ], but contrasting responses to elevated [ CO 2 ]. Seed yield increased by 26% at elevated [ CO 2 ] (600 μmol/mol) in the responsive cultivar Loda, but only by 11% in HS 93‐4118. Canopy light interception and leaf area index were greater in HS 93‐4118 in ambient [ CO 2 ], but increased more in response to elevated [ CO 2 ] in Loda. Radiation use efficiency and harvest index were also greater in Loda than HS 93‐4118 at both ambient and elevated [ CO 2 ]. Daily C assimilation was greater at elevated [ CO 2 ] in both cultivars, while stomatal conductance was lower. Electron transport capacity was also greater in Loda than HS 93‐4118, but there was no difference in the response of photosynthetic traits to elevated [ CO 2 ] in the two cultivars. Overall, this greater understanding of leaf‐ and canopy‐level photosynthetic traits provides a strong conceptual basis for modeling genotypic variation in response to elevated [ CO 2 ].

What makes fish vulnerable to capture by hooks? A conceptual framework and a review of key determinants - Robert J Lennox; Josep Alós; Robert Arlinghaus; Andrij Horodysky; Thomas Klefoth; Christopher T Monk; Steven J Cooke (Fish and Fisheries, 2017)
Considerable time and money are expended in the pursuit of catching fish with hooks (e.g., handlining, angling, longlining, trolling, drumlining) across the recreational, commercial and subsistence fishing sectors. The fish and other aquatic organisms (e.g., squid) that are captured are not a random sample of the population because external (e.g., turbidity) and underlying internal variables (e.g., morphology) contribute to variation in vulnerability to hooks. Vulnerability is the probability of capture for any given fish in a given location at a given time and mechanistically explains the population‐level catchability coefficient, which is a fundamental and usually time‐varying (i.e., dynamic) variable in fisheries science and stock assessment. The mechanistic drivers of individual vulnerability to capture are thus of interest to fishers by affecting catch rates, but are also of considerable importance to fisheries managers whenever hook‐and‐line‐generated data contribute to stock assessments. In this paper, individual vulnerability to hooks is conceptualized as a dynamic state, in which individual fish switch between vulnerable and invulnerable states as a function of three interdependent key processes: an individual fish's internal state, its encounter with the gear, and the characteristics of the encountered gear. We develop a new conceptual framework of “vulnerability,” summarize the major drivers of fish vulnerability, and conclude that fish vulnerability involves complex processes. To understand vulnerability, a shift to interdisciplinary research and the integration of ecophysiology, fish ecology, fisheries ecology and human movement ecology, facilitated by new technological developments, is required.

Taxonomy of the order Mononegavirales: update 2017 - Gaya K. Amarasinghe; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Martin Beer; Nicolás Bejerman; Kim R. Blasdell; Alisa Bochnowski; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; Kartik Chandran; et al. (Archives of Virology, 2017)

Global synthesis of the temperature sensitivity of leaf litter breakdown in streams and rivers - Jennifer J. Follstad Shah; John S. Kominoski; Marcelo Ardón; Walter K. Dodds; Mark O. Gessner; Natalie A. Griffiths; Charles P. Hawkins; Sherri L. Johnson; Antoine Lecerf; Carri J. LeRoy; David W. P. Manning; Amy D. Rosemond; et al. (Global Change Biology, 2017)
Streams and rivers are important conduits of terrestrially derived carbon (C) to atmospheric and marine reservoirs. Leaf litter breakdown rates are expected to increase as water temperatures rise in response to climate change. The magnitude of increase in breakdown rates is uncertain, given differences in litter quality and microbial and detritivore community responses to temperature, factors that can influence the apparent temperature sensitivity of breakdown and the relative proportion of C lost to the atmosphere vs. stored or transported downstream. Here, we synthesized 1025 records of litter breakdown in streams and rivers to quantify its temperature sensitivity, as measured by the activation energy ( E a , in eV ). Temperature sensitivity of litter breakdown varied among twelve plant genera for which E a could be calculated. Higher values of E a were correlated with lower‐quality litter, but these correlations were influenced by a single, N‐fixing genus ( Alnus ). E a values converged when genera were classified into three breakdown rate categories, potentially due to continual water availability in streams and rivers modulating the influence of leaf chemistry on breakdown. Across all data representing 85 plant genera, the E a was 0.34 ± 0.04 eV , or approximately half the value (0.65 eV ) predicted by metabolic theory. Our results indicate that average breakdown rates may increase by 5–21% with a 1–4 °C rise in water temperature, rather than a 10–45% increase expected, according to metabolic theory. Differential warming of tropical and temperate biomes could result in a similar proportional increase in breakdown rates, despite variation in E a values for these regions (0.75 ± 0.13 eV and 0.27 ± 0.05 eV, respectively). The relative proportions of gaseous C loss and organic matter transport downstream should not change with rising temperature given that E a values for breakdown mediated by microbes alone and microbes plus detritivores were similar at the global scale.

Suspended-Sediment Impacts on Light-Limited Productivity in the Delaware Estuary - Jacqueline M. McSweeney; Robert J. Chant; John L. Wilkin; Christopher K. Sommerfield (Estuaries and Coasts, 2017)

Influence of Local, Landscape, and Regional Variables on Sedge and Marsh Wren Occurrence in Great Lakes Coastal Wetlands - Hannah G. Panci; Gerald J. Niemi; Ronald R. Regal; Douglas C. Tozer; Thomas M. Gehring; Robert W. Howe; Christopher J. Norment (Wetlands, 2017)

Trans-ethnic fine-mapping of genetic loci for body mass index in the diverse ancestral populations of the Population Architecture using Genomics and Epidemiology (PAGE) Study reveals evidence for multiple signals at established loci - Lindsay Fernández-Rhodes; Jian Gong; Jeffrey Haessler; Nora Franceschini; Mariaelisa Graff; Katherine K. Nishimura; Yujie Wang; Heather M. Highland; Sachiko Yoneyama; William S. Bush; Robert Goodloe; Marylyn D. Ritchie; et al. (Human Genetics, 2017)

A roadmap for island biology: 50 fundamental questions after 50 years of The Theory of Island Biogeography - Jairo Patiño; Robert J. Whittaker; Paulo A.V. Borges; José María Fernández‐Palacios; Claudine Ah‐Peng; Miguel B. Araújo; Sergio P. Ávila; Pedro Cardoso; Josselin Cornuault; Erik J. de Boer; Lea de Nascimento; Artur Gil; et al. (Journal of Biogeography, 2017)
Aims The 50th anniversary of the publication of the seminal book, The Theory of Island Biogeography , by Robert H. MacArthur and Edward O. Wilson, is a timely moment to review and identify key research foci that could advance island biology. Here, we take a collaborative horizon‐scanning approach to identify 50 fundamental questions for the continued development of the field. Location Worldwide. Methods We adapted a well‐established methodology of horizon scanning to identify priority research questions in island biology, and initiated it during the Island Biology 2016 conference held in the Azores. A multidisciplinary working group prepared an initial pool of 187 questions. A series of online surveys was then used to refine a list of the 50 top priority questions. The final shortlist was restricted to questions with a broad conceptual scope, and which should be answerable through achievable research approaches. Results Questions were structured around four broad and partially overlapping island topics, including: (Macro)Ecology and Biogeography, (Macro)Evolution, Community Ecology, and Conservation and Management. These topics were then subdivided according to the following subject areas: global diversity patterns (five questions in total); island ontogeny and past climate change (4); island rules and syndromes (3); island biogeography theory (4); immigration–speciation–extinction dynamics (5); speciation and diversification (4); dispersal and colonization (3); community assembly (6); biotic interactions (2); global change (5); conservation and management policies (5); and invasive alien species (4). Main conclusions Collectively, this cross‐disciplinary set of topics covering the 50 fundamental questions has the potential to stimulate and guide future research in island biology. By covering fields ranging from biogeography, community ecology and evolution to global change, this horizon scan may help to foster the formation of interdisciplinary research networks, enhancing joint efforts to better understand the past, present and future of island biotas.

A global database of nitrogen and phosphorus excretion rates of aquatic animals - Michael J. Vanni; Peter B. McIntyre; Dennis Allen; Diane L. Arnott; Jonathan P. Benstead; David J. Berg; Åge Brabrand; Sébastien Brosse; Paul A. Bukaveckas; Adriano Caliman; Krista A. Capps; Luciana S. Carneiro; et al. (Ecology, 2017)
Animals can be important in modulating ecosystem‐level nutrient cycling, although their importance varies greatly among species and ecosystems. Nutrient cycling rates of individual animals represent valuable data for testing the predictions of important frameworks such as the Metabolic Theory of Ecology ( MTE ) and ecological stoichiometry ( ES ). They also represent an important set of functional traits that may reflect both environmental and phylogenetic influences. Over the past two decades, studies of animal‐mediated nutrient cycling have increased dramatically, especially in aquatic ecosystems. Here we present a global compilation of aquatic animal nutrient excretion rates. The dataset includes 10,534 observations from freshwater and marine animals of N and/or P excretion rates. These observations represent 491 species, including most aquatic phyla. Coverage varies greatly among phyla and other taxonomic levels. The dataset includes information on animal body size, ambient temperature, taxonomic affiliations, and animal body N:P. This data set was used to test predictions of MTE and ES , as described in Vanni and McIntyre (2016; Ecology DOI : 10.1002/ecy.1582 ).

Influence of Nrf2 activators on subcellular skeletal muscle protein and DNA synthesis rates after 6 weeks of milk protein feeding in older adults - Adam R. Konopka; Jaime L. Laurin; Robert V. Musci; Christopher A. Wolff; Justin J. Reid; Laurie M. Biela; Qian Zhang; Fredrick F. Peelor; Christopher L. Melby; Karyn L. Hamilton; Benjamin F. Miller (GeroScience, 2017)

Anticipatory capacity in response to global change across an extreme elevation gradient in the Ica Basin, Peru - Rafael de Grenade; Joshua Rudow; Rossi Taboada Hermoza; Maria Elena Adauto Aguirre; Christopher A. Scott; Bram Willems; Jennifer L. Schultz; Robert G. Varady (Regional Environmental Change, 2017)

A multicenter assessment of single-cell models aligned to standard measures of cell health for prediction of acute hepatotoxicity - Rowena L. Sison-Young; Volker M. Lauschke; Esther Johann; Eliane Alexandre; Sébastien Antherieu; Hélène Aerts; Helga H. J. Gerets; Gilles Labbe; Delphine Hoët; Martina Dorau; Christopher A. Schofield; Cerys A. Lovatt; et al. (Archives of Toxicology, 2017)

Urban ponds as an aquatic biodiversity resource in modified landscapes - Matthew J. Hill; Jeremy Biggs; Ian Thornhill; Robert A. Briers; David G. Gledhill; James C. White; Paul J. Wood; Christopher Hassall (Global Change Biology, 2017)
Urbanization is a global process contributing to the loss and fragmentation of natural habitats. Many studies have focused on the biological response of terrestrial taxa and habitats to urbanization. However, little is known regarding the consequences of urbanization on freshwater habitats, especially small lentic systems. In this study, we examined aquatic macro‐invertebrate diversity (family and species level) and variation in community composition between 240 urban and 782 nonurban ponds distributed across the United Kingdom. Contrary to predictions, urban ponds supported similar numbers of invertebrate species and families compared to nonurban ponds. Similar gamma diversity was found between the two groups at both family and species taxonomic levels. The biological communities of urban ponds were markedly different to those of nonurban ponds, and the variability in urban pond community composition was greater than that in nonurban ponds, contrary to previous work showing homogenization of communities in urban areas. Positive spatial autocorrelation was recorded for urban and nonurban ponds at 0–50 km (distance between pond study sites) and negative spatial autocorrelation was observed at 100–150 km and was stronger in urban ponds in both cases. Ponds do not follow the same ecological patterns as terrestrial and lotic habitats (reduced taxonomic richness) in urban environments; in contrast, they support high taxonomic richness and contribute significantly to regional faunal diversity. Individual cities are complex structural mosaics which evolve over long periods of time and are managed in diverse ways. This facilitates the development of a wide range of environmental conditions and habitat niches in urban ponds which can promote greater heterogeneity between pond communities at larger scales. Ponds provide an opportunity for managers and environmental regulators to conserve and enhance freshwater biodiversity in urbanized landscapes whilst also facilitating key ecosystem services including storm water storage and water treatment.

Passive gear‐induced timidity syndrome in wild fish populations and its potential ecological and managerial implications - Robert Arlinghaus; Kate L Laskowski; Josep Alós; Thomas Klefoth; Christopher T Monk; Shinnosuke Nakayama; Arne Schröder (Fish and Fisheries, 2017)
Human exploitation of wild‐living animals has been suggested to create a ‘landscape of fear’. A consequence could be that individuals surviving intensive harvesting, either as a result of behavioural plasticity and/or evolutionary change, exhibit increased average timidity. In the aquatic world, such effects are particularly well documented in passively operated fishing gears common to many commercial and recreational fisheries, such as angling, trapping or gill netting. We thus propose that an exploitation‐induced timidity syndrome should be a widespread pattern in fisheries. Importantly, we argue that the syndrome can be associated with several ecological and managerial consequences for social groups, populations, food webs, fisheries and assessment of stocks. We suggest research priorities to deepen our understanding of how exploited fish populations behaviourally respond to harvesting.

Standardized Measures of Coastal Wetland Condition: Implementation at a Laurentian Great Lakes Basin-Wide Scale - Donald G. Uzarski; Valerie J. Brady; Matthew J. Cooper; Douglas A. Wilcox; Dennis A. Albert; Richard P. Axler; Peg Bostwick; Terry N. Brown; Jan J. H. Ciborowski; Nicholas P. Danz; Joseph P. Gathman; Thomas M. Gehring; et al. (Wetlands, 2017)

Pharmacogenetics of stimulant abuse liability: association of CDH13 variant with amphetamine response in a racially-heterogeneous sample of healthy young adults - Adam M. Leventhal; Matthew G. Kirkpatrick; Mollie S. Pester; John E. McGeary; Robert M. Swift; Steve Sussman; Christopher W. Kahler (Psychopharmacology, 2017)

Aging and the effects of a half marathon on Achilles tendon force–elongation relationship - Thijs Maria Anne Ackermans; Gaspar Epro; Christopher McCrum; Kai Daniel Oberländer; Frank Suhr; Maarten Robert Drost; Kenneth Meijer; Kiros Karamanidis (European Journal of Applied Physiology, 2016)

Differential vascular reactivity responses acutely following ingestion of a nitrate rich red spinach extract - Cody T. Haun; Wesley C. Kephart; Angelia M. Holland; Christopher B. Mobley; Anna E. McCloskey; Joshua J. Shake; David D. Pascoe; Michael D. Roberts; Jeffrey S. Martin (European Journal of Applied Physiology, 2016)

Performance on the Cogstate Brief Battery Is Related to Amyloid Levels and Hippocampal Volume in Very Mild Dementia - Yen Ying Lim; Victor L. Villemagne; Simon M. Laws; Robert H. Pietrzak; David Ames; Christopher Fowler; Stephanie Rainey-Smith; Peter J. Snyder; Pierrick Bourgeat; Ralph N. Martins; Olivier Salvado; Christopher C. Rowe; et al. (Journal of Molecular Neuroscience, 2016)

Natural hazards in Australia: storms, wind and hail - Kevin Walsh; Christopher J. White; Kathleen McInnes; John Holmes; Sandra Schuster; Harald Richter; Jason P. Evans; Alejandro Di Luca; Robert A. Warren (Climatic Change, 2016)

Contrasting patterns of genetic diversity and spatial structure in an invasive symbiont-host association - Alexandre Mestre; Roger K. Butlin; William E. Kelso; Robert Romaire; Christopher P. Bonvillain; Juan S. Monrós; Francesc Mesquita-Joanes (Biological Invasions, 2016)

Reconstructing a millennial‐scale record of flooding in a single valley setting: the 2011 flood‐affected Lockyer Valley, south‐east Queensland, Australia - Jacky Croke; Christopher Thompson; Robert Denham; Heather Haines; Ashneel Sharma; Timothy Pietsch (Journal of Quaternary Science, 2016)
This paper reconstructs past flooding from a range of settings in Lockyer Creek, a key tributary of the mid‐Brisbane River, which experienced extreme flood events in AD 2011 and AD 2013. Optically stimulated luminescence samples ( n = 110) were collected from alluvial material preserved in within‐channel benches and floodplains. Age distributions from material in the bedrock reaches confirm an event ∼ 300 years ago which stripped the valley alluvium to bedrock. In the unconfined reaches floodplain deposits indicate lateral stability over the past 6000 years. Marked differences in the inundation patterns of the AD 2011 event highlighted changes in downstream channel geometry. The age distribution of alluvium in reaches not inundated during AD 2011 was older, ∼12 000 years, with no preserved evidence of deposition during the past 1000 years. A relatively continuous record of floodplain deposition in reaches which were inundated in AD 2011 identifies a major peak in flood activity also around 300 years ago (∼AD 1730) with five additional peaks occurring at approximately AD 1962, AD 1897, AD 1300, AD 550 and 5400 BC. The main climatic driver of changes in flooding over this timescale is oscillations in El Niño Southern Oscillation and although proxy records are scarce for this region, some correlations with high‐resolution records of rainfall variability are apparent.

Polysorbates prevent biofilm formation and pathogenesis of Escherichia coli O104:H4 - Rudolph E. Sloup; Roberto J. Cieza; David B. Needle; Robert B. Abramovitch; Alfredo G. Torres; Christopher M. Waters (Biofouling, 2016)

Trace Elements in Sea Ducks of the Alaskan Arctic Coast: Patterns of Variation Among Species, Sexes, and Ages - Micah W. C. Miller; James R. Lovvorn; Angela C. Matz; Robert J. Taylor; Christopher J. Latty; David E. Safine (Archives of Environmental Contamination and Toxicology, 2016)

Taxonomy of the order Mononegavirales: update 2016 - Claudio L. Afonso; Gaya K. Amarasinghe; Krisztián Bányai; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Nicolás Bejerman; Kim R. Blasdell; François-Xavier Briand; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; et al. (Archives of Virology, 2016)

Long-Term Functional Efficacy of a Novel Electrospun Poly(Glycerol Sebacate)-Based Arterial Graft in Mice - Ramak Khosravi; Cameron A. Best; Robert A. Allen; Chelsea E. T. Stowell; Ekene Onwuka; Jennifer J. Zhuang; Yong-Ung Lee; Tai Yi; Matthew R. Bersi; Toshiharu Shinoka; Jay D. Humphrey; Yadong Wang; et al. (Annals of Biomedical Engineering, 2016)

Quantitative Analysis of Three-Dimensional Distribution and Clustering of Intramuscular Fat in Muscles of the Rotator Cuff - Anthony C. Santago; Meghan E. Vidt; Christopher J. Tuohy; Gary G. Poehling; Michael T. Freehill; Jennifer H. Jordan; Robert A. Kraft; Katherine R. Saul (Annals of Biomedical Engineering, 2016)

Thermal stratification in small arctic lakes of southwest Greenland affected by water transparency and epilimnetic temperatures - Jasmine E. Saros; Robert M. Northington; Christopher L. Osburn; Benjamin T. Burpee; Nicholas John Anderson (Limnology and Oceanography, 2016)
We assessed which factors control summer epilimnion thickness in arctic lakes of southwest Greenland. A suite of 22 lakes that thermally stratify was measured in the summer of 2013; a sub‐set of eight of the lakes was measured again in 2014, which was a warmer summer than 2013. Regression analysis of the 22 lakes indicated that the 1% attenuation depth for photosynthetically active radiation (PAR) was the strongest single predictor ( R 2 = 0.75) of epilimnion thickness across lakes; the addition of epilimnion temperature to the PAR model explained additional variability ( R 2 = 0.79). The importance of including temperature in the model was apparent in the results of model validation as well as when comparing across years: while the 1% PAR was 0.4–2 m deeper in 2014 compared with 2013, water temperatures were 2–3°C higher, resulting in July epilimnion thicknesses that were equal to or shallower than in 2013. In these lakes with low color dissolved organic carbon (DOC), multiple factors control the 1% PAR, including absorbance at 440 nm ( a 440 ), 380 nm ( a 380 ), and 320 ( a 320 ), chlorophyll a (Chl a ) and DOC concentration. In 2014, when 1% PAR was deeper than in 2013, a 380, Chl a and DOC were lower in six of the eight lakes. Our results reveal that the thermal structure of these arctic lakes is under complex control by air temperatures and factors that affect PAR attenuation, particularly Chl a and DOC quality, suggesting that continued warming in the Arctic will have strong effects on lake stratification.

Cognitive activity, cognitive function, and brain diffusion characteristics in old age - Konstantinos Arfanakis; Robert S. Wilson; Christopher M. Barth; Ana W. Capuano; Anil Vasireddi; Shengwei Zhang; Debra A. Fleischman; David A. Bennett (Brain Imaging and Behavior, 2016)

Five ways to support interdisciplinary work before tenure - Melinda Harm Benson; Christopher D. Lippitt; Ryan Morrison; Barbara Cosens; Jan Boll; Brian C. Chaffin; Alexander K. Fremier; Robert Heinse; Derek Kauneckis; Timothy E. Link; Caroline E. Scruggs; Mark Stone; et al. (Journal of Environmental Studies and Sciences, 2016)

A review of human sensory dynamics for application to models of driver steering and speed control - Christopher J. Nash; David J. Cole; Robert S. Bigler (Biological Cybernetics, 2016)

Association of genetic susceptibility variants for type 2 diabetes with breast cancer risk in women of European ancestry - Zhiguo Zhao; Wanqing Wen; Kyriaki Michailidou; Manjeet K. Bolla; Qin Wang; Ben Zhang; Jirong Long; Xiao-Ou Shu; Marjanka K. Schmidt; Roger L. Milne; Montserrat García-Closas; Jenny Chang-Claude; et al. (Cancer Causes & Control, 2016)

Regional carbon footprints of households: a German case study - Robert Miehe; Rene Scheumann; Christopher M. Jones; Daniel M. Kammen; Matthias Finkbeiner (Environment, Development and Sustainability, 2016)

A Comparison of the Pharmacokinetics and Pulmonary Lymphatic Exposure of a Generation 4 PEGylated Dendrimer Following Intravenous and Aerosol Administration to Rats and Sheep - Gemma M. Ryan; Robert J. Bischof; Perenlei Enkhbaatar; Victoria M. McLeod; Linda J. Chan; Seth A. Jones; David J. Owen; Christopher J. H. Porter; Lisa M. Kaminskas (Pharmaceutical Research, 2016)

Periodontal disease severity and cancer risk in postmenopausal women: the Buffalo OsteoPerio Study - Xiaodan Mai; Michael J. LaMonte; Kathleen M. Hovey; Jo L. Freudenheim; Christopher A. Andrews; Robert J. Genco; Jean Wactawski-Wende (Cancer Causes & Control, 2016)

Emotional traits predict individual differences in amphetamine-induced positive mood in healthy volunteers - Matthew G. Kirkpatrick; Nicholas I. Goldenson; Nahel Kapadia; Christopher W. Kahler; Harriet de Wit; Robert M. Swift; John E. McGeary; Steve Sussman; Adam M. Leventhal (Psychopharmacology, 2016)

Genetic variation in the immunosuppression pathway genes and breast cancer susceptibility: a pooled analysis of 42,510 cases and 40,577 controls from the Breast Cancer Association Consortium - Jieping Lei; Anja Rudolph; Kirsten B. Moysich; Sabine Behrens; Ellen L. Goode; Manjeet K. Bolla; Joe Dennis; Alison M. Dunning; Douglas F. Easton; Qin Wang; Javier Benitez; John L. Hopper; et al. (Human Genetics, 2016)

Effects of age on arterial stiffness and central blood pressure after an acute bout of resistance exercise - Robert S. Thiebaud; Christopher A. Fahs; Lindy M. Rossow; Jeremy P. Loenneke; Daeyeol Kim; J. Grant Mouser; Travis W. Beck; Debra A. Bemben; Rebecca D. Larson; Michael G. Bemben (European Journal of Applied Physiology, 2016)

Spawning and rearing behavior of bull trout in a headwater lake ecosystem - Lora B. Tennant; Robert E. Gresswell; Christopher S. Guy; Michael H. Meeuwig (Environmental Biology of Fishes, 2016)

Critical biogeochemical functions in the subsurface are associated with bacteria from new phyla and little studied lineages - Laura A. Hug; Brian C. Thomas; Itai Sharon; Christopher T. Brown; Ritin Sharma; Robert L. Hettich; Michael J. Wilkins; Kenneth H. Williams; Andrea Singh; Jillian F. Banfield (Environmental Microbiology, 2016)
Summary Nitrogen, sulfur and carbon fluxes in the terrestrial subsurface are determined by the intersecting activities of microbial community members, yet the organisms responsible are largely unknown. Metagenomic methods can identify organisms and functions, but genome recovery is often precluded by data complexity. To address this limitation, we developed subsampling assembly methods to re‐construct high‐quality draft genomes from complex samples. We applied these methods to evaluate the interlinked roles of the most abundant organisms in biogeochemical cycling in the aquifer sediment. Community proteomics confirmed these activities. The eight most abundant organisms belong to novel lineages, and two represent phyla with no previously sequenced genome. Four organisms are predicted to fix carbon via the C alvin– B enson– B assham, W ood– L jungdahl or 3‐hydroxyproprionate/4‐hydroxybutarate pathways. The profiled organisms are involved in the network of denitrification, dissimilatory nitrate reduction to ammonia, ammonia oxidation and sulfate reduction/oxidation, and require substrates supplied by other community members. An ammonium‐oxidizing T haumarchaeote is the most abundant community member, despite low ammonium concentrations in the groundwater. This organism likely benefits from two other relatively abundant organisms capable of producing ammonium from nitrate, which is abundant in the groundwater. Overall, dominant members of the microbial community are interconnected through exchange of geochemical resources.

A genome-wide association study for colorectal cancer identifies a risk locus in 14q23.1 - Mathieu Lemire; Conghui Qu; Lenora W. M. Loo; Syed H. E. Zaidi; Hansong Wang; Sonja I. Berndt; Stéphane Bézieau; Hermann Brenner; Peter T. Campbell; Andrew T. Chan; Jenny Chang-Claude; Mengmeng Du; et al. (Human Genetics, 2015)

Exposure-driven macroalgal phase shift following catastrophic disturbance on coral reefs - George Roff; Iliana Chollett; Christopher Doropoulos; Yimnang Golbuu; Robert S. Steneck; Adelle L. Isechal; Robert van Woesik; Peter J. Mumby (Coral Reefs, 2015)

Geographic Variability of Sea-Level Change - Robert E. Kopp; Carling C. Hay; Christopher M. Little; Jerry X. Mitrovica (Current Climate Change Reports, 2015)

Net primary production of a temperate deciduous forest exhibits a threshold response to increasing disturbance severity - Ellen J. Stuart-Haëntjens; Peter S. Curtis; Robert T. Fahey; Christoph S. Vogel; Christopher M. Gough (Ecology, 2015)
The global carbon (C) balance is vulnerable to disturbances that alter terrestrial C storage. Disturbances to forests occur along a continuum of severity, from low‐intensity disturbance causing the mortality or defoliation of only a subset of trees to severe stand‐replacing disturbance that kills all trees; yet considerable uncertainty remains in how forest production changes across gradients of disturbance intensity. We used a gradient of tree mortality in an upper Great Lakes forest ecosystem to: (1) quantify how aboveground wood net primary production (ANPP w ) responds to a range of disturbance severities; and (2) identify mechanisms supporting ANPP w resistance or resilience following moderate disturbance. We found that ANPP w declined nonlinearly with rising disturbance severity, remaining stable until >60% of the total tree basal area senesced. As upper canopy openness increased from disturbance, greater light availability to the subcanopy enhanced the leaf‐level photosynthesis and growth of this formerly light‐limited canopy stratum, compensating for upper canopy production losses and a reduction in total leaf area index (LAI). As a result, whole‐ecosystem production efficiency (ANPP w /LAI) increased with rising disturbance severity, except in plots beyond the disturbance threshold. These findings provide a mechanistic explanation for a nonlinear relationship between ANPP w and disturbance severity, in which the physiological and growth enhancement of undisturbed vegetation is proportional to the level of disturbance until a threshold is exceeded. Our results have important ecological and management implications, demonstrating that in some ecosystems moderate levels of disturbance minimally alter forest production.

Phase shift facilitation following cyclone disturbance on coral reefs - George Roff; Christopher Doropoulos; Mirta Zupan; Alice Rogers; Robert S. Steneck; Yimnang Golbuu; Peter J. Mumby (Oecologia, 2015)

Quantified, multi-scale X-ray fluorescence element mapping using the Maia detector array: application to mineral deposit studies - Louise A. Fisher; Denis Fougerouse; James S. Cleverley; Christopher G. Ryan; Steven Micklethwaite; Angela Halfpenny; Robert M. Hough; Mary Gee; David Paterson; Daryl L. Howard; Kathryn Spiers (Mineralium Deposita, 2015)

Post Mortem Human Surrogate Injury Response of the Pelvis and Lower Extremities to Simulated Underbody Blast - Ann M. Bailey; John J. Christopher; Frederick Brozoski; Robert S. Salzar (Annals of Biomedical Engineering, 2015)

The effects of foundation species on community assembly: a global study on alpine cushion plant communities - Zaal Kikvidze; Robin W. Brooker; Bradley J. Butterfield; Ragan M. Callaway; Lohengrin A. Cavieres; Bradley J. Cook; Christopher J. Lortie; Richard Michalet; Francisco I. Pugnaire; Sa Xiao; Fabien Anthelme; Robert G. Björk; et al. (Ecology, 2015)
Foundation species can change plant community structure by modulating important ecological processes such as community assembly, yet this topic is poorly understood. In alpine systems, cushion plants commonly act as foundation species by ameliorating local conditions. Here, we analyze diversity patterns of species' assembly within cushions and in adjacent surrounding open substrates (83 sites across five continents) calculating floristic dissimilarity between replicate plots, and using linear models to analyze relationships between microhabitats and species diversity. Floristic dissimilarity did not change across biogeographic regions, but was consistently lower in the cushions than in the open microhabitat. Cushion plants appear to enable recruitment of many relatively stress‐intolerant species that otherwise would not establish in these communities, yet the niche space constructed by cushion plants supports a more homogeneous composition of species than the niche space beyond the cushion's influence. As a result, cushion plants support higher α‐diversity and a larger species pool, but harbor assemblies with lower β‐diversity than open microhabitats. We conclude that habitats with and without dominant foundation species can strongly differ in the processes that drive species recruitment, and thus the relationship between local and regional species diversity.

Ontogenetic shifts in trait‐mediated mechanisms of plant community assembly - Jesse R. Lasky; Bénédicte Bachelot; Robert Muscarella; Naomi Schwartz; Jimena Forero-Montaña; Christopher J. Nytch; Nathan G. Swenson; Jill Thompson; Jess K. Zimmerman; María Uriarte (Ecology, 2015)
Identifying the processes that maintain highly diverse plant communities remains a central goal in ecology. Species variation in growth and survival rates across ontogeny, represented by tree size classes and life history stage‐specific niche partitioning, are potentially important mechanisms for promoting forest diversity. However, the role of ontogeny in mediating competitive dynamics and promoting functional diversity is not well understood, particular in high‐diversity systems such as tropical forests. The interaction between interspecific functional trait variation and ontogenetic shifts in competitive dynamics may yield insights into the ecophysiological mechanisms promoting community diversity. We investigated how functional trait (seed size, maximum height, SLA, leaf N, and wood density) associations with growth, survival, and response to competing neighbors differ among seedlings and two size classes of trees in a subtropical rain forest in Puerto Rico. We used a hierarchical Bayes model of diameter growth and survival to infer trait relationships with ontogenetic change in competitive dynamics. Traits were more strongly associated with average growth and survival than with neighborhood interactions, and were highly consistent across ontogeny for most traits. The associations between trait values and tree responses to crowding by neighbors showed significant shifts as trees grew. Large trees exhibited greater growth as the difference in species trait values among neighbors increased, suggesting trait‐associated niche partitioning was important for the largest size class. Our results identify potential axes of niche partitioning and performance‐equalizing functional trade‐offs across ontogeny, promoting species coexistence in this diverse forest community.

Genetic analysis of glucosinolate variability in broccoli florets using genome-anchored single nucleotide polymorphisms - Allan F. Brown; Gad G. Yousef; Robert W. Reid; Kranthi K. Chebrolu; Aswathy Thomas; Christopher Krueger; Elizabeth Jeffery; Eric Jackson; John A. Juvik (Theoretical and Applied Genetics, 2015)

Multi-location wheat stripe rust QTL analysis: genetic background and epistatic interactions - M. Dolores Vazquez; Robert Zemetra; C. James Peterson; Xianming M. Chen; Adam Heesacker; Christopher C. Mundt (Theoretical and Applied Genetics, 2015)

Hexabromocyclododecane Flame Retardant Isomers in Sediments from Detroit River and Lake Erie of the Laurentian Great Lakes of North America - Robert J. Letcher; Zhe Lu; Shaogang Chu; G. Douglas Haffner; Ken Drouillard; Christopher H. Marvin; Jan J. H. Ciborowski (Bulletin of Environmental Contamination and Toxicology, 2015)

Predicting survival in head and neck squamous cell carcinoma from TP53 mutation - David L. Masica; Shuli Li; Christopher Douville; Judith Manola; Robert L. Ferris; Barbara Burtness; Arlene A. Forastiere; Wayne M. Koch; Christine H. Chung; Rachel Karchin (Human Genetics, 2015)

Erratum: Recharge mixing in a complex distributary spring system in the Missouri Ozarks, USA - Benjamin V. Miller; Robert N. Lerch; Christopher G. Groves; Jason S. Polk (Hydrogeology Journal, 2015)

Recharge mixing in a complex distributary spring system in the Missouri Ozarks, USA - Benjamin V. Miller; Robert N. Lerch; Christopher G. Groves; Jason S. Polk (Hydrogeology Journal, 2015)

BAAD: a Biomass And Allometry Database for woody plants - Daniel S. Falster; Remko A. Duursma; Masae I. Ishihara; Diego R. Barneche; Richard G. FitzJohn; Angelica Vårhammar; Masahiro Aiba; Makoto Ando; Niels Anten; Michael J. Aspinwall; Jennifer L. Baltzer; Christopher Baraloto; et al. (Ecology, 2015)
Understanding how plants are constructed—i.e., how key size dimensions and the amount of mass invested in different tissues varies among individuals—is essential for modeling plant growth, carbon stocks, and energy fluxes in the terrestrial biosphere. Allocation patterns can differ through ontogeny, but also among coexisting species and among species adapted to different environments. While a variety of models dealing with biomass allocation exist, we lack a synthetic understanding of the underlying processes. This is partly due to the lack of suitable data sets for validating and parameterizing models. To that end, we present the Biomass And Allometry Database (BAAD) for woody plants. The BAAD contains 259 634 measurements collected in 176 different studies, from 21 084 individuals across 678 species. Most of these data come from existing publications. However, raw data were rarely made public at the time of publication. Thus, the BAAD contains data from different studies, transformed into standard units and variable names. The transformations were achieved using a common workflow for all raw data files. Other features that distinguish the BAAD are: (i) measurements were for individual plants rather than stand averages; (ii) individuals spanning a range of sizes were measured; (iii) plants from 0.01–100 m in height were included; and (iv) biomass was estimated directly, i.e., not indirectly via allometric equations (except in very large trees where biomass was estimated from detailed sub‐sampling). We included both wild and artificially grown plants. The data set contains the following size metrics: total leaf area; area of stem cross‐section including sapwood, heartwood, and bark; height of plant and crown base, crown area, and surface area; and the dry mass of leaf, stem, branches, sapwood, heartwood, bark, coarse roots, and fine root tissues. We also report other properties of individuals (age, leaf size, leaf mass per area, wood density, nitrogen content of leaves and wood), as well as information about the growing environment (location, light, experimental treatment, vegetation type) where available. It is our hope that making these data available will improve our ability to understand plant growth, ecosystem dynamics, and carbon cycling in the world's vegetation.

Quantifying Florida Bay Habitat Suitability for Fishes and Invertebrates Under Climate Change Scenarios - Kelly A. Kearney; Mark Butler; Robert Glazer; Christopher R. Kelble; Joseph E. Serafy; Erik Stabenau (Environmental Management, 2015)

Historical and contemporary demography of leaf-toed geckos (Phyllodactylidae: Phyllodactylus tuberculosus saxatilis) in the Mexican dry forest - Christopher Blair; Victor H. Jiménez Arcos; Fausto R. Méndez de la Cruz; Robert W. Murphy (Conservation Genetics, 2015)

The Y ersinia pestis HmsCDE regulatory system is essential for blockage of the oriental rat flea ( X enopsylla cheopis ), a classic plague vector - Alexander G. Bobrov; Olga Kirillina; Viveka Vadyvaloo; Benjamin J. Koestler; Angela K. Hinz; Dietrich Mack; Christopher M. Waters; Robert D. Perry (Environmental Microbiology, 2015)
Summary The second messenger molecule cyclic diguanylate is essential for Y ersinia pestis biofilm formation that is important for blockage‐dependent plague transmission from fleas to mammals. Two diguanylate cyclases ( DGCs ) HmsT and Y 3730 ( HmsD ) are responsible for biofilm formation in vitro and biofilm‐dependent blockage in the oriental rat flea X enopsylla cheopis respectively. Here, we have identified a tripartite signalling system encoded by the y3729‐y3731 operon that is responsible for regulation of biofilm formation in different environments. We present genetic evidence that a putative inner membrane‐anchored protein with a large periplasmic domain Y 3729 ( HmsC ) inhibits HmsD DGC activity in vitro while an outer membrane P al‐like putative lipoprotein Y 3731 ( HmsE ) counteracts HmsC to activate HmsD in the gut of X . cheopis . We propose that HmsE is a critical element in the transduction of environmental signal(s) required for HmsD ‐dependent biofilm formation.

Identification of Cephalosporium stripe resistance quantitative trait loci in two recombinant inbred line populations of winter wheat - M. Dolores Vazquez; Robert Zemetra; C. James Peterson; Christopher C. Mundt (Theoretical and Applied Genetics, 2015)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

Demystifying the RAD fad - Jonathan B. Puritz; Mikhail V. Matz; Robert J. Toonen; Jesse N. Weber; Daniel I. Bolnick; Christopher E. Bird (Molecular Ecology, 2014)
We are writing in response to the population and phylogenomics meeting review by Andrews & Luikart ( ) entitled ‘Recent novel approaches for population genomics data analysis’. Restriction‐site‐associated DNA ( RAD ) sequencing has become a powerful and useful approach in molecular ecology, with several different published methods now available to molecular ecologists, none of which can be considered the best option in all situations. A & L report that the original RAD protocol of Miller et al . ( ) and Baird et al . ( ) is superior to all other RAD variants because putative PCR duplicates can be identified (see Baxter et al . ), thereby reducing the impact of PCR artefacts on allele frequency estimates (Andrews & Luikart ). In response, we (i) challenge the assertion that the original RAD protocol minimizes the impact of PCR artefacts relative to that of other RAD protocols, (ii) present additional biases in RAD seq that are at least as important as PCR artefacts in selecting a RAD protocol and (iii) highlight the strengths and weaknesses of four different approaches to RAD seq which are a representative sample of all RAD variants: the original RAD protocol (mb RAD , Miller et al . ; Baird et al . ), double digest RAD (dd RAD , Peterson et al . ), ez RAD (Toonen et al . ) and 2b RAD (Wang et al . ). With an understanding of the strengths and weaknesses of different RAD protocols, researchers can make a more informed decision when selecting a RAD protocol.

The potential for indirect effects between co‐flowering plants via shared pollinators depends on resource abundance, accessibility and relatedness - Luísa Gigante Carvalheiro; Jacobus Christiaan Biesmeijer; Gita Benadi; Jochen Fründ; Martina Stang; Ignasi Bartomeus; Christopher N. Kaiser‐Bunbury; Mathilde Baude; Sofia I. F. Gomes; Vincent Merckx; Katherine C. R. Baldock; Andrew T. D. Bennett; et al. (Ecology Letters, 2014)
Co‐flowering plant species commonly share flower visitors, and thus have the potential to influence each other's pollination. In this study we analysed 750 quantitative plant–pollinator networks from 28 studies representing diverse biomes worldwide. We show that the potential for one plant species to influence another indirectly via shared pollinators was greater for plants whose resources were more abundant (higher floral unit number and nectar sugar content) and more accessible. The potential indirect influence was also stronger between phylogenetically closer plant species and was independent of plant geographic origin (native vs. non‐native). The positive effect of nectar sugar content and phylogenetic proximity was much more accentuated for bees than for other groups. Consequently, the impact of these factors depends on the pollination mode of plants, e.g. bee or fly pollinated. Our findings may help predict which plant species have the greatest importance in the functioning of plant–pollination networks.

The Effect of Tunicamycin on the Glucose Uptake, Growth, and Cellular Adhesion in the Protozoan Parasite Crithidia fasciculata - Robert Rojas; Christopher Segovia; Annette Nicole Trombert; Javier Santander; Patricio Manque (Current Microbiology, 2014)

Investigation of Dry Powder Inhaler (DPI) Resistance and Aerosol Dispersion Timing on Emitted Aerosol Aerodynamic Particle Sizing by Multistage Cascade Impactor when Sampled Volume Is Reduced from Compendial Value of 4 L - Hlack Mohammed; Jan Arp; Frank Chambers; Mark Copley; Volker Glaab; Mark Hammond; Derek Solomon; Kerry Bradford; Theresa Russell; Yvonne Sizer; Steven C. Nichols; Daryl L. Roberts; et al. (AAPS PharmSciTech, 2014)

Effect of exercise intensity on post-exercise oxygen consumption and heart rate recovery - Theresa N. Mann; Christopher Webster; Robert P. Lamberts; Michael I. Lambert (European Journal of Applied Physiology, 2014)

Floral Scent Contributes to Interaction Specificity in Coevolving Plants and Their Insect Pollinators - Magne Friberg; Christopher Schwind; Lindsey C. Roark; Robert A. Raguso; John N. Thompson (Journal of Chemical Ecology, 2014)

Validation of PyMBMS as a High-throughput Screen for Lignin Abundance in Lignocellulosic Biomass of Grasses - Bryan W. Penning; Robert W. Sykes; Nicholas C. Babcock; Christopher K. Dugard; John F. Klimek; David Gamblin; Mark Davis; Timothy R. Filley; Nathan S. Mosier; Clifford F. Weil; Maureen C. McCann; Nicholas C. Carpita (BioEnergy Research, 2014)

Factors influencing paternity in multiply mated female red-sided garter snakes and the persistent use of sperm stored over winter - Christopher R. Friesen; Amelia R. Kerns; Robert T. Mason (Behavioral Ecology and Sociobiology, 2014)

An assessment of chemical contaminants in sediments from the St. Thomas East End Reserves, St. Thomas, USVI - Anthony S. Pait; S. Ian Hartwell; Andrew L. Mason; Robert A. Warner; Christopher F. G. Jeffrey; Anne M. Hoffman; Dennis A. Apeti; Simon J. Pittman (Environmental Monitoring and Assessment, 2014)

History of periodontal disease diagnosis and lung cancer incidence in the Women’s Health Initiative Observational Study - Xiaodan Mai; Michael J. LaMonte; Kathleen M. Hovey; Ngozi Nwizu; Jo L. Freudenheim; Mine Tezal; Frank Scannapieco; Andrew Hyland; Christopher A. Andrews; Robert J. Genco; Jean Wactawski-Wende (Cancer Causes & Control, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Best Practices for the Development, Scale-up, and Post-approval Change Control of IR and MR Dosage Forms in the Current Quality-by-Design Paradigm - Glenn A. Van Buskirk; Satish Asotra; Christopher Balducci; Prabir Basu; Gerald DiDonato; Angelica Dorantes; W. Mark Eickhoff; Tapash Ghosh; Mario A. González; Theresa Henry; Matthew Howard; Jason Kamm; et al. (AAPS PharmSciTech, 2014)

Erratum to: A genome-wide association study of prostate cancer in West African men - Michael Blaise Cook; Zhaoming Wang; Edward D. Yeboah; Yao Tettey; Richard B. Biritwum; Andrew A. Adjei; Evelyn Tay; Ann Truelove; Shelley Niwa; Charles C. Chung; Annand P. Chokkalingam; Lisa W. Chu; et al. (Human Genetics, 2014)

A genome-wide association study of prostate cancer in West African men - Michael Blaise Cook; Zhaoming Wang; Edward D. Yeboah; Yao Tettey; Richard B. Biritwum; Andrew A. Adjei; Evelyn Tay; Ann Truelove; Shelley Niwa; Charles C. Chung; Annand P. Chokkalingam; Lisa W. Chu; et al. (Human Genetics, 2014)

A killer choice for cancer immunotherapy - Tobi L. Schmidt; Robert S. Negrin; Christopher H. Contag (Immunologic Research, 2014)

Adaptations of aortic and pulmonary artery flow parameters measured by phase-contrast magnetic resonance angiography during supine aerobic exercise - Guido E. Pieles; Gergely Szantho; Jonathan C. L. Rodrigues; Christopher B. Lawton; A. Graham Stuart; Chiara Bucciarelli-Ducci; Mark S. Turner; Craig A. Williams; Robert M. R. Tulloh; Mark C. K. Hamilton (European Journal of Applied Physiology, 2014)

Erratum to: EURO-CORDEX: new high-resolution climate change projections for European impact research - Daniela Jacob; Juliane Petersen; Bastian Eggert; Antoinette Alias; Ole Bøssing Christensen; Laurens M. Bouwer; Alain Braun; Augustin Colette; Michel Déqué; Goran Georgievski; Elena Georgopoulou; Andreas Gobiet; et al. (Regional Environmental Change, 2014)

EURO-CORDEX: new high-resolution climate change projections for European impact research - Daniela Jacob; Juliane Petersen; Bastian Eggert; Antoinette Alias; Ole Bøssing Christensen; Laurens M. Bouwer; Alain Braun; Augustin Colette; Michel Déqué; Goran Georgievski; Elena Georgopoulou; Andreas Gobiet; et al. (Regional Environmental Change, 2014)

Vascular adaptations to low-load resistance training with and without blood flow restriction - Christopher A. Fahs; Lindy M. Rossow; Robert S. Thiebaud; Jeremy P. Loenneke; Daeyeol Kim; Takashi Abe; Travis W. Beck; Daniel L. Feeback; Debra A. Bemben; Michael G. Bemben (European Journal of Applied Physiology, 2014)

Abdominally implanted satellite transmitters affect reproduction and survival rather than migration of large shorebirds - Jos C. E. W. Hooijmeijer; Robert E. Gill; Daniel M. Mulcahy; T. Lee Tibbitts; Rosemarie Kentie; Gerrit J. Gerritsen; Leo W. Bruinzeel; David C. Tijssen; Christopher M. Harwood; Theunis Piersma (Journal of Ornithology, 2014)

GEOTRACES: Changing the Way We Explore Ocean Chemistry - Robert Anderson; Edward Mawji; Gregory Cutter; Christopher Measures; Catherine Jeandel (Oceanography, 2014)

Recent Trends in Product Development and Regulatory Issues on Impurities in Active Pharmaceutical Ingredient (API) and Drug Products. Part 1: Predicting Degradation Related Impurities and Impurity Considerations for Pharmaceutical Dosage Forms - Karen M. Alsante; Kim Huynh-Ba; Steven W. Baertschi; Robert A. Reed; Margaret S. Landis; Mark H. Kleinman; Christopher Foti; Venkatramana M. Rao; Paul Meers; Andreas Abend; Daniel W. Reynolds; Biren K. Joshi (AAPS PharmSciTech, 2014)

Facilitative plant interactions and climate simultaneously drive alpine plant diversity - Lohengrin A. Cavieres; Rob W. Brooker; Bradley J. Butterfield; Bradley J. Cook; Zaal Kikvidze; Christopher J. Lortie; Richard Michalet; Francisco I. Pugnaire; Christian Schöb; Sa Xiao; Fabien Anthelme; Robert G. Björk; et al. (Ecology Letters, 2014)
Interactions among species determine local‐scale diversity, but local interactions are thought to have minor effects at larger scales. However, quantitative comparisons of the importance of biotic interactions relative to other drivers are rarely made at larger scales. Using a data set spanning 78 sites and five continents, we assessed the relative importance of biotic interactions and climate in determining plant diversity in alpine ecosystems dominated by nurse‐plant cushion species. Climate variables related with water balance showed the highest correlation with richness at the global scale. Strikingly, although the effect of cushion species on diversity was lower than that of climate, its contribution was still substantial. In particular, cushion species enhanced species richness more in systems with inherently impoverished local diversity. Nurse species appear to act as a ‘safety net’ sustaining diversity under harsh conditions, demonstrating that climate and species interactions should be integrated when predicting future biodiversity effects of climate change.

Mercury in bats from the northeastern United States - David E. Yates; Evan M. Adams; Sofia E. Angelo; David C. Evers; John Schmerfeld; Marianne S. Moore; Thomas H. Kunz; Timothy Divoll; Samuel T. Edmonds; Christopher Perkins; Robert Taylor; Nelson J. O’Driscoll (Ecotoxicology, 2014)

A new species of Eimeria Schneider, 1875 (Apicomplexa: Eimeriidae) from the Solomon ground skink, Sphenomorphus solomonis (Boulenger) (Sauria: Scincidae) from Papua New Guinea - Chris T. McAllister; Donald W. Duszynski; Robert N. Fisher; Christopher C. Austin (Systematic Parasitology, 2014)

Two new species of Eimeria (Apicomplexa, Eimeriidae) from tree skinks, Prasinohaema spp. (Sauria: Scincidae), from Papua New Guinea - Chris McAllister; Donald Duszynski; Robert Fisher; Christopher Austin (Acta Parasitologica, 2014)
Between September 1991 and June 1992, feces from 4 species of tree skinks, Prasinohaema spp. from Papua New Guinea, were collected and examined for coccidia. Two species, P. flavipes and P. prehensicauda were found to harbor eimerians which are described as new. Oocysts of Eimeria krausi sp. nov. from P. flavipes were ellipsoidal to subspheroidal with a smooth bilayered wall and measured (L × W) 19.2 × 16.9 μm, with a length/width (L/W) ratio of 1.1. Micropyle and oocyst residuum were absent but a fragmented polar granule was present. Sporocysts were ellipsoidal, 9.7 × 6.7 μm, L/W of 1.5. Stieda, subStieda and paraStieda bodies were absent. The sporocyst residuum was composed of many small granules in a compact mass between sporozoites. The sporozoites were sausage-shaped, 11.7 × 2.7 μm, in situ, with an ellipsoidal posterior refractile body and a spheroidal anterior refractile body. Oocysts of Eimeria greeri sp. nov. from P. prehensicauda were ellipsoidal with a smooth bilayered wall, (L × W) 23.0 × 18.3 μm, with a L/W of 1.3. Micropyle and oocyst residuum were absent but a fragmented polar granule was present. Sporocysts were ellipsoidal, 9.7 × 8.4 μm, with a L/W of 1.2. Stieda, subStieda and paraStieda bodies were absent. The sporocyst residuum was composed of many large granules in a compact mass between sporozoites. The sporozoites were sausage-shaped, with an ellipsoidal posterior refractile body and a spheroidal anterior refractile body. We document here the first report of coccidia from skinks of the genus Prasinohaema.

Testing the sensitivity of the East Antarctic Ice Sheet to Southern Ocean dynamics: past changes and future implications - CHRISTOPHER J. FOGWILL; CHRISTIAN S. M. TURNEY; KATRIN J. MEISSNER; NICHOLAS R. GOLLEDGE; PAUL SPENCE; JASON L. ROBERTS; MATHEW H. ENGLAND; RICHARD T. JONES; LIONEL CARTER (Journal of Quaternary Science, 2014)
The stability of Antarctic ice sheets and their potential contribution to sea level under projected future warming remains highly uncertain. The Last Interglacial (135 000–116 000 years ago) provides a potential analogue, with global temperatures 2 °C higher and rates of sea‐level rise >5.6 m ka −1 , leading to sea levels 6.6–9.4 m higher than present. The source(s) of this sea‐level rise remain fiercely debated. Here we report a series of independent model simulations exploring the effects of migrating Southern Hemisphere Westerlies (SHWs) on Southern Ocean circulation and Antarctic ice‐sheet dynamics. We suggest that southerly shifts in winds may have significantly impacted the sub‐polar gyres, inducing pervasive warming (0.2–0.8 °C in the upper 1200 m) adjacent to sectors of the East Antarctic Ice Sheet (EAIS), which due to their geometries and connectivity to the Southern Ocean are highly sensitive to ocean forcing. We conclude that the EAIS potentially made a substantial, hitherto unsuspected, contribution to interglacial sea levels, and given 21st‐century projections in the Southern Annular Mode and associated SHW migration, we highlight how pervasive circum‐Antarctic warming may threaten EAIS stability.

Localization of CGRP Receptor Components, CGRP, and Receptor Binding Sites in Human and Rhesus Cerebellar Cortex - Sajedeh Eftekhari; Christopher A. Salvatore; Renee C. Gaspar; Rhonda Roberts; Stacey O’Malley; Zhizhen Zeng; Lars Edvinsson (The Cerebellum, 2013)

No evidence of interaction between known lipid-associated genetic variants and smoking in the multi-ethnic PAGE population - Logan Dumitrescu; Cara L. Carty; Nora Franceschini; Lucia A. Hindorff; Shelley A. Cole; Petra Bůžková; Fredrick R. Schumacher; Charles B. Eaton; Robert J. Goodloe; David J. Duggan; Jeff Haessler; Barbara Cochran; et al. (Human Genetics, 2013)

On regional dynamical downscaling for the assessment and projection of temperature and precipitation extremes across Tasmania, Australia - Christopher J. White; Kathleen L. McInnes; Robert P. Cechet; Stuart P. Corney; Michael R. Grose; Gregory K. Holz; Jack J. Katzfey; Nathaniel L. Bindoff (Climate Dynamics, 2013)

Parental genetic distance and patterns in nonrandom mating and seed yield in predominately selfing Arabidopsis thaliana - Ann L. Carlson; Hui Gong; Christopher Toomajian; Robert J. Swanson (Plant Reproduction, 2013)

Skeletal muscle satellite cell migration to injured tissue measured with111In-oxine and high-resolution SPECT imaging - Jennifer L. Elster; Christopher R. Rathbone; Zhonglin Liu; Xiasong Liu; Harrison H. Barrett; Robert P. Rhoads; Ronald E. Allen (Journal of Muscle Research and Cell Motility, 2013)

Prevalence of HOXB13 mutation in a population of Ashkenazi Jewish men treated for prostate cancer - Shaheen Alanee; Sohela Shah; Joseph Vijai; Kasmintan Schrader; Robert Hamilton; Rohini Rau-Murthy; Kara Sarrel; Christopher Manschreck; James Eastham; Kenneth Offit (Familial Cancer, 2013)

Continental‐Scale Governance and the Hastening of Loss of Australia's Biodiversity - Euan G. Ritchie; Corey J. A. Bradshaw; Chris R. Dickman; Richard Hobbs; Christopher N. Johnson; Emma L. Johnston; William F. Laurance; David Lindenmayer; Michael A. McCarthy; Dale G. Nimmo; Hugh H. Possingham; Robert L. Pressey; et al. (Conservation Biology, 2013)

Excitotoxic injury to thoracolumbar gray matter alters sympathetic activation and thermal pain sensitivity - Charles J. Vierck; Christopher D. King; Sara A. Berens; Robert P. Yezierski (Experimental Brain Research, 2013)

A multi‐decade time series of kelp forest community structure at San Nicolas Island, California (USA) - Michael C. Kenner; James A. Estes; M. Tim Tinker; James L. Bodkin; Robert K. Cowen; Christopher Harrold; Brian B. Hatfield; Mark Novak; Andrew Rassweiler; Daniel C. Reed (Ecology, 2013)
San Nicolas Island is surrounded by broad areas of shallow subtidal habitat, characterized by dynamic kelp forest communities that undergo dramatic and abrupt shifts in community composition. Although these reefs are fished, the physical isolation of the island means that they receive less impact from human activities than most reefs in Southern California, making San Nicolas an ideal place to evaluate alternative theories about the dynamics of these communities. Here we present monitoring data from seven sampling stations surrounding the island, including data on fish, invertebrate, and algal abundance. These data are unusual among subtidal monitoring data sets in that they combine relatively frequent sampling (twice per year) with an exceptionally long time series (since 1980). Other outstanding qualities of the data set are the high taxonomic resolution captured and the monitoring of permanent quadrats and swaths where the history of the community structure at specific locations has been recorded through time. Finally, the data span a period that includes two of the strongest ENSO events on record, a major shift in the Pacific decadal oscillation, and the reintroduction of sea otters to the island in 1987 after at least 150 years of absence. These events provide opportunities to evaluate the effects of bottom‐up forcing, top‐down control, and physical disturbance on shallow rocky reef communities.

Two new species of Eimeria Schneider, 1875 (Apicomplexa: Eimeriidae) from emerald tree skinks, Lamprolepis smaragdina (Lesson) (Sauria: Scincidae) from Papua New Guinea and the Philippines - Chris T. McAllister; R. Scott Seville; Donald W. Duszynski; Sarah E. Bush; Robert N. Fisher; Christopher C. Austin (Systematic Parasitology, 2013)

A new species of Eimeria Schneider, 1875 (Apicomplexa: Eimeriidae) from Carlia spp. (Sauria: Scincidae) from Papua New Guinea - Chris T. McAllister; Donald W. Duszynski; Robert N. Fisher; Christopher C. Austin (Systematic Parasitology, 2013)

Wind‐induced variability in coastal larval retention areas: a case study on Western Baltic spring‐spawning herring - Robert Klaus Bauer; Daniel Stepputtis; Ulf Gräwe; Christopher Zimmermann; Cornelius Hammer (Fisheries Oceanography, 2013)
The investigation of larval dispersal and retention, their variability and dependence on wind conditions, has become a major topic in fisheries research owing to potential effects on stock recruitment and stock structuring. The present study quantifies the wind‐induced variability of larval retention of herring in a highly productive coastal lagoon of the Western Baltic Sea. This lagoon, the Greifswalder Bodden, represents the main spawning area of Western Baltic Spring‐Spawning Herring, a stock that has recently undergone a continuous decline in recruitment. The study tests whether this decline was related to changes in larval retention, more precisely to changes in wind conditions, the main forcing of the lagoon's circulation. To answer this, a model approach was applied. Larvae were tracked as Lagrangian drifters under constant and variable wind conditions, examining the main drift patterns and reconstructing the incidents during the period of recruitment decline. For the latter, weekly cohorts of virtual larvae were released in the lagoon over the entire spawning period (April–June; >16 weeks). The fraction of retained larvae per cohort was related to observed larval abundances. On this basis, a new retention index was defined to evaluate the annual larval retention. The results presented cannot explain the observed recruitment decline but characterize the lagoon as an important larval retention area by virtue of unsteady wind conditions that prevent a steady outflow of larvae.

Non-Arrhenius Protein Aggregation - Wei Wang; Christopher J. Roberts (The AAPS Journal, 2013)

Land Management Restrictions and Options for Change in Perpetual Conservation Easements - Adena Rissman; Menka Bihari; Christopher Hamilton; Christina Locke; David Lowenstein; Melissa Motew; Jessica Price; Robert Smail (Environmental Management, 2013)

Initial epidemic area is strongly associated with the yearly extent of soybean rust spread in North America - Christopher C. Mundt; LaRae D. Wallace; Tom W. Allen; Clayton A. Hollier; Robert C. Kemerait; Edward J. Sikora (Biological Invasions, 2013)

Combined analyses of kinship and F ST suggest potential drivers of chaotic genetic patchiness in high gene‐flow populations - Matthew Iacchei; Tal Ben‐Horin; Kimberly A. Selkoe; Christopher E. Bird; Francisco J. García‐Rodríguez; Robert J. Toonen (Molecular Ecology, 2013)
We combine kinship estimates with traditional F ‐statistics to explain contemporary drivers of population genetic differentiation despite high gene flow. We investigate range‐wide population genetic structure of the C alifornia spiny (or red rock) lobster ( P anulirus interruptus ) and find slight, but significant global population differentiation in mt DNA (Φ ST = 0.006, P = 0.001; D est_Chao = 0.025) and seven nuclear microsatellites ( F ST = 0.004, P 0.001; D est_Chao = 0.03), despite the species’ 240‐ to 330‐day pelagic larval duration. Significant population structure does not correlate with distance between sampling locations, and pairwise F ST between adjacent sites often exceeds that among geographically distant locations. This result would typically be interpreted as unexplainable, chaotic genetic patchiness. However, kinship levels differ significantly among sites (pseudo‐ F 16,988 = 1.39, P = 0.001), and ten of 17 sample sites have significantly greater numbers of kin than expected by chance ( P 0.05). Moreover, a higher proportion of kin within sites strongly correlates with greater genetic differentiation among sites ( D est_Chao , R 2 = 0.66, P 0.005). Sites with elevated mean kinship were geographically proximate to regions of high upwelling intensity ( R 2 = 0.41, P = 0.0009). These results indicate that P. interruptus does not maintain a single homogenous population, despite extreme dispersal potential. Instead, these lobsters appear to either have substantial localized recruitment or maintain planktonic larval cohesiveness whereby siblings more likely settle together than disperse across sites. More broadly, our results contribute to a growing number of studies showing that low F ST and high family structure across populations can coexist, illuminating the foundations of cryptic genetic patterns and the nature of marine dispersal.

Humans, megafauna and environmental change in tropical Australia - MICHAEL I. BIRD; LINDSAY B. HUTLEY; MICHAEL J. LAWES; JON LLOYD; JON G. LULY; PETER V. RIDD; RICHARD G. ROBERTS; SEAN ULM; CHRISTOPHER M. WURSTER (Journal of Quaternary Science, 2013)
Debate concerning the environmental impact of human arrival in Australia has continued for more than a century. Here we review the evidence for human impact and the mechanisms by which humans may have affected the environment of tropical Australia. We limit our review to tropical Australia because, over three decades ago, it was proposed that the imposition of an anthropogenic fire regime upon human occupation of the Australian continent may have resulted in profound changes in regional vegetation and climate across this region. We conclude that ecological processes and vegetation–fire–climate–human feedbacks do exist that could have driven a significant shift in boundary conditions and ecosystem state at the sub‐continental scale through the sustained imposition of an anthropogenic fire regime over tens of millennia. These potential feedbacks operate through the inhibition of forest expansion both directly, by targeted burning at established forest edges and newly irrupted forest patches, and indirectly, through lengthening of the dry season because of changes to the timing of burning. However, the impact of any such anthropogenic forcing may have been entirely overshadowed by the effects of natural climate change and variability, as well as the generally low nutrient status of Australian soils. A robust assessment of the degree to which the environment of tropical Australia at the large scale has been modified from its ‘natural’ state because of human occupation will require new, coordinated collaborations between indigenous traditional landowners, archaeologists, anthropologists, geochronologists, geoscientists, ecologists, climatologists and modellers.

The Evolutionary Histories of Clinical and Environmental SHV β-Lactamases are Intertwined - Robert L. Dorit; Christopher M. Roy; Sandra M. Robinson; Margaret A. Riley (Journal of Molecular Evolution, 2013)

Simultaneous Analysis of Multiple Monoclonal Antibody Biotherapeutics by LC-MS/MS Method in Rat Plasma Following Cassette-Dosing - Hongyan Li; Robert Ortiz; Linh T. B. Tran; Hossein Salimi-Moosavi; Jennifer Malella; Christopher A. James; Jean W. Lee (The AAPS Journal, 2013)

Blood flow restriction does not result in prolonged decrements in torque - Jeremy P. Loenneke; Robert S. Thiebaud; Christopher A. Fahs; Lindy M. Rossow; Takashi Abe; Michael G. Bemben (European Journal of Applied Physiology, 2013)

Integrin α3β1 regulates tumor cell responses to stromal cells and can function to suppress prostate cancer metastatic colonization - Afshin Varzavand; Justin M. Drake; Robert U. Svensson; Mary E. Herndon; Bo Zhou; Michael D. Henry; Christopher S. Stipp (Clinical & Experimental Metastasis, 2013)

Development of a Chronic Care Ostomy Self-Management Program - Marcia Grant; Ruth McCorkle; Mark C. Hornbrook; Christopher S. Wendel; Robert Krouse (Journal of Cancer Education, 2013)

Sensitivity of Quantified Intracranial Aneurysm Geometry to Imaging Modality - Manasi Ramachandran; Rohini Retarekar; Robert E. Harbaugh; David Hasan; Bruno Policeni; Robert Rosenwasser; Christopher Ogilvy; Madhavan L. Raghavan (Cardiovascular Engineering and Technology, 2013)

Science, policy, and the public discourse of shark “attack”: a proposal for reclassifying human–shark interactions - Christopher Neff; Robert Hueter (Journal of Environmental Studies and Sciences, 2013)

Do increased summer precipitation and N deposition alter fine root dynamics in a M ojave D esert ecosystem? - Paul S. J. Verburg; Andrew C. Young; Bryan A. Stevenson; Isabelle Glanzmann; John A. Arnone; Giles M. Marion; Christopher Holmes; Robert S. Nowak (Global Change Biology, 2013)
Climate change is expected to impact the amount and distribution of precipitation in the arid southwestern U nited S tates. In addition, nitrogen (N) deposition is increasing in these regions due to increased urbanization. Responses of belowground plant activity to increases in soil water content and N have shown inconsistent patterns between biomes. In arid lands, plant productivity is limited by water and N availability so it is expected that changes in these factors will affect fine root dynamics. The objectives of this study were to quantify the effects of increased summer precipitation and N deposition on fine root dynamics in a Mojave Desert ecosystem during a 2‐year field experiment using minirhizotron measurements. Root length density, production, and mortality were measured in field plots in the M ojave D esert receiving three 25 mm summer rain events and/or 40 kg N ha −1 yr −1 . Increased summer precipitation and N additions did not have an overall significant effect on any of the measured root parameters. However, differences in winter precipitation resulting from interannual variability in rainfall appeared to affect root parameters with root production and turnover increasing following a wet winter most likely due to stimulation of annual grasses. In addition, roots were distributed more deeply in the soil following the wet winter. Root length density was initially higher under canopies compared to canopy interspaces, but converged toward the end of the study. In addition, roots tended to be distributed more deeply into the soil in canopy interspace areas. Results from this study indicated that increased summer precipitation and N deposition in response to climate change and urbanization are not likely to affect fine root dynamics in these M ojave D esert ecosystems, despite studies showing aboveground plant physiological responses to these environmental perturbations. However, changes in the amount and possibly distribution of winter precipitation may affect fine root dynamics.

Agonist and antagonist binding to the nuclear vitamin D receptor: dynamics, mutation effects and functional implications - Sepideh Yaghmaei; Christopher Roberts; Rizi Ai; Mathew T Mizwicki; Chia-en A Chang (In Silico Pharmacology, 2013)
Purpose The thermodynamically favored complex between the nuclear vitamin D receptor (VDR) and 1α,25(OH) 2 -vitamin D 3 (1,25D3) triggers a shift in equilibrium to favor VDR binding to DNA, heterodimerization with the nuclear retinoid x receptor (RXR) and subsequent regulation of gene transcription. The key amino acids and structural requirements governing VDR binding to nuclear coactivators (NCoA) are well defined. Yet very little is understood about the internal changes in amino acid flexibility underpinning the control of ligand affinity, helix 12 conformation and function. Herein, we use molecular dynamics (MD) to study how the backbone and side-chain flexibility of the VDR differs when a) complexed to 1α,25(OH) 2 -vitamin D 3 (1,25D3, agonist) and (23S),25-dehydro-1α(OH)-vitamin D 3 -26,23-lactone (MK, antagonist); b) residues that form hydrogen bonds with the C25-OH (H305 and H397) of 1,25D3 are mutated to phenylalanine; c) helix 12 conformation is changed and ligand is removed; and d) x-ray water near the C1- and C3-OH groups of 1,25D3 are present or replaced with explicit solvent. Methods We performed molecular dynamic simulations on the apo- and holo-VDRs and used T-Analyst to monitor the changes in the backbone and side-chain flexibility of residues that form regions of the VDR ligand binding pocket (LBP), NCoA surface and control helix 12 conformation. Results The VDR-1,25D3 and VDR-MK MD simulations demonstrate that 1,25D3 and MK induce highly similar changes in backbone and side-chain flexibility in residues that form the LBP. MK however did increase the backbone and side-chain flexibility of L404 and R274 respectively. MK also induced expansion of the VDR charge clamp (i.e. NCoA surface) and weakened the intramolecular interaction between H305---V418 (helix 12) and TYR401 (helix 11). In VDR_FF, MK induced a generally more rigid LBP and stronger interaction between F397 and F422 than 1,25D3, and reduced the flexibility of the R274 side-chain. Lastly the VDR MD simulations indicate that R274 can sample multiple conformations in the presence of ligand. When the R274 is extended, the β-OH group of 1,25D3 lies proximal to the backbone carbonyl oxygen of R274 and the side-chain forms H-bonds with hinge domain residues. This differs from the x-ray, kinked geometry, where the side-chain forms an H-bond with the 1α-OH group. Furthermore, 1,25D3, but not MK was observed to stabilize the x-ray geometry of R274 during the > 30 ns MD runs. Conclusions The MD methodology applied herein provides an in silico foundation to be expanded upon to better understand the intrinsic flexibility of the VDR and better understand key side-chain and backbone movements involved in the bimolecular interaction between the VDR and its’ ligands.

Relationship between thigh muscle mass and augmented pressure from wave reflections in healthy adults - Jeremy P. Loenneke; Christopher A. Fahs; Kevin S. Heffernan; Lindy M. Rossow; Robert S. Thiebaud; Michael G. Bemben (European Journal of Applied Physiology, 2013)

A genome-wide association study of breast cancer in women of African ancestry - Fang Chen; Gary K. Chen; Daniel O. Stram; Robert C. Millikan; Christine B. Ambrosone; Esther M. John; Leslie Bernstein; Wei Zheng; Julie R. Palmer; Jennifer J. Hu; Tim R. Rebbeck; Regina G. Ziegler; et al. (Human Genetics, 2013)

Relationship between anthropometric factors, radiation exposure, and colon cancer incidence in the Life Span Study cohort of atomic bomb survivors - Erin O. Semmens; Kenneth J. Kopecky; Eric Grant; Robert W. Mathes; Nobuo Nishi; Hiromi Sugiyama; Hiroko Moriwaki; Ritsu Sakata; Midori Soda; Fumiyoshi Kasagi; Michiko Yamada; Saeko Fujiwara; et al. (Cancer Causes & Control, 2013)

Trait-dependent declines of species following conversion of rain forest to oil palm plantations - Michael J. M. Senior; Keith C. Hamer; Simon Bottrell; David P. Edwards; Tom M. Fayle; Jennifer M. Lucey; Peter J. Mayhew; Robert Newton; Kelvin S.-H. Peh; Frederick H. Sheldon; Christopher Stewart; Alison R. Styring; et al. (Biodiversity and Conservation, 2013)

Contaminants in Stream Sediments From Seven United States Metropolitan Areas: Part II—Sediment Toxicity to the Amphipod Hyalella azteca and the Midge Chironomus dilutus - Nile E. Kemble; Douglas K. Hardesty; Christopher G. Ingersoll; James L. Kunz; Paul K. Sibley; Daniel L. Calhoun; Robert J. Gilliom; Kathryn M. Kuivila; Lisa H. Nowell; Patrick W. Moran (Archives of Environmental Contamination and Toxicology, 2013)

Contaminants in Stream Sediments From Seven United States Metropolitan Areas: Part I: Distribution in Relation to Urbanization - Lisa H. Nowell; Patrick W. Moran; Robert J. Gilliom; Daniel L. Calhoun; Christopher G. Ingersoll; Nile E. Kemble; Kathryn M. Kuivila; Patrick J. Phillips (Archives of Environmental Contamination and Toxicology, 2013)

Lipidomic Profiling of Phosphocholine Containing Brain Lipids in Mice with Sensorimotor Deficits and Anxiety-Like Features After Exposure to Gulf War Agents - Laila Abdullah; James E. Evans; Alex Bishop; Jon M. Reed; Gogce Crynen; John Phillips; Robert Pelot; Myles A. Mullan; Austin Ferro; Christopher M. Mullan; Michael J. Mullan; Ghania Ait-Ghezala; et al. (NeuroMolecular Medicine, 2012)

Corneal microprojections in coleoid cephalopods - Christopher Talbot; Thomas M. Jordan; Nicholas W. Roberts; Shaun P. Collin; N. Justin Marshall; Shelby E. Temple (Journal of Comparative Physiology A, 2012)

Extreme weather and experience influence reproduction in an endangered bird - Brian E. Reichert; Christopher E. Cattau; Robert J. Fletcher; William L. Kendall; Wiley M. Kitchens (Ecology, 2012)
Extreme weather events, such as droughts and heat waves, are expected to become more severe and more frequent in the coming years, and understanding their impacts on demographic rates is of increasing interest to both evolutionary ecologists and conservation practitioners. An individual's breeding probability can be a sensitive indicator of the decision to initiate reproductive behavior under varying environmental conditions, has strong fitness consequences, and can be considered the first step in a life history trade‐off between allocating resources for breeding activities or self‐survival. Using a 14‐year time series spanning large variation in climatic conditions and the entirety of a population's breeding range, we estimated the effects of extreme weather conditions (drought) on the state‐specific probabilities of breeding and survival of an endangered bird, the Florida Snail Kite ( Rostrhamus sociabilis plumbeus ). Our analysis accounted for uncertainty in breeding status assignment, a common source of uncertainty that is often ignored when states are based on field observations. Breeding probabilities in adult kites (>1 year of age) decreased during droughts, whereas the probability of breeding in young kites (1 year of age) tended to increase. Individuals attempting to breed showed no evidence of reduced future survival. Although population viability analyses of this species and other species often implicitly assume that all adults will attempt to breed, we find that breeding probabilities were significantly

Detectability of changes to the Atlantic meridional overturning circulation in the Hadley Centre Climate Models - Christopher D. Roberts; Matthew D. Palmer (Climate Dynamics, 2012)

Effects of Mining-Derived Metals on Riffle-Dwelling Crayfish in Southwestern Missouri and Southeastern Kansas, USA - Ann L. Allert; Robert J. DiStefano; Christopher J. Schmitt; James F. Fairchild; William G. Brumbaugh (Archives of Environmental Contamination and Toxicology, 2012)

A physiological trait‐based approach to predicting the responses of species to experimental climate warming - Sarah E. Diamond; Lauren M. Nichols; Neil McCoy; Christopher Hirsch; Shannon L. Pelini; Nathan J. Sanders; Aaron M. Ellison; Nicholas J. Gotelli; Robert R. Dunn (Ecology, 2012)
Physiological tolerance of environmental conditions can influence species‐level responses to climate change. Here, we used species‐specific thermal tolerances to predict the community responses of ant species to experimental forest‐floor warming at the northern and southern boundaries of temperate hardwood forests in eastern North America. We then compared the predictive ability of thermal tolerance vs. correlative species distribution models (SDMs) which are popular forecasting tools for modeling the effects of climate change. Thermal tolerances predicted the responses of 19 ant species to experimental climate warming at the southern site, where environmental conditions are relatively close to the ants' upper thermal limits. In contrast, thermal tolerances did not predict the responses of the six species in the northern site, where environmental conditions are relatively far from the ants' upper thermal limits. Correlative SDMs were not predictive at either site. Our results suggest that, in environments close to a species' physiological limits, physiological trait‐based measurements can successfully forecast the responses of species to future conditions. Although correlative SDMs may predict large‐scale responses, such models may not be accurate for predicting site‐level responses.

Large scale international replication and meta-analysis study confirms association of the 15q14 locus with myopia. The CREAM consortium - Virginie J. M. Verhoeven; Pirro G. Hysi; Seang-Mei Saw; Veronique Vitart; Alireza Mirshahi; Jeremy A. Guggenheim; Mary Frances Cotch; Kenji Yamashiro; Paul N. Baird; David A. Mackey; Robert Wojciechowski; M. Kamran Ikram; et al. (Human Genetics, 2012)

Insight in glioma susceptibility through an analysis of 6p22.3, 12p13.33-12.1, 17q22-23.2 and 18q23 SNP genotypes in familial and non-familial glioma - Yanhong Liu; Beatrice S. Melin; Preetha Rajaraman; Zhaoming Wang; Martha Linet; Sanjay Shete; Christopher I. Amos; Ching C. Lau; Michael E. Scheurer; Spiridon Tsavachidis; Georgina N. Armstrong; Richard S. Houlston; et al. (Human Genetics, 2012)

Using next-generation DNA sequencing for rapid microsatellite discovery in Mexican leaf-toed geckos (Phyllodactylus tuberculosus) - Christopher Blair; Victor H. Jiménez-Arcos; Fausto R. Méndez de la Cruz; Robert W. Murphy (Conservation Genetics Resources, 2012)

On the Shelf Life of Pharmaceutical Products - Robert Capen; David Christopher; Patrick Forenzo; Charles Ireland; Oscar Liu; Svetlana Lyapustina; John O’Neill; Nate Patterson; Michelle Quinlan; Dennis Sandell; James Schwenke; Walter Stroup; et al. (AAPS PharmSciTech, 2012)

Effects of cuff width on arterial occlusion: implications for blood flow restricted exercise - Jeremy P. Loenneke; Christopher A. Fahs; Lindy M. Rossow; Vanessa D. Sherk; Robert S. Thiebaud; Takashi Abe; Debra A. Bemben; Michael G. Bemben (European Journal of Applied Physiology, 2012)

Acoustically Detected Year‐Round Presence of Right Whales in an Urbanized Migration Corridor - JANELLE L. MORANO; AARON N. RICE; JAMEY T. TIELENS; BOBBI J. ESTABROOK; ANITA MURRAY; BETHANY L. ROBERTS; CHRISTOPHER W. CLARK (Conservation Biology, 2012)
Species' conservation relies on understanding their seasonal habitats and migration routes. North Atlantic right whales ( Eubalaena glacialis ), listed as endangered under the U.S. Endangered Species Act, migrate from the southeastern U.S. coast to Cape Cod Bay, Massachusetts, a federally designated critical habitat, from February through May to feed. The whales then continue north across the Gulf of Maine to northern waters (e.g., Bay of Fundy). To enter Cape Cod Bay, right whales must traverse an area of dense shipping and fishing activity in Massachusetts Bay, where there are no mandatory regulations for the protection of right whales or management of their habitat. We used passive acoustic recordings of right whales collected in Massachusetts Bay from May 2007 through October 2010 to determine the annual spatial and temporal distribution of the whales and their calling activity. We detected right whales in the bay throughout the year, in contrast to results from visual surveys. Right whales were detected on at least 24% of days in each month, with the exception of June 2007, in which there were no detections. Averaged over all years, right whale calls were most abundant from February through May. During this period, calls were most frequent between 17:00 and 20:00 local time; no diel pattern was apparent in other months. The spatial distribution of the approximate locations of calling whales suggests they may use Massachusetts Bay as a conduit to Cape Cod Bay in the spring and as they move between the Gulf of Maine and waters to the south in September through December. Although it is unclear how dependent right whales are on the bay, the discovery of their widespread presence in Massachusetts Bay throughout the year suggests this region may need to be managed to reduce the probability of collisions with ships and entanglement in fishing gear .

Algorithm to Assess Cranial Suture Fusion with Varying and Discontinuous Mineral Density - Christopher D. Hermann; Megan A. Richards; Rene Olivares-Navarrete; Joseph K. Williams; Robert E. Guldberg; Oskar Skrinjar; Zvi Schwartz; Barbara D. Boyan (Annals of Biomedical Engineering, 2012)

Chronic traumatic encephalopathy: neurodegeneration following repetitive concussive and subconcussive brain trauma - Christine M. Baugh; Julie M. Stamm; David O. Riley; Brandon E. Gavett; Martha E. Shenton; Alexander Lin; Christopher J. Nowinski; Robert C. Cantu; Ann C. McKee; Robert A. Stern (Brain Imaging and Behavior, 2012)

Sympatric Speciation in the Post “Modern Synthesis” Era of Evolutionary Biology - Christopher E. Bird; Iria Fernandez-Silva; Derek J. Skillings; Robert J. Toonen (Evolutionary Biology, 2012)

Characterisation of nine microsatellite loci in the caecilian amphibian Boulengerula uluguruensis (Gymnophiona), and their cross-species utility in three congeneric species - Christopher D. Barratt; Gavin J. Horsburgh; Deborah A. Dawson; David J. Gower; Mark Wilkinson; Simon P. Loader; Robert Jehle (Conservation Genetics Resources, 2012)

Scaling up from epidemiology to biogeography: local infection patterns predict geographical distribution in fish parasites - Robert Poulin; Christopher A. Blanar; David W. Thieltges; David J. Marcogliese (Journal of Biogeography, 2012)
Aim We investigated how the spatial distribution of parasites, measured as either their geographical range size or their frequency of occurrence among localities, relates to either their average local abundance or the variance in their abundance among localities where they occur. Location We used data on the abundance of 46 metazoan parasite species in 66 populations of threespine sticklebacks, Gasterosteus aculeatus , from Europe and North America. Methods For each parasite species, frequency of occurrence was calculated as the proportion of stickleback populations in which it occurred, and geographical range size as the area within the smallest possible polygon delimited using the coordinates of the localities where it occurred. Generalized linear models were used to assess how these two measures of spatial distribution were influenced by several predictor variables: geographical region (North America or Europe), life cycle (simple or complex), average local abundance, the coefficient of variation in abundance across localities, and median prevalence (proportion of infected hosts within a locality). Results Our analyses uncovered four patterns. First, parasites in North America tend to have higher frequencies of occurrence among surveyed localities, but not broader geographical ranges, than those in Europe. Second, parasite species with simple life cycles have wider geographical ranges than those with complex cycles. Third, there was a positive relationship between average abundance of the different parasite species and their frequency of occurrence, but not between average abundance and geographical range size. Fourth, the coefficient of variation in abundance covaried positively with both the frequency of occurrence and geographical range size across the different parasite species. Thus, all else being equal, parasites showing greater site‐to‐site variability in abundance occur in a greater proportion of localities and over a broader geographical area than those with a more stable abundance among sites. Main conclusions Local infection patterns are linked with large‐scale distributional patterns in fish parasites, independently of host effects, such that local commonness translates into regional commonness. The mechanisms linking parasite success at both scales remain unclear, but may include those that maintain the continuum between specialist and generalist parasites. Regardless, the observed patterns have implications for the predicted changes in the geographical distributions of many parasites in response to climate change.

Terrestrial biosphere model performance for inter‐annual variability of land‐atmosphere CO 2 exchange - T.F. Keenan; Ian Baker; Alan Barr; Philippe Ciais; Ken Davis; Michael Dietze; Danillo Dragoni; Christopher M Gough; Robert Grant; David Hollinger; Koen Hufkens; Ben Poulter; et al. (Global Change Biology, 2012)
Interannual variability in biosphere‐atmosphere exchange of CO 2 is driven by a diverse range of biotic and abiotic factors. Replicating this variability thus represents the ‘acid test’ for terrestrial biosphere models. Although such models are commonly used to project responses to both normal and anomalous variability in climate, they are rarely tested explicitly against inter‐annual variability in observations. Herein, using standardized data from the N orth A merican Carbon Program, we assess the performance of 16 terrestrial biosphere models and 3 remote sensing products against long‐term measurements of biosphere‐atmosphere CO 2 exchange made with eddy‐covariance flux towers at 11 forested sites in N orth A merica. Instead of focusing on model‐data agreement we take a systematic, variability‐oriented approach and show that although the models tend to reproduce the mean magnitude of the observed annual flux variability, they fail to reproduce the timing. Large biases in modeled annual means are evident for all models. Observed interannual variability is found to commonly be on the order of magnitude of the mean fluxes. None of the models consistently reproduce observed interannual variability within measurement uncertainty. Underrepresentation of variability in spring phenology, soil thaw and snowpack melting, and difficulties in reproducing the lagged response to extreme climatic events are identified as systematic errors, common to all models included in this study.

Estrogen-related genes and their contribution to racial differences in breast cancer risk - Kerryn W. Reding; Chu Chen; Kimberly Lowe; David R. Doody; Christopher S. Carlson; Christina T. Chen; John Houck; Linda K. Weiss; Polly A. Marchbanks; Leslie Bernstein; Robert Spirtas; Jill A. McDonald; et al. (Cancer Causes & Control, 2012)

Common bacterial responses in six ecosystems exposed to 10 years of elevated atmospheric carbon dioxide - John Dunbar; Stephanie A. Eichorst; La Verne Gallegos‐Graves; Shannon Silva; Gary Xie; N. W. Hengartner; R. David Evans; Bruce A. Hungate; Robert B. Jackson; J. Patrick Megonigal; Christopher W. Schadt; Rytas Vilgalys; et al. (Environmental Microbiology, 2012)
Summary Six terrestrial ecosystems in the USA were exposed to elevated atmospheric CO 2 in single or multifactorial experiments for more than a decade to assess potential impacts. We retrospectively assessed soil bacterial community responses in all six‐field experiments and found ecosystem‐specific and common patterns of soil bacterial community response to elevated CO 2 . Soil bacterial composition differed greatly across the six ecosystems. No common effect of elevated atmospheric CO 2 on bacterial biomass, richness and community composition across all of the ecosystems was identified, although significant responses were detected in individual ecosystems. The most striking common trend across the sites was a decrease of up to 3.5‐fold in the relative abundance of Acidobacteria Group 1 bacteria in soils exposed to elevated CO 2 or other climate factors. The Acidobacteria Group 1 response observed in exploratory 16S rRNA gene clone library surveys was validated in one ecosystem by 100‐fold deeper sequencing and semi‐quantitative PCR assays. Collectively, the 16S rRNA gene sequencing approach revealed influences of elevated CO 2 on multiple ecosystems. Although few common trends across the ecosystems were detected in the small surveys, the trends may be harbingers of more substantive changes in less abundant, more sensitive taxa that can only be detected by deeper surveys.

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

Marine dispersal as a pre‐requisite for Gondwanan vicariance among elements of the galaxiid fish fauna - Christopher P. Burridge; Robert M. McDowall; Dave Craw; Mark V. H. Wilson; Jonathan M. Waters (Journal of Biogeography, 2012)
Aim The aim of this study was to determine the contributions of Gondwanan vicariance and marine dispersal to the contemporary distribution of galaxiid fishes. This group has been central in arguments concerning the roles of dispersal and vicariance in the Southern Hemisphere, as some taxa have marine life history stages through which transoceanic dispersal may have been facilitated, yet other galaxiids are entirely restricted to freshwaters. Location Southern Hemisphere land masses of Gondwanan derivation. Methods Biogeographic hypotheses of Gondwanan vicariance and marine dispersal were tested using four lines of evidence: (1) concordance of species–area phylogenetic relationships, (2) molecular estimates of lineage divergence times with a priori expectations based on plate tectonics, (3) reconstructions of ancestral dispersal capabilities, and (4) reconstructions of distribution inheritance scenarios (using the dispersal–extinction–cladogenesis model to infer historical ranges and dispersal and extinction events). Results Phylogenetic relationships were reconstructed from 4531 mitochondrial and nuclear nucleotide characters, and 181 morphological characters, across 53 of the 56 presently recognized species. Phylogenetic relationships were generally well resolved and supported among galaxiids using the combined dataset, and conflicting relationships between molecular and morphological datasets typically received low topological support from either or both datasets. Transoceanic disjunctions were exhibited at 16 nodes, but only three pre‐dated relevant continental fragmentation events; furthermore, ancestral distribution inheritance scenarios for two of these nodes reflected cladogenesis within, rather than between, Gondwanan land masses, and ancestral marine dispersal capability could not be rejected for all three. Instead, the four lines of evidence surveyed suggest that Gondwanan vicariance occurred twice, but in both instances was preceded by marine dispersal between land masses, and in at least one instance was initiated by the cessation of marine dispersal subsequent to continental fragmentation. Main conclusions Gondwanan vicariance appears to have been preceded by marine dispersal in the few instances where it may explain contemporary galaxiid distribution, such that these biogeographic mechanisms may sometimes have a synergistic relationship.

Terrestrial biosphere models need better representation of vegetation phenology: results from the N orth A merican C arbon P rogram S ite S ynthesis - Andrew D. Richardson; Ryan S. Anderson; M. Altaf Arain; Alan G. Barr; Gil Bohrer; Guangsheng Chen; Jing M. Chen; Philippe Ciais; Kenneth J. Davis; Ankur R. Desai; Michael C. Dietze; Danilo Dragoni; et al. (Global Change Biology, 2012)
Phenology, by controlling the seasonal activity of vegetation on the land surface, plays a fundamental role in regulating photosynthesis and other ecosystem processes, as well as competitive interactions and feedbacks to the climate system. We conducted an analysis to evaluate the representation of phenology, and the associated seasonality of ecosystem‐scale CO 2 exchange, in 14 models participating in the N orth A merican C arbon P rogram S ite S ynthesis. Model predictions were evaluated using long‐term measurements (emphasizing the period 2000–2006) from 10 forested sites within the A meri F lux and F luxnet‐ C anada networks. In deciduous forests, almost all models consistently predicted that the growing season started earlier, and ended later, than was actually observed; biases of 2 weeks or more were typical. For these sites, most models were also unable to explain more than a small fraction of the observed interannual variability in phenological transition dates. Finally, for deciduous forests, misrepresentation of the seasonal cycle resulted in over‐prediction of gross ecosystem photosynthesis by +160 ± 145 g C m −2 yr −1 during the spring transition period and +75 ± 130 g C m −2 yr −1 during the autumn transition period (13% and 8% annual productivity, respectively) compensating for the tendency of most models to under‐predict the magnitude of peak summertime photosynthetic rates. Models did a better job of predicting the seasonality of CO 2 exchange for evergreen forests. These results highlight the need for improved understanding of the environmental controls on vegetation phenology and incorporation of this knowledge into better phenological models. Existing models are unlikely to predict future responses of phenology to climate change accurately and therefore will misrepresent the seasonality and interannual variability of key biosphere–atmosphere feedbacks and interactions in coupled global climate models.

Who likes it hot? A global analysis of the climatic, ecological, and evolutionary determinants of warming tolerance in ants - Sarah E. Diamond; D. Magdalena Sorger; Jiri Hulcr; Shannon L. Pelini; Israel Del Toro; Christopher Hirsch; Erik Oberg; Robert R. Dunn (Global Change Biology, 2012)
Effects of climate warming on wild populations of organisms are expected to be greatest at higher latitudes, paralleling greater anticipated increases in temperature in these regions. Yet, these expectations assume that populations in different regions are equally susceptible to the effects of warming. This is unlikely to be the case. Here, we develop a series of predictive models for physiological thermal tolerances in ants based on current and future climates. We found that tropical ants have lower warming tolerances, a metric of susceptibility to climate warming, than temperate ants despite greater increases in temperature at higher latitudes. Using climatic, ecological and phylogenetic data, we refine our predictions of which ants (across all regions) were most susceptible to climate warming. We found that ants occupying warmer and more mesic forested habitats at lower elevations are the most physiologically susceptible to deleterious effects of climate warming. Phylogenetic history was also a strong indicator of physiological susceptibility. In short, we find that ants that live in the canopies of hot, tropical forest are the most at risk, globally, from climate warming. Unfortunately this is where many, perhaps most, ant and other species on Earth live.

Predicting Species Distributions from Samples Collected along Roadsides - KYLE P. MCCARTHY; ROBERT J. FLETCHER JR; CHRISTOPHER T. ROTA; RICHARD L. HUTTO (Conservation Biology, 2012)
Predictive models of species distributions are typically developed with data collected along roads. Roadside sampling may provide a biased (nonrandom) sample; however, it is currently unknown whether roadside sampling limits the accuracy of predictions generated by species distribution models. We tested whether roadside sampling affects the accuracy of predictions generated by species distribution models by using a prospective sampling strategy designed specifically to address this issue. We built models from roadside data and validated model predictions at paired locations on unpaved roads and 200 m away from roads (off road), spatially and temporally independent from the data used for model building. We predicted species distributions of 15 bird species on the basis of point‐count data from a landbird monitoring program in Montana and Idaho (U.S.A.). We used hierarchical occupancy models to account for imperfect detection. We expected predictions of species distributions derived from roadside‐sampling data would be less accurate when validated with data from off‐road sampling than when it was validated with data from roadside sampling and that model accuracy would be differentially affected by whether species were generalists, associated with edges, or associated with interior forest. Model performance measures (kappa, area under the curve of a receiver operating characteristic plot, and true skill statistic) did not differ between model predictions of roadside and off‐road distributions of species. Furthermore, performance measures did not differ among edge, generalist, and interior species, despite a difference in vegetation structure along roadsides and off road and that 2 of the 15 species were more likely to occur along roadsides. If the range of environmental gradients is surveyed in roadside‐sampling efforts, our results suggest that surveys along unpaved roads can be a valuable, unbiased source of information for species distribution models.

Positive and negative impacts of plants on acid production in exposed acid sulphate soils - Robert J. Reid; Christopher S. Butcher (Plant and Soil, 2011)

MicroRNA-101 Inhibits Growth of Epithelial Ovarian Cancer by Relieving Chromatin-Mediated Transcriptional Repression of p21waf1/cip1 - Assaad Semaan; Aamer M. Qazi; Shelly Seward; Sreedhar Chamala; Christopher S. Bryant; Sanjeev Kumar; Robert Morris; Christopher P. Steffes; David L. Bouwman; Adnan R Munkarah; Donald W. Weaver; Scott A. Gruber; et al. (Pharmaceutical Research, 2011)

Forest Management, Engineering, and Operations / Global Competency and Issues in Contemporary Education - Finto Antony; Lewis Jordan; Laurie Schimleck; Richard Daniels; Rapeepan Kantavichai; Lara Hansen; Jessica Hitt; William Hubbard; Gwendolyn Boyd; Ryan Boyles; Heather Dinon; Joshua Idassi; et al. (Journal of Forestry, 2011)
31Maps depicting spatial variation in wood properties are important for forest product industries as they aid decision making regarding raw material procurement, can assist in product categorization and help improve utilization. Loblolly pine is an important commercial species grown throughout the southern Unites States of America (USA). Wood Quality Consortium (WQC)—a joint collaboration between the University of Georgia, USDA Forest Service and industries—was established in 1999 with the objective of characterizing wood property variation of plantation grown loblolly pine. Data on wood specific gravity (SG), modulus of elasticity (MOE) and modulus of rupture (MOR) collected by the WQC was utilized in this study. Maps showing spatial variation in SG at different stand ages and SG, MOE and MOR at different heights within a tree were developed using appropriate spatial prediction methods (kriging). The geographical variation of these wood properties across southeastern USA was demonstrated here.

The Business of Forest Enterprise / Urban Ecosystems / Forest Policy / Biosecurity - David Nicholls; Allen Brackley; Charles Keegan; Colin Sorenson; Jean Daniels; Erik Berg; Charles Gale; Robert Campbell; Charles Gale; Charles Keegan; Erik Berg; Colin Sorenson; et al. (Journal of Forestry, 2011)
172Business clusters are geographic concentrations of companies that provide mutual advantages for their participants. Clusters can include diverse members including competitors, customers, partners, and/or suppliers. In Alaska, wood products business clusters can have unique challenges associated with remote locations, high raw material costs, limited local markets, and potentially long transportation distances. Further, multiple land ownership near communities (for example state versus federal ownership) can influence raw material procurement, since different administrative processes for timber harvesting may be required. This study evaluates 2 resource dependent communities in southeast Alaska (Haines, AK and Craig, AK), seeking to identify elements that could enhance their potential for wood products clusters and new business formation. We consider how the flow of forest resources, from harvest to finished product, can influence local communities and either enhance or limit opportunities for wood products businesses. We evaluate the effect of various product mixes—including firewood, woody residues, house logs, lumber, and secondary wood products—on the composition, scale, and dynamics of wood products firms. We consider the effect of harvesting practices and proximity to timber sales in evaluating how land ownership can influence the viability of wood products clusters. Lastly we consider the impact of transportation costs on serving local and export markets. Our research builds upon past work in Alaska that evaluated national-forest based communities in Alaska, finding opportunities for greater innovation, higher productivity, and greater social well-being associated with wood products clusters.

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Forest Management, Engineering, and Operations - Randy Kolka; Matt Powers; John Bradford; Brian Palik; Marty Jurgensen; Dalia Abbas; Tom Gallagher; Stephen Ambagis; Finto Antony; Lewis Jordan; Richard Daniels; Laurie Schimleck; et al. (Journal of Forestry, 2011)
9Forests represent a major global C sink, and forest management strategies that maximize carbon storage offer one avenue for mitigating increases in atmospheric carbon dioxide concentrations. Our understanding of relationships between forest management, productivity, carbon storage, and stand age, however, is limited. We established research plots in a chronosequence of thinned and unmanaged red pine stands in northern Minnesota to study patterns of carbon storage, and the major fluxes that influence carbon sequestration. We completed an inventory of all major C pools across a chronosequence of 57 red pine stands ages 9-306 years on the Chippewa National Forest in the fall of 2009. Results indicate total ecosystem C pools increase as red pine stands age for at least 150 years, and on-site C storage in thinned stands appears similar to unmanaged stands of comparable ages, despite different age-related trends in the live tree and forest floor pools. Thinned stands may have the potential to store more C than unmanaged stands in old age when C removed during harvesting is added into the total ecosystem C pool.

Consulting Forestry / Certification and Ecosystem Services - James Coufal; Carl Wiedemann; Jacob Gorman; Larry Teeter; Yaoqi Zhang; Michael Kilgore; Kristell Miller; Stephanie Snyder; Sun Chang; Miriam Davis; Stanley Asah; J. Mark Fly; et al. (Journal of Forestry, 2011)
45The industrialization of the United States throughout the 19th century resulted in the exploitation of millions of acres of timberland across the country. Logging during that era was described by critics as “cut out and get out” because the land was usually abandoned after the merchantable timber was exhausted. Concern about future timber supplies and the effect of logging on watersheds spurred the development of professional forestry after the Civil War. The first forestry leaders, including Bernhard Fernow and Gifford Pinchot, encouraged private non-industrial forest owners to sustainably manage their woodlands and specifically warned against destructive logging practices—including “cutting the best and leaving the rest”—aka high-grading. During the 1920s and 30s both the Forest Service and SAF spurred initiatives to encourage sustainable timber harvesting practices on private forestland. Although great progress has been made in forest management, logging on most private non-industrial forest land in the east has not changed significantly since the 19th century. Landowners usually sell timber without using the services of a forester, allowing the buyer to selectively cut the most valuable trees in the woodlot. Although this can reduce future value by 70-90%, it remains common practice because both the landowner and the timber buyer maximize short term income. The timber value and productivity of millions of acres of woodland throughout the United States have been significantly degraded as a result. This paper will trace the history of high-grading as described by forestry leaders from the 19th century through the 21st and will show that much work remains unfinished.

Forest Policy / Biosecurity - Linda Heath; Clark Row; Robert Perschel; Douglas Boucher; Patricia Elias; Katherine Lininger; Calen May-Tobin; Earl Saxon; Steven Ruddell; Sally Collins; Sarah Ruddell; Mo Zhou; et al. (Journal of Forestry, 2011)
7Massive fires in Indonesian peatlands in the 1990s and in eastern Russian peatlands in 2002 and last year have highlighted the need to manage forests overlying peat deposits, as well as converted peat forests and open peatlands. Peat or peaty soils, contain 65% or more of partially decayed vegetation, can burn freely or underground. They cover some 10 percent of worldwide forests and contain 25 percent of all terrestrial carbon. Recent massive greenhouse gas (GHG) emissions from fires in forested peat and peatland in Indonesia and in Russia highlight the need for policies to reduce GHG emissions. We discuss major peatland areas and quantify their carbon stocks and potential GHG emissions. Trends show that year-to-year emissions are variable, with huge pulses that are a significant share of global GHG emissions. We group suggested policy options into three approaches. The first approach, which will reduce peat-related product demand, includes a) restricting peat, and products produced on cleared forested peatland, from being labeled or counted in GHG reduction achievements, as renewable (which palm oil currently is considered); b) developing full substitutes for horticultural peat (comprising about half mined peat use); and c) developing renewable power in countries still dependent on peat for power generation. These options reduce the rate of developing newly mined peat/forest areas. Options for a second approach, which treat already drained and cleared forested peatlands, are: d) restoring functioning peat ecosystems by closing drainage ditches, allowing natural rewetting, and “seeding” with peat vegetation fragments, e) requiring current peat operators to restore mined areas right after all peat is removed, and f) converting them to other land uses, despite the acidic conditions of mined peat bogs. These options sharply reduce risks of peat fires. Finally, a third group of policy options reduces ignition risks and limit fire spread: g) developing monitoring, suppression techniques, h) organizing local landowner protection groups and i) improving public fire organizations.

Human Dimensions / Recreation and Ecotourism - Rachel Billingham; Marissa Jo Daniel; Francisco Aguilar; Hank Stelzer; Guy Robertson; Stanley Asah; Michelle King; Angela Gupta; Samatha Grant; Christopher Jones; Melanie Lenart; Richard Tholen; et al. (Journal of Forestry, 2011)
8With the current state of the economy and the budget woes found in everyone's workplace, every extra dollar we can use to offset the cost of projects counts—and what if those extra dollars came with public relations opportunities at no cost to you? For the last several years, the Pennsylvania Bureau of Forestry has cultivated relationships with a variety of non-traditional partners. These relationships have not only provided additional funds for tree planting projects through our TreeVitalize program, but have also provided fantastic public relations exposure and access to new audiences. Come hear how we used a “win-win” approach with our new partners and be inspired to try some of these ideas in your “neck of the woods.”

The Business of Forest Enterprise / Urban Ecosystems - Steve Narolski; Richard Bin Mei; Rafael De La Torre; Mike Clutter; John Pait; Maggi Kelly; Frederick Cubbage; Patricio MacDonagh; Gustavo Balmelli; Virginia Morales Olmos; Adriana Bussoni; Rafael Rubilar; et al. (Journal of Forestry, 2011)
22In 2009, five unique methods were used to inspect vegetation-related conditions along Bonneville Power Administration (BPA) rights-of-way (ROW). Some methods were trials that BPA committed to execute as part of a settlement with its regional regulatory organization, the Western Electric Coordination Council (WECC), for violations of reliability standards from vegetation grow-in related outages. A combination of simple, stratified, and 100% sampling were used to compare and contrast each inspection technique. A cost-replacement comparison between all inspection techniques was performed, weighting efficacy of one technique to another in the form of replacement value. Cost-benefit and return-on-investment analyses were also computed. From these analyses, LiDAR proved most effective in identifying vegetation related clearance issues but proved most costly, at least for initial establishment. The average cost of LiDAR trended downward with subsequent flights. The most cost effective method was using helicopters with either Natural Resource Specialists (NRS) or Transmission Line Maintenance (TLM) personnel serving as aerial observers, but this methodology proved the most inaccurate. Furthermore, the ancillary utility of LiDAR for related asset assessments more than justify the initial expense, includes power line sag ratings, asset (structures, insulators, roads, etc.) health, and encroachment identification. It is hypothesized that incorporating LiDAR sampling from 20% of the whole system per year to 40+ % may actually represent a cost-savings when allocating available resources system-wide. This data can also be used for documenting compliance with all federal regulations and requirements, as well as substitute for manual on-the-ground inspections, whether by BPA staff or third-party contractors.

Expansion of human mesenchymal stem cells on microcarriers - Christopher J. Hewitt; Ken Lee; Alvin W. Nienow; Robert J. Thomas; Mark Smith; Colin R. Thomas (Biotechnology Letters, 2011)

Spatial gradients of methylmercury for breeding common loons in the Laurentian Great Lakes region - David C. Evers; Kathryn A. Williams; Michael W. Meyer; Anton M. Scheuhammer; Nina Schoch; Andrew T. Gilbert; Lori Siegel; Robert J. Taylor; Robert Poppenga; Christopher R. Perkins (Ecotoxicology, 2011)

The association between height and prostate cancer grade in the Early Stage Prostate Cancer Cohort Study - Wildon R. Farwell; Christopher Lourenco; Erika Holmberg; Robert B. Hall; Leonard D’Avolio; Elizabeth V. Lawler; J. Michael Gaziano (Cancer Causes & Control, 2011)

Cross-Spectrum of Wind Speed for Meso-Gamma Scales in the Upper Surface Layer over South-Eastern Australia - Milton J. Woods; Robert J. Davy; Christopher J. Russell; Peter A. Coppin (Boundary-Layer Meteorology, 2011)

Responses of soil cellulolytic fungal communities to elevated atmospheric CO 2 are complex and variable across five ecosystems - Carolyn F. Weber; Donald R. Zak; Bruce A. Hungate; Robert B. Jackson; Rytas Vilgalys; R. David Evans; Christopher W. Schadt; J. Patrick Megonigal; Cheryl R. Kuske (Environmental Microbiology, 2011)
Summary Elevated atmospheric CO 2 generally increases plant productivity and subsequently increases the availability of cellulose in soil to microbial decomposers. As key cellulose degraders, soil fungi are likely to be one of the most impacted and responsive microbial groups to elevated atmospheric CO 2 . To investigate the impacts of ecosystem type and elevated atmospheric CO 2 on cellulolytic fungal communities, we sequenced 10 677 cbhI gene fragments encoding the catalytic subunit of cellobiohydrolase I, across five distinct terrestrial ecosystem experiments after a decade of exposure to elevated CO 2 . The cbhI composition of each ecosystem was distinct, as supported by weighted Unifrac analyses (all P ‐values; cbhI sequence database compiled from known fungi, less than 1% of the environmental sequences could be classified at the family level indicating that cellulolytic fungi in situ are likely dominated by novel fungi or known fungi that are not yet recognized as cellulose degraders. Shifts in fungal cbhI composition and richness that were correlated with elevated CO 2 exposure varied across the ecosystems. In aspen plantation and desert creosote bush soils, cbhI gene richness was significantly higher after exposure to elevated CO 2 (550 µmol mol −1 ) than under ambient CO 2 (360 µmol mol −1 CO 2 ). In contrast, while the richness was not altered, the relative abundance of dominant OTUs in desert soil crusts was significantly shifted. This suggests that responses are complex, vary across different ecosystems and, in at least one case, are OTU‐specific. Collectively, our results document the complexity of cellulolytic fungal communities in multiple terrestrial ecosystems and the variability of their responses to long‐term exposure to elevated atmospheric CO 2 .

On the utility of identification schemes for digital earth science data: an assessment and recommendations - Ruth E. Duerr; Robert R. Downs; Curt Tilmes; Bruce Barkstrom; W. Christopher Lenhardt; Joseph Glassy; Luis E. Bermudez; Peter Slaughter (Earth Science Informatics, 2011)

Effects of transforming growth factor-beta (TGF-β1) on satellite cell activation and survival during oxidative stress - Christopher R. Rathbone; Keitaro Yamanouchi; Xiaoyu K. Chen; Cedrine J. Nevoret-Bell; Robert P. Rhoads; Ronald E. Allen (Journal of Muscle Research and Cell Motility, 2011)

Taxonomical developments in the family Polyomaviridae - Reimar Johne; Christopher B. Buck; Tobias Allander; Walter J. Atwood; Robert L. Garcea; Michael J. Imperiale; Eugene O. Major; Torbjorn Ramqvist; Leonard C. Norkin (Archives of Virology, 2011)

A 20-Year Hydroacoustic Time Series of Seismic and Volcanic Events in the Northeast Pacific Ocean - Robert Dziak; Stephen Hammond; Christopher Fox (Oceanography, 2011)

Complex interactions between marine sponges and their symbiotic microbial communities - Christopher J. Freeman; Robert W. Thacker (Limnology and Oceanography, 2011)
To investigate the importance of symbiont‐derived nutrition to host sponges, we coupled manipulative shading experiments with stable isotope analyses of isolated symbiont and host cell fractions. Experiments were conducted with four common reef sponges: Aplysina cauliformis , A. fulva , Neopetrosia subtriangularis , and Niphates erecta . The sponge N. erecta lacks photosymbionts, had a higher growth rate under shaded conditions, and displayed no difference in chlorophyll a (Chl a ) concentrations across treatments. Isotope values suggested that this sponge obtains nutrition from particulate organic matter in the water column. In contrast, sponges hosting cyanobacterial symbionts ( Aplysina spp. and Neopetrosia ) had lower growth rates and lower Chl a concentrations under shaded conditions, suggesting that these hosts rely on photosymbiont nutrition. δ 15 N and δ 13 C values of sponge and microbial cell fractions demonstrated that, while both carbon and nitrogen are transferred from symbionts to host cells in A. cauliformis , only carbon is transferred in N. subtriangularis , and only nitrogen is transferred in A. fulva . Under shaded conditions, shifts in symbiont δ 13 C values were coupled to shifts in host δ 13 C values in some, but not all, host species, suggesting that the stability of these interactions varies across host species. Symbiont‐derived nutrients are transferred to the cells of host sponges, and the variability observed among host species indicates that these interactions are more complex than originally hypothesized.

Prediction of oxygen uptake during over-ground walking in people with and without Down syndrome - Stamatis Agiovlasitis; Robert W. Motl; Sushant M. Ranadive; Christopher A. Fahs; Huimin Yan; George H. Echols; Lindy Rossow; Bo Fernhall (European Journal of Applied Physiology, 2011)

Candida northwykensis sp. nov., A Novel Yeast Isolated from the Gut of the Click Beetle Melanotus villosus - Sreenivas Rao Ravella; Neil Donovan; Stephen A. James; Sisinthy Shivaji; Kotakonda Arunasri; Christopher J. Bond; Ian N. Roberts; Phil J. Hobbs (Current Microbiology, 2011)

Hemodynamic Changes Quantified in Abdominal Aortic Aneurysms with Increasing Exercise Intensity Using MR Exercise Imaging and Image-Based Computational Fluid Dynamics - Ga-Young Suh; Andrea S. Les; Adam S. Tenforde; Shawn C. Shadden; Ryan L. Spilker; Janice J. Yeung; Christopher P. Cheng; Robert J. Herfkens; Ronald L. Dalman; Charles A. Taylor (Annals of Biomedical Engineering, 2011)

Proteome changes in the initial bacterial colonist during ecological succession in an acid mine drainage biofilm community - Ryan S. Mueller; Brian D. Dill; Chongle Pan; Christopher P. Belnap; Brian C. Thomas; Nathan C. VerBerkmoes; Robert L. Hettich; Jillian F. Banfield (Environmental Microbiology, 2011)
Summary Proteomes of acid mine drainage biofilms at different stages of ecological succession were examined to understand microbial responses to changing community membership. We evaluated the degree of reproducibility of the community proteomes between samples of the same growth stage and found stable and predictable protein abundance patterns across time and sampling space, allowing for a set of 50 classifier proteins to be identified for use in predicting growth stages of undefined communities. Additionally, physiological changes in the dominant species, Leptospirillum Group II, were analysed as biofilms mature. During early growth stages, this population responds to abiotic stresses related to growth on the acid mine drainage solution. Enzymes involved in protein synthesis, cell division and utilization of 1‐ and 2‐carbon compounds were more abundant in early growth stages, suggesting rapid growth and a reorganization of metabolism during biofilm initiation. As biofilms thicken and diversify, external stresses arise from competition for dwindling resources, which may inhibit cell division of Leptospirillum Group II through the SOS response. This population also represses translation and synthesizes more complex carbohydrates and amino acids in mature biofilms. These findings provide unprecedented insight into the physiological changes that may result from competitive interactions within communities in natural environments.

Mapping Fusarium wilt race 1 resistance genes in cotton by inheritance, QTL and sequencing composition - Mauricio Ulloa; Congli Wang; Robert B. Hutmacher; Steven D. Wright; R. Michael Davis; Christopher A. Saski; Philip A. Roberts (Molecular Genetics and Genomics, 2011)

Preclinical strategies to define predictive biomarkers for therapeutically relevant cancer subtypes - Marina Pajic; Christopher J. Scarlett; David K. Chang; Robert L. Sutherland; Andrew V. Biankin (Human Genetics, 2011)

Lack of GNAQ germline mutations in uveal melanoma patients with high risk for hereditary cancer predisposition - Mohamed H. Abdel-Rahman; Robert Pilarski; James B. Massengill; Benjamin B. Christopher; Frederick H. Davidorf (Familial Cancer, 2011)

Quantitative trait loci analysis for resistance to Cephalosporium stripe, a vascular wilt disease of wheat - Martin C. Quincke; C. James Peterson; Robert S. Zemetra; Jennifer L. Hansen; Jianli Chen; Oscar Riera-Lizarazu; Christopher C. Mundt (Theoretical and Applied Genetics, 2011)

Assessment of the economic viability of goat management systems in Goma Sub County and Mukono Town Council in Mukono District, Uganda - Robert Mwebe; Francis Ejobi; Christopher Dennis Laker (Tropical Animal Health and Production, 2011)

Variation in folate pathway genes and distal colorectal adenoma risk: a sigmoidoscopy-based case–control study - A. Joan Levine; Won Lee; Jane C. Figueiredo; David V. Conti; David J. Vandenberg; Brian D. Davis; Christopher K. Edlund; Susanne M. Henning; David Heber; Mariana C. Stern; Robert W. Haile (Cancer Causes & Control, 2011)

Quantification of Particle Residence Time in Abdominal Aortic Aneurysms Using Magnetic Resonance Imaging and Computational Fluid Dynamics - Ga-Young Suh; Andrea S. Les; Adam S. Tenforde; Shawn C. Shadden; Ryan L. Spilker; Janice J. Yeung; Christopher P. Cheng; Robert J. Herfkens; Ronald L. Dalman; Charles A. Taylor (Annals of Biomedical Engineering, 2011)

Determination of environmental impacts of antimicrobial usage for US Northern Great Plains swine-production facilities: a life-cycle assessment approach - James J. Stone; Katherine R. Aurand; Christopher R. Dollarhide; Ramith Jinka; Robert C. Thaler; David E. Clay; Sharon A. Clay (The International Journal of Life Cycle Assessment, 2011)

Positive effects of ectomycorrhizal colonization on growth of seedlings of a tropical tree across a range of forest floor light conditions - Philippe Saner; Christopher Philipson; Robert C. Ong; Noreen Majalap; Simon Egli; Andy Hector (Plant and Soil, 2011)

Hydrologic and nutrient dynamics of a coastal bay and wetland receiving discharge from the Atchafalaya River - Robert R. Lane; Christopher J. Madden; John W. Day; Darrell J. Solet (Hydrobiologia, 2011)

Salinity and Chlorophyll a as Performance Measures to Rehabilitate a Mangrove-Dominated Deltaic Coastal Region: the Ciénaga Grande de Santa Marta–Pajarales Lagoon Complex, Colombia - Victor H. Rivera-Monroy; Robert R. Twilley; J. Ernesto Mancera-Pineda; Christopher J. Madden; Ariel Alcantara-Eguren; E. Barry Moser; Bror F. Jonsson; Edward Castañeda-Moya; Oscar Casas-Monroy; Paola Reyes-Forero; Jorge Restrepo (Estuaries and Coasts, 2011)

Ligand-Binding Mass Spectrometry to Study Biotransformation of Fusion Protein Drugs and Guide Immunoassay Development: Strategic Approach and Application to Peptibodies Targeting the Thrombopoietin Receptor - Michael P. Hall; Colin Gegg; Kenneth Walker; Christopher Spahr; Robert Ortiz; Vimal Patel; Steven Yu; Liana Zhang; Hsieng Lu; Binodh DeSilva; Jean W. Lee (The AAPS Journal, 2010)

Holocene climatic fluctuations and positioning of the Southern Hemisphere westerlies in Tierra del Fuego (54° S), Patagonia - Nicolas Waldmann; Daniel Ariztegui; Flavio S. Anselmetti; James A. Austin; Christopher M. Moy; Charles Stern; Cristina Recasens; Robert B. Dunbar (Journal of Quaternary Science, 2010)
Recent advances in the chronology and the palaeoclimatic understanding of Antarctic ice core records point towards a larger heterogeneity of latitudinal climate fluctuations than previously thought. Thus, realistic palaeoclimate reconstructions rely in the development of a tight array of well‐constrained records with a dense latitudinal coverage. Climatic records from southernmost South America are critical cornerstones to link these Antarctic palaeoclimatic archives with their South American counterparts. At 54° S on the Island of Tierra del Fuego, Lago Fagnano is located in one of the most substantially and extensively glaciated regions of southernmost South America during the Late Pleistocene. This elongated lake is the largest (∼110 km long) and non‐ice covered lake at high southern latitudes. A multi‐proxy study of selected cores allows the characterisation of a Holocene sedimentary record. Detailed petrophysical, sedimentological and geochemical studies of a complete lacustrine laminated sequence reveal variations in major and trace elements, as well as organic content, suggesting high variability in environmental conditions. Comparison of these results with other regional records allows the identification of major known late Holocene climatic intervals and the proposal for a time for the onset of the Southern Westerlies in Tierra del Fuego. These results improve our understanding of the forcing mechanisms behind climate change in southernmost Patagonia. Copyright © 2009 John Wiley & Sons, Ltd.

Bactrian (“Double Hump”) Acetaminophen Pharmacokinetics: A Case Series and Review of the Literature - Robert G. Hendrickson; Nathanael J. McKeown; Patrick L. West; Christopher R. Burke (Journal of Medical Toxicology, 2010)

Can Plant Competition and Diversity Reduce the Growth and Survival of Exotic Phragmites australis Invading a Tidal Marsh? - Christopher Robert Peter; David M. Burdick (Estuaries and Coasts, 2010)

Retrieval of Substrate Bearing Strength from Hyperspectral Imagery during the Virginia Coast Reserve (VCR’07) Multi-Sensor Campaign - Charles M. Bachmann; C. Reid Nichols; Marcos J. Montes; Rong-Rong Li; Patrick Woodward; Robert A. Fusina; Wei Chen; Vimal Mishra; Wonkook Kim; James Monty; Kevin Mcilhany; Ken Kessler; et al. (Marine Geodesy, 2010)

Amelioration of ketamine-induced working memory deficits by dopamine D1 receptor agonists - Brooke M. Roberts; Patricia A. Seymour; Christopher J. Schmidt; Graham V. Williams; Stacy A. Castner (Psychopharmacology, 2010)

Distribution and community-level effects of the Chinese mystery snail (Bellamya chinensis) in northern Wisconsin lakes - Christopher T. Solomon; Julian D. Olden; Pieter T. J. Johnson; Robert T. Dillon; M. Jake Vander Zanden (Biological Invasions, 2010)

An Assessment of Land Conservation Patterns in Maine Based on Spatial Analysis of Ecological and Socioeconomic Indicators - Christopher S. Cronan; Robert J. Lilieholm; Jill Tremblay; Timothy Glidden (Environmental Management, 2010)

Effects of variations in carbonate chemistry on the calcification rates of Madracis auretenra (= Madracis mirabilis sensu Wells, 1973): bicarbonate concentrations best predict calcification rates - CHRISTOPHER P. JURY; ROBERT F. WHITEHEAD; ALINA M. SZMANT (Global Change Biology, 2010)
Physiological data and models of coral calcification indicate that corals utilize a combination of seawater bicarbonate and (mainly) respiratory CO 2 for calcification, not seawater carbonate. However, a number of investigators are attributing observed negative effects of experimental seawater acidification by CO 2 or hydrochloric acid additions to a reduction in seawater carbonate ion concentration and thus aragonite saturation state. Thus, there is a discrepancy between the physiological and geochemical views of coral biomineralization. Furthermore, not all calcifying organisms respond negatively to decreased pH or saturation state. Together, these discrepancies suggest that other physiological mechanisms, such as a direct effect of reduced pH on calcium or bicarbonate ion transport and/or variable ability to regulate internal pH, are responsible for the variability in reported experimental effects of acidification on calcification. To distinguish the effects of pH, carbonate concentration and bicarbonate concentration on coral calcification, incubations were performed with the coral Madracis auretenra (= Madracis mirabilis sensu Wells, 1973) in modified seawater chemistries. Carbonate parameters were manipulated to isolate the effects of each parameter more effectively than in previous studies, with a total of six different chemistries. Among treatment differences were highly significant. The corals responded strongly to variation in bicarbonate concentration, but not consistently to carbonate concentration, aragonite saturation state or pH. Corals calcified at normal or elevated rates under low pH (7.6–7.8) when the seawater bicarbonate concentrations were above 1800 μ m . Conversely, corals incubated at normal pH had low calcification rates if the bicarbonate concentration was lowered. These results demonstrate that coral responses to ocean acidification are more diverse than currently thought, and question the reliability of using carbonate concentration or aragonite saturation state as the sole predictor of the effects of ocean acidification on coral calcification.

Mercury bioaccumulation and trophic transfer in the terrestrial food web of a montane forest - Christopher C. Rimmer; Eric K. Miller; Kent P. McFarland; Robert J. Taylor; Steven D. Faccio (Ecotoxicology, 2010)

Vulnerability to epidemic malaria in the highlands of Lake Victoria basin: the role of climate change/variability, hydrology and socio-economic factors - Shem O. Wandiga; Maggie Opondo; Daniel Olago; Andrew Githeko; Faith Githui; Michael Marshall; Tim Downs; Alfred Opere; Christopher Oludhe; Gilbert O. Ouma; Pius Z. Yanda; Richard Kangalawe; et al. (Climatic Change, 2010)

Statistical Downscaling of Wind Variability from Meteorological Fields - Robert J. Davy; Milton J. Woods; Christopher J. Russell; Peter A. Coppin (Boundary-Layer Meteorology, 2010)

What Conservation Biologists Can Do to Counter Trap‐Neuter‐Return: Response to Longcore et al. - CHRISTOPHER A. LEPCZYK; NICO DAUPHINÉ; DAVID M. BIRD; SHEILA CONANT; ROBERT J. COOPER; DAVID C. DUFFY; PAMELA JO HATLEY; PETER P. MARRA; ELIZABETH STONE; STANLEY A. TEMPLE (Conservation Biology, 2010)

Erratum: Discriminant analysis for estimation of groundwater age from hydrochemistry and well construction: application to New Zealand aquifers - Christopher J. Daughney; Uwe Morgenstern; Rob van der Raaij; Robert R. Reeves (Hydrogeology Journal, 2010)

Discriminant analysis for estimation of groundwater age from hydrochemistry and well construction: application to New Zealand aquifers - Christopher J. Daughney; Uwe Morgenstern; Rob van der Raaij; Robert R. Reeves (Hydrogeology Journal, 2010)

Postnatal exposure to MK801 induces selective changes in GAD67 or parvalbumin - Christopher Paul Turner; Danielle DeBenedetto; Emily Ware; Robert Stowe; Andrew Lee; John Swanson; Caroline Walburg; Alexandra Lambert; Melissa Lyle; Priyanka Desai; Chun Liu (Experimental Brain Research, 2010)

Microclimate and limits to photosynthesis in a diverse community of hypolithic cyanobacteria in northern Australia - Christopher R. Tracy; Claire Streten‐Joyce; Robert Dalton; Kenneth E. Nussear; Karen S. Gibb; Keith A. Christian (Environmental Microbiology, 2010)
Summary Hypolithic microbes, primarily cyanobacteria, inhabit the highly specialized microhabitats under translucent rocks in extreme environments. Here we report findings from hypolithic cyanobacteria found under three types of translucent rocks (quartz, prehnite, agate) in a semiarid region of tropical Australia. We investigated the photosynthetic responses of the cyanobacterial communities to light, temperature and moisture in the laboratory, and we measured the microclimatic variables of temperature and soil moisture under rocks in the field over an annual cycle. We also used molecular techniques to explore the diversity of hypolithic cyanobacteria in this community and their phylogenetic relationships within the context of hypolithic cyanobacteria from other continents. Based on the laboratory experiments, photosynthetic activity required a minimum soil moisture of 15% (by mass). Peak photosynthetic activity occurred between approximately 8°C and 42°C, though some photosynthesis occurred between −1°C and 51°C. Maximum photosynthesis rates also occurred at light levels of approximately 150–550 μmol m −2 s −1 . We used the field microclimatic data in conjunction with these measurements of photosynthetic efficiency to estimate the amount of time the hypolithic cyanobacteria could be photosynthetically active in the field. Based on these data, we estimated that conditions were appropriate for photosynthetic activity for approximately 942 h (∼75 days) during the year. The hypolithic cyanobacteria community under quartz, prehnite and agate rocks was quite diverse both within and between rock types. We identified 115 operational taxonomic units (OTUs), with each rock hosting 8–24 OTUs. A third of the cyanobacteria OTUs from northern Australia grouped with Chroococcidiopsis , a genus that has been identified from hypolithic and endolithic communities from the Gobi, Mojave, Atacama and Antarctic deserts. Several OTUs identified from northern Australia have not been reported to be associated with hypolithic communities previously.

Effects of nutrition on larval growth and survival in bivalves - Robert Marshall; Scott McKinley; Christopher M. Pearce (Reviews in Aquaculture, 2010)
This review examines the nutritional factors that influence the growth and survival of larval bivalves. Factors considered include feed form (live phytoplankton, preserved phytoplankton and artificial feeds) and feed biochemical composition (protein, lipid, carbohydrate and essential fatty acids). These factors, as they relate to larval production, are discussed in terms of growth and survival rates. To facilitate comparisons among larval studies, growth rates and feeding rates are standardized to common units. In addition, the standardized results for larvae of the Pacific oyster ( Crassostrea gigas Thunberg) are analysed using linear regression techniques to determine the strength of the correlations between daily doses of biochemical feed components and daily growth rates. Piecewise linear spline modelling is used to determine maximum effective dose response, the point where feeding additional biochemical components to the larvae yields no significant improvements in growth. Derived from these analyses are suggested daily rations of lipid, protein, carbohydrate, eicosapentanoic acid, docosahexanoic acid and energy for larvae of C. gigas .

Bathymetry Retrieval from Hyperspectral Imagery in the Very Shallow Water Limit: A Case Study from the 2007 Virginia Coast Reserve (VCR'07) Multi-Sensor Campaign - Charles M. Bachmann; Marcos J. Montes; Robert A. Fusina; Christopher Parrish; Jon Sellars; Alan Weidemann; Wesley Goode; C. Reid Nichols; Patrick Woodward; Kevin McIlhany; Victoria Hill; Richard Zimmerman; et al. (Marine Geodesy, 2010)

Effects of Fire and Fire Surrogate Treatments on Bark Beetle-Caused Tree Mortality in the Southern Cascades, California - Christopher Fettig; Robert Borys; Christopher Dabney (Forest Science, 2010)
We examined bark beetle responses to fire and fire surrogate treatments 2 and 4 years after the application of prescribed fire in a mixed-conifer forest in northern California. Treatments included an untreated control (C), thinning from below (T), and applications of prescribed fire (B) and T + B replicated three times in 10-ha experimental units. A total of 1,822 pine and fir trees (5.1% of all trees) were killed by bark beetles. Mountain pine beetle (Dendroctonus ponderosae Hopkins) was found infesting ponderosa pine (Pinus ponderosa Dougl. ex Laws.), sugar pine (Pinus lambertiana Dougl.), and lodgepole pine (Pinus contorta Dougl. ex Loud.); western pine beetle (Dendroctonus brevicomis LeConte) was found infesting ponderosa pine; and fir engraver (Scolytus ventralis LeConte) was found infesting white fir (Abies concolor [Gord. & Glend.] Lindl. ex Hildebr.). Significantly higher rates of bark beetle-caused tree mortality occurred on B (9.2%) than on C (3.2%), T (<1%), or T + B (3.3%) cumulatively during the 4-year period. A total of 723 pines (4.4% of all pines) were killed by bark beetles, primarily mountain pine beetle. Attacks resulted in significantly more pine mortality on B (5%) than on C, T, or T + B (all <1%) 2 years after the application of prescribed fire. No significant treatment effects were found during the second sample period or cumulatively during the 4-year period. A total of 1,098 white fir trees (5.8% of all white fir) were killed by the fir engraver. Attacks resulted in significantly higher rates of fir mortality on T + B than on T during both sample periods but not cumulatively during the 4-year period. Overall, bark beetle-caused tree mortality was concentrated in the smaller diameter classes. The implications of these and other results to forest management are discussed.

Rimonabant (SR141716) has no effect on alcohol self-administration or endocrine measures in nontreatment-seeking heavy alcohol drinkers - David Ted George; David W. Herion; Cheryl L. Jones; Monte J. Phillips; Jacqueline Hersh; Debra Hill; Markus Heilig; Vijay A. Ramchandani; Christopher Geyer; David E. Spero; Erick D. Singley; Stephanie S. O’Malley; et al. (Psychopharmacology, 2010)

Cryptococcus shivajii sp. nov.: A Novel Basidiomycetous Yeast Isolated from Biogas Reactor - Sreenivas Rao Ravella; Stephen A. James; Christopher J. Bond; Ian N. Roberts; Kathryn Cross; Andy Retter; Phil J. Hobbs (Current Microbiology, 2010)

trans-Fatty acid consumption and its association with distal colorectal cancer in the North Carolina Colon Cancer Study II - Lisa C. Vinikoor; Robert C. Millikan; Jessie A. Satia; Jane C. Schroeder; Christopher F. Martin; Joseph G. Ibrahim; Robert S. Sandler (Cancer Causes & Control, 2010)

Vulnerability and Resilience of Tropical Forest Species to Land‐Use Change - NIGEL E. STORK; JONATHAN A. CODDINGTON; ROBERT K. COLWELL; ROBIN L. CHAZDON; CHRISTOPHER W. DICK; CARLOS A. PERES; SEAN SLOAN; KATHY WILLIS (Conservation Biology, 2009)
We provide a cross‐taxon and historical analysis of what makes tropical forest species vulnerable to extinction. Several traits have been important for species survival in the recent and distant geological past, including seed dormancy and vegetative growth in plants, small body size in mammals, and vagility in insects. For major past catastrophes, such as the five mass extinction events, large range size and vagility or dispersal were key to species survival. Traits that make some species more vulnerable to extinction are consistent across time scales. Terrestrial organisms, particularly animals, are more extinction prone than marine organisms. Plants that persist through dramatic changes often reproduce vegetatively and possess mechanisms of die back. Synergistic interactions between current anthropogenic threats, such as logging, fire, hunting, pests and diseases, and climate change are frequent. Rising temperatures threaten all organisms, perhaps particularly tropical organisms adapted to small temperature ranges and isolated by distance from suitable future climates. Mutualist species and trophic specialists may also be more threatened because of such range‐shift gaps. Phylogenetically specialized groups may be collectively more prone to extinction than generalists. Characterization of tropical forest species’ vulnerability to anthropogenic change is constrained by complex interactions among threats and by both taxonomic and ecological impediments, including gross undersampling of biotas and poor understanding of the spatial patterns of taxa at all scales.

Hydrologic control of nitrogen removal, storage, and export in a mountain stream - Robert Jr. O. Hall; Michelle A. Baker; Christopher D. Arp; Benjamin J. Koch (Limnology and Oceanography, 2009)
Nutrient cycling and export in streams and rivers should vary with flow regime, yet most studies of stream nutrient transformation do not include hydrologic variability. We used a stable isotope tracer of nitrogen ( 15 N) to measure nitrate (NO 3 − ) uptake, storage, and export in a mountain stream, Spring Creek, Idaho, U.S.A. We conducted two tracer tests of 2‐week duration during snowmelt and baseflow. Dissolved and particulate forms of 15 N were monitored over three seasons to test the hypothesis that stream N cycling would be dominated by export during floods, and storage during low flow. Floods exported more N than during baseflow conditions; however, snowmelt floods had higher than expected demand for NO 3 − because of hyporheic exchange. residence times of benthic N during both tracer tests were longer than 100 d for ephemeral pools such as benthic algae and wood biofilms. Residence times were much longer in fine detritus, insects, and the particulate N from the hyporheic zone, showing that assimilation and hydrologic storage can be important mechanisms for retaining particulate N. Of the tracer N stored in the stream, the primary form of export was via seston during periods of high flows, produced by summer rainstorms or spring snowmelt the following year. Spring Creek is not necessarily a conduit for nutrients during high flow; hydrologic exchange between the stream and its valley represents an important storage mechanism.

IGF-1 and pAKT Signaling Promote Hippocampal CA1 Neuronal Survival Following Injury to Dentate Granule Cells - Robert N. Wine; Christopher A. McPherson; G. Jean Harry (Neurotoxicity Research, 2009)

Complexity in water and carbon dioxide fluxes following rain pulses in an African savanna - Christopher Alan Williams; Niall Hanan; Robert J. Scholes; Werner Kutsch (Oecologia, 2009)

Hybrid analytical and finite element numerical modeling of mass and heat transport in fractured rocks with matrix diffusion - Christopher I. McDermott; Robert Walsh; Ralph Mettier; Georg Kosakowski; Olaf Kolditz (Computational Geosciences, 2009)

THE GODAE HIGH-RESOLUTION SEA SURFACE TEMPERATURE PILOT PROJECT - Craig Donlon; Kenneth Casey; Ian Robinson; Chelle Gentemann; Richard Reynolds; Ian Barton; Olivier Arino; John Stark; Nick Rayner; Pierre LeBorgne; David Poulter; Jorge Vazquez-Cuervo; et al. (Oceanography, 2009)

Hydrogeomorphology, environment, and vegetation associations across a latitudinal gradient in highland wetlands of the northeastern USA - Jessica Peterson-Smith; Denice Heller Wardrop; Charles Andrew Cole; Christopher P. Cirmo; Robert P. Brooks (Plant Ecology, 2009)

Angular momentum synergies during walking - Thomas Robert; Bradford C. Bennett; Shawn D. Russell; Christopher A. Zirker; Mark F. Abel (Experimental Brain Research, 2009)

Market information and food insecurity response analysis - Christopher B. Barrett; Robert Bell; Erin C. Lentz; Daniel G. Maxwell (Food Security, 2009)

The NOPP O-SCOPE and MOSEAN Projects: Advanced Sensing for Ocean Observing Systems - Tommy Dickey; Nick Bates; Robert Byrne; Grace Chang; Francisco Chavez; Richard Feely; Alfred Hanson; David Karl; Derek Manov; Casey Moore; Christopher Sabine; Rik Wanninkhof (Oceanography, 2009)

Remote Detection of Marine Microbes, Small Invertebrates, Harmful Algae, and Biotoxins using the Environmental Sample Processor (ESP) - Christopher Scholin; Gregory Doucette; Scott Jensen; Brent Roman; Douglas Pargett; Roman Marin III; Christina Preston; William Jones; Jason Feldman; Cheri Everlove; Adeline Harris; Nilo Alvarado; et al. (Oceanography, 2009)

Longitudinal changes in haemoglobin mass and VO2max in adolescents - Annette Eastwood; Pitre C. Bourdon; Robert T. Withers; Christopher J. Gore (European Journal of Applied Physiology, 2009)

Forest Biomass Supply in the Southeastern United States—Implications for Industrial Roundwood and Bioenergy Production - Christopher S. Galik; Robert Abt; Yun Wu (Journal of Forestry, 2009)
This analysis explores regional aggregate bioenergy potential, the interaction of logging residues and roundwood supply, and the potential supply costs of woody biomass from three southern states. Significant amounts of forest residues are potentially available within the study area: approximately 2.8 million dry tons in North Carolina, 1.8 million dry tons in South Carolina, and 1.3 million dry tons in Virginia. These quantities are sufficient to satisfy regional biomass electricity production requirements only through 2012 under a hypothetical national Renewable Portfolio Standard and Renewable Fuels Standard, after which changes in the biomass resource stream will be necessary. Supply curves generated for multiple regions in each state indicate that forest residues vary regionally in both supply and price, and exceeding the supply of forest residues could be accompanied by a dramatic spike in resource pricing, with implications for timberland owners and users of the forest resource base.

Modelling the time course of shade, temperature, and wood recovery in streams with riparian forest restoration - Robert J. Davies‐Colley; Mark A. Meleason; Raeme M.J. Hall; J. Christopher Rutherford (New Zealand Journal of Marine and Freshwater Research, 2009)
Action is increasingly being taken in New Zealand and elsewhere to restore ecological function to streams through planting of riparian zones. We used simulation modelling to explore the relative performance of three strategies to restore the riparian zone of a pastoral stream to native forest by: (1) passive regeneration; (2) planting then abandonment of a Pinus radiata plantation; and (3) active restoration by planting selected native trees. We linked the forest model LINKNZ with a shade and temperature model (sWAIORA), and a wood model (OSU_STREAMWOOD) to simulate recovery trajectories for key forest stream attributes in hypothetical streams (1.3–14.0 m channel width) in the central North Island, New Zealand. Both active restoration strategies outperformed passive regeneration in shade, temperature and stream wood volume for most of the simulation time (800 years). Although the abandoned pine plantation provided greatest shade initially (

Symposium review: long-term shifts in faunal assemblages in eastern North American estuaries: a review of a workshop held at the biennial meeting of the Coastal and Estuarine Research Federation (CERF), November 2007, Providence, Rhode Island - Robert Buchsbaum; J. Christopher Powell (Reviews in Fish Biology and Fisheries, 2008)

Cocaine self-administration reinforced on a progressive ratio schedule decreases with continuous d-amphetamine treatment in rats - Keri A. Chiodo; Christopher M. Läck; David C. S. Roberts (Psychopharmacology, 2008)

Vertical distribution and characterization of aerobic phototrophic bacteria at the Juan de Fuca Ridge in the Pacific Ocean - Christopher Rathgeber; Michael T. Lince; Jean Alric; Andrew S. Lang; Elaine Humphrey; Robert E. Blankenship; André Verméglio; F. Gerald Plumley; Cindy L. Van Dover; J. Thomas Beatty; Vladimir Yurkov (Photosynthesis Research, 2008)

Drought–herbivory interaction disrupts competitive displacement of native plants by Microstegium vimineum, 10-year results - Christopher R. Webster; Janet H. Rock; Robert E. Froese; Michael A. Jenkins (Oecologia, 2008)

US Forest Service Bark Beetle Research in the Western United States: Looking Toward the Future - José F. Negròn; Barbara J. Bentz; Christopher J. Fettig; Nancy Gillette; E. Matthew Hansen; Jane L. Hayes; Rick G. Kelsey; John E. Lundquist; Ann M. Lynch; Robert A. Progar; Steven J. Seybold (Journal of Forestry, 2008)
Bark beetles cause extensive tree mortality in coniferous forests of western North America and play an important role in the disturbance ecology of these ecosystems. Recently, elevated populations of bark beetles have been observed in all conifer forest types across the western United States. This has heightened public awareness of the issue and triggered legislation for increased funding for state and federal agencies to address issues associated with bark beetle outbreaks. Recently, US Forest Service, Research and Development entomologists from the western research stations met with US Forest Service, State and Private Forestry, Forest Health Protection entomologists, our primary stakeholder, to identify bark beetle research priorities. These include vegetation management; ecological, economic, and social consequences of outbreaks; fire and bark beetle interactions; effects of climate change on bark beetle populations; and chemical ecology.

Molecular characterisation of a cypovirus isolated from the western spruce budworm Choristoneura occidentalis - Robert I. Graham; Benoit Morin; Renée Lapointe; Vincent G. Nealis; Christopher J. Lucarotti (Archives of Virology, 2008)

Transferability of an HGM wetland classification scheme to a longitudinal gradient of the central Appalachian Mountains: Initial hydrological results - Charles Andrew Cole; Christopher P. Cirmo; Denice Heller Wardrop; Robert P. Brooks; Jessica Peterson-Smith (Wetlands, 2008)

Spatial–temporal pattern of bluefin tuna (Thunnus thynnus L. 1758) gonad maturation across the Mediterranean Sea - Gilad Heinisch; Aldo Corriero; Antonio Medina; Francisco J. Abascal; Jose-Miguel de la Serna; Robert Vassallo-Agius; Antonio Belmonte Ríos; Antonio García; Fernando de la Gándara; Christian Fauvel; Christopher R. Bridges; Constantinos C. Mylonas; et al. (Marine Biology, 2008)

Refined mapping of X-linked reticulate pigmentary disorder and sequencing of candidate genes - Lane J. Jaeckle Santos; Chao Xing; Robert B. Barnes; Lesley C. Ades; Andre Megarbane; Christopher Vidal; Angela Xuereb; Patrick S. Tarpey; Raffaella Smith; Mahmoud Khazab; Cheryl Shoubridge; Michael Partington; et al. (Human Genetics, 2008)

In vivo deuteration strategies for neutron scattering analysis of bacterial polyhydroxyoctanoate - Robert A. Russell; Peter J. Holden; Karyn L. Wilde; Christopher J. Garvey; Kerie M. Hammerton; L. John R. Foster (European Biophysics Journal, 2008)

Gold nanoparticles decorated with oligo(ethylene glycol) thiols: kinetics of colloid aggregation driven by depletion forces - Fajun Zhang; Donald G. Dressen; Maximilian W. A. Skoda; Robert M. J. Jacobs; Stefan Zorn; Richard A. Martin; Christopher M. Martin; Graham F. Clark; Frank Schreiber (European Biophysics Journal, 2008)

Virtual observatories for space and solar physics research - Christopher C. Harvey; Michel Gangloff; Todd King; Christopher H. Perry; D. Aaron Roberts; James R. Thieman (Earth Science Informatics, 2008)

Forest Management Solutions for Mitigating Climate Change in the United States - Robert W. Malmsheimer; Patrick Heffernan; Steve Brink; Douglas Crandall; Fred Deneke; Christopher Galik; Edmund Gee; John A. Helms; Nathan McClure; Michael Mortimer; Steve Ruddell; Matthew Smith; et al. (Journal of Forestry, 2008)

The complete nucleotide sequence of the cassava (Manihot esculenta) chloroplast genome and the evolution of atpF in Malpighiales: RNA editing and multiple losses of a group II intron - Henry Daniell; Kenneth J. Wurdack; Anderson Kanagaraj; Seung-Bum Lee; Christopher Saski; Robert K. Jansen (Theoretical and Applied Genetics, 2008)

Life cycle assessment of water-based acrylic floor finish maintenance programs - Lanka Thabrew; Shannon Lloyd; Christopher C. Cypcar; John D. Hamilton; Robert Ries (The International Journal of Life Cycle Assessment, 2008)

Life cycle assessment of water-based acrylic floor finish maintenance programs - Lanka Thabrew; Shannon Lloyd; Christopher C. Cypcar; John D. Hamilton; Robert Ries (The International Journal of Life Cycle Assessment, 2008)

Neurobehavioral effects of human immunodeficiency virus infection among former plasma donors in rural China - Robert K Heaton; Lucette A Cysique; Hua Jin; Chuan Shi; Xin Yu; Scott Letendre; Donald R Franklin; Christopher Ake; Ofilio Vigil; J Hampton Atkinson; Thomas D Marcotte; Igor Grant; et al. (Journal of NeuroVirology, 2008)

A Real-Time PCR Method for the Quantification of the Two Isoforms of Metallothionein in Lake Trout (Salvelinus namaycush) - Julieta Werner; Vince Palace; Christopher Baron; Robert Shiu; Alison Yarmill (Archives of Environmental Contamination and Toxicology, 2008)

Plant reproductive systems and evolution during biological invasion - SPENCER C. H. BARRETT; ROBERT I. COLAUTTI; CHRISTOPHER G. ECKERT (Molecular Ecology, 2008)
Recent biological invasions provide opportunities to investigate microevolution during contemporary timescales. The tempo and scope of local adaptation will be determined by the intensity of natural selection and the amounts and kinds of genetic variation within populations. In flowering plants, genetic diversity is strongly affected by interactions between reproductive systems and stochastic forces associated with immigration history and range expansion. Here, we explore the significance of reproductive system diversity for contemporary evolution during plant invasion. We focus in particular on how reproductive modes influence the genetic consequences of long‐distance colonization and determine the likelihood of adaptive responses during invasion. In many clonal invaders, strong founder effects and restrictions on sexual reproduction limit opportunities for local adaptation. In contrast, adaptive changes to life‐history traits should be a general expectation in both outbreeding and inbreeding species. We provide evidence that evolutionary modifications to reproductive systems promote the colonizing ability of invading populations and that reproductive timing is an important target of selection during range expansion. Knowledge of the likelihood and speed at which local adaptation evolves in invasive plants will be particularly important for management practices when evolutionary changes enhance ecological opportunities and invasive spread.

Mid-Ocean Ridge Exploration with an Autonomous Underwater Vehicle - Dana Yoerger; Albert Bradley; Michael Jakuba; Maurice Tivey; Christopher German; Timothy Shank; Robert Embley (Oceanography, 2007)

A Temporally Explicit Production Efficiency Model for Fuel Load Allocation in Southern Africa - Christelle Hély; Kelly K. Caylor; Peter Dowty; Samuel Alleaume; Robert J. Swap; Hank H. Shugart; Christopher O. Justice (Ecosystems, 2007)

Increased breakpoints on a progressive ratio schedule reinforced by IV cocaine are associated with reduced locomotor activation and reduced dopamine efflux in nucleus accumbens shell in rats - Christopher M. Lack; Sara R. Jones; David C. S. Roberts (Psychopharmacology, 2007)

Chemical Ecology of Fruit Bat Foraging Behavior in Relation to the Fruit Odors of Two Species of Paleotropical Bat-Dispersed Figs (Ficus hispida and Ficus scortechinii) - Robert Hodgkison; Manfred Ayasse; Elisabeth K. V. Kalko; Christopher Häberlein; Stefan Schulz; Wan Aida Wan Mustapha; Akbar Zubaid; Thomas H. Kunz (Journal of Chemical Ecology, 2007)

Characterization of Cauxin in the Urine of Domestic and Big Cats - Lynn McLean; Jane L. Hurst; Christopher J. Gaskell; John C. M. Lewis; Robert J. Beynon (Journal of Chemical Ecology, 2007)

Corrigendum: 2007 highlights of advances in the pharmaceutical sciences: An American Association of Pharmaceutical Scientists (AAPS) perspective - Marilyn N. Martinez; Peter Bonate; Robert L. Chapman; Anne De Groot; Susan D'Souza; Naushad Ghilazi; Vivian Gray; Vishal K. Gupta; Kim Huynh-Ba; Sunil Iyer; Arya Jayatilaka; Amita Joshi; et al. (The AAPS Journal, 2007)

Pharmacological effects of naltrexone and intravenous alcohol on craving for cigarettes among light smokers: a pilot study - Lara A. Ray; Robert Miranda; Christopher W. Kahler; Adam M. Leventhal; Peter M. Monti; Robert Swift; Kent E. Hutchison (Psychopharmacology, 2007)

Complete chloroplast genome sequences of Hordeum vulgare, Sorghum bicolor and Agrostis stolonifera, and comparative analyses with other grass genomes - Christopher Saski; Seung-Bum Lee; Siri Fjellheim; Chittibabu Guda; Robert K. Jansen; Hong Luo; Jeffrey Tomkins; Odd Arne Rognli; Henry Daniell; Jihong Liu Clarke (Theoretical and Applied Genetics, 2007)

Complete chloroplast genome sequences of Hordeum vulgare, Sorghum bicolor and Agrostis stolonifera, and comparative analyses with other grass genomes - Christopher Saski; Seung-Bum Lee; Siri Fjellheim; Chittibabu Guda; Robert K. Jansen; Hong Luo; Jeffrey Tomkins; Odd Arne Rognli; Henry Daniell; Jihong Liu Clarke (Theoretical and Applied Genetics, 2007)

Genetic variation in C57BL/6 ES cell lines and genetic instability in the Bruce4 C57BL/6 ES cell line - Elizabeth D. Hughes; Yun Yan Qu; Suzanne J. Genik; Robert H. Lyons; Christopher D. Pacheco; Andrew P. Lieberman; Linda C. Samuelson; Igor O. Nasonkin; Sally A. Camper; Margaret L. Van Keuren; Thomas L. Saunders (Mammalian Genome, 2007)

A twin study of auditory processing indicates that dichotic listening ability is a strongly heritable trait - Robert J. Morell; Carmen C. Brewer; Dongliang Ge; Harold Snieder; Christopher K. Zalewski; Kelly A. King; Dennis Drayna; Thomas B. Friedman (Human Genetics, 2007)

Contrasting phylogeography in three endemic Hawaiian limpets ( Cellana spp .) with similar life histories - CHRISTOPHER E. BIRD; BRENDEN S. HOLLAND; BRIAN W. BOWEN; ROBERT J. TOONEN (Molecular Ecology, 2007)
The marine environment offers few obvious barriers to dispersal for broadcast‐spawning species, yet population genetic structure can occur on a scale much smaller than the theoretical limits of larval dispersal. Comparative phylogeographical studies of sympatric sister species can illuminate how differences in life history, behaviour, and habitat affinity influence population partitioning. Here we use a mitochondrial DNA marker (612 bp of cytochrome c oxidase subunit I) to investigate population structure of three endemic Hawaiian broadcast‐spawning limpets ( Cellana spp.) with planktonic larvae that are competent to settle within 4 days. All three species exhibit significant population structure and isolation by distance, but the spatial scales of partitioning differ among the species. Cellana talcosa ( n = 105) exhibits strong population structure between Kauai and the other main Hawaiian Islands (MHI) where the maximum channel width is 117 km, and no shared haplotypes were observed (Φ CT = 0.30, P Cellana exarata ( n = 149) and Cellana sandwicensis ( n = 109) exhibit weaker population structure within the MHI (Φ ST = 0.03–0.04, P ST = 0.03–0.09, P

Linkage and association analysis of candidate genes for TB and TNFα cytokine expression: evidence for association with IFNGR1, IL-10, and TNF receptor 1 genes - Catherine M. Stein; Sarah Zalwango; Allan B. Chiunda; Christopher Millard; Dmitry V. Leontiev; Amanda L. Horvath; Kevin C. Cartier; Keith Chervenak; W. Henry Boom; Robert C. Elston; Roy D. Mugerwa; Christopher C. Whalen; et al. (Human Genetics, 2007)

2007 highlights of advances in the pharmaceutical sciences: An American Association of Pharmaceutical Scientists (AAPS) perspective - Marilyn N. Martinez; Peter Bonate; Robert L. Chapman; Anne De Groot; Susan D'Souza; Naushad Ghilazi; Vivian Gray; Vishal K. Gupta; Kim Huynh-Ba; Sunil Iyer; Arya Jayatilaka; Amita Joshi; et al. (The AAPS Journal, 2007)

Evaluating forest management practices using a GIS-based cellular automata modeling approach with multispectral imagery - Christopher Bone; Suzana Dragićević; Arthur Roberts (Environmental Modeling & Assessment, 2007)

Molecular analysis of fungal communities and laccase genes in decomposing litter reveals differences among forest types but no impact of nitrogen deposition - Christopher B. Blackwood; Mark P. Waldrop; Donald R. Zak; Robert L. Sinsabaugh (Environmental Microbiology, 2007)
Summary The fungal community of the forest floor was examined as the cause of previously reported increases in soil organic matter due to experimental N deposition in ecosystems producing predominantly high‐lignin litter, and the opposite response in ecosystems producing low‐lignin litter. The mechanism proposed to explain this phenomenon was that white‐rot basidiomycetes are more important in the degradation of high‐lignin litter than of low‐lignin litter, and that their activity is suppressed by N deposition. We found that forest floor mass in the low‐lignin sugar‐maple dominated system decreased in October due to experimental N deposition, whereas forest floor mass of high‐lignin oak‐dominated ecosystems was unaffected by N deposition. Increased relative abundance of basidiomycetes in high‐lignin forest floor was confirmed by denaturing gradient gel electrophoresis (DGGE) and sequencing. Abundance of basidiomycete laccase genes, encoding an enzyme used by white‐rot basidiomycetes in the degradation of lignin, was 5–10 times greater in high‐lignin forest floor than in low‐lignin forest floor. While the differences between the fungal communities in different ecosystems were consistent with the proposed mechanism, no significant effects of N deposition were detected on DGGE profiles, laccase gene abundance, laccase length heterogeneity profiles, or phenol oxidase activity. Our observations indicate that the previously detected accumulation of soil organic matter in the high‐lignin system may be driven by effects of N deposition on organisms in the mineral soil, rather than on organisms residing in the forest floor. However, studies of in situ gene expression and temporal and spatial variability within forest floor communities will be necessary to further relate the ecosystem dynamics of organic carbon to microbial communities and atmospheric N deposition.

Aluminum adjuvant linked to gulf war illness induces motor neuron death in mice - Michael S. Petrik; Margaret C. Wong; Rena C. Tabata; Robert F. Garry; Christopher A. Shaw (NeuroMolecular Medicine, 2007)

Redirection of carotenoid metabolism for the efficient production of taxadiene [taxa-4(5),11(12)-diene] in transgenic tomato fruit - Katalin Kovacs; Lina Zhang; Robert S. T. Linforth; Benjamin Whittaker; Christopher J. Hayes; Rupert G. Fray (Transgenic Research, 2007)

Analysis of nitrite reductase ( nirK and nirS ) genes and cultivation reveal depauperate community of denitrifying bacteria in the Black Sea suboxic zone - Brian B. Oakley; Christopher A. Francis; Kathryn J. Roberts; Clara A. Fuchsman; S. Srinivasan; James T. Staley (Environmental Microbiology, 2007)
Summary Chemical profiles of the Black Sea suboxic zone show a distribution of nitrogen species which is traditionally associated with denitrification, i.e. a secondary nitrite maximum associated with nitrate depletion and a N 2 gas peak. To better understand the distribution and diversity of the denitrifier community in the Black Sea suboxic zone, we combined a cultivation approach with cloning and sequencing of PCR‐amplified nitrite reductase ( nirS and nirK ) genes. The Black Sea suboxic zone appears to harbour a homogeneous community of denitrifiers. For nirK , over 94% of the sequences fell into only three distinct phylogenetic clusters, and for nirS , a single closely related sequence type accounted for 91% of the sequences retrieved. Both nirS and nirK genes showed a dramatic shift in community composition at the bottom of the suboxic zone, but overall, nirK ‐based community composition showed much greater variation across depths compared with the highly uniform distribution of nirS sequences throughout the suboxic zone. The dominant nirK and nirS sequences differed at the amino acid level by at least 17% and 8%, respectively, from their nearest database matches. Denitrifying isolates recovered from the suboxic zone shared 97% 16S rRNA gene sequence similarity with Marinobacter maritimus . Analysis of the recently discovered nirS gene from the anammox bacterium Candidatus ‘Kuenenia stuttgartiensis’ revealed that mismatches with commonly used primers may have prevented the previous detection of this divergent sequence.

Variation of the Schmelzmuster and Other Enamel Characters in Molars of the Primitive Pliocene Vole Ogmodontomys from Kansas - Robert A. Martin; Christopher P. Crockett; Federica Marcolini (Journal of Mammalian Evolution, 2006)

Ecological response to hurricane events in the Pamlico Sound system, North Carolina, and implications for assessment and management in a regime of increased frequency - Hans W. Paerl; Lexia M. Valdes; Alan R. Joyner; Benjamin L. Peierls; Michael F. Piehler; Stanley R. Riggs; Robert R. Christian; Lisa A. Eby; Larry B. Crowder; Joseph S. Ramus; Erika J. Clesceri; Christopher P. Buzzelli; et al. (Estuaries and Coasts, 2006)

Genetic characterization and fine mapping of susceptibility loci for sarcoidosis in African Americans on chromosome 5 - Courtney Gray-McGuire; Ritwik Sinha; Sudha Iyengar; Christopher Millard; Benjamin A. Rybicki; Robert C. Elston; Michael C. Iannuzzi (Human Genetics, 2006)

Remarkable Amphibian Biomass and Abundance in an Isolated Wetland: Implications for Wetland Conservation - J. WHITFIELD GIBBONS; CHRISTOPHER T. WINNE; DAVID E. SCOTT; JOHN D. WILLSON; XAVIER GLAUDAS; KIMBERLY M. ANDREWS; BRIAN D. TODD; LUKE A. FEDEWA; LUCAS WILKINSON; RIA N. TSALIAGOS; STEVEN J. HARPER; JUDITH L. GREENE; et al. (Conservation Biology, 2006)
Despite the continuing loss of wetland habitats and associated declines in amphibian populations, attempts to translate wetland losses into measurable losses to ecosystems have been lacking. We estimated the potential productivity from the amphibian community that would be compromised by the loss of a single isolated wetland that has been protected from most industrial, agricultural, and urban impacts for the past 54 years. We used a continuous drift fence at Ellenton Bay, a 10‐ha freshwater wetland on the Savannah River Site, near Aiken, South Carolina (U.S.A.), to sample all amphibians for 1 year following a prolonged drought. Despite intensive agricultural use of the land surrounding Ellenton Bay prior to 1951, we documented 24 species and remarkably high numbers and biomass of juvenile amphibians (>360,000 individuals; >1,400 kg) produced during one breeding season. Anurans (17 species) were more abundant than salamanders (7 species), comprising 96.4% of individual captures. Most (95.9%) of the amphibian biomass came from 232095 individuals of a single species of anuran (southern leopard frog [Rana sphenocephala ]). Our results revealed the resilience of an amphibian community to natural stressors and historical habitat alteration and the potential magnitude of biomass and energy transfer from isolated wetlands to surrounding terrestrial habitat. We attributed the postdrought success of amphibians to a combination of adult longevity (often >5 years), a reduction in predator abundance, and an abundance of larval food resources. Likewise, the increase of forest cover around Ellenton Bay from 60% in 2001 probably contributed to the long‐term persistence of amphibians at this site. Our findings provide an optimistic counterpoint to the issue of the global decline of biological diversity by demonstrating that conservation efforts can mitigate historical habitat degradation.

Effect of von Willebrand Factor on the Pharmacokinetics of Recombinant Human Platelet Glycoprotein Ibα-Immunoglobulin G1 Chimeric Proteins - Qin Wang; Douglas Shorten; Xin Xu; Gray D. Shaw; Robert G. Schaub; Christopher Shea; Jonathan Brooks; Dianne Sako; Erin Wiswall; Jin Xu; Pamela Szklut; Vikram S. Patel (Pharmaceutical Research, 2006)

Self-selected exercise intensity during household/garden activities and walking in 55 to 65-year-old females - Robert T. Withers; Anthony G. Brooks; Simon M. Gunn; John L. Plummer; Christopher J. Gore; John Cormack (European Journal of Applied Physiology, 2006)

The Use of Bioluminescence for Monitoring in planta Growth Dynamics of a Pseudomonas syringae Plant Pathogen - Christopher D. Paynter; Vyvyan C. Salisbury; Dawn L. Arnold; Robert W. Jackson (European Journal of Plant Pathology, 2006)

Detailed characterization of the peptide binding specificity of five common Patr class I MHC molecules - John Sidney; Shinichi Asabe; Bjoern Peters; Kelly-Anne Purton; Josan Chung; Timothy J. Pencille; Robert Purcell; Christopher M. Walker; Francis V. Chisari; Alessandro Sette (Immunogenetics, 2006)

Molecular genotype identification of the Gallus gallus major histocompatibility complex - Janet E. Fulton; Helle R. Juul-Madsen; Christopher M. Ashwell; Amy M. McCarron; James A. Arthur; Neil P. O’Sullivan; Robert L. Taylor (Immunogenetics, 2006)

A tumor vasculature targeted liposome delivery system for combretastatin A4: Design, characterization, and in vitro evaluation - Ramakrishna Nallamothu; George C. Wood; Christopher B. Pattillo; Robert C. Scott; Mohammad F. Kiani; Bob M. Moore; Laura A. Thoma (AAPS PharmSciTech, 2006)

Complete chloroplast genome sequences of Solanum bulbocastanum, Solanum lycopersicum and comparative analyses with other Solanaceae genomes - Henry Daniell; Seung-Bum Lee; Justin Grevich; Christopher Saski; Tania Quesada-Vargas; Chittibabu Guda; Jeffrey Tomkins; Robert K. Jansen (Theoretical and Applied Genetics, 2006)

Discrete-trials heroin self-administration produces sensitization to the reinforcing effects of cocaine in rats - Sara J. Ward; Christopher Läck; Drake Morgan; David C. S. Roberts (Psychopharmacology, 2006)

Molecular Detection of Marine Invertebrate Larvae - Shana K. Goffredi; William J. Jones; Christopher A. Scholin; Roman Marin; Robert C. Vrijenhoek (Marine Biotechnology, 2006)

Sequence diversity, natural selection and linkage disequilibrium in the human T cell receptor alpha/delta locus - Rachel Mackelprang; Robert J. Livingston; Michael A. Eberle; Christopher S. Carlson; Qian Yi; Joshua M. Akey; Deborah A. Nickerson (Human Genetics, 2006)

Evidence that Soil Carbon Pool Determines Susceptibility of Semi-Natural Ecosystems to Elevated Nitrogen Leaching - Christopher D. Evans; Brian Reynolds; Alan Jenkins; Rachel C. Helliwell; Christopher J. Curtis; Christine L. Goodale; Robert C. Ferrier; Bridget A. Emmett; Michael G. Pilkington; Simon J. M. Caporn; Jacky A. Carroll; David Norris; et al. (Ecosystems, 2006)

Magnetically Responsive Polymeric Microparticles for Oral Delivery of Protein Drugs - Jianjun Cheng; Benjamin A. Teply; Seok Yoon Jeong; Christopher H. Yim; Dennis Ho; Ines Sherifi; Sangyong Jon; Omid C. Farokhzad; Ali Khademhosseini; Robert S. Langer (Pharmaceutical Research, 2006)

N-acetylcysteine augmentation in serotonin reuptake inhibitor refractory obsessive-compulsive disorder - Daniel L. Lafleur; Christopher Pittenger; Ben Kelmendi; Tom Gardner; Suzanne Wasylink; Robert T. Malison; Gerard Sanacora; John H. Krystal; Vladimir Coric (Psychopharmacology, 2006)

Striatal dopamine transporter availability with [123I]β-CIT SPECT is unrelated to gender or menstrual cycle - Susan E. Best; Philip M. Sarrel; Robert T. Malison; Marc Laruelle; Sami S. Zoghbi; Ronald M. Baldwin; John P. Seibyl; Robert B. Innis; Christopher H. van Dyck (Psychopharmacology, 2005)

Hydroxyl and Peroxy Radical Chemistry in a Rural Area of Central Pennsylvania: Observations and Model Comparisons - Xinrong Ren; William H. Brune; Christopher A. Cantrell; Gavin D. Edwards; Terry Shirley; Andrew R. Metcalf; Robert L. Lesher (Journal of Atmospheric Chemistry, 2005)

Complete Chloroplast Genome Sequence of Glycine max and Comparative Analyses with other Legume Genomes - Christopher Saski; Seung-Bum Lee; Henry Daniell; Todd C. Wood; Jeffrey Tomkins; Hyi-Gyung Kim; Robert K. Jansen (Plant Molecular Biology, 2005)

Effect of Thioligands on Plant-Hg Accumulation and Volatilisation from Mercury-contaminated Mine Tailings - Fabio N. Moreno; Christopher W. N. Anderson; Robert B. Stewart; Brett H. Robinson; Roberto Nomura; Mory Ghomshei; John A Meech (Plant and Soil, 2005)

Sleep disturbance at simulated altitude indicated by stratified respiratory disturbance index but not hypoxic ventilatory response - Tahnee A. Kinsman; Nathan E. Townsend; Christopher J. Gore; Allan G. Hahn; Sally A. Clark; Robert J. Aughey; Michael J. McKenna; John A. Hawley; Chin-Moi Chow (European Journal of Applied Physiology, 2005)

The energy cost of household and garden activities in 55- to 65-year-old males - Simon M. Gunn; Anthony G. Brooks; Robert T. Withers; Christopher J. Gore; John L. Plummer; John Cormack (European Journal of Applied Physiology, 2005)

Periphyton nutrient limitation and nitrogen fixation potential along a wetland nutrient-depletion gradient - J. Thad Scott; Robert D. Doyle; Christopher T. Filstrup (Wetlands, 2005)

Determination of Mercury Content in a Shallow Firn Core from Greenland by Isotope Dilution Inductively Coupled Plasma Mass Spectrometry - Jacqueline L. Mann; Stephen E. Long; Christopher A. Shuman; W. Robert Kelly (Water, Air, & Soil Pollution, 2005)

Hypoxic ventilatory response is correlated with increased submaximal exercise ventilation after live high, train low - Nathan E. Townsend; Christopher J. Gore; Allan G. Hahn; Robert J. Aughey; Sally A. Clark; Tahnee A. Kinsman; Michael J. McKenna; John A. Hawley; Chin-Moi Chow (European Journal of Applied Physiology, 2005)

Mercury Concentrations in Bicknell?s Thrush and Other Insectivorous Passerines in Montane Forests of Northeastern North America - Christopher C. Rimmer; Kent P. McFarland; David C. Evers; Eric K. Miller; Yves Aubry; Daniel Busby; Robert J. Taylor (Ecotoxicology, 2005)

Heme-copper/dioxygen adduct formation relevant to cytochrome c oxidase: spectroscopic characterization of [(6L)FeIII-(O22?)-CuII]+ - Reza A. Ghiladi; Hong-wei Huang; Pierre Monne-Loccoz; Jay Stasser; Ninian J. Blackburn; Amina S. Woods; Robert J. Cotter; Christopher D. Incarvito; Arnold L. Rheingold; Kenneth D. Karlin (JBIC Journal of Biological Inorganic Chemistry, 2005)

Estimated contribution of Atlantic Coastal loggerhead turtle nesting populations to offshore feeding aggregations - Mark A. Roberts; Christopher J. Anderson; Bruce Stender; Al Segars; J. David Whittaker; James M. Grady; Joseph M. Quattro (Conservation Genetics, 2005)

Novel copper‐binding and nitrogen‐rich thiols produced and exuded by Emiliania huxleyi - Christopher L. Dupont; Robert K. Nelson; Saj Bashir; James W. Moffett; Beth A. Ahner (Limnology and Oceanography, 2004)
In surface seawater, dissolved copper (Cu) is predominantly bound by a small pool of strong ligands, with further complexation by a larger pool of weaker ligands. Although the chemical structure of both classes of ligands observed in the open ocean remains unknown, it is believed that the stronger ligands are of biological origin, and it has been hypothesized that they are thiols. Using precolumn derivatization high‐performance liquid chromatography electrospray ionization ion‐trap mass spectrometry, we found that the ubiquitous coccolithophorid Emiliania huxleyi constitutively produces two previously uncharacterized thiols, arginine‐cysteine and glutamine‐cysteine, in high intracellular concentrations. E. huxleyi exudes these novel thiols, along with cysteine, in response to increased Cu concentrations in the growth media. Furthermore, stable Cu (I) complexes with the exuded thiols were observed in the growth media using matrix‐assisted laser desorption time‐of‐flight mass spectrometry following size exclusion chromatography. Additionally, E. huxleyi appears to utilize these novel thiols in nitrogen storage and assimilation, as they are rapidly synthesized upon nitrogen addition to a nitrogen‐depleted culture. The identification of specific ligands produced by this organism will facilitate further linkages between this likely source and the pools of Cu‐binding ligands observed in surface seawater, while the discovery of novel thiols signifies the presence of unique and previously unknown biochemical pathways in E. huxleyi .

Analysis of the Maize Polyubiquitin-1 Promoter Heat Shock Elements and Generation of Promoter Variants with Modified Expression Characteristics - Stephen J. Streatfield; Maria E. Magallanes-Lundback; Katherine K. Beifuss; Christopher A. Brooks; Robin L. Harkey; Robert T. Love; Jeff Bray; John A. Howard; Joseph M. Jilka; Elizabeth E. Hood (Transgenic Research, 2004)

Postfire Management on Forested Public Lands of the Western United States - ROBERT L. BESCHTA; JONATHAN J. RHODES; J. BOONE KAUFFMAN; ROBERT E. GRESSWELL; G. WAYNE MINSHALL; JAMES R. KARR; DAVID A. PERRY; F. RICHARD HAUER; CHRISTOPHER A. FRISSELL (Conservation Biology, 2004)
Forest ecosystems in the western United States evolved over many millennia in response to disturbances such as wildfires. Land use and management practices have altered these ecosystems, however, including fire regimes in some areas. Forest ecosystems are especially vulnerable to postfire management practices because such practices may influence forest dynamics and aquatic systems for decades to centuries. Thus, there is an increasing need to evaluate the effect of postfire treatments from the perspective of ecosystem recovery. We examined, via the published literature and our collective experience, the ecological effects of some common postfire treatments. Based on this examination, promising postfire restoration measures include retention of large trees, rehabilitation of firelines and roads, and, in some cases, planting of native species. The following practices are generally inconsistent with efforts to restore ecosystem functions after fire: seeding exotic species, livestock grazing, placement of physical structures in and near stream channels, ground‐based postfire logging, removal of large trees, and road construction. Practices that adversely affect soil integrity, persistence or recovery of native species, riparian functions, or water quality generally impede ecological recovery after fire. Although research provides a basis for evaluating the efficacy of postfire treatments, there is a continuing need to increase our understanding of the effects of such treatments within the context of societal and ecological goals for forested public lands of the western United States.

Estimates of Down Woody Materials in Eastern US Forests - David C. Chojnacky; Robert A. Mickler; Linda S. Heath; Christopher W. Woodall (Environmental Management, 2004)

Measurement and prediction of energy expenditure in males during household and garden tasks - Simon M. Gunn; Grant E. van der Ploeg; Robert T. Withers; Christopher J. Gore; Neville Owen; Adrian E. Bauman; John Cormack (European Journal of Applied Physiology, 2004)

An Assessment of the Potential for Selenium to Impair Reproduction in Bull Trout, Salvelinus confluentus, from an Area of Active Coal Mining - Vince P. Palace; Christopher Baron; Robert E. Evans; Jodi Holm; Suzanne Kollar; Kerry Wautier; Jeffrey Werner; Paula Siwik; George Sterling; Craig F. Johnson (Environmental Biology of Fishes, 2004)

Morphological and genetic variation within Metrosideros polymorpha (Myrtaceae) on Hawai'i - Shelley A. James; Christopher F. Puttock; Susan Cordell; Robert P. Adams (New Zealand Journal of Botany, 2004)
The highly polymorphic taxon Metrosideros polymorpha ('ohi'a) is the most abundant endemic tree in Hawai'i, occupying a wide but fragmented range of habitats across Federal, State, and privately managed lands. Morphological character states of 342 herbarium specimens from the island of Hawai'i distributed the five recognised varieties in ordinal space, but intermediate pheno‐types were prevalent. Morphological and random amplified polymorphic DNA (RAPD) analyses were undertaken for 10 individuals at 3 sites on Hawai'i. Individuals at a high‐elevation dry site and mid‐elevation dry site had smaller, pubescent leaves with a higher leaf mass per area and nitrogen content than individuals at a moist mid‐elevation site. While the populations were separated in ordinal space, taxo‐nomic varieties overlapped. The high degree of overlap between the taxonomic varieties, based on genetic and morphological characteristics, does not support the current varietal subdivision of Metrosideros polymorpha on Hawai'i.

Expression of the poly-glutamine-ataxin-3 transgene causes loss of orexin expression: A rat model of narcolepsy - Carsten T. BEUCKMANN; Christopher M. SINTON; S. Clay WILLIAMS; James A. RICHARDSON; Robert E. HAMMER; Takeshi SAKURAI; Masashi YANAGISAWA (Sleep and Biological Rhythms, 2004)

Fine mapping a gene for pediatric gastroesophageal reflux on human chromosome 13q14 - Fen Ze Hu; Joseph Donfack; Azad Ahmed; Richard Dopico; Sandra Johnson; J. Christopher Post; Garth D. Ehrlich; Robert A. Preston (Human Genetics, 2004)

Measurement and prediction of METs during household activities in 35- to 45-year-old females - Anthony G. Brooks; Robert T. Withers; Christopher J. Gore; Andrew J. Vogler; John Plummer; John Cormack (European Journal of Applied Physiology, 2004)

Sperm swimming speed and energetics vary with sperm competition risk in bluegill ( Lepomis macrochirus ) - Gary Burness; Stephen J. Casselman; Albrecht I. Schulte-Hostedde; Christopher D. Moyes; Robert Montgomerie (Behavioral Ecology and Sociobiology, 2004)

A study into the anti-microbial properties of an amino functionalised polymer using multi-parameter flow cytometry - Christopher J. Hewitt; Robert Franke; Achim Marx; Beate Kossmann; Peter Ottersbach (Biotechnology Letters, 2004)

Urotensin-II: a novel systemic hypertensive factor in the cat - Kristeen Maniscalco; Gerald P. Stankus; Alexandra Wibberley; Robert N. Willette; Stephen A. Douglas; David J. Behm; Christopher P. A. Doe; Douglas G. Johns (Naunyn-Schmiedeberg's Archives of Pharmacology, 2004)

Postindustrial enhancement of aragonite undersaturation in the upper tropical andsubtropical Atlantic Ocean: The role of fossil fuel CO 2 - Sook‐Nye Chung; Geun‐Ha Park; Kitack Lee; Robert M. Key; Frank J. Millero; Richard A. Feely; Christopher L. Sabine; Paul G. Falkowski (Limnology and Oceanography, 2004)
The dissolution of aragonite particles in the ocean primarily depends on the degree of undersaturation of seawater with respect to that mineral. Most of the upper Atlantic Ocean, particularly north of 308S and at depths of less than 2000 m, is supersaturated with respect to aragonite, whereas much of the deep Atlantic is undersaturated. Here we report, for the first time, shallow layers of aragonite‐undersaturated water between 20°S and 15°N in the eastern tropical Atlantic. These layers are centered at 800 m and are surrounded by aragonite‐supersaturated water above and below. This feature most likely results from a combination of chemical and biological processes including the uptake of anthropogenic CO 2 and the oxidation of organic matter falling from the highly productive overlying surface water. Reaction with protons resulting from these processes decreases the carbonate ion concentration and consequently the saturation state of the waters with respect to aragonite. The oceanic uptake of anthropogenic CO 2 during the industrial era has caused a significant increase in the size of the undersaturated layers. Future expansion will likely occur laterally to the west and south, where the degree of supersaturation is low compared to waters to the north. This expansion of the undersaturated layers is a prime example of how human activity during the industrial era has altered the upper ocean chemistry by injecting fossil fuel CO 2 into the ocean.

Photochemistry in the Arctic Free Troposphere: Ozone Budget and Its Dependence on Nitrogen Oxides and the Production Rate of Free Radicals - Craig Stroud; Sasha Madronich; Elliot Atlas; Christopher Cantrell; Alan Fried; Brian Wert; Brian Ridley; Fred Eisele; Lee Mauldin; Richard Shetter; Barry Lefer; Frank Flocke; et al. (Journal of Atmospheric Chemistry, 2004)

A Laser-induced Fluorescence Instrument for Detecting Tropospheric OH and HO2: Characteristics and Calibration - Ian C. Faloona; David Tan; Robert L. Lesher; Nathan L. Hazen; Christopher L. Frame; James B. Simpas; Hartwig Harder; Monica Martinez; Piero Di Carlo; Xinrong Ren; William H. Brune (Journal of Atmospheric Chemistry, 2004)

Measurement and prediction of energy expenditure in males during household and garden tasks - Simon M. Gunn; Grant E. van der Ploeg; Robert T. Withers; Christopher J. Gore; Neville Owen; Adrian E. Bauman; John Cormack (European Journal of Applied Physiology, 2004)

A Paradigm for Functional Tissue Engineering of Articular Cartilage via Applied Physiologic Deformational Loading - Clark T. Hung; Robert L. Mauck; Christopher C.-B. Wang; Eric G. Lima; Gerard A. Ateshian (Annals of Biomedical Engineering, 2004)

A strategy for the integration of QTL, gene expression, and sequence analyses - Robert Hitzemann; Barry Malmanger; Cheryl Reed; Maureen Lawler; Barbara Hitzemann; Shannon Coulombe; Kari Buck; Brooks Rademacher; Nicole Walter; Yekatrina Polyakov; James Sikela; Brenda Gensler; et al. (Mammalian Genome, 2003)

Resource dispersion and consumer dominance: scavenging at wolf‐ and hunter‐killed carcasses in Greater Yellowstone, USA - Christopher C. Wilmers; Daniel R. Stahler; Robert L. Crabtree; Douglas W. Smith; Wayne M. Getz (Ecology Letters, 2003)
The Greater Yellowstone Ecosystem in the northern Rocky Mountains provides the context for a natural experiment to investigate the response of consumers to resources with differing spatial and temporal dispersion regimes. Grey wolves ( Canis lupus ) and human hunters both provide resource subsidies to scavengers by provisioning them with the remains of their kills. Carrion from hunter kills is highly aggregated in time and space whereas carrion from wolf kills is more dispersed in both time and space. We estimated the total amount of carrion consumed by each scavenger species at both wolf and hunter kills over 4 years. Species with large feeding radii [bald eagles ( Haliaeetus leucocephalus ) and ravens ( Corvus corax )], defined as the area over which a consumer can efficiently locate and integrate resources, dominated consumption at the highly aggregated hunter kills whereas competitively dominant species [coyotes ( Canis latrans )] dominated at the more dispersed wolf kills. In addition, species diversity and the evenness of carrion consumption between scavengers was greater at wolf kills than at hunter kills while the total number of scavengers at hunter kills exceeded those at wolf kills. From a community perspective, the top–down effect of predation is likely to be stronger in the vicinity of highly aggregated resource pulses as species with large feeding radii switch to feeding on alternative prey once the resource pulse subsides.

Tea intake and risk of colon cancer in African-Americans and Whites: North Carolina colon cancer study - Dora Il'yasova; Christopher Martin; Robert S. Sandler (Cancer Causes & Control, 2003)

Seasonal variation in top-down and bottom-up processes in a grassland arthropod community - Alison G. Boyer; Robert E. Swearingen; Margo A. Blaha; Christopher T. Fortson; Sara K. Gremillion; Kelly A. Osborn; Matthew D. Moran (Oecologia, 2003)

Fluorescent Substrates of Sister-P-Glycoprotein (BSEP) Evaluated as Markers of Active Transport and Inhibition: Evidence for Contingent Unequal Binding Sites - Er-jia Wang; Christopher N. Casciano; Robert P. Clement; William W. Johnson (Pharmaceutical Research, 2003)

Fine scale mapping of a genetic locus for conditioned fear - Christopher J. Talbot; Richard A. Radcliffe; Jan Fullerton; Robert Hitzemann; Jeanne M. Wehner; Jonathan Flint (Mammalian Genome, 2003)

The Effect of Precipitation Amount and Atmospheric Concentrations on Wet Deposition Fluxes of Oxidized and Reduced Nitrogen Species in Connecticut - Farhad Nadim; Snieguole Stapcinskaite; Michael M. Trahiotis; Christopher Perkins; Robert J. Carley; Shili Liu; Xiusheng Yang (Water, Air, & Soil Pollution, 2003)

Trimethyltin-induced neurogenesis in the murine hippocampus - G. Jean Harry; Christopher A. McPherson; Robert N. Wine; Kelly Atkinson; Christian Lefebvre d'Hellencourt (Neurotoxicity Research, 2003)

Alterations in cyclin A, B, and D1 in mouse dentate gyrus following TMT-induced hippocampal damage - Christopher A. McPherson; Julie Kubik; Robert N. Wine; Christian Lefebvre D'Hellencourt; G. Jean Harry (Neurotoxicity Research, 2003)

Managing Troubled Data: Coastal Data Partnerships Smooth Data Integration - Stephen S. Hale; Anne Hale Miglarese; M. Patricia Bradley; Thomas J. Belton; Larry D. Cooper; Michael T. Frame; Christopher A. Friel; Linda M. Harwell; Robert E. King; William K. Michener; David T. Nicolson; Bruce G. Peterjohn (Environmental Monitoring and Assessment, 2003)

Modulation of integrins and integrin signaling molecules in the pressure-loaded murine ventricle - Christopher J. Babbitt; Shaw-Yung Shai; Alice E. Harpf; Can G. Pham; Robert S. Ross (Histochemistry and Cell Biology, 2002)

Multivariate cluster analysis of a human hepatic cytochrome P 450 database - Sherwin Sy; James Johnston; Christopher Class; Eve Roberts; Werner Kalow; Bing-Kou Tang (European Journal of Clinical Pharmacology, 2002)

The Late Cenozoic uplift - climate change paradox - William Hay; Emanuel Soeding; Robert DeConto; Christopher Wold (International Journal of Earth Sciences, 2002)

A novel locus for Meckel-Gruber syndrome, MKS3 , maps to chromosome 8q24 - Neil Morgan; Paul Gissen; Saghira Sharif; Laura Baumber; Joan Sutherland; Deirdre Kelly; Kingi Aminu; Christopher Bennett; Geoffrey Woods; Robert Mueller; Richard Trembath; Eamonn Maher; et al. (Human Genetics, 2002)

Nestedness analysis and conservation planning: the importance of place, environment, and life history across taxonomic groups - Erica Fleishman; Christopher J. Betrus; Robert B. Blair; Ralph Mac Nally; Dennis D. Murphy (Oecologia, 2002)

Quantification of Vessel Wall Cyclic Strain Using Cine Phase Contrast Magnetic Resonance Imaging - Mary T. Draney; Robert J. Herfkens; Thomas J. R. Hughes; Norbert J. Pelc; Kristin L. Wedding; Christopher K. Zarins; Charles A. Taylor (Annals of Biomedical Engineering, 2002)

Preparation of budesonide and budesonide-PLA microparticles using supercritical fluid precipitation technology - Todd M. Martin; Nagesh Bandi; Ryan Shulz; Christopher B. Roberts; Uday B. Kompella (AAPS PharmSciTech, 2002)

Root production and demography in a california annual grassland under elevated atmospheric carbon dioxide - Paul A. T. Higgins; Robert B. Jackson; Julia M. Des Rosiers; Christopher B. Field (Global Change Biology, 2002)
This study examined root production and turnover in a California grassland during the third year of a long‐term experiment with ambient (LO) and twice‐ambient atmospheric CO 2 (HI), using harvests, ingrowth cores, and minirhizotrons. Based on one‐time harvest data, root biomass was 32% greater in the HI treatment, comparable to the stimulation of aboveground production during the study year. However, the 30–70% increase in photosynthesis under elevated CO 2 for the dominant species in our system is considerably larger than the combined increase in above and belowground biomass. One possible explanation is, increased root turnover, which could be a sink for the additional fixed carbon. Cumulative root production in ingrowth cores from both treatments harvested at four dates was 2–3 times that in the single harvested cores, suggesting substantial root turnover within the growing season. Minirhizotron data confirmed this result, demonstrating that production and mortality occurred simultaneously through much of the season. As a result, cumulative root production was 54%, 47% and 44% greater than peak standing root length for the no chamber (X), LO, and HI plots, respectively. Elevated CO 2 , however, had little effect on rates of turnover (i.e. rates of turnover were equal in the LO and HI plots throughout most of the year) and cumulative root production was unaffected by treatment. Elevated CO 2 increased monthly production of new root length (59%) only at the end of the season (April–June) when root growth had largely ceased in the LO plots but continued in the HI plots. This end‐of‐season increase in production coincided with an 18% greater soil moisture content in the HI plots previously described. Total standing root length was not affected by CO 2 treatment. Root mortality was unaffected by elevated CO 2 in all months except April, in which plants grown in the HI plots had higher mortality rates. Together, these results demonstrate that root turnover is considerable in the grassland community and easily missed by destructive soil coring. However, increased fine root turnover under elevated CO 2 is apparently not a major sink for extra photosynthate in this system.

Cardiac neural crest ablation alters aortic smooth muscle force and voltage-sensitive Ca2+ responses - Christopher J. Wingard; Robert E. Godt (Journal of Muscle Research and Cell Motility, 2002)

Ischemic Cell Death: Dynamics of Delayed Secondary Energy Failure During Reperfusion Following Focal Ischemia - W. David Lust; Christopher Taylor; Svetlana Pundik; Warren R. Selman; Robert A. Ratcheson (Metabolic Brain Disease, 2002)

The Effect of Gypsy Moth Defoliation on Cavity-Nesting Bird Communities - Christopher R. Showalter; Robert C. Whitmore (Forest Science, 2002)
Gypsy moths (Lymantria Dispar) kill trees and create snags, a resource vital to cavitynesting birds. With this in mind, population trends of 11 cavity-nesting birds and their relationship to snags in an area that was defoliated by gypsy moths were investigated from 1984 to 1999. Vegetation and bird point-count data from before a major gypsy moth outbreak (1984–1986), during (1987–1988), and after (1989–1999) enabled us to ake inferences about this forest bird community. The combined abundance of the 11 cavity-nesting species examined increased during the years immediately after the outbreak (1989–1993) followed by a decline in the last 6 yr (1994–1999). The abundance of snags also increased from 1989 to 1993 followed by a decline from 1994 to 1999. Regression analysis confirmed that cavity-nesting bird populations were highly associated with snag abundance. These data suggest the importance of snags to cavity-nesting birds and that cavity-nesters were able to take immediate advantage of a new population of snags. FOR. SCI. 48(2):273–281.

In Vivo Quantification of Blood Flow and Wall Shear Stress in the Human Abdominal Aorta During Lower Limb Exercise - Charles A. Taylor; Christopher P. Cheng; Leandro A. Espinosa; Beverly T. Tang; David Parker; Robert J. Herfkens (Annals of Biomedical Engineering, 2002)

Tree Mortality in Gap Models: Application to Climate Change - Robert E. Keane; Mike Austin; Christopher Field; Andreas Huth; Manfred J. Lexer; Debra Peters; Allen Solomon; Peter Wyckoff (Climatic Change, 2001)

Iron fertilization and the Trichodesmiumresponse on the West Florida shelf - Jason M. Lenes; Brian P. Darrow; Christopher Cattrall; Cynthia A. Heil; Michael Callahan; Gabriel A. Vargo; Robert H. Byrne; Joseph M. Prospero; David E. Bates; Kent A. Fanning; John J. Walsh (Limnology and Oceanography, 2001)
Prior laboratory studies of Trichodesmium have shown a high iron requirement that is consistent with the biochemical demand for iron in the enzyme nitrogenase. Summer delivery of iron, in the form of Saharan dust, may provide an explanation for Trichodesmium blooms observed in offshore waters of the West Florida shelf over the last 50 yr. During ecology and oceanography of harmful algal blooms (ECOHAB) field studies, background iron levels (0.1–0.5 nmol kg −1 ) were found at the surface during periods of minimal dust delivery (May 2000 and October 1999). In contrast, total dissolved iron concentrations on the order of ∼16 nmol kg −1 were measured at the West Florida shelfߚbreak after a July 1999 Saharan dust event that was identified by advanced very high resolution radiometer (AVHRR) imagery, groundߚbased radiometers, air mass analysis, and aerosol samples (dust and nonߚseaߚsalt nitrate) collected throughout South Florida. The Trichodesmium response following this July dust event was a 100–fold increase over background biomass, reaching a surface stock of ∼20 colonies L −1 . Surface dissolved concentrations of both inorganic and organic phosphorus decreased below detectable limits during this bloom. Dissolved organic nitrogen concentrations associated with the bloom (15–20 µM) were 3–4–fold greater than background and much larger than ambient NO 3 − concentrations ( −1 ). If all dissolved organic nitrogen (DON) is converted to urea and ammonium, this organic nitrogen could have supported the red tide of >20 µg chl L −1 of the toxic dinoflagellate, Gymnodinium breve , found along the West Florida coast during October 1999.

Bathymetric Map of the Gorda Plate: Structural and Geomorphological Processes Inferred from Multibeam Surveys - Robert P. Dziak; Christopher G. Fox; Andra M. Bobbitt; Chris Goldfinger (Marine Geophysical Research, 2001)

Blood lipids of young distance runners: distribution and inter-relationships among training volume, peak oxygen consumption, and body fatness - Joey C. Eisenmann; Christopher J. Womack; Mathew J. Reeves; James M. Pivarnik; Robert M. Malina (European Journal of Applied Physiology, 2001)

HMG-CoA Reductase Inhibitors (Statins) Characterized as Direct Inhibitors of P-Glycoprotein - Er-jia Wang; Christopher N. Casciano; Robert P. Clement; William W. Johnson (Pharmaceutical Research, 2001)

Inhibition of P-Glycoprotein Transport Function by Grapefruit Juice Psoralen - Er-jia Wang; Christopher N. Casciano; Robert P. Clement; William W. Johnson (Pharmaceutical Research, 2001)

Regulation of loblolly pine (Pinus taeda L.) arginase in developing seedling tissue during germination and post-germinative growth - Christopher D. Todd; Janice E.K. Cooke; Robert T. Mullen; David J. Gifford (Plant Molecular Biology, 2001)

Modeling submersed macrophyte growth in relation to underwater light climate: modeling approaches and application potential - Elly P. H. Best; Christopher P. Buzzelli; Steven M. Bartell; Richard L. Wetzel; William A. Boyd; Robert D. Doyle; Kym R. Campbell (Hydrobiologia, 2001)

Alterations in the oxidative metabolic profile in vascular smooth muscle from hyperlipidemic and diabetic swine - Tina M. Roberts; Michael Sturek; Joseph L. Dixon; Christopher D. Hardin (Molecular and Cellular Biochemistry, 2001)

Real-Time Data Assimilative Modeling on Georges Bank - Daniel Lynch; Christopher Naimie; Justin Ip; Craig Lewis; Francisco Werner; Richard Leuttich; Brian Blanton; John Quinlan; Dennis McGillicuddy; James Ledwell; James Churchill; Valery Kosnyrev; et al. (Oceanography, 2001)

Chemoenzymatic preparation of dermatan sulfate oligosaccharides as arylsulfatase B and α-L-iduronidase substrates - Falguni Dasgupta; Riyuko Irene Masada; Christopher M. Starr; Balaguranathan Kuberan; Hyun-Ok Yang; Robert J. Linhardt (Glycoconjugate Journal, 2000)

Non-erythroid form of acute intermittent porphyria caused by promoter and frameshift mutations distant from the coding sequence of exon 1 of the HMBS gene - Sharon D. Whatley; Andrew G. Roberts; David H. Llewellyn; Christopher P. Bennett; Christine Garrett; George H. Elder (Human Genetics, 2000)

Recent tectonics of the Blanco Ridge, eastern blanco transform fault zone - Robert P. Dziak; Christopher G. Fox; Robert W. Embley; John L. Nabelek; Jochen Braunmiller; Randolph A. Koski (Marine Geophysical Research, 2000)

Transport and Reaction at Endothelial Plasmalemma: Distinguishing Intra- From Extracellular Events - Christopher A. Dawson; Said H. Audi; Robert D. Bongard; Yoshiyuki Okamoto; Lars Olson; Marilyn P. Merker (Annals of Biomedical Engineering, 2000)

Verwendung von Java für die kartographische Visualisierung von statistischen Daten auf dem Internet - Alessandro Cecconi; Christopher Shenton; Robert Weibel Zürich (KN - Journal of Cartography and Geographic Information, 2000)

An examination of the sensitivity of reported trends in childhood leukemia incidence rates to geographic location and diagnostic coding (United States) - Gary L. Liberson; Robert J. Golden; William J. Blot; Harry Fisch; Christopher Watson (Cancer Causes & Control, 2000)

Cyanide Increases Reduction but Decreases Sequestration of Methylene Blue by Endothelial Cells - Lars E. Olson; Marilyn P. Merker; Meha K. Patel; Robert D. Bongard; Jason M. Daum; Rebecca A. Johns; Christopher A. Dawson (Annals of Biomedical Engineering, 2000)

Biochemical and behavioral anxiolytic-like effects of R (+)HA-966 at the level of the ventral tegmental area in rats - B. A. Morrow; John D. Elsworth; Christopher Zito; Robert H. Roth (Psychopharmacology, 1999)

The 1882 tilefish kill — a cold event in shelf waters off the north‐eastern United States? - ROBERT MARSH; BRIAN PETRIE; CHRISTOPHER R. WEIDMAN; ROBERT R. DICKSON; JOHN W. LODER; CHARLES G. HANNAH; KENNETH FRANK; KEN DRINKWATER (Fisheries Oceanography, 1999)
A mass mortality of `warm‐water' tilefish in the Middle Atlantic Bight between April and August of 1882 suggests an episode of extreme cold in the shelf waters off the north‐eastern United States. This cooling is hypothesized to be a consequence of enhanced equatorwards transport of cold water in the Labrador Current, coincident with a minimum in the North Atlantic Oscillation (NAO) index during the early 1880s. Although there is little direct evidence for this historical event, an analogue for the 1880s cooling is found in the 1960s, at the most recent NAO‐index minimum. Post‐1945 observations in the Middle Atlantic Bight / Gulf of Maine region reveal changes in winter baroclinic circulation between cool and warm decades, with greater equatorward penetration of south‐westwards flow along the shelf‐edge during the cool 1960s. Over the period 1934–77, the NAO is found to account for 17% of the interannual variance in Labrador Current transport around the Grand Banks. Proxy evidence for the cold episode of the early 1880s is sought. Records of bottom temperature in the Middle Atlantic Bight region are reconstructed using stable oxygen isotopic analysis on the annual bands of shells of a bivalve mollusc ( Arctica islandica ) and an empirical model of covariability with local air temperature. The result is confirmation of the presence of anomalously cold water during the early 1880s.

Impacts of Land Degradation on Historical Temperature Records from the Sonoran Desert - Robert C. Balling; Jeffrey M. Klopatek; Mark L. Hildebrandt; Cherie K. Moritz; Christopher J. Watts (Climatic Change, 1998)

A Model for Deep Geothermal Brines, II: Thermodynamic Properties – Density - Christopher Palliser; Robert Mckibbin (Transport in Porous Media, 1998)

A Model for Deep Geothermal Brines,III: Thermodynamic Properties – Enthalpy and Viscosity - Christopher Palliser; Robert McKibbin (Transport in Porous Media, 1998)

A Model for Deep Geothermal Brines, I: T-p-X State-Space Description - Christopher Palliser; Robert McKIBBIN (Transport in Porous Media, 1998)

Factors Influencing Succession: Lessons from Large, Infrequent Natural Disturbances - Monica G. Turner; William L. Baker; Christopher J. Peterson; Robert K. Peet (Ecosystems, 1998)

Seasonal coupling of a tropical mangrove forest and an estuarine water column: enhancement of aquatic primary productivity - Victor H. Rivera-Monroy; Christopher J. Madden; John W. Day; Robert R. Twilley; Francisco Vera-Herrera; Hernán Alvarez-Guillén (Hydrobiologia, 1998)

Spectroscopic characterization of metal binding by Klebsiella aerogenes UreE urease accessory protein - Gerard J. Colpas; Timothy G. Brayman; John McCracken; Michelle A. Pressler; Gerald T. Babcock; Li-June Ming; Christopher M. Colangelo; Robert A. Scott; R. P. Hausinger (JBIC Journal of Biological Inorganic Chemistry, 1998)

Polymorphisms of the glucocorticoid receptor gene in laboratory and wild rats: steroid binding properties of trinucleotide CAG repeat length variants - Robert P. Heeley; Erica Gill; Bert van Zutphen; Christopher J. Kenyon; Roger G. Sutcliffe (Mammalian Genome, 1998)

Land use effects on habitat, water quality, periphyton, and benthic invertebrates in Waikato, New Zealand, hill‐country streams - John M. Quinn; A. Bryce Cooper; Robert J. Davies‐Colley; J. Christopher Rutherford; R. Bruce Williamson (New Zealand Journal of Marine and Freshwater Research, 1997)
Water quality, habitat, and biota were compared during spring amongst c. 100 m reaches on 11 streams draining pasture, native (podocarp‐broadleaf) forest, and exotic pine forest established on pasture 15 years previously. Differences were greatest between the pasture and native forest streams. Only 1–3% of incident light reached native and pine forest streams whereas 30% reached pasture streams. Pasture streams had 2.2°C higher mean temperature than the native streams, and 5‐fold higher nitrate, 30‐fold higher algal biomass, and 11‐fold higher gross photosynthesis. Native streams were 60% wider than pasture, with pine streams intermediate. Pine and pasture streams had 3‐fold higher suspended solids and fine sediment stored in the streambed than native streams. Woody debris volume was 17‐fold greater in pine than pasture streams, with native streams intermediate. Invertebrate taxa richness did not differ between land uses. Community composition differed most between pasture and native forest, with pine forest streams intermediate. Invertebrate densities were 3‐fold higher in pasture than native streams, mainly because of more chironomids and snails, but mayflies, stoneflies, and caddisflies densities were 2–3‐fold higher in forest streams than pasture.

Predicting the effects of shade on water temperature in small streams - J. Christopher Rutherford; Shane Blackett; Colin Blackett; Laurel Saito; Robert J. Davies‐Colley (New Zealand Journal of Marine and Freshwater Research, 1997)
A computer model for stream water temperature was developed, and tested in a small pasture stream near Hamilton, New Zealand. The model quantifies shading by riparian vegetation, hillsides, and stream banks using three coefficients: canopy angle, topography angle, and canopy shade factor. Shade was measured directly and found to vary significantly along the channel. Using the maximum measured shade, a close match was achieved between observed and predicted daily maximum and minimum water and bed sediment temperature. Model predictions of incoming and outgoing long‐wave radiation flux closely matched measurements, but there were unexplained discrepancies in short‐wave radiation flux. Model predictions indicate that moderate shade levels (c. 70%) may be sufficient in temperate climates to restore headwater pasture stream temperatures to 20°C, an estimate of the thermal tolerance for sensitive invertebrates.

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Deception by helpers in cooperatively breeding white-winged choughs and its experimental manipulation - Christopher R. J. Boland; Robert Heinsohn; Andrew Cockburn (Behavioral Ecology and Sociobiology, 1997)

An acoustic tracking of a megamouth shark, Megachasma pelagios: a crepuscular vertical migrator - Donald R. Nelson; James N. McKibben; Wesley R. Strong; Christopher G. Lowe; Joseph A. Sisneros; Donna M. Schroeder; Robert J. Lavenberg (Environmental Biology of Fishes, 1997)

A clinical evaluation of risperidone in the treatment of schizophrenia: a 10-week, open-label, multicenter trial - D. V. Jeste; Mark Klausner; Martin Brecher; Christopher Clyde; Robert Jones (Psychopharmacology, 1997)

The reduction of aromatic alpha-keto acids by cytoplasmic malate dehydrogenase and lactate dehydrogenase - Christopher A. Friedrich; Donald C. Morizot; Michael J. Siciliano; Robert E. Ferrell (Biochemical Genetics, 1987)

Effect of ambient temperature on the hypometabolic and hypothermic effects of sulfolane in rats - Christopher J. Gordon; Merritt D. Long; Robert S. Dyer (Archives of Toxicology, 1984)

A general method for visualizing enzymes releasing adenosine or adenosine-5?-monophosphate - Christopher A. Friedrich; Shukti Chakravarti; Robert E. Ferrell (Biochemical Genetics, 1984)

Blue crab mortality: Interaction of temperature and DDT residues - Christopher C. Koenig; Robert J. Livingston; Claude R. Cripe (Archives of Environmental Contamination and Toxicology, 1976)